Analyse und Optimierung von österreichischem Polystyrol-Haushaltsabfall für die Wiederverwendung in Joghurtbecher-Lebensmittelverpackungen - Krempl, Nina; Frühwirth, Matthias; Zidar, David; Shahroodi, Zahra; Holzer, Clemens; Pinter, Elisabeth; Archodoulaki, Maria Vasiliki; Bichler, Lorenz; Jahn, Elisabeth; Gabriel, Viktoria Helene; Aschermayer, Florian (Recy & DepoTech 2024, 2024)

Backside metallization affects residual stress and bending strength of the recast layer in laser-diced Si - Ziegelwanger, T.; Reisinger, M.; Matoy, K.; Medjahed, A. A.; Zalesak, J.; Gruber, Manuel; Meindlhumer, M.; Keckes, J. (Materials Science in Semiconductor Processing, 2024)
Publisher Copyright: © 2024
Keywords: Die bending strength; Local residual stresses; Nanosecond laser dicing; Ultra-thin Si dies; X-ray nanodiffraction

Biaxial bending strength testing of uniaxially curved thin plates using a modified ball on three balls test - Supancic, Peter; Maurer, Florian; Danzer, Robert (Journal of non-crystalline solids, 2024)
Publisher Copyright: © 2024
Keywords: Ring-on-ring test, Ball-on-three-balls test; Uniaxially curved glass plates

Coupling structural, chemical composition and stress fluctuations with relaxation dynamics in metallic glasses - Şopu, Daniel; Yuan, Xudong; Spieckermann, Florian; Eckert, Jürgen (Acta Materialia, 2024)
Understanding the atomistic mechanisms of relaxation dynamics in metallic glasses remains a longstanding challenge. Here, using microsecond time scale molecular dynamics simulations, three main relaxation stages in metallic glasses are identified. At about 0.6T, chemical composition plays a dominant role in the relaxation, manifested by stress accumulation and only minimal variations in structure. As T approaches, the confluence of structural heterogeneity and chemical composition leads to the decoupling of relaxation mechanisms. At this temperature, the relaxation results in a structure with a lower energy state and a lower level of stress. In the supercooled liquid regime, an extensive increase in the number of closed-packed icosahedral clusters is responsible for accelerated structural relaxation while their packing frustration leads to the accumulation of intrinsic residual stresses in the glass. The atomistic origin of these dynamic relaxation modes is discussed in terms of structural, chemical composition and stress variations.
Publisher Copyright: © 2024 Acta Materialia Inc.
Keywords: Dynamics relaxation; Metallic glasses; Molecular dynamics simulations

Fertilization efficiency of thirty marketed and experimental recycled phosphorus fertilizers - Hernandez-Mora, Alicia; Duboc, Olivier; Lombi, Enzo; Bünemann, Else K.; Ylivainio, Kari; Symanczik, Sarah; Delgado, Antonio; Abu Zahra, Nadine; Nikama , Johanna; Zuin, Lucia; Doolette, Casey L.; Eigner, Herbert; et al. (Journal of Cleaner Production, 2024)
Recycling phosphorus (P) from waste streams like sewage sludge, animal manures or food industry by-products is required to sustain soil fertility without depleting non-renewable P resources. Several technologies are available for P recovery, leading to fertilizers differing in P solubility and bioavailability. In this study, thirty fertilizers obtained through different technologies were tested to assess if their fertilization efficiency was equivalent to mineral soluble fertilizer applied as triple superphosphate (TSP). The main selection criteria were (1) ensuring a wide chemical diversity, and (2) choosing products already on the market or at a late stage of development, to encompass a representative selection of current and future recycled fertilizers. The products were classified according to their organic carbon content and neutral ammonium citrate (NAC), and the main P species of each fertilizer was determined through K-edge and L2,3-edge X-ray absorption near edge structure spectroscopy (XANES). Three pot experiments with wheat, barley and ryegrass were conducted in three growing substrates with contrasting properties, all within a pH range of 5.8–6.9. Fertilizers containing ammonium magnesium phosphate, monoammonium phosphate, monocalcium phosphate, and dicalcium phosphate type species as dominant P species showed a similar fertilization efficiency to TSP, while fertilizers with hydroxyapatite, tricalcium phosphate, phytic acid or iron phosphates as their main P species had lower fertilization efficiencies. We conclude that while the trend towards high-efficiency, refined inorganic recycled P fertilizers is positive, lower-performing, mostly unrefined fertilizers must be assessed in light of their long-term P supply potential and additional benefits to soil health owing to their content of organic matter and other nutrients.
Publisher Copyright: © 2024 The Authors
Keywords: Industrial by-product; Manure; Mineral replacement value; Sewage sludge; Struvite; XANES speciation

Geomechanical characterization and mineralogical correlation of compositionally diverse world-class Kazakhstani source rocks - Nurbekova, Riza; Shi, Xiangyun; Hazlett, Randy; Misch, David; Fustic, Milovan; Sachsenhofer, Reinhard (International journal of coal geology, 2024)
Extensive nanoindentation testing over a range of deflection depths of up to 4 μm yielded a large dataset, providing a viable framework for the statistical assessment of the mechanical properties, specifically elastic modulus (E) and hardness (H), of compositionally diverse organic-rich mudstone samples. The data from indentations as shallow as 300–400 nm were clustered using the k-means algorithm to identify three mechanical categories in the samples: a soft pseudophase (e.g., organic matter, gypsum, and clay minerals), a stiff pseudophase (e.g., quartz and feldspar), and a transitional composite-like pseudophase bridging the soft and hard minerals. The initially diverse values of E and H for the mechanical pseudophases were observed to converge to a constant value at indentations beyond 2–2.5 μm (varying between different samples), implying the existence of a minimal probing depth for assessing the bulk E and H of heterogeneous mudstone samples. The obtained bulk E and H values (8–21 GPa and 0.3–0.9 GPa, respectively) demonstrated a strong correlation with the mineralogical composition of the indented samples. Despite containing a notable proportion of mechanically stiff components (>45 vol%), the bulk mechanical parameters determined in this study were significantly lower than those reported for major shale formations such as the Barnett and Longmaxi Shale. This discrepancy is primarily due to the presence of organic matter with low thermal maturity (Ro < 0.6%), which constitutes <36 vol% of the samples, and a significant gypsum content, accounting for <15 vol%.The employed approach not only demonstrated the importance of choosing the proper indentation depths for investigating the mechanical properties of highly heterogeneous mudstone rocks and their constituent minerals, but it also illustrated the capability of examining various volumes of investigation using nanoindentation, approaching macroscopic values, and identifying a representative element volume (REV). The findings also provided crucial insights into the fracability and overall producibility of the investigated formations, thereby enhancing our understanding of their extraction potential.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Continuous stiffness measurement; Elastic modulus; Hardness; Nanoindentation; Organic-rich mudstones

Digitalisation and technological innovations towards energy-efficient quarries - Sánchez, Felipe; Kopeinig, Hanspeter; Lee, Christina; Hartlieb, Philipp (SDIMI 2024: Sustainable Development in the Minerals Industry 11th International Conference, 2024)

Dissolution of Oxide Particles in Multi-component Slags Governed by Diffusive and Convective Fluxes - Ogris, Daniel Marian; Michelic, Susanne Katharina; Gamsjäger, Ernst (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)

INFLUENCE OF FLUID PROPERTIES ON TRANSVERSE FABRIC COMPRESSIBILITY DURING IN-SITU IMPREGNATION - Bender, Marcel; Fauster, Ewald (2024)
In this study, the influence of different fluids on the transverse compressibility behaviour of technical reinforcing fabrics was investigated. Specifically, a glass fibre woven and a non-crimp fabric with comparable fibre areal weight, were studied in a novel test-rig with in-situ impregnation of the samples under transverse load. Four test fluids with varying viscosity and polarity, respectively, were chosen to analyse the influence of fluid viscosity and polarity on the relaxation behaviour. In addition, silicone oil with four different levels of viscosity across three orders of magnitude was used to isolate the influence of fluid viscosity, as no significant difference in polarity was observed. A qualitative analysis showed that the fabrics reacted significantly different to the impregnation, as with lower flexibility and increasing viscosity, hydrostatic effects in the compressed area counteracted a lubricating effect. However, only in the fabric with lower fibre bundle flexibility a slight to significant relative pressure relaxation was measured only as a result of fluid polarity. In addition, the viscosity of the fluid had no significant effect on the relative relaxation at the same polarity, but with increasing viscosity the time to reach pressure equilibrium increased significantly.
Keywords: Composites; Compression test; Processing of Composite Materials

Automatic and time-resolved determination of fracture characteristics from in situ experiments - Schmuck, Klemens Silvester; Antenreiter, Martin; Alfreider, Markus; Kiener, Daniel (Materials & design, 2024)
The characterization of materials in ever smaller dimensions is crucial for the growing demand for miniaturized devices. Hence, in situ fracture experiments are frequently performed at the micron to sub-micron scale. To evaluate fracture process of these experiments, knowledge of the crack length or the crack tip opening displacement is required. Acquired in situ frames provide a direct measurement of the crack length, crack tip opening displacement and -angle. An algorithm was developed to extract these parameters from the in situ frame sequences automatically. To verify the performance of the algorithm, fracture characteristics were measured manually for several frames of the available in situ experiments. The fracture behavior of these samples ranged from brittle over semi-brittle to ductile. The comparison between algorithmic results and manual measurements demonstrated the applicability of the algorithm to different fracture behaviors. Additionally, the fracture characteristics determined by the algorithm are in accordance with the fracture toughness data reported in literature. The crack tip opening displacement measurement gives thorough insight into the plastic deformation during fracture. The automatic extraction of the fracture characteristics allows a more detailed analysis of small-scale fracture processes and enables a reproducible, continuous evaluation of the fracture characteristics of all frames.
Publisher Copyright: © 2024 The Author(s)
Keywords: Crack propagation; Image processing techniques; In-situ microcantilever testing; Small scale fracture experiments

Metal impact and vaporization on the Moon’s surface - Gopon, Phillip; Douglas, James; Gardner, Hazel; Moody, Michael; Wood, Bernard; Halliday, Alexander; Wade, Jon (Meteoritics and planetary science, 2024)
Millimeter-to-nanometer-sized iron- and nickel-rich metals are ubiquitous on the lunar surface. The proposed origin of these metals falls into two broad classes which should have distinct geochemical signatures—(1) the reduction of iron-bearing minerals or (2) the addition of metals from meteoritic sources. The metals measured here from the Apollo 16 regolith possess low Ni (2–6 wt%) and elevated Ge (80–350 ppm) suggesting a meteoritic origin. However, the measured Ni is lower, and the Ge higher than currently known iron meteorites. In comparison to the low Ni iron meteorites, the even lower Ni and higher Ge contents exhibited by these lunar metals are best explained by impact-driven volatilization and condensation of Ni-poor meteoritic metal during their impact and addition to the lunar surface. The presence of similar, low Ni-bearing metals in Apollo return samples from geographically distant sites suggests that this geochemical signature might not be restricted to just the Apollo 16 locality and that volatility-driven modification of meteoritic metals are a common feature of lunar regolith formation. The possibility of a significant low Ni/high Ge meteoritic component in the lunar regolith, and the observation of chemical fractionation during emplacement, has implications for the interpretation of both lunar remote-sensing data and bulk geochemical data derived from sample return material. Additionally, our observation of predominantly meteoritic sourced metals has implications for the prevalence of meteoritic addition on airless planetary bodies.
Publisher Copyright: © 2024 The Authors. Meteoritics & Planetary Science published by Wiley Periodicals LLC on behalf of The Meteoritical Society.

Experimental, analytical, and numerical quantification of the Marangoni effect in static refractory finger test - Vollmann, Sandra; Guarco, Jeronimo; Burhanuddin, Burhanuddin (Ceramics International : CI, 2024)
This study investigated the local corrosion of alumina and magnesia refractory in CaO–Al2O3–SiO2–MgO slag due to the Marangoni effect, which is a key factor for localized wear in different industrial processes, using experimental, analytical, and numerical approaches. The objective is to explore the Marangoni effect using computational fluid dynamics simulation aiming to provide insights into the dominant slag flow patterns influencing refractory corrosion and to determine whether the observed corrosion groove can be attributed solely to the Marangoni effect. Static finger tests were conducted at temperatures of 1500 and 1550 °C employing a continuous wear testing device. A two-dimensional axisymmetrical section model of the test assembly was created, incorporating concentration-dependent surface tension gradients and surface tension forces to replicate the Marangoni flow. As the surface-tension simulation required time steps in the order of 10−5 s, modeling up to the experimental time scale cannot be realized. Consequently, the simulation outcomes were extrapolated to anticipate the groove radii of the experimental corrosion steps. Corrosion rates were derived from measurements and analytical methodologies. Established analytical equations for corrosion under surface-tension-flows were adapted to enhance the accuracy of corrosion rate estimation. However, the analytical considerations yielded poor estimates. Meanwhile, the employed simulation model successfully generated plausible predictions of the Marangoni flow. Drawing from the extrapolated simulation outcomes, the projected groove radii exhibited a close correspondence to the measured values, demonstrating a relative error of approximately 3 %, 11 %, and 15 % for the magnesia system at 1500 °C and alumina systems at 1500 and 1550 °C, respectively. Taking into account the uncertainties inherent in the methodological approach, the disparities in the alumina values suggest the involvement of mechanisms beyond the Marangoni effect in the localized wear. Consequently, this study effectively clarifies the impact of the Marangoni effect on the local wear of the examined material systems.
Publisher Copyright: © 2024 The Authors
Keywords: C. Corrosion; D. Al O MgO; E. Refractories

Cobalt-free high-entropy perovskite La0.2Pr0.2Nd0.2Sm0.2Sr0.2FeO3-δ solid oxide cell air electrode with enhanced performance - Pretschuh, Patrick; Egger, Andreas; Paulachan, Priya; Schöggl, Johanna; Brunner, Roland; Bucher, Edith (Fuel Cells, 2024)
This study investigates the novel cobalt-free high-entropy perovskite, La 0.2Pr 0.2Nd 0.2Sm 0.2Sr 0.2FeO 3–δ (LPNSSF), as an air electrode material for solid oxide cells (SOCs). When testing a button cell with a single-phase LPNSSF electrode, a current density of 0.55 A cm −2 is obtained at 0.7 V in fuel cell mode at 800°C. In order to mitigate the moderate electronic conductivity of LPNSSF, two approaches are explored. Incorporating a Co-free highly conductive perovskite, LaNi 0.6Fe 0.4O 3–δ (LNF), either as an LPNSSF–LNF composite electrode or as a current collector layer (CCL), enhances the performance to 0.61 and 0.66 A cm −2, respectively, under the same conditions. Microstructural features are studied by electron microscopy and show a rather dense structure of the CCL. Optimization of the current collector increases the current density further to 0.96 A cm −2 at 0.7 V in a 5 × 5 cm 2 anode-supported cell at 800°C. This cell exhibits good long-term stability in electrolysis mode in H 2-H 2O with 80% humidification. Continuous polarization of −0.69 A cm −2 is sustained for 1000 h, with an average degradation rate of 10 mV kh −1 after an initial run-in phase. These findings demonstrate the promising performance and durability of LPNSSF as cobalt-free SOC air electrode.
Publisher Copyright: © 2024 The Author(s). Fuel Cells published by Wiley-VCH GmbH.
Keywords: cobalt-free air electrode; current collector layer; electrochemical impedance spectroscopy; high-entropy perovskite; long-term stability; solid oxide electrolyzer cell; solid oxide fuel cell

Influence of Tramp Elements on Surface Properties of Liquid Medium-Carbon Steels - Cejka, Julian; Sammer, Bernhard; Gruber, Isabell; Michelic, Susanne Katharina (Steel research international, 2024)
The transformation of the steel industry is inevitably linked to increased recycling rates of steel. However, end-of-life scrap is often contaminated with tramp elements like copper, molybdenum, and tin and while their influence on mechanical properties of steels is well described, their effect on nonmetallic inclusions remains largely unknown. Therefore, herein, two medium-carbon steels are alloyed with up to 1 wt% of the listed tramp elements. The influence these elements have on the inclusion behavior in liquid steel is investigated using the sessile drop method in contact with alumina and zirconia as well as in steel/slag melting experiments to evaluate the formation and separation of new inclusions. Additionally, a semiempirical approach using CALPHAD to model the surface tension of steels with tramp elements is done. Copper and tin decrease the surface tension, while molybdenum increases the surface tension. It is demonstrated that most investigated alloys lead to a decrease of wetting angle as compared to the nonalloyed steels. The shown trends in the sessile drop experiments are lower contact angles with increased surface tension while a higher number of inclusions occurs with a decrease in surface tension. Thus, this study demonstrates that tramp elements affect the oxidic cleanness of steels.
Publisher Copyright: © 2024 The Author(s). Steel Research International published by Wiley-VCH GmbH.
Keywords: medium-carbon steels; nonmetallic inclusions; steel cleanness; surface behavior; tramp elements; wetting

Designing Intelligent Rock Support Systems to Detect Gravity-Driven Wedges - Varelija, Michel; Hartlieb, Philipp (Rock mechanics and rock engineering, 2024)
Intelligent rock bolts can be used in mining operations to acquire information on the bolt's status and movements of the rock mass. The future value of this technology resides in optimizing the support layout and increasing safety. The primary goal of this research is to investigate the sensor spatial distribution necessary for efficiently identifying roof wedges in mines. Roof wedges occur when three joints intersect over the roof, forming a triangular shape. They present a hazard by falling and causing damage. Sensor density refers to the number of sensors on a single rock bolt and the number of intelligent rock bolts in the mine or one section. Too many sensors drive costs up, and too few sensors compromise measurement quality. This research visualizes and investigates the results of the simulated models of intelligent rock bolts depending on the number of installed sensors and intelligent bolts to get a better understanding of the problem and describe the technique used, including numerical simulations and the considered parameters. Furthermore, it offers insight into the findings' possible implications, providing knowledge about the viability of using intelligent rock bolts.
Publisher Copyright: © The Author(s) 2024.
Keywords: Intelligent rock bolt; Sensor density; Numerical Modelling; Measurement; Numerical modelling; Roof wedge

Polymetallic tungsten skarn mineralisation related to the Periadriatic intrusion at Lienzer Schlossberg, East Tyrol, Austria - Raith, Johann; Hutter, Florian; Altenberger, Florian; Weilbold, Julia; Auer, Christian; Krause, Joachim; Berndt, Jasper; Neinavaie, Hassan (Austrian journal of earth sciences, 2024)
A regional tungsten anomaly was discovered and explored in the Lienzer Schlossberg area that is part of the crystalline Austroalpine nappe complex of the Eastern Alps in the 1970/80-ties. Tungsten is present as scheelite, which occurs in steeply SSW dipping WNW-ENE oriented quartz veinlets and joints within the porphyritic dioritic to tonalitic/granodioritic host rocks of the Oligocene Lienz/Edenwald intrusion and in the exoskarn, which developed at the contact of the intrusion with Ca-rich lithologies. The skarn system is characterised by two stages: (1) a primary high-temperature calc-silicate stage characterised by grossular, diopside-hedenbergite, vesuvianite, wollastonite and Ca-plagioclase and (2) a retrograde skarn stage including scheelite-bearing massive sulphide ores (pyrrhotite, chalcopyrite, tremolite-actinolite, diopside-hedenbergite) and scheelite-rich fault rocks with calcite, sericite and chlorite. The two ore stages, the mineral paragenesis and composition is like that of a reduced tungsten skarn; i.e., garnet is grossular-rich, clinopyroxene is diopside-hedenbergite. Vesuvianite contains up to 1.8 mass % fluorine. Scheelite has been studied by cathodoluminescence (CL), electron probe microanalysis and laser ablation-inductively coupled plasma-mass spectrometry. Three types of scheelite (Scheelite 1–3) are distinguished. In short-wave UV light, all types show blue fluorescence but CL revealed internal micro-textures in scheelite grains which are dominated by oscillatory zoning. Prolonged hydrothermal activity is indicated by dissolution-replacement and overgrowth textures affecting the primary zonation and trace element composition of scheelite. The distribution of rare earth elements (REE) in Scheelite 1 in tonalite-hosted quartz veinlets shows a convex (i.e., middle REE-enriched), heavy REE-depleted pattern with negative Eu anomalies (EuA). The evolution of REE patterns from skarn-hosted Scheelite 2 and 3 illustrates a gradation of convex REE patterns with high ΣREE and distinct negative Eu anomalies to relatively flat REE patterns with small to no EuA. Scheelite at Lienzer Schlossberg has one of the highest ΣREE+Y contents of all scheelite-bearing ore settings in the Eastern Alps but incorporates minor Mo and the least Sr. High Na and Nb contents together with the positive correlation of REE+Y vs. Na+Nb+Ta suggests that the main exchange vectors for REE incorporation in scheelite is via a combined coupled substitution mechanism. Results of this study confirm the genetic similarity with reduced tungsten skarns and highlight the tungsten potential of this area.
Publisher Copyright: © 2023 Johann G. Raith et al., published by Sciendo.
Keywords: Eastern Alps; scheelite; tungsten skarn; Periadriatic intrusion; trace elements; LA-ICP-MS

Dual cross-linking of XNBR latex with epoxy-functional calcium silicate particles for the production of accelerator-free medical gloves - Grabmayer, Theresa; Manhart, Jakob; Fleischmann, Darya; Kaiser, Simon; Schaller, Raimund; Holzner, Armin; Schlögl, Sandra (Journal of applied polymer science, 2024)
In this work, an innovative dual cross-linking strategy for carboxylated nitrile butadiene rubber (XNBR) latex using epoxy-modified calcium silicate particles is presented. In their role as dual cross-linker, the particles are able to form covalent bonds (nucleophilic ring opening of epoxy moieties) as well as ionic cross-links (calcium ions of the inorganic core) across the carboxylic acid groups of the rubber. To characterize the curing efficiency, thin elastomer films are prepared by using a conventional coagulant dipping process and their cross-link densities, curing kinetics, and tensile properties are investigated as a function of the concentration of the cross-linker and curing time. The results show that latex films containing 5 phr of epoxy-functional particles give the highest tensile strength, which is further improved by pre-vulcanizing the liquid latex compound at 60°C for 30 min. The latex formulations are stable over 3 days and the pre-cured films exhibit a high resistance against gamma sterilization and subsequent accelerated aging. Moreover, sterile films do not cause any skin irritation or skin sensitization reactions, showing the high potential of epoxy-functional particles in the production of accelerator-free hypoallergenic gloves.
Publisher Copyright: © 2024 Wiley Periodicals LLC.
Keywords: applications; elastomers; films; rubber

A methodology for the determination of future Carbon Management Strategies - Hochmeister, Susanne; Kühberger, Lisa; Kulich, Jakob; Ott, Holger; Kienberger, Thomas (International Journal of Sustainable Energy Planning and Management, 2024)
The achievement of global climate targets outlined in the Paris Agreement represents a critical challenge in the coming decades. Certain industry sectors cannot completely avoid all emissions from their processes. In this context, the term unavoidable or Hard-to-abate emissions is used. Carbon Capture and Utilization (CCU) and Carbon Capture and Storage (CCS) are recognized as essential components for addressing those emissions to achieve Net Zero Emissions. To identify effective Carbon Management Strategies, balancing future CO2 sources and possible sinks for achieving long-term climate targets is essential. Especially in Austria hardly any comprehensive studies have been carried out.This work presents a comprehensive analysis of Austria’s CO2 point sources as well as their projected development until 2050 based on technology-based scenarios. Geological CO2 storage in Austria is primarily feasible in former hydrocarbon reservoirs and saline aquifers. Future demands for CO2 as CCU feedstock will arise in the chemical industry. By 2050, industry will emit approximately 4 Million tons (Mt) of unavoidable CO2 annually. These emissions must be stored in the long term and correspond to the minimum demand for CCS. Fugitive emissions from agriculture, for example, cannot be captured. Thus, they are not subject of CCU/S measures. Negative emissions are therefore necessary to achieve the climate targets. These negative emissions and the possible use of CO2 as feedstock are covered by biogenic CO2

Hydrogen diffusivity, uptake and embrittlement of solution annealed and cold deformed austenitic stainless steel 1.4435 at hydrogen pressures up to 1000 bar and 200 °C - Eichinger, Matthias; Pengg, Johann; Zwittnig, Dino; Mori, Gregor Karl (Corrosion science, 2024)
Austenitic stainless steel 1.4435, a candidate material for high-pressure tubing for hydrogen applications, was investigated in two different stages of cold deformation (0 and 27 %) regarding its hydrogen embrittlement tendency. The determination of effective diffusion coefficients revealed slightly increased diffusion kinetics at 60°C for the cold-reduced material (8.0 · 10−15 m²/s) compared to the solution annealed one (5.0 · 10−15 m²/s). High-pressure gaseous hydrogen charging shows no differences regarding the degree of cold deformation with a maximum hydrogen concentration of 112 wt.-ppm. Furthermore, a significant ductility loss expressed by the ratio of the reduction of area was observed.
Publisher Copyright: © 2024 The Author(s)
Keywords: austenitic stainless steel; high-pressure charging; hydrogen embrittlement; Hydrogen uptake

Capacity of hydrogen traps affects H-assisted crack initiation and propagation mechanisms in martensitic steels - Safyari, Mahdieh; Bhosale, Saurabh; Moshtaghi, Masoud (Engineering Failure Analysis, 2024)
Low-carbon martensitic steels are candidate materials for different hydrogen applications. Hydrogen embrittlement (HE) of the steels can be mitigated by designing trap site characteristics. In this study, the different capacities of hydrogen trapping, and reversibility of the trap sites are studied to reveal the extent of HE susceptibility of the steels and H-assisted crack initiation and propagation mechanisms. The trap sites in Ti-contained and Mo-contained martensitic steels were identified and discussed. The trap sites in Ti-contained martensitic steel include basic martensitic microstructure, the interface of the TiC/matrix interface and carbon vacancies inside the TiC carbides. The trap sites in Mo-contained martensitic steel including basic martensitic microstructure and interface of the Mo 2C/matrix interface. Ti-contained steel indicates a mitigated HE susceptibility, controlled by carbon vacancies inside TiC acting as strong hydrogen trap sites, and a higher possibility of building up a critical hydrogen content at Mo 2C carbide due to lower hydrogen capacity. These results prove that hydrogen trapping capacity at the designated hydrogen trap sites is a determinant factor for H-assisted crack initiation and propagation in martensitic steels. A critical local hydrogen amount should be built up at the trap site to assist the crack to develop. It was also revealed that crack initiation originated from Mo 2C carbides accompanied by interfacial decohesion at the interface of martensitic matrix/Mo 2C carbides and propagated in quasi-cleavage patterns along {0 1 1} planes.
Publisher Copyright: © 2024 The Author(s)
Keywords: Crack initiation; Crack propagation; Hydrogen embrittlement; Hydrogen trapping capacity; Martensitic steels

A comparative analysis of the economic feasibility of reversible hydrogen systems based on time-resolved operation optimisation - Banasiak, David; Kienberger, Thomas (Applied energy, 2024)
The expansion of fluctuating renewable energy production, such as wind and PV, increases the mismatch to consumption. Power-to-Hydrogen-to-Power (PtHtP) systems are believed to be a key for balancing under and overproductions. PtHtP systems can provide temporal and spatial flexibilities and among them reversible solid oxide cells (rSOC) are a promising technology. They combine production of hydrogen and power in the same electrochemical stack. This generates a financial and environmental benefit since less resources are necessary for enabling both Power-to-Hydrogen and Hydrogen-to-Power. This work investigates the application of rSOC systems in comparison to reversible PEM systems consisting of electrolysis and fuel cell unit. In the present studies time-resolved optimization is employed for simulation of the optimal operation of the PtHtP technologies in different market price conditions for electricity, hydrogen and natural gas and with coupling to industry and district heat. Both systems have a zone of market prices, that allows for a positive economic performance over lifetime. The electricity‑hydrogen price difference in this zone is in the range from −83 €/MWh to 133 €/MWh depending on the scenario. Furthermore, the electricity price fluctuations are found to have the major impact on the profitability. By studying the influence of gas grid fees, one finds that local compressed hydrogen storages can be used only for very short storage timescales up to a few hours. Finally, the derivation of application conditions, that are suitable for the two different spatial kinds of reversible hydrogen systems – spatially concentrated and delocalized and the two technologies – rSOC and PEM, is made.
Publisher Copyright: © 2024
Keywords: rSOC; PEM electrolysis; power-to-gas-to-power; sector coupling; Energy Efficiency; techno-economic assessment; Sector coupling; PEM; Energy efficiency; Power-to-gas-to-power; Techno-economic

A new approach for in situ electrochemical nanoindentation: Side charging as a promising alternative - Zeiler, Stefan; Jelinek, Anna; Terziyska, Velislava; Schwaiger, Ruth; Mitterer, Christian; Brinckmann, Steffen; Maier-Kiener, Verena (Acta materialia, 2024)
Understanding hydrogen embrittlement in metals is an essential task for the energy transition, where hydrogen plays a key role. Besides the economic consequences of embrittlement, safety aspects are a very important factor to consider. Therefore, materials need to be screened in order to evaluate their mechanical response under hydrogen influence. Besides macroscopic mechanical testing, in situ electrochemical nanoindentation and micromechanical testing —in general— represent promising methods as they allow to characterize individual microstructural features. In the established “front-side” charging approach, hydrogen enters the sample at the same surface on which indentation tests are performed. An alternative is “back-side” charging, where hydrogen is introduced at the opposite side of the indentation location. In the present study, a novel “side” charging cell was designed and the results were compared to those obtained by “front-side” charging. For this purpose, a ferritic steel with high chromium content (X6Cr17) underwent a grain coarsening heat treatment to ensure that multiple nanoindentation experiments can be performed within a single grain. A similar grain orientation was tested with both charging approaches. The novel “side” charging cell design outperforms the stiffness of the reference front-side charging cell by 60 %. Both cell designs yielded constant Young's moduli before, during and several hours after charging. The hardness increased during charging due to hydrogen uptake, whereas the hardness settled several hours after charging to the values before charging started. The presence of hydrogen at the indentation side was confirmed by in situ X-ray diffraction using a self-reporting titanium film.

Influence of Mo carbides and two-stage tempering methodology on the susceptibility of medium carbon martensitic steel to hydrogen embrittlement - Eskinja, Magdalena; Winter, Gerald; Schnideritsch, Holger; Klarner, Jürgen; Razumovskiy, Vsevolod I.; Moshtaghi, Masoud; Mori, Gregor Karl (Engineering Failure Analysis, 2024)
The objective of the present study was to enhance the hydrogen embrittlement (HE) resistance of the quenched and tempered martensitic steel via the interplay of heat treatment variance and precipitation of nanosized carbides. For this purpose, one-stage tempering and two-stage tempering methodologies were implemented, and steel was alloyed with Mo to instigate the precipitation of Mo carbides. The results revealed that two-stage tempered steel exhibited superior resistance to HE, as a result of reduced dislocation density and higher quantity of Mo2C. To discern the role and trapping behaviour of Mo2C carbides, Thermal Desorption Spectroscopy (TDS) combined with electrochemical hydrogen charging was utilized. Precipitated nanosized Mo2C exhibited the ability to trap hydrogen. On the contrary, an increase of dislocations and higher diffusible hydrogen content in one-stage tempered steel promoted deterioration of mechanical properties which was investigated by Slow Strain Rate Test (SSRT) and fracture surface morphology analysis. In addition, the effective diffusion coefficient for one-stage tempered steel was lower, as dislocations served as additional trap sites.
Publisher Copyright: © 2024 The Author(s)
Keywords: Hydrogen embrittlement; Martensitic steels; Mo carbides; Tempering

Mapping electro-vortex flow patterns from tornado to inverted tornado in a hemispherical container - Abdi, Mehran; Karimi Sibaki, Ebrahim; Sommitsch, Christof; Barati, Hadi; Al Nasser, Mohamad; Wu, Menghuai; Teplyakov, I.; Kharicha, Abdellah (International Journal of Thermofluids, 2024)
This study aims to investigate the intricate interaction between fluid flow and magnetic fields, known as magnetohydrodynamic (MHD) phenomena, within a hemispherical container filled with conducting gallium–indium–tin (Ga-In-Sn) liquid. The primary objective is to explain the influence of the external magnetic field and electric current intensities on the flow structure. Novel insights into the emergence of Lorentz forces that drive the flow dynamics are pursued by varying these parameters. The motivation for this investigation is rooted in the desire to deepen our understanding and uncover new insights into magnetohydrodynamic (MHD) phenomena within a specific experimental setup. Specifically, we aim to understand how swirl velocity is generated and altered by fluctuations in magnetic field strength and electric current intensity within the system. Our investigation reveals a transformation in the flow pattern in a hemispherical pool as the magnetic field strength increases while maintaining a constant electric current intensity. Sequential transformations from a rope tornado to a tornado, cyclone, and finally an inverted tornado are observed, shedding light on the complex behavior of the system. On the other hand, under fixed external magnetic field conditions, it is observed that, as the electric current intensifies, the flow pattern evolves from a tornado to a rope tornado or from a cyclone to a tornado. Furthermore, once the electric current intensity exceeds a specific threshold, the flow pattern remains unchanged, providing valuable insights for process optimization and control. This study contributes to a deeper understanding of MHD phenomena and offers practical implications for optimizing processes such as electroslag remelting (ESR) and vacuum arc remelting (VAR) that involve a similar hemispherical pool of conductive liquid. The simulation results are validated against experimental measurements, ensuring the reliability and accuracy of our findings.

Mechanical processing and thermal stability of the equiatomic high entropy alloy TiVZrNbHf under vacuum and hydrogen pressure - Schweiger, Lukas; Römer, Felix; Gizer, Gökhan; Burtscher, Michael; Kiener, Daniel; Pistidda, Claudio; Schökel, Alexander; Spieckermann, Florian; Eckert, Jürgen (Applied physics letters, 2024)
Publisher Copyright: © 2024 Author(s).

Effect of cold rolling route and annealing on the microstructure and mechanical properties of AISI 316 L stainless steel - Mohammadzehi, Sara; Roostaei, Milad; Mirzadeh, Hamed; Mahmudi, Reza; Weißensteiner, Irmgard (Materials characterization, 2024)
Since cross rolling promotes the transformation of austenite to deformation-induced α΄-martensite and increases the dislocation density in the retained austenite, the reversion/recrystallization annealing after cross rolling might be more effective to achieve finer grain sizes in metastable austenitic stainless steels. Accordingly, the effect of cold rolling route and annealing for grain refinement and improvement of mechanical properties of AISI 316 L stainless steel was systematically investigated in the present work. It was found and formulated that by increasing strain, the grain refinement efficiency during annealing is improved, the effect being more pronounced if the cold rolling step is applied by cross rolling instead of unidirectional rolling. The evaluation of tensile properties revealed that all cold rolling and annealing routes lead to significant improvements of mechanical properties in terms of strength and plasticity, the influence of cross rolling being more prominent again. Moreover, the cross rolling and annealing route led to a remarkable strength-ductility balance, which revealed the opportunities that this route can offer for the improvement of mechanical properties of austenitic stainless steels. Accordingly, the results of the present work may shed light on the further utilization of cold rolling route and annealing treatment.
Publisher Copyright: © 2023
Keywords: Austenitic stainless steels; Cross rolling; Grain refinement; Mechanical behavior; Recrystallization

Exploring Refinement Characteristics in FeTi‐Cu x Composites: A Study of Localization and Abrasion Constraints - Schweiger, Lukas; Spieckermann, Florian; Buchebner, Nadine; Keckes, Julius; Kiener, Daniel; Eckert, Jürgen (Advanced Engineering Materials, 2024)
FeTi–Cu composites with varying Cu contents are subjected to high-pressure torsion, and their deformation behavior is explored systematically using scanning electron microscopy, microhardness, and nanoindentation. The study identifies the limiting factors influencing the refinement during severe plastic deformation. The pronounced strength differences between phases lead to fragmentation primarily through hard–hard (FeTi–FeTi) contact points, promoted by homogeneous, i.e., nonlocalized, and possibly turbulent material flow. These conditions are prevalent in Cu-rich composites and during high-temperature deformation. Conversely, Cu-lean composites exhibit deformation localization, hindering the fragmentation process. Abrasion becomes an efficient refinement mechanism at the submicron-/nanoscale, particularly for composites containing higher concentrations of nanocrystalline FeTi and exhibiting homogeneous plastic deformation. Consequently, deformation localization in Cu-lean composites inhibits both refinement mechanisms, while Cu-rich compositions and higher temperatures result in efficient refinement but at the risk of coarsening at the nanoscale. Refinement is localization-limited in the former case and abrasion-limited in the latter. Optimized processing conditions can overcome these constraints, yielding a uniform nanocomposite. This study sheds light on the intricate interplay of the mechanical properties of the respective phases in a composite, emphasizing the importance of tailored compositions and deformation conditions to optimize nanocomposites, particularly when dealing with challenging material pairings.
Publisher Copyright: © 2024 The Author(s). Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: deformation localization; high-pressure torsion; mechanical properties; nanocomposites; refinement

Multiphase evolution of fluids in the Rudnik hydrothermal-skarn deposit (Serbia) - Petrovic, Stefan; Bakker, Ronald Jack; Cvetkovic, Vladica; Jelenkovic, Rade (Mineralogy and Petrology, 2024)
This study presents and discusses first detailed petrographic, microthermometric and Raman spectroscopic data from quartz-hosted fluid inclusions at Rudnik Zn-Pb-Cu-Ag skarn deposit (Serbia) and combines them with the information on skarn- and ore paragenesis. Three periods in the metamorphic-hydrothermal history of the deposit are recognized: 1) the pre-ore prograde skarn period when garnet-clinopyroxene skarns formed, 2) the syn-ore period that encompasses a retrograde stage marked by epidote and zoisite and a quartz-sulfide stage characterized by quartz, pyrrhotite, sphalerite, galena and chalcopyrite, and 3) the post-ore period associated with precipitation of calcite and quartz. The hydrothermal evolution is inferred from studying six groups of quartz-hosted fluid inclusions (FI). Two-phase FI of high- (Group A) and moderate salinity (Group B) are found in quartz cores and homogenized at 380–390 °C (mode) and 370–380 °C (mode), respectively. Group A FI consists of H 2O-NaCl liquids and CO 2-CH 4 gas mixtures and likely represents the original fluid composition, whereas Group B FI records dilution of the original fluid at constant temperature, with a slight increase in CH 4 contents. The quartz cores also contain Group C as volatile-rich FI (mostly CO 2 with up to 10 mol% CH 4 and H 2S) of a moderately low salinity and liquid-rich Group D FI composed of pure water with homogenization temperatures of 180–200 °C (mode). The transitional zones of quartz crystals show overgrowth textures and host Group E FI with low salinity that homogenized at 235–401 °C, which vapour phase is a CO 2-CH 4 mixture with up to 17 mol% CH 4. Group F comprises FI found within the rim zones of quartz crystals and they exhibit a low salinity and homogenization temperatures between 259–365 °C. Accordingly, the hydrothermal history at Rudnik involved: a) mixing of different salinity fluids at high temperatures (Groups A and B—retrograde stage), b) introduction of fluids with high volatile contents (Group C) and cooling of fluids with constant salinity (between Groups E and F), which likely correspond to the quartz-sulfide stage, and c) inflow of meteoric water (Group D—the post-ore quartz-calcite stage).
Publisher Copyright: © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.
Keywords: Fluid inclusions; Rudnik; Serbian Cenozoic Magmatic Province; Skarn deposit; Western Tethyan Metallogenetic Belt

Reshapable bio-based thiol-ene vitrimers for nanoimprint lithography - Sölle, Bernhard; Reisinger, David; Heupl, Sarah; Jelinek, Alexander; Schlögl, Sandra; Rossegger, Elisabeth (Reactive & functional polymers, 2024)
Taking inspiration from natural surfaces known for their ability to adaptively remodel their shape, we fabricated stimuli-responsive microstructures by using UV-induced nanoimprint lithography. For this, a fully bio-based dynamic thiol-ene photopolymer was synthetized by the radical mediated addition of a trifunctional eugenol-based thiol (SH3E) crosslinker across an allylated linseed oil (ALELO). To catalyze the bond exchange reactions between the hydroxyl and ester groups within the network, a bio-based eugenol phosphate ester was introduced as a transesterification catalyst. Pure eugenol was further added as a reactive diluent to increase the number of hydroxyl groups and thus, accelerate the thermo-activated bond exchange reactions. Once cured by UV exposure, the dynamic photopolymer is thermally stable up to 250 °C and is able to relax 63% of the original stress within 62 min at 160 °C. Subsequently, films with micropillars, having an aspect ratio of 1:2.5 were prepared by using nanoimprint lithography. The macroscopic reflow capability of the dynamic network enabled a reorientation of the imprinted structures during a thermal reshaping step. The imprints were characterized by 2D/3D optical microscopy, μCT imaging and static water contact angle measurements. Based on the orientation of the micropillars, the water contact angle was varied between 118° and 95°, giving rise to a possible application in microfluidic devices.
Publisher Copyright: © 2024
Keywords: Biobased thiol-ene networks; Nanoimprint lithography; Photopolymerization; Switchable surfaces; Vitrimers

Energy Absorption and Beam Damage during Microfocus Synchrotron X-ray Diffraction - Stanko, Štefan T.; Schawe, Jürgen E. K.; Spieckermann, Florian; Eckert, Jürgen; Löffler, Jörg F. (The journal of physical chemistry letters, 2024)
In this study, we combine in situ fast differential scanning calorimetry (FDSC) with synchrotron X-ray measurements to study simultaneously the structure and thermophysical properties of materials. Using the example of the organic compound BCH-52, we show that the X-ray beam can heat the sample and induce a shift of the heat-flow signal. The aim of this paper is to investigate the influence of radiation on sample behavior. The calorimetric data is used to quantify the absorbed beam energy and, together with the diffraction data, reveal an irreversible damage of the sample. The results are especially important for materials with high absorption coefficients and for high-energy X-ray and electron beams. Our findings illustrate that FDSC combined with X-ray diffraction is a suitable characterization method when beam damage must be minimized.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.

KIRAMET - Neubauer, Melanie; Rückert, Elmar (Integrated Computational Materials, Process and Product Engineering 2024, 2024)

Influence of broad ion beam polishing on the surface roughness of hydrated cement paste and its implications on microstructural analysis - Sammer, Thomas; Shi, Xiangyun; Khan, Muhammad Zubair; Matkovic, Aleksandar; Teichert, Christian; Raith, Johann (Cement and concrete research, 2024)
In recent years, the technical capabilities of high-resolution Scanning Electron Microscopes (SEM) improved significantly. To fully utilise their potential, it is crucial that also the preparation techniques are advanced to obtain a high-quality surface which preserves even nanometre sized microstructural features. In this study, state-of-the-art resin-embedded polishing, and novel Broad Ion Beam (BIB) milling of hydrated cement paste are compared. SEM microstructural investigations are aided by image processing to determine porosity and pore geometry factors. Additionally, a comprehensive quantitative surface roughness analysis based on Atomic Force Microscopy scans is carried out. BIB-milling enabled the study of nanoscale features such as gel porosity or the acicular morphology of calcium-silicate-hydrates. Pores exhibit increased aspect ratios whereas resin-embedded polishing results in higher circularity. However, a superior vertical surface roughness was achieved by the resin-embedded polishing approach. The research highlights the advantages and drawbacks of BIB-milling as a polishing method for hydrated cement pastes.
Publisher Copyright: © 2024 The Authors
Keywords: Atomic force microscopy; Broad ion beam milling; Hydrated cement paste; Image processing; Surface roughness analysis

Detachment of a Soluble Particle at the Slag-Argon Interface - Zhang, Xiaomeng; Michelic, Susanne Katharina; Pirker, Stefan; Saeedipour, Mahdi (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)
The behavior of non-metallic inclusions at interfaces of high-temperature melt and molten slag affects the removal of inclusions and the consequent melt cleanness. This study presents real-time in situ observations on the behavior of an oxide particle in the vicinity of the slag-argon interface by means of high-temperature confocal scanning laser microscopy (HT-CSLM). On top of that, CFD simulations are conducted to investigate the underlying mechanisms of particle-interface interactions. In addition to revealing the particle motion process from the argon phase toward the slag, a significant particle morphology alteration associated with its dissolution in the slag is experimentally observed. Particularly, upon detachment from the slag-argon interface, the particle exhibits more dissolution at the near-interface area. By combining with numerical simulations, this study indicates that particle separation at the interface can be characterized as two stages. First, a short-term capillary force-driven motion stage happens until the particle initially settles at the interface. The settling position estimated by simulation shows good consistency with experimental measurement. Second, the particle takes a relatively long time to eventually detach from the interface, and this period is accompanied by particle dissolution. Investigations suggest that the concentration variation near the interface arising from particle dissolution triggers a Marangoni flow. This flow, in turn, enhances the local dissolution rate, consequently causing a significant particle morphology change that influences the detachment. This study provides new insight into the mechanism of inclusion removal through slag absorption in metallurgical processes. Both particle dynamics and dissolution kinetics, especially the effect of solutal Marangoni convection, are highlighted in detaching a small-scale particle from the fluid-fluid interface.
Publisher Copyright: © The Author(s) 2024.

Near-infrared spectroscopy in resin transfer molding—determination of the degree of cure - Salzmann, Moritz; Märzinger, Wolfgang; Teuchtmann, Michael; Ravindran, Bharath; Kirschnick, Ulrike; Fauster, Ewald (International Journal of Advanced Manufacturing Technology, 2024)
Near-infrared (NIR) spectroscopy is employed to directly monitor the degree of cure of composite material during the curing phase in the resin transfer molding (RTM) process. The composite material consists of natural fibers and an epoxy-amine resin system. The quantitative determination of the degree of cure, α, from the NIR spectra is realized by partial least square (PLS) regression in conjunction with various pre-treatments of the spectral data. As a reference, the degree of cure is determined by isothermal differential scanning calorimetry (DSC) experiments. The best PLS model that could be obtained for α is characterized by a determination coefficient of prediction (R²P) of 0.980 and root mean square error of prediction (RMSEP) of 4.4 %. While the spectra change during curing according to the literature for each RTM trial, significant differences can be observed between the spectra of different RTM trials. The reasons for this are discussed in detail. The findings show the potential of inline NIR spectroscopy for monitoring α in the RTM process.
Publisher Copyright: © The Author(s) 2024.
Keywords: Bio-composite; Degree of cure; Near-infrared spectroscopy; Resin transfer molding

Improving the corrosion resistance of 7055 alloy by manipulating passivation film through trace addition of TiB2 nanoparticles - Li, Xuekai; Wang, Wei; Wu, Yihong; Kang, Huijun; Guo, Enyu; LI, Jiehua; Chen, Zongning; Xu, Yanjin; Wang, Tongmin (Applied surface science, 2024)
In this study, 7055 alloy inoculated by a minor addition of TiB 2 nanoparticles was prepared and subjected to passivation treatment. The microstructures, pitting behaviors, and electrochemical properties of the 7055-0.5TiB 2 composite were comparatively investigated with respect to the base alloy. The results show that the incorporation of 0.5 wt% TiB 2 nanoparticles refines the grain size (from 142.4 μm to 44.1 μm) and reduces the volume fractions of the residual intermediates from 0.59 % to 0.49 %, leading to an increased thickness (from 4.05 nm to 5.95 nm) and improved homogeneity of the passivation film. Both the pitting diameter and the pitting area fractions are reduced upon immersing in 3.5 % NaCl for 24 h. Electrochemical test results show that the values of passivation layer resistance, charge transfer resistance, and polarization resistance are significantly increased, while the corrosion current is reduced after the incorporation of TiB 2 nanoparticles, confirming the formation of a more effective barrier layer, i.e., the passivation film. The improved corrosion resistance of 7055 alloy with the incorporation of TiB 2 nanoparticles is attributed to the reduced active dissolution rate in the grain boundary region and a more uniform and thicker passivation film with a lower corrosion rate.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Aluminum matrix composite; Aluminum microstructure; Corrosion; Passive film

Nanocomposite versus solid solution formation in the TiSiN system - Schalk, Nina; Moritz, Yvonne; Nayak, Ganesh Kumar; Holec, David; Hugenschmidt, C.; Burwitz, V.V.; Mathes, L.; Schiester, Maximilian; Saringer, Christian; Czettl, Christoph; Pohler, Markus; Mitterer, Christian; et al. (Acta materialia, 2024)
This work contributes to the ongoing scientific debate on the structure of TiSiN coatings. In order to illuminate the formation of a nanocomposite structure versus the formation of a Ti 1-xSi xN solid solution, a series of TiSiN coatings was synthesized and the influence of varying N 2 pressures and the addition of Ar to the deposition atmosphere on the structure of TiSiN coatings was investigated in detail. The powdered TiSiN coatings all exhibited a lower lattice parameter than reported for TiN, which further decreased with increasing N 2 pressure, at comparable elemental compositions. For all coatings the presence of a crystalline Ti 1-xSi xN solid solution as well as an amorphous SiN x phase fraction could be detected, where more Si was incorporated into the Ti 1-xSi xN solid solution at higher pressures, due to less energetic growth conditions and the additional kinetic activation stemming from Ar ions resulted in less Si incorporation. Density functional theory calculations showed that defects only play a subordinate role for the low observed lattice parameters.
Publisher Copyright: © 2024
Keywords: Atom probe tomography; Coatings; Microstructure; Nanocomposite; Solid solution; TiSiN; X-ray diffraction

Artificial thermal shock cracks in WRe – A proof of concept study - Sommerauer, Michael; Siller, Maximilian; Pippan, Reinhard; Bostrom, Neil; Maier-Kiener, Verena (Nuclear Materials and Energy, 2024)
Thermal shock cracks are frequently observed in environments where extensive thermal cycling at high amplitudes is common. Typical cases for such are first wall materials in proposed fusion reactors and rotating anodes for computed tomography scanners. The formation of these cracks is driven by significant tensile stresses during the cooldown phase, following prior plastic deformation at elevated temperatures. This work proposes an experimental approach, where artificial thermal shock-like structures are generated via femtosecond laser ablation in WRe as a model material. Following a detailed laser parameter study in a W sheet material, patterns were introduced to WRe samples and investigated by different microscopy techniques. Their morphology as well as their response to thermo-cyclic loads was investigated and compared to conventionally induced thermal shock cracks. The introduction of artificial cracks by femtosecond laser ablation that mimic the morphology and behaviour of naturally induced thermal shock cracks is feasible within certain boundaries. Cuts, comparable to thermal shock cracks in width and depth, can be ablated. The cuts show an effect on the surrounding microstructure in line with the thermal shock cracks. Therefore, comparability could be proven concerning morphological and microstructural aspects. The conducted thermo-cyclic fatigue tests revealed an analogous effect on subsequent damage accumulation between the thermal shock cracks induced by thermal loading and artificial laser ablated cuts, proving the comparability under dynamic loading conditions. The extent of the effect is adjustable by tailoring the geometry of the lasered structures. The presented work suggests the possibility of studying the influence of thermal shock cracks on further fatigue mechanisms in exceptionally demanding applications, such as first wall materials or rotating anodes, by practical experimentation. Based on the resulting in-depth understanding of underlying interactions, the lifetime of these components might be prolonged by a deliberate introduction of crack networks or laser-ablated structures.
Publisher Copyright: © 2024 The Author(s)
Keywords: Fatigue Testing; Femtosecond Laser Ablation; High-Temperature Electron Scanning Microscopy; In-situ Damage Acquisition; Thermal Expansion; Thermal Shock Cracking

Critical properties of plastic packaging waste for recycling: A case study on non-beverage plastic bottles in an urban MSW system in Austria - Gritsch, Lea; Breslmayer, Gisela; Rainer, Ricarda; Stipanovic, Hana; Tischberger-Aldrian, Alexia; Lederer, Jakob (Waste management, 2024)
The low recycling rate of post-consumer plastic packaging waste (PPW), which is partly due to insufficient separate collection, heterogeneous composition and high levels of contamination, poses a challenge in Austria, where the recycling rate must double in order to meet the target of 55 %. This study analyzes key packaging characteristics of non-beverage plastic bottles influencing recyclability, using Vienna as a case study. Additionally, a net quantity indicator and separate collection rates were calculated. 738 bottles from mixed MSW and 1,159 bottles from separate PPW collection were analyzed. The main polymer's proportion described by the net quantity indicator was higher for bottles from separate collection (69–72 %) than from mixed MSW (58 %), showing that a large share of the foreign materials are residues and dirt, with significantly higher contents in mixed MSW (20 %) than in separate collection (11 %). With a separate collection rate of 19.2 %, the great potential for recycling currently lies in mixed MSW at 4,112 t/yr. Thereof, 46 % is uncolored, 54 % is colored/white and, in terms of material grade, 30 % is food grade. The most common filling volume for PET, PP and HDPE was 0.5 < x ≤ 1.5 L (23–59 %) and the most common decoration technology was label (60–85 %). PET and PP had the highest shares of food-grade bottles (37–46 %), while PP had the highest share of colored bottles (22–31 %). The mechanical recycling potential of bottles depends largely on packaging characteristics, influencing separate collection and also automatic sorting. Harmonized design specifications are therefore crucial for this heterogeneous PPW fraction.
Publisher Copyright: © 2024 The Author(s)
Keywords: Verpackungsabfall; Getrennte Sammlung; Verpackungsdesign; Produktrückstände; Packaging design; Packaging waste; Product residues; Separate waste collection

Optimizing the tunnel ventilation design related to respirable dust in tunnelling by using CFD - Wei, Ranzhu; Galler, Robert; Weiß, Christian (World Tunnel Congress 2024, 2024)
Keywords: Optimization tunnel ventilation; Dust movement; Tunnel construction; Numerical simulation

Experimental investigation and computational thermodynamics of the quaternary system Fe-C-Mn-S - Littringer, Robert (51st International Conference on Computer Coupling of Phase Diagrams and Thermochemistry (CALPHAD LI), 2024)
During the reduction of iron ores, substantial amounts of S, originating from the coke, dissolve in the molten iron. S poses several problems during the casting and processing of steels, such as hot tearing or surface defects, respectively. Residual amounts of S are typically bound by adding Mn to the steel to avoid the formation of low-melting phases. Mn is also an important alloying element for large variety of steel grades. To track the steel quality during the casting process, online quality prediction systems are currently under development in numerous steel plants. Thermodynamic data of the steel grade are combined with solidification calculations and kinetic models to describe the casting process as a function of the casting parameters, whereby the thermodynamic information is obtained from the CALPHAD approach.In the present work, experiments in the systems Fe-Mn and Fe-Mn-S with very low amount of C (~ 150 ppm) were performed using Differential Scanning Calorimetry (DSC) and Differential Thermal Analysis (DTA). The Fe-Mn-Clow phase diagram at high temperatures was experimentally reconstructed up to 40 mass pct. Mn. [1] Previous thermodynamic assessments [2,3] showed noticeable deviation from the measured peritectic phase equilibria, which required further investigation and re-optimization of the thermodynamic database. Hence, a CALPHAD-type thermodynamic modeling of the Fe-Mn and Fe-Mn-C system using FactSage thermochemical software [4] was performed to improve the prediction of solid/liquid phase equilibrium temperatures. For the liquid phase, the Modified Quasichemical Model (MQM) was used, solid solutions were described by the Compound Energy Formalism (CEF) and several compounds with constant composition were treated as stoichiometric. In the second part, the experimental and computational approach is combined and applied to the ternary Fe-Mn-S system, as shown exemplary in Figure 1 (a). Two isopleth sections of 0.5 and 2.0 mass pct. Mn with up to 0.3 mass pct. S were studied. The DSC technique enabled also to analyze the dissolution of manganese sulfides (Mn,Fe)S, as can be seen in Figure 1 (b), which was additionally in situ by high temperature laser scanning confocal microscopy (HT-LSCM). Hence, the proper evaluation of the DSC signals could be confirmed. Though a significant improvement was obtained for calculating the Fe-C-Mn system, the previous evaluation of the Fe-Mn-S system, which in this case was selected from the studies of Kang and coworkers [2,3], already led to excellent results.References:[1] Presoly, P., private communication, Montanuniversitaet Leoben, 2023[2] Y.-B. Kang, Critical evaluations and thermodynamic optimizations of the Mn–S and the Fe–Mn–S systems. Calphad, 34 (2010), 2, pp. 232–244.[3] M.-S. Kim and Y.-B. Kang, Thermodynamic Modeling of the Fe-Mn-C and the Fe-Mn-Al Systems Using the Modified Quasichemical Model for Liquid Phase. Journal of Phase Equilibria and Diffusion, 36 (2015), 5, pp. 453–470.[4] C.W. Bale et al., FactSage thermochemical software and databases, 2010–2016. Calphad, 54 (2016), pp. 35–53.

Hybrid data-driven thermodynamically-based temperature modeling of secondary steelmaking - Kavic, Daniel; Bernhard, Michael Christian; Rössler, Roman; Bernhard, Christian (51st International Conference on Computer Coupling of Phase Diagrams and Thermochemistry (CALPHAD LI), 2024)

Interplay between alloying and tramp element effects on temper embrittlement in bcc iron: DFT and thermodynamic insights - Reiners-Sakic, Amin; Schnitzer, Ronald; Holec, David (Acta materialia, 2024)
The details of the temper embrittlement mechanism in steels caused by impurities are unknown. Especially from an atomistic point of view, there are still open questions regarding their interactions with alloying elements such as Ni, Cr, and Mo. Therefore, we used density functional theory to investigate the segregation and co-segregation behavior and the resulting influence on the cohesion of three representative tilt grain boundaries in iron. The results are implemented in a multi-site and multi-component kinetic and thermodynamic model for grain boundary segregation, to gain insights into the temporal and final grain boundary coverage. Our results show that the segregation tendency of As, Sb, and Sn is stronger than that of the alloying elements and significantly mitigates the grain boundary cohesion. Depending on the GB type, interactions between Sb and Sn vary from negligible to strongly attractive, which increases the likelihood of co-segregation. The cohesion-weakening effect is further amplified when elements such as Sb, Sn, and As co-segregate, compared to their individual segregation. In contrast, the co-segregation of Ni and Cr does not significantly increase the enrichment of impurities at grain boundaries, and their impact on cohesion is found to be negligible. The ability of Mo to mitigate reversible temper embrittlement is primarily attributed to its cohesion-enhancing effect and its capability to repel tramp elements from GBs, rather than scavenging them within the bulk, as suggested by previous literature.

Multi-Material 3D Printing of Biobased Epoxy Resins - Bergoglio, Matteo; Rossegger, Elisabeth; Schlögl, Sandra; Griesser, Thomas; Waly, Christoph; Arbeiter, Florian; Sangermano, Marco (Polymers, 2024)
Additive manufacturing (AM) has revolutionised the manufacturing industry, offering versatile capabilities for creating complex geometries directly from a digital design. Among the various 3D printing methods for polymers, vat photopolymerisation combines photochemistry and 3D printing. Despite the fact that single-epoxy 3D printing has been explored, the fabrication of multi-material bioderived epoxy thermosets remains unexplored. This study introduces the feasibility and potential of multi-material 3D printing by means of a dual-vat Digital Light Processing (DLP) technology, focusing on bioderived epoxy resins such as ELO (epoxidized linseed oil) and DGEVA (vanillin alcohol diglycidyl ether). By integrating different materials with different mechanical properties into one sample, this approach enhances sustainability and offers versatility for different applications. Through experimental characterisation, including mechanical and thermal analysis, the study demonstrates the ability to produce structures composed of different materials with tailored mechanical properties and shapes that change on demand. The findings underscore the promising technology of dual-vat DLP technology applied to sustainable bioderived epoxy monomers, allowing sustainable material production and complex structure fabrication.
Publisher Copyright: © 2024 by the authors.
Keywords: 3D printing; biobased; epoxy thermosets; multi-materials; photopolymers

On matching and periodicity for (N,alpha)-expansions - Langeveld, Niels; Kraaikamp, Cor (The Ramanujan Journal, 2024)
Keywords: N-continued fractions; quadratic irrationals; matching; periodicity

Experimental and thermodynamic evaluation of the Fe-Si system and application to the processing of silicon steels - Bernhard, Michael Christian; Presoly, Peter; Kavic, Daniel; Wi, Tae-Gyu; Park, Won-Bum; Rössler, Roman; Jungreithmeier, Alfred; Ilie, Sergiu; Bernhard, Christian; Kang, Youn-Bae (2024)

How DSC measurements and CALPHAD helps to avoid breakouts during the continuous casting of peritectic steels - Presoly, Peter; Bernhard, Michael Christian; Bernhard, Christian; Hahn, Susanne; Ilie, Sergiu (2024)
Keywords: DSC; peritectic; casting

Microstructural investigation of the undercooled austenite in the Fe-C - Jacob, Aurélie; Presoly, Peter; Gürtenhofer, Richard; Kozeschnik, Ernst; Povoden-Karadeniz, Erwin (2024)

All van der Waals Semiconducting PtSe2 Field Effect Transistors with Low Contact Resistance Graphite Electrodes - Aslam, Muhammad Awais; Leitner, Simon; Tyagi, Shubham; Provias, Alexandros; Tkachuk, Vadym; Pavlica, Egon; Dienstleder, Martina; Knez, Daniel; Watanabe, Kenji; Taniguchi, Takashi; Yan, Dayu; Shi, Youguo; et al. (Nano Letters, 2024)
Contact resistance is a multifaceted challenge faced by the 2D materials community. Large Schottky barrier heights and gap-state pinning are active obstacles that require an integrated approach to achieve the development of high-performance electronic devices based on 2D materials. In this work, we present semiconducting PtSe2 field effect transistors with all-van-der-Waals electrode and dielectric interfaces. We use graphite contacts, which enable high ION/IOFF ratios up to 109 with currents above 100 μA μm-1 and mobilities of 50 cm2 V-1 s-1 at room temperature and over 400 cm2 V-1 s-1 at 10 K. The devices exhibit high stability with a maximum hysteresis width below 36 mV nm-1. The contact resistance at the graphite-PtSe2 interface is found to be below 700 Ω μm. Our results present PtSe2 as a promising candidate for the realization of high-performance 2D circuits built solely with 2D materials.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society
Keywords: contact resistance; graphene; graphite electrodes; Platinum diselenide; transistors

Improved conditions for the distributivity of the product for σ-algebras with respect to the intersection - Steinicke, Alexander; Rao, K.P.S. Bhaskara (Mathematica Slovaca, 2024)
We present a variety of refined conditions for σ-Algebras A (on a set X), F; G (on a set U) such that the distributivity equation (Formula Presented) The article generalizes the results in an article of Steinicke (2021) and includes a positive result for-Algebras generated by at most countable partitions, which was not covered before. We also present a proof that counterexamples may be constructed whenever X is uncountable and there exist two α-Algebras on X which are both countably separated, but their intersection is not. We present examples of such structures. In the last section, we extend Theorem 2 in Steinicke (2021) from analytic to the setting of Blackwell spaces.
Publisher Copyright: © 2024 Mathematical Institute Slovak Academy of Sciences.
Keywords: sigma-algebra; intersection of sigma-algebras; product sigma-algebras; counterexample for sigma-algebras; sigma-Algebra; intersection of sigma-Algebras; product sigma-Algebras; counterexample for sigma-algebras.

Applied Life Cycle Based Environmental Analysis - Feichtinger, Gerald; Schlar, Daniel; Mark, Daniel; Grabner, Christoph (Science 4 Technology @MUL, 2024)
Keywords: Environmental Assessment; Carbon Footprint; Data Analysis Software; Applications

Compaction behaviour of textile reinforcements - Bender, Marcel (Science 4 Technology @MUL, 2024)
Keywords: Composites; RTM; Compression test

Hydrogen uptake and embrittlement of steels under highest pressures - Eichinger, Matthias; Mori, Gregor Karl (Science 4 Technology @MUL, 2024)

Parameter Study for the Numerical Analysis of the Wire Arc Additive Manufacturing Process - Czipin, Marcel (2024)

Recycling of Paper Machine Clothing - Duretek, Ivica (Science 4 Technology @MUL, 2024)

Additive Manufacturing Material Extrusion @ Institute of Polymer Processing - Schuschnigg, Stephan (Science 4 Technology @MUL, 2024)

Additive Manufacturing of Aluminium by Material Extrusion MEX - Momeni, Vahid (Science 4 Technology @MUL, 2024)

Chemitecture: Dielectric Elastomer Actuator (DEA) produced by Material Extrusion (MEX) - Raguz, Ivan (Science 4 Technology @MUL, 2024)

Closing the circle of polyolefin packaging - Krempl, Nina (Science 4 Technology @ MUL, 2024)

Extrusion and Additive Manufacturing@ Institute of Polymer Processing - Schuschnigg, Stephan (Science 4 Technology @MUL, 2024)

LightCycle: Upcycling of regenerates with a new Injection Moulding Compounder (IMC) - Shahroodi, Zahra (Science 4 Technology @MUL, 2024)

Material Data Determination @ Institute of Polymer Processing - Duretek, Ivica (Science 4 Technology @MUL, 2024)

Recycling Biobased Plastics - Main, Priyanka (Science 4 Technology @MUL, 2024)

Successful Integration of Circular Economy Concepts for the Extractive Industry - Murphy, Mariaelena; Obenaus-Emler, Robert; Pacher, Corina (Springer, 2024)
This chapter delves into the area of transversal skill development within the engineering domain, with a specific focus on the Extractive Mining Industry. It commences by underlining the importance of the Sustainable Development Goals (SDGs), notably focusing on SDG12, Responsible Consumption and Production. The chapter elucidates the pivotal role SDG12 plays in fostering sustainable consumption and production patterns, offering a contextual backdrop to the subsequent exploration of transversal skills within the extractive sector. A pivotal theme within the context of this chapter is the profound impact of the extractive industry on the environment. Recognising the imperative to address environmental concerns, the chapter introduces the principles of the Circular Economy as a strategic avenue for instilling sustainability within the industry. It ventures into the conceptual landscape of circular economy principles and their potential applications in mitigating environmental impact, thereby paving the way for a more sustainable extractive sector. Central to the discourse is the integration of circular economy concepts into the extractive industry, emphasising the transformative potential it holds. The narrative underscores the need for a paradigm shift in industry practices, advocating for a holistic approach that not only meets current demands but also ensures the preservation of resources for future generations. Moving beyond environmental considerations, the chapter critically examines the concept of competence and its symbiotic relationship with transversal skills. Providing a solid theoretical foundation, it delineates the intrinsic value of cultivating competence profiles within the extractive industry. By elucidating the nexus between competence and transversal skills, the chapter advocates for a comprehensive approach to professional development that transcends traditional skill sets. In a culminating synthesis, the chapter presents a purpose-designed competence profile tailored to the extractive industry. This profile encapsulates the transversal skills imperative for professionals to navigate the dynamic landscape of the sector successfully. Through this multifaceted exploration, readers are equipped with a nuanced and comprehensive understanding of the fundamental components essential for cultivating transversal skills indispensable for success in the extractive industry. The chapter serves as a leading light for industry practitioners, educators, and policymakers alike, propelling them towards a future where sustainable practices and transversal skills converge for a resilient and competitive extractive sector.
Keywords: Circular Economy; Extractive Industry

Wintersport Ressource Efficiency and Improved Circular Economy - Krempl, Nina (Science 4 Technology @MUL, 2024)

Beyond Hot Air. - Saxinger, Gertrude; Auer, Marlene; Batterbury, Simon P.; Eyselein, Gabriel; Jensen, Ellen Marie; Kowasch, Matthias; Melcher, Frank; Wilson, Emma (Mining the connections, 2024)

Multi-proxy record of the Austrian Upper Triassic Polzberg Konservat-Lagerstätte in light of the Carnian Pluvial Episode - Lukeneder, Alexander; Lukeneder, Petra; Sachsenhofer, Reinhard; Roghi, Guido; Rigo, Manuel (Scientific Reports, 2024)
We present a multi-proxy investigation of a lower Carnian basinal succession from Polzberg in the Northern Calcareous Alps (Lower Austria). A section comprising a unique Konservat-Lagerstätte was studied based on bio- and chemostratigraphy along with geophysical methods, yielding a detailed and robust stratigraphic calibration of the Polzberg succession. The Polzberg section revealed the paleoceanographic history and helped to identify a global climatic reversal, the Carnian Pluvial Episode. The age of the Upper Triassic Reingraben formation in the Northern Calcareous Alps is refined as the Austrotrachyceras austriacum Zone within the lower Carnian (Julian 2). Ammonoids and conodonts provide a detailed biostratigraphic subdivision that serves as a basis for analyses of the faunal distribution and the paleoenvironmental evolution of the Upper Triassic Reifling Basin. The succession includes lithological and facies changes similar to those of coeval units in the Tethys. The Carnian was characterized by a weak (~ 1‰) positive δ13C trend, punctuated by a negative shift during the lower Carnian corresponding to the initiation of the Carnian Pluvial Episode, a period representing the onset of early/late Carnian transitional global greenhouse conditions. Organic maturity parameters and the conodont alteration index (CAI) show that the thermal overprint of the Polzberg section is low. Biomarker proxies suggest that the organic matter of the uppermost Göstling formation is a mixture of marine and terrestrial material deposited in a dysoxic environment. Within the overlaying Reingraben formation, the amount of marine biomass decreased gradually upwards. Oxygen-depleted conditions, probably due to water-column stratification, continued during deposition of the Reingraben formation. Bacterial sulfate reduction played a major role in organic matter degradation.
Publisher Copyright: © The Author(s) 2024.

Student perspectives on the Wolfsberg lithium project in Austria - Kowasch, Matthias; Baumann, Christoph; Batterbury, Simon P.; Melcher, Frank; Saxinger, Gertrude; Wilson, Emma (Mining the connections, 2024)

Time for green extractivism in the EU? - Kowasch, Matthias; Melcher, Frank; Auer, Marlene; Batterbury, Simon P.; Eyselein, Gabriel; Lesser, Pamela; Saxinger, Gertrude; Wilson, Emma (Mining the connections, 2024)

Green and blue infrastructure as model system for emissions of technology-critical elements - Trimmel, Simone; Spörl, Philipp; Haluza, Daniela; Lashin, Nagi; Meisel, Thomas C.; Pitha, Ulrike; Prohaska, Thomas; Puschenreiter, Markus; Rückert, Elmar; Spangl, Bernhard; Wiedenhofer, Dominik; Irrgeher, Johanna (Science of the total environment, 2024)
Over the recent decades, technological advancements have led to a rise in the use of so-called technology-critical elements (TCEs). Environmental monitoring of TCEs forms the base to assess whether this leads to increased anthropogenic release and to public health implications. This study employs an exploratory approach to investigate the distribution of the TCEs Li, Be, V, Ga, Ge, Nb, Sb, Te, Ta, Tl, Bi and the REYs (rare-earth elements including yttrium) in urban aerosol in the city of Vienna, Austria.Leaf samples (n = 292) from 8 plant species and two green facades and water samples (n = 18) from the Wienfluss river were examined using inductively coupled plasma tandem mass spectrometry (ICP-MS/MS). Surface dust contributions were assessed by washing one replicate of each leaf sample and analysing the washing water (n = 146). The impacts of sampling month, plant species and storey level on elemental distribution were assessed by statistical tools and generative deep neural network modelling. Higher TCE levels, including Li, V, Ga, Ge, Tl, Bi, and the REYs, were found in the winter months, likely due to the use of de-icing materials and fossil fuel combustion. A. millefolium and S. heufleriana displayed the highest levels of Li and Ge, respectively. In addition, increased elemental accumulation at lower storeys was observed, including Be, Sb, Bi and the REYs, indicating greater atmospheric dust deposition and recirculation closer to ground level.The results suggest a broad association of TCE levels with urban dust. This study enhances the current understanding of TCE distribution in urban settings and underscores the importance of their inclusion in pollution monitoring. It highlights the complex interplay of human activities, urban infrastructure, and environmental factors, offering valuable insights for managing urban environmental health risks and underlining the need for comprehensive urban ecosystem studies.
Publisher Copyright: © 2024 The Authors
Keywords: ICP-MS/MS; REEs; TCEs; Urban aerosol; Urban dust; Multielement analysis; Urban greening; Air pollution; Environmental monitoring; Rare-earth elements; Emerging pollutants

Small-angle neutron scattering reveals high-density adsorbed hydrogen in carbon micropores at low pressures and supercritical temperature - Stock, Sebastian; Seyffertitz, Malina; Kostoglou, Nikolaos; Rauscher, Max; Demé, Bruno; Mitterer, Christian; Paris, Oskar (9th International Workshop on Characterization of Porous Materials: From Angstroms to Millimeters, 2024)

Bio-Based Backbone for Highly Reactive Metal Alloys Feedstocks for MEX - Holzer, Clemens; Momeni, Vahid; Pöhle, Georg; Riecker, Sebastian; Schuschnigg, Stephan; Kukla, Christian (39th International Conference of Polymer Processing Society, 2024)
Keywords: Additive Manufacturing; Aluminium alloy; Material Extrusion

Magnetospheric Venus Space Explorers (MVSE) mission: A proposal for understanding the dynamics of induced magnetospheres - Albers, Roland; Andrews, Henrik; Boccacci, Gabriele; Castro Pires, Vasco Daniel; Laddha, Sunny; Lundén, Ville; Maraqten, Nadim; Matias, João; Krämer, Eva; Schulz, Leonard; Palanca, Inés Terraza; Teubenbacher, Daniel; et al. (Acta astronautica, 2024)
Induced magnetospheres form around planetary bodies with atmospheres through the interaction of the solar wind with their ionosphere. Induced magnetospheres are highly dependent on the solar wind conditions and have only been studied with single spacecraft missions in the past. Without simultaneous measurements of solar wind variations and phenomena in the magnetosphere, establishing a link between both can only be done indirectly, using statistics over a large set of measurements. This gap in knowledge could be addressed by a multi-spacecraft plasma mission, optimized for studying global spatial and temporal variations in the magnetospheric system around Venus, which hosts the most prominent example of an induced magnetosphere in our solar system. The MVSE mission comprises four satellites, of which three are identical scientific spacecraft, carrying the same suite of instruments probing different regions of the induced magnetosphere and the solar wind simultaneously. The fourth spacecraft is the transfer vehicle which acts as a relay satellite for communications at Venus. In this way, changes in the solar wind conditions and extreme solar events can be observed, and their effects can be quantified as they propagate through the Venusian induced magnetosphere. Additionally, energy transfer in the Venusian induced magnetosphere can be investigated. The scientific payload includes instrumentation to measure the magnetic field, electric field, and ion–electron velocity distributions. This study presents the scientific motivation for the mission as well as requirements and the resulting mission design. Concretely, a mission timeline along with a complete spacecraft design, including mass, power, communication, propulsion and thermal budgets are given. This mission was initially conceived at the Alpbach Summer School 2022 and refined during a week-long study at ESA’s Concurrent Design Facility in Redu, Belgium.
Publisher Copyright: © 2024 The Author(s)
Keywords: Induced magnetosphere; Mission concept; Multi-spacecraft mission; Space Plasma Physics; Venus

Simulation of the Melting Region in Additive Manufacturing Material Extrusion Dies for Highly Filled Feedstocks - Schuschnigg, Stephan; Hentschel, Lukas; Holzer, Clemens (39th International Conference of Polymer Processing Society, 2024)
Material Extrusion (MEX) is a simpler AM technology, aﬀordable also for home use. There are diﬀerent designs of the dies, and we investigated two designs (MK10 and E3D), with each two variants. We assumed that the forces of the ﬁlament are related to the melt pool and not on the friction. For the investigation we used Ansys Polyﬂow and constructed the nozzle assemblies. We used a highly ﬁlled feedstock (55 vol.% 316L steel powder in a polymeric binder) and measured the temperature and shear dependent viscosity and the other material data. The region where we assume solid ﬁlament has a temperature dependent slip condition as a boundary, to obtain a smoother transition between the solid area and the melting region. The thermal conditions are diﬀerent for each variant. The MK10 variants are an all-metal construction and a PTFE tube inside. The E3D version has a shorter or longer PTFE insert. The calculations showed interesting results, especially for the temperatures, whereas the pressures were not satisfactory as the temperature dependent viscosity model had to be adapted to calculate lower temperatures. The temperature of the all-metal design showed that, at low extrusion speeds, the melt pool was approximately 15 mm, while in the PTFE version it was only 10 mm. At higher speeds the temperature in the all-metal does not change much, but in the PTFE the desired temperature cannot be reached. In the E3D version we can see similar results between the long and short PTFE tubes. One thing is the high thermal conductivity of the feedstock at 0.98 W/(m·K), in contrast to polymers having about 0.2 W/(m·K). The MEX printer is set at increasing speeds until the gears can be heard trying to push the ﬁlament, but the solid ﬁlament is blocked in the die because there is not enough heaHng capacity. This can be heard during trials to achieve maximum prinHng speeds. The next steps are measurements with a die equipped with a load cell between the die and the gear.
Keywords: Feedstocks; Simulation Model; Additive Manufacturing

Unlocking the Potential of Recycled Polypropylene in Food Packaging - Krempl, Nina; Holzer, Clemens; Pinter, Elisabeth; Frühwirth, Matthias; Shahroodi, Zahra; Jahn, Elisabeth; Aschermayer, Florian; Gabriel, Viktoria Helene (PPS 2024: 39th International Conference of the Polymer Processing Society, 2024)

Utilization of Charcoal Obtained from Woody Biomass in Metallurgical Processes Based on Solid–Gas Reactions - Dornig, Christian; Hanke, Gustav; Antrekowitsch, Jürgen (Metals, 2024)
The high demand for carbon-based products within pyrometallurgy is placing the industry in an increasingly challenging position to meet stringent requirements. To transition away from fossil carbon carriers, biochar emerges as a sustainable and CO2-neutral alternative, presenting a viable solution without necessitating fundamental adjustments to plant technology, unlike hydrogen as an alternative reducing agent. Prior investigations have underscored the potential of woody biomass pyrolysis products for CO2-neutral metallurgy. Nonetheless, it is imperative to recognize that biochar must meet distinct requirements across various metallurgical processes. This paper conducts a comparative analysis between biochar and petroleum coke using thermogravimetric analyses, surface measurements, reactivity assessments, and scanning electron microscopy. Furthermore, the performance in a furnace for simulating the Waelz process, specifically regarding ZnO reduction, is scrutinized. The results illustrate the optical differences between petroleum coke and biochar and the significantly higher reactivity and specific surface area of biochar. When used in solid–gas reactors, it is observed that due to its high reactivity, biochar reacts more vigorously and carbon is completely consumed. However, during the reduction of ZnO, only minor differences were monitored, making biochar comparable to petroleum coke. Therefore, under certain constraints, biochar can be considered a potential substitute for metallurgical solid–gas reactions.
Keywords: Charcoal; Biomass; Secondary Meatllurgy

Recovery of plastic packaging from mixed municipal solid waste. A case study from Austria - Blasenbauer, Dominik; Lipp, Anna-Maria; Fellner, Johann; Tischberger-Aldrian, Alexia; Stipanovic, Hana; Lederer, Jakob (Waste management, 2024)
Austria must recycle more packaging materials. Especially for plastic packaging waste, significant increases are necessary to reach the EU recycling targets for 2025 and 2030. In addition to improving separate collection and introducing a deposit system for specific fractions, the share of plastic packaging in mixed municipal solid waste (MSW) could be utilized.In Austria, about 1.8 million tonnes of mixed MSW are generated. This includes about 110,000 t/a of plastic packaging waste. Most of the mixed MSW (94 %) is sent directly or via residues from pre-treatment, such as mechanical–biological treatment or waste sorting, to waste incineration. While materials such as glass and metals can also be recovered from the bottom ash, combustible materials such as plastics must be recovered before incineration.This work aims to evaluate the recovery potential of plastic packaging waste in mixed MSW with automated waste sorting. For this purpose, two of the largest Austrian waste sorting plants, with a total annual throughput of about 280,000 t/a, were investigated. The investigation included regular sampling of selected output streams and sorting analysis.The results show that the theoretical recovery potential of plastic packaging from these two plants is 6,500 t/a on average. An extrapolation to Austria results in a potential of about 83,000 t/a. If losses due to further treatment, such as sorting and recycling, are considered, about 30,000 t/a of recyclate could be returned to plastic production. This would correspond to an increase in plastic packaging recycling rate from 25 % to 35 %.
Publisher Copyright: © 2024 The Author(s)
Keywords: Municipal solid waste; Plastic packaging waste; Recycling; Circular Economy; Material revovery facility; Automated waste sorting; Automated waste sorting; Circular economy; Material recovery facility; Municipal solid waste; Plastic packaging waste; Recycling

Increasing the melt viscosity of post-consumer recycled polypropylene via E-Beam techniques - Krämer, Johannes; Guedes de la Cruz, Gema del Carmen; Kern, Wolfgang; Roitner, Julia; Witschnigg, Andreas; Rittmannsberger, Franz; Schnetzinger, Karl (Radiation physics and chemistry, 2024)
Polypropylene from post-consumer waste (PCR-PP) was melt-mixed with a di- and trifunctional molecule and treated with E-Beam radiation, to increase its viscosity and melt strength by long-chain branching and partial crosslinking. After adding diallyl- or triallylisocyanurate to polypropylene by melt compounding, the compounds were subjected to e-beam irradiation with doses between 10 and 60 kGy. Two types of polypropylene recyclates were investigated, both differing in the content of polyethylene. The samples were investigated with respect to the formation of microgels (gel content), rheological behaviour, melt flow rate and their mechanical properties. It was found that low irradiation doses in the range from 10 to 30 kGy reduce the melt flow rate significantly, and increase the tensile properties of PCR-PP while the gel content stays low. The results are discussed with respect to the amount of polyethylene impurities, and the processing behaviour of polypropylene, aiming at technically feasible recycling strategies for polyolefin recyclates.
Publisher Copyright: © 2024 The Authors
Keywords: Electron beam techniques; Melt flow rate; Polypropylene recycling; Recyclate quality

Cu-doped perovskite-type oxides - Berger, Tobias; Drexler, Hedda; Ruh, Thomas; Lindenthal, Lorenz; Schrenk, Florian; Bock, Johannes; Rameshan, Raffael; Föttinger, Karin; Irrgeher, Johanna; Rameshan, Christoph (Catalysis today, 2024)
Perovskite-type oxides have gained significant attention in the scientific community due to their unique properties and potential applications. Their ability to exsolve reducible B-site cations (e.g. Co, Ni, Cu) combined with their flexibility regarding A-site and B-site composition allows for the tailoring of novel catalytic materials. This study focuses on B-site doped perovskite-type oxides with a general formula of Nd0.6Ca0.4Fe1-xCuxO3 and Pr0.6Ca0.4Fe1-xCuxO3 (x = 0.0, 0.03, 0.05, 0.10) for potential use as a catalyst for Methanol Steam Reforming via the exsolution of catalytically active Cu nanoparticles. The atomic and electronic structure, morphology, and exsolution behaviour of these materials were investigated experimentally and with density functional theory, with a specific emphasis on the impact of B-site doping with varying Cu content as well as choice of A-site element. Both parameters influenced the crystal structure, surface area, and morphology of the materials. The exsolution behaviour of the materials was observed using in-situ XRD at DESY beamline P02.1 at PETRA III, with nanoparticles forming after reductive treatments on the host oxide surface. The quantity and size of the nanoparticles were found to be adjustable by selecting the A-site ion, doping content at the B-site, and the choice of reducing agent. Materials with higher Cu content on the B-site exhibited facilitated exsolution. Furthermore, exsolution was promoted with Nd as the A-site element compared to Pr. In conclusion, the controlled exsolution of Cu nanoparticles introduces Cu-doped perovskite-type oxides as promising candidates for developing novel catalytic systems. The findings underscore the importance of fine-tuning the oxide composition (A-site element, amount of B-site dopant) to achieve tailored exsolution of nanoparticles, which is crucial for rational material design. By leveraging this knowledge, catalysts with finely tuned properties can be created for specific applications and operational environments.
Publisher Copyright: © 2024 The Authors
Keywords: DFT; Exsolution; In-situ XRD; Perovskite; Synchrotron

Thermodynamic Information and Evaporation Mechanism of Fe-M-C-S (M = As, Cu, Pb, Sb, Sn) Alloys for Controlling Tramp Elements in Steel - Park, Won-Bum; Bernhard, Michael Christian; Jung, Chanumul; Kang, Youn-Bae (2024)

Simulation of Secondary Metallurgical Processes by Using Computational Thermodynamics and Comprehensive Statistical Learning Methods - Kavic, Daniel; Bernhard, Michael Christian; Rössler, Roman; Bernhard, Christian (2024)

Corrigendum to “From abandoned mines to carbon sinks: Assessing the CO2 storage capacity of Austrian low-rank coal deposits” [International Journal of Coal Geology 286 (2024) 1–13/104495] - Safaei Farouji , Majid; Misch, David; Sachsenhofer, Reinhard F.; Rauscher, Max; Kostoglou, Nikolaos (International journal of coal geology, 2024)
This study represents the first assessment of CO 2 storage potential in Austrian coal seams. Coal samples were taken from Fohnsdorf and Leoben abandoned coal mines, with particular emphasis on the Fohnsdorf coal since Leoben coal reserves were largely mined during previous coal production. Several methods were used to compare coal characteristics, including Rock-Eval pyrolysis (RE), organic petrography, and low-pressure N 2 and CO 2 sorption measurements. Both Fohnsdorf and Leoben coal samples show low sulfur and ash yields, as well as correspondingly high total organic carbon (TOC) contents. The pyrolysis T max and vitrinite reflectance values agree with a low coal rank for both sites. According to the N 2 adsorption measurements at 77 K, low-lying mire coals from Fohnsdorf show a higher BET-specific surface area (BET-SSA) and BJH pore volume compared to raised-mire coals from Leoben. However, sapropelic shales and high-ash coals from Leoben show the highest BET-SSA and BJH pore volumes of all investigated samples and considerably exceed the N 2 adsorption volumes of pure coals from both locations (N 2 uptake up to 16 cm 3/g; avg. for all samples 5.4 cm 3/g). In contrast, the mean adsorbed CO 2 uptake measured at 273 K and ∼ 1 bar followed the order of Fohnsdorf low-lying mire coals > Leoben raised-mire coals > Leoben sapropelic coals and shales, ranging at ∼0.8 mmol/g, ∼0.7 mmol/g, and ∼ 0.2 mmol/g, respectively. This shows that BET-SSA and BJH equations did not allow for adequate estimation of CO 2 adsorption capacity trends in the investigated sample set. Furthermore, based on the existence of a hysteresis loop between CO 2 adsorption and desorption branches for all investigated samples, the occurrence of weak chemisorption phenomena during CO 2 adsorption is indicated. This effect helps to increase CO 2 uptake and storage safety since the chemisorption process is not fully reversible upon pressure decrease. Ultimately, the theoretical CO 2 sequestration potential of the remaining unmined Fohnsdorf coal reserves was estimated at 4.65 million tons, with an additional potential for enhanced coal bed methane production due to the gas-rich nature of Fohnsdorf coals with an estimated 1.2 billion m 3 of CH 4 in place.
Publisher Copyright: © 2024 The Authors
Keywords: CO adsorption; Coal; Fohnsdorf; Leoben; Nanopores; Nitrogen adsorption

High-cellulose content of in-situ Miocene fossil tree stumps and trunks from Lusatia lignite mining district, Federal Republic of Germany - Kus, J.; Dolezych, M.; Schneider, W.; Hower, J. C.; Hofmann, T.; Visiné Rajczi, E.; Bidló, A.; Bolodár-Varga, B.; Sachsenhofer, R. F.; Bechtel, A.; Stojanović, K.; Životić, D.; et al. (International journal of coal geology, 2024)
Publisher Copyright: © 2023
Keywords: Biomarkers; Calcofluor-stained CLSM; Carbon isotope; CLSM; Fossil and modern wood; Holocellulose; Lignite; micro-FTIR; Second Lusatian lignite seam; Xylite

Cationic UV-curing of bio-based epoxidized castor oil vitrimers with electrically conductive properties - Bergoglio, Matteo; Palazzo, Gabriele; Reisinger, David; Porcarello, Matilde; Kortaberria, Galder; Schlögl, Sandra; Sangermano, Marco (Reactive & functional polymers, 2024)
The growing appeal of carbon nanotube composites in the contemporary market derives from their exceptional thermal and chemical stability, coupled with electrical conductivity. In this study, we combined these salient features with a biobased epoxy matrix having vitrimeric properties, hence being reprocessable and resheapable, to obtain a biobased conductive coating. Epoxidised castor oil (ECO) was chosen as a monomer precursor for the straightforward synthesis. The synthesis relied on a cationic UV-curing process, embedding the conductive carbon nanotubes in the matrix. Photo DSC and transmission FTIR analysis were conducted to determine the final conversion of the epoxy rings in the cationic photocuring process. Thermo-mechanical properties were evaluated by tensile tests, and DMTA. Thermal stability was assessed by TGA. Dielectric spectroscopy confirmed increased electrical conductivity in the presence of increasing CNT content, reaching a percolation threshold at 0.5 phr of CNTs. Vitrimeric properties were proved by stress relaxation experiments, and the UV-cured composite underwent a thermo-activated transesterification reaction starting from 70 °C, catalysed by dibutyl phosphate. Overall, the ECO-CNT composite showed high thermal resistance (up to 400 °C) electrical conductivity with 0.5 phr CNT concentration, and vitrimeric properties. The study can be, therefore, considered a promising starting point to obtain sustainable biobased and electrically conductive vitrimers.
Publisher Copyright: © 2023
Keywords: Bio-based epoxy monomers; Cationic photopolymerization; Conductive films; Vitrimers

Laser-induced graphene formation on different wood species - Lengger, Sabine K.; Neumaier, Lukas; Haiden, Lukas; Feuchter, Michael; Griesser, Thomas; Kosel, Jürgen (Sustainable Materials and Technologies, 2024)
Conductive, 3D, porous graphene can be produced with a CO2 laser from a large variety of materials, including wood, at room temperature, and under inert atmosphere or after treatment for fire protection. Here, we investigated the suitability for direct conversion of 46 typical European and Asian woods into laser-induced graphene (LIG), without pre-treatment. The LIG was characterized by resistance measurements to determine if a conductive layer had formed, and via Raman spectroscopy. Here, we show, for the first time, that it is possible to produce LIG on certain woods under atmospheric conditions without additional fire protection treatment. We determined that the ability to produce LIG on untreated, natural wood under ambient atmosphere is favoured overall by a high density and a diffuse-porous xylem structure, as well as a high soluble lignin content. Some of these characteristics are similar to those required for high yields in char production. Problematic for the production of LIG-based electronics is the presence of pronounced growth rings, or other geometric wood features, with density variations, which can be reduced using specific cuts with minimized growth rings and absence of rays. This is the first time that untreated wood has been directly converted into LIG using a conventional CO2 laser and ambient atmosphere. Our results represent a further step towards the development of a new generation of sustainable electronics relying on natural materials.
Publisher Copyright: © 2023
Keywords: Laser-induced graphene; Natural materials; Supercapacitors; Sustainable electronics; Sustainable sensors; Wood

Design of Reversible Adhesives by Using a Triple Function of Ionic Liquids - Wanghofer, Florian; Kriehuber, Matthias; Reisinger, David; Floh, Florian; Wolfahrt, Markus; Schlögl, Sandra (Macromolecular materials and engineering, 2024)
Reversible adhesives are crucial for a circular economy of composites as they play a key role for rework, repair, and recycling of adhesively bonded components. Herein, electrically debondable adhesives are prepared by introducing ionic liquids in dynamic thiol–epoxy networks. The function of the ionic liquid in the networks is threefold as it accelerates the curing reaction between thiol and epoxy monomers, facilitates electrical debonding, and catalyzes thermoactivated transesterification reactions, required for rebonding at elevated temperature. A library of 1,3-dibutylimidazolium-based ionic liquids with varying anions is synthetized and it is found that 1,3-dibutyl-1H-imidazol-3-ium dicyanamide (DiButIm─N(CN)2) is superior in accelerating bond-exchange reactions between hydroxy and ester moieties at elevated temperature. Thus, a thiol–epoxy resin containing 20 wt% of DiButIm─N(CN)2 is used to impregnate glass fiber mats yielding adhesive connections for aluminum substrates with 10.2 MPa pull-off strength. The adhesive connections are successfully debonded at the metal–adhesive interface by applying 120 V. The samples are then rebonded via the thermoactivated change in the networks’ viscoelastic properties and ≈80% (8.1 MPa) of their original bond strength can be regained. By providing a simple strategy to synthetize reversible adhesives, this approach paves a way toward improved recyclability and repairability of adhesively bonded structures.
Publisher Copyright: © 2024 The Authors. Macromolecular Materials and Engineering published by Wiley-VCH GmbH.
Keywords: dynamic polymer networks; electrical debonding; ionic liquids; reversible adhesives; vitrimers

Recycling of mineral wool waste as supplementary cementitious material through thermochemical treatment - Doschek-Held, Klaus; Krammer, Anna; Steindl, Florian Roman; Sattler, Theresa Magdalena; Juhart, Joachim (Waste Management and Research, 2024)
Mineral wool is commonly used in construction as thermal insulation material. After the product’s lifetime, it is classified as hazardous waste if no trademark of the European Certification Board for Mineral Wool Products (EUCEB) or the German Institute for Quality Assurance and Labelling (RAL) exists. Mineral Wool Waste (MWW) is typically landfilled in Europe, which is challenging due to its low bulk density and dimensional stability. This circumstance highlights the need for alternative recycling methods that increase the recycling rate of construction and demolition (C&D) waste. This article outlines the recycling opportunities of MWW and focuses on the use of thermochemical treatment of different mixtures of input materials to produce a supplementary cementitious material (SCM). The material characterisation results and investigations on the binder suitability demonstrate that the slag fractions after the thermochemical treatment are well-qualified to be used as reactive binder components. Additionally, a material flow analysis was conducted to estimate the substitution potential of MWW as SCM in the Austrian cement industry.
Publisher Copyright: © The Author(s) 2024.
Keywords: glass wool; mineral wool waste; Recycling; stone wool; supplementary cementitious material; thermochemical treatment

Turning of high entropy alloy into high entropy carbides by modifying carbon content during reactive sintering - Valášek, D.; Pouchlý, V.; Salamon, David (Ceramics International, 2024)
Publisher Copyright: © 2024 Elsevier Ltd and Techna Group S.r.l.
Keywords: Carbides; Hardness; High entropy; Phase transition; Spark plasma sintering

Hydrogenation/Dehydrogenation kinetics of magnesium-based metal powders originating from different process routes - Vigl, Elias; Eisbacher-Lubensky, Jan; Kittinger, Friedrich; Weiß, Christian; Dopler, Martin; Schäffler, Peter; Edinger, Stefan; Dimopoulos, Theodoros; Gneiger, Stefan (18th International Symposium on Metal-Hydrogen Systems, 2024)

Large-scale experimental research in waste management: WASTE SCANNER and DIGITAL WASTE RESEARCH LAB - Kandlbauer, Lisa (Science 4 Technology @MUL, 2024)

Method development for digital waste analysis for digital waste analysis for non-hazardous mixed commercial waste - Kandlbauer, Lisa (Science 4 Technology @ MUL, 2024)

Micro-Mechanical Fracture Investigations on Grain Size Tailored Tungsten-Copper Nanocomposites - Schmuck, Klemens Silvester; Burtscher, Michael; Alfreider, Markus; Wurmshuber, Michael; Kiener, Daniel (JOM, 2024)
Tungsten-copper composites are used in harsh environments because of their superior material properties. This work addresses a tungsten-copper composite made of 20 wt.% copper, which was subjected to grain refinement by high-pressure torsion, whereby the deformation temperature was varied between room temperature and 400 °C to tailor the grain size. Deformation was performed up to microstructural saturation and verified by hardness measurement and scanning electron microscopy. From the refined nanostructured material, micro-cantilever bending beams with cross-sections spanning from 5 × 5 to 35 × 35 µm 2 were cut to examine possible size effects and the grain size influence on the fracture behavior. Fracture experiments were performed in situ inside a scanning electron microscope by applying a quasi-static loading protocol with partial unloading steps. Inspection of the fracture surfaces showed that all cantilevers failed in an inter-crystalline fashion. Nevertheless, remaining coarser tungsten grains impacted the resultant fracture toughness and morphology. Cantilevers fabricated from the 400 °C specimen exhibited a fracture toughness of 220 ± 50 Jm2 . For the room temperature cantilevers, a fracture toughness of 410 ± 50 Jm2 was observed, which declined to 340 ± 30 Jm2 for cantilevers < 10 × 10 µm 2, confirming a size effect. The increased fracture toughness is attributed to the delamination-like structures formed in the room temperature sample.
Publisher Copyright: © 2024, The Author(s).

Neuartige Sensoren und digitale Innovationen zur kontinuierlichen Prozessüberwachung am Beispiel von Schwingsieben - Krukenfellner, Philip (Stein & Kies (Mitgliederzeitung - Forum mineralische Rohstoffe), 2024)
Keywords: Schwingsiebe; Condition Monitoring; Schwingungsanalyse; Industrie 4.0; Vibrating Screens; Condition Monitoring; Vibration Analysis; Industrie 4.0

Prediction of thermal shock induced cracking in multi-material ceramics using a stress-energy criterion - Papšík, Roman; Sevecek, Oldřich; Schlacher, Josef; Bermejo Moratinos, Raul (Engineering Fracture Mechanics, 2024)

Walk the line: Erfolgsfaktor Citizen Science - Maurer, Jakob; Längauer, Julia; Duboc, Olivier; Hascher, Cornelia; Irrgeher, Johanna; Prohaska, Thomas; Puschenreiter, Markus; Schober, Michael; Teschler-Nicola, Maria; Pieler, Franz (2024)

Effect of Flashlamp Heating System Parameters on the Wedge Peel Strength of Thermoplastic Carbon Fiber Tape in the Automated Tape Placement Process - Legenstein, Alexander; Fauster, Ewald (Journal of Manufacturing and Materials Processing, 2024)
Laser-assisted automated tape placement systems are currently the state of the art regarding thermoplastic tape placement. Flashlamp heating systems are rather new in this field of application and offer high energy density with low safety requirements and moderate costs compared to laser-assisted automated tape placement systems. In this study, the effect of processing parameters on interlaminar bonding of carbon fiber-reinforced polyamide 6 tapes is investigated using a flashlamp heating system. The temperature during placement is monitored using an infrared camera, and the bonding strength is characterized by a wedge peel test. The bonding quality of the tapes placed between 210 °C and 330 °C at a lay-up speed of 50 mm/s is investigated. Thermogravimetric analysis, differential scanning calorimetry, and micrographs are used to investigate the material properties and effects of the processing conditions on the thermophysical properties and geometric properties of the tape. No significant changes in the thermophysical or geometric properties were found. Moisture within the tapes and staining of the quartz guides of the flashlamp system have significant influence on the bonding strength. The highest wedge peel strength of dried tapes was found at around 330 °C.
Publisher Copyright: © 2024 by the authors.
Keywords: automated tape placement; bonding; material characterization; polymer matrix composites; thermoplastic resin

Investigation of probable squat growth from initial surface cracks in rails using a three-dimensional rollover simulation - Gschwandl, Timna Jakomijna; Antretter, Thomas; Künstner, David; Scheriau, Stephan; Daves, Werner (Proceedings of the Institution of Mechanical Engineers, Part F: Journal of Rail and Rapid Transit, 2024)
Squats are rather complex failure mechanisms in rails and challenge railway operators all over the world, thus calling for a detailed investigation of squats by means of finite element analysis to locate the initiation and propagating mechanisms. In this work, a cyclic three-dimensional (3D) finite element model of a wheel-rail contact including an initial penny-shaped defect is used. This work presents the implementation of the starting penny-shaped crack in the rail for a wheel-rail simulation by utilising a submodel strategy. Moreover, viable evaluation options are shown. In the future, this set-up will help to assess multiple crack positions and possible squat growth mechanisms.
Publisher Copyright: © IMechE 2023.
Keywords: configurational force; crack driving force; elasto-plastic material model; finite element analysis; penny-shaped crack; residual stresses; Squats; initial surface cracks in rails; three-dimensional rollover simulation

Peculiarity of hydrogen absorption in duplex steels - Pogrielz, Thomas; Eichinger, Matthias; Weiser, Adam; Todt, Juraj; Hohenwarter, Anton; Ascii, Atacan; Sarac, Baran; Brandl, Dominik; Ressel, Gerald; Jary, Milan; Dlouhý, Antonin; Mori, Gregor Karl; et al. (Scripta Materialia, 2024)
Electrochemical hydrogen absorption in duplex steels is not fully understood. In this work, an in-situ synchrotron cross-sectional X-ray micro-diffraction analysis is performed on steel with comparable phase fractions of ferrite and austenite, coupled with electrolytic hydrogen charging. The results reveal that charging with a constant current density of 10 mA/cm² for 5 h leads to expanding the austenitic lattice to a depth of approximately 250 µm, up to ≥0.15 %. In contrast, the lattice parameter of the ferrite phase remains unchanged during this process. As the austenite expansion progresses, it generates different amounts of equivalent in-plane compressive stresses, which amount to approximately -150 and -450 MPa in the austenite and ferrite phases at the sample surface, respectively. Using a finite element model of grain interaction, this difference is qualitatively interpreted by mutual mechanical constraints between ferrite and austenite, as well as between the hydrogen-charged surface layer and the underlying material.
Publisher Copyright: © 2024 The Author(s)
Keywords: Duplex steel; Electrochemistry; Hydrogen embrittlement; Residual stress; Synchrotron x-ray diffraction

Metallographic Etching of Al–Mg–Zn–(Cu) Crossover Alloys - Samberger, Sebastian; Kremmer, Thomas; Stemper, Lukas; Tourey, Serena; Uggowitzer, Peter; Pogatscher, Stefan (Advanced engineering materials, 2024)
Various alloys demand customized etchants due to their diverse chemical compositions, particularly in the realm of aluminum alloys. Consequently, in this study, a technique is proposed for metallographic visualization of small grain structures within Al–Mg–Zn–(Cu) crossover alloys. In this method, a thermal pretreatment combined with an etching process is relied on. In the study, it is primarily sought to comprehend how grain-boundary precipitation affects etchability, addressing the complexities of characterizing these alloys. The demonstrated approach facilitates the swift assessment of grain sizes <10 μm using light optical microscopy. Exploring the etchability of Al–Mg–Zn–(Cu) crossover alloys across a standard heat-treatment pathway identifies the optimal treatment and suitable etchant for grain visualization. Through process refinement, a reduction in processing time is achieved by employing a single-step preheat treatment lasting 20 min at 180 °C post solution annealing. Transmission electron microscope analysis reveals continuous occupancy of the grain boundary with T-phase as the key factor influencing the alloy's etchability. Grain size assessment involves line intercept counting and equivalent circle diameter measurement for precise characterization.
Publisher Copyright: © 2024 The Authors. Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: aluminum alloys; crossover alloys; etching; grain size measurements; grain-boundary precipitations; light optical microscopies; T-phase

Vitrimer Transition Phenomena from the Perspective of Thermal Volume Expansion and Shape (In)stability - Klingler, Andreas; Reisinger, David; Schlögl, Sandra; Wetzel, Bernd; Breuer, Ulf; Krüger, Jan Kristian (Macromolecules, 2024)
Vitrimers are covalently cross-linked polymers that can be reshaped and recycled, triggered by the temperature. Well above the canonical glass transition temperature Tg, they gain malleable, thermoplastic-like properties; below, they behave as thermosets. The responsible molecular mechanism is enabled by dynamic covalent bond exchange. However, the underlying physics of the transition from thermoplastic to thermoset properties is rather unclear and the subject of current scientific debate. In this work, we address the questions of what extent the temperature-dependent malleability of vitrimers is reflected in the thermal expansion behavior and, conversely, to what extent the thermal expansion behavior is suited to characterize the respective creep behavior of vitrimers. It will be shown that at least in the case of the used model vitrimer, only the canonical glass transition is able to stop the vitrimer to undergo irreversible shape changes and that the often-discussed topology freezing temperature of vitrimers Tv is purely operational.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.

Reducing part deformation of isotactic polypropylene specimens fabricated with powder bed fusion technique through controlling crystallization behaviors - Gao, Xia; Guo, Junqiang; Zhang, Daijun; Li, Jing; Su, Yunlan; Arbeiter, Florian; Li, Huayi (Journal of polymer science, 2024)
Serious shrinkage and warpage are obstacles to the development of ideal isotactic polypropylene (iPP) materials for polymer-based powder bed fusion (PBF) technique. In this work, the variations of the dimensional accuracy of the PBF-printed iPP parts were investigated with various printing parameter and nucleating agent. The iPP parts printed at a scanning speed of 700 mm/s exhibit smaller extents of shrinkage and curling than those at lower speeds, due to a lower degree of crystallinity. Interestingly, iPP blended with the α- or β-nucleating agent demonstrates more serious part deformation with respect to neat iPP. Especially, α-nucleating agent tends to trigger the most severe curling under the investigated printing parameters. Based on X-ray diffraction and differential scanning calorimetry (DSC) results, both neat iPP and α-iPP parts crystallize into α-crystal, while β-iPP parts display the coexistence of β- and α-crystals. And, the difference of the crystallinity is less than 3% in three specimens. This suggests that both crystallinity and crystalline structure are not the main reasons for the shrinkage and warpage in this case. Instead, the severe part deformation of the α-iPP parts is assigned to the narrower sintering window as well as the higher onset crystallization temperature of α-iPP, which hinder relaxation of residual stresses. This work provides insights into the part deformation mechanism for PBF-processed polymer materials.
Publisher Copyright: © 2024 Wiley Periodicals LLC.
Keywords: crystallization behavior; isotactic polypropylene; part deformation; powder bed fusion technique

Evaluating Multi-target Regression Framework for Dynamic Condition Prediction in Wellbore - Keshavarz, Sahar; Elmgerbi, Asad; Vita, Petr; Thonhauser, Gerhard (The Arabian journal for science and engineering, 2024)
In recent years, the focus has shifted towards leveraging physics-based modelling and data-driven analysis to predict drilling incidents and anomalies in real time, with the goal of reducing non-productive periods. However, much of this attention has directed at specific drilling operations like drilling and tripping, leaving other vital processes, such as wellbore conditioning, comparatively overlooked. The primary objective of this study is to employ data-driven techniques for predicting the dynamic state of the wellbore by utilising sensor data, operating parameters, and surface measurements. Accurate predictions are pivotal for automating these processes, promising significant savings in both redundant time and associated costs, ultimately elevating operational efficiency.In this research, the surface drilling parameters such as flowrate, rotation speed, block position, and drill string length are incorporated with the surface measurements such as hookload, pressure, and torque during wellbore conditioning operation to predict further surface sensor measurements. Different parameter settings are evaluated to find the best approach. Six supervised learning algorithms are used to select the best prediction method. The findings reveal that considering all surface parameters and measurements yields the most accurate predictions. Among various single and multi-target regression methods, including deep learning approaches, the Gaussian process and random forest models exhibit the lowest prediction errors.By reliably predicting and understanding wellbore behaviour, this research paves the way for more efficient and autonomous drilling operations in the future, bridging a critical gap in the industry's automation capabilities.
Publisher Copyright: © The Author(s) 2024.
Keywords: Supervised learning; Wellbore monitoring; Surface drilling parameters; Wellbore conditioning; Multi-targetregression; Multi-target regression

Morphological investigations on silica and carbon-black filled acrylonitrile butadiene rubber for sealings used in high-pressure H2 applications - Clute, Clara; Balasooriya, Winoj; Cano Murillo, Natalia; Theiler, Géraldine; Kaiser, Andreas; Fasching, Michael; Schwarz, Thomas; Hausberger, Andreas; Pinter, Gerald; Schlögl, Sandra (International Journal of Hydrogen Energy, 2024)
To understand the effects of additives on the properties of rubber grades suitable for sealing applications in high-pressure H2 gas infrastructure, five acrylonitrile butadiene rubber (NBR) vulcanizates with different fillers and curing agents are investigated. Structure-property relationships of these grades are correlated with the additives and properties required for high-pressure gas atmospheres are evaluated. Further, the influence of the exposure to high-pressure hydrogen, i.e., hydrogen uptake and morphological changes after exposure, is evaluated. With the addition of a silica filler and a coupling agent for improved filler-matrix interfaces, similar overall properties, e.g. crosslink density, tensile strength, and storage modulus are obtained, compared to a carbon black (CB) filled grade. Density reduction after hydrogen exposure is significantly higher for CB-filled NBR, indicating higher hydrogen uptake in CB-filled rubber compared to silica filled NBR grades, or slower gas desorption. However, CB-filled specimens show to be less prone to filler migration than the silica-filled samples.
Publisher Copyright: © 2024 Hydrogen Energy Publications LLC
Keywords: Acrylonitrile butadiene rubber; Filler-rubber-interaction; High-pressure hydrogen gas; Rapid gas decompression (RGD); Sealing

Investigation on the Duration of Action of Mg3N2 as a Grain Refiner for AZ80 Alloy - Hösele, Thomas; Neunteufl, Ernst; Li, Jiehua (Metals, 2024)
In magnesium alloys with aluminum as an alloying component, zirconium loses its grain refinement effect as a grain refiner. Instead of zirconium, Mg3N2 can be used, and promising results have already been obtained. However, the duration of action of Mg3N2 has not been elucidated yet. The aim of this work is therefore to determine the grain size of the AZ80 alloy as a function of the duration of action of Mg3N2 and thus the economically reasonable duration of use. It was found that the Mg3N2 reaches its full effect from 30 min after a complete remelting and does not lose this grain refinement effect even after 90 min. It thus proves to be a stable and reliable grain refiner. A grain size of 146.3 ± 10.3 µm was achieved. Furthermore, a minimum tensile strength of 205 MPa with a break elongation of 5.99% was achieved.
Publisher Copyright: © 2024 by the authors.
Keywords: AZ80 alloy; grain refinement; growth restriction factor; mechanical properties; MgN; thermal analysis

Imaging hydrothermal alteration with electrical resistivity tomography in La Soufrière de Guadeloupe volcano - Mendieta, Aida; Rosas-Carbajal, Marina; Bajou, Raphaël; Baud, Patrick; Deroussi, Sébastien; Esposti Ongaro, Tomaso; Komorowski, Jean-Christophe; Kushnir, Alexandra; Villeneuve, Marlene C.; Heap, M. J. (2024)
Hydrothermal alteration plays a major role in volcanic instability. Improving techniques that allow us to better understand the timescales of alteration in active volcanoes is thus paramount. Since the reactivation of the fumarolic field at the top of the dome of La Soufrière de Guadeloupe (Guadeloupe, France) in 1992 and the expansion of its surface area in recent years, the area of study is subjected to prolonged variable alteration that has promoted past flank collapses and can also influence permeability and thus shallow depth overpressurization. During a field campaign in May 2022 we performed 25 electrical resistivity tomography (ERT) profiles in the summit of La Soufrière, next to active fumaroles and acid boiling ponds. These ERT profiles were inverted using the open-source code pyGIMLi. Thanks to the ERT profiles we are able to roughly map the altered areas to a depth of about 20 m in this zone of La Soufrière. Some of the byproducts of alteration that have been identified in La Soufrière are clays, sulfates and pyrite. Thus, we infer that the low electrical resistivity zones (<20 Ωm) correspond to alteration and high electrical resistivity (>1500 Ωm) corresponds to unaltered rock. Low electrical resistivity anomalies are observed north of the Breislack fault, near the fumaroles. The explored north-most region is characterized by higher values of electrical resistivity. We take into account ground temperature and spatial variability to interpret the electrical conductivity anomalies and we use this first high-resolution resistivity model to plan a repetition of our experiment. This time-lapse experiment will allow us to estimate the evolution of hydrothermal alteration in the volcano’s summit over a 2-year period in the context of the current ongoing multiparameter unrest.

Synthesis of Bio-Based Polyester Resins for Vat Photopolymerization 3D Printing - Cazin, Ines; Ocepek, Martin; Kecelj, Janez; Stražar, Aleš Stanislav; Schlögl, Sandra (Materials, 2024)
Driven by environmental considerations, the scientific community has directed great effort towards the synthesis of new materials derived from renewable resources. However, for photocurable resins, most commercially available building blocks still rely on petroleum-based precursors. Herein, we present a simple synthesis route for bio-based acrylate-modified polyester resins, whose viscosity is sufficiently low for processing them with vat photopolymerization 3D printing. The established synthesis route enables the gradual substitution of fossil-based raw materials with bio-based alternatives. The acid number, color and viscosity of the bio-based acrylic resins are characterized and photocurable formulations are prepared by adding a radical photoinitiator. The photopolymerization kinetics, and thermomechanical and mechanical properties of the photopolymers are investigated as a function of the resin structure and benchmarked against a commercially available petroleum-based counterpart. Finally, the processability of the new bio-based resins via digital light processing 3D printing is demonstrated and test specimens are successfully 3D printed with a resolution in the millimeter range.
Publisher Copyright: © 2024 by the authors.
Keywords: additive manufacturing; bio-based polymers; photocuring; polyester resins; vat photopolymerization 3D printing

Production of Permanent Magnets from Recycled NdFeB Powder with Powder Extrusion Moulding - Rathfelder, Stefan; Schuschnigg, Stephan; Kukla, Christian; Holzer, Clemens; Burkhardt, Carlo (Journal of Manufacturing and Materials Processing, 2024)
In the last fifteen years, several groups have investigated metal injection moulding (MIM) of NdFeB powder to produce isotropic or anisotropic rare earth magnets of greater geometric complexity than that achieved by the conventional pressing and sintering approach. However, due to the powder’s high affinity for oxygen and carbon uptake, sufficient remanence and coercivity remains difficult. This article presents a novel approach to producing NdFeB magnets from recycled material using Powder Extrusion Moulding (PEM) in a continuous process. The process route uses powder obtained from recycling rare earth magnets through Hydrogen Processing of Magnetic Scrap (HPMS). This article presents the results of tailored powder processing, the production of mouldable feedstock based on a special binder system, and moulding with PEM to produce green and sintered parts. The magnetic properties and microstructures of debinded and sintered samples are presented and discussed, focusing on the influence of filling ratio and challenging processing conditions on interstitial content as well as density and magnetic properties.
Keywords: powder extrusion moulding (PEM; metal injection moulding (MIM); production of NdFeB permanent magnets; recycling of EOL-magnets

Seismic while drilling with a diamond drill bit in project DIVE DT-1B borehole in the Ivrea-Verbano Zone (Western Alps, Italy) - Trabi, Bernd; Bleibinhaus, Florian; Greenwood, Andrew (EGU General Assembly 2024, 2024)
A unique Seismic While Drilling (SWD) experiment, whereby a diamond coring drill rig as the seismic source has been conducted in the Val d’Ossola, Western Alps, Italy. For the SWD experiment 64 3C-sensors are employed in an array at the surface and the vibrational action of coring the rock acts as an active seismic source within the borehole. The maximum offset of the sensor array is 480 m with non-uniform spacing that increases with distance. The drilling operation took place from early October until mid-December 2022 and reached a depth of approximately 580 m. The seismic sensors recorded at a sampling rate of 1 ms, which is more than sufficient for an expected frequency of up to 200 Hz. The proposed SWD experiment is to evaluate the potential and limitations of the SWD method for diamond core drilling commonly utilized in scientific drilling projects with a focus on fundamental developments of the methodology and data processing techniques. Ideally the drill-bit seismic record should produce a seismic image around the bore hole and ahead of the drill bit. First it is important to determine if a signal can be detected, and to what depth, from a diamond core drill bit. In contrast to percussion or reverse circulation drilling, the diamond core drilling method produces a very weak signal. The seismic data is also heavily contaminated by coherent and random noises generated at the drill site, including rig engines, generators and mud-pumps, vehicles, and the movement of equipment. Separation of theses coherent noises using radon transform has thus far failed and other wavefield separation methods are investigated. Using seismic interferometric methods for unknown source positions, we aim to detect the weak signal at known drill bit positions. This is promising especially at drilling depths where the drill-rig and drill-bit wave-fields are spatial or temporal separated from each other, due to their different origins and velocities. Interferograms are obtained using the cross-coherence method, which is applied to the recorded passive seismic data. These are computed from 30sec time windows of the continuous recordings and then stacked into the final interferogram to increase the signal-to-noise ratio. Instead of migration summation, semblance is measured for the interferometric migration process. For the migration process, a constant velocity model is sufficient in this hard-rock environment. The major noise sources that we image are the vibrations of the drill rig and power generator, which appear to mask the weaker signal from the drill bit. In an ongoing second experiment, we utilize grid power, reducing the noise sources to the mud-pumps, rotating string, and rig.
Keywords: Seismic while drilling; interferometry; matched field processing; source location imaging; geophysics; FWF; icdp; dive

Mapping elemental solutes at sub-picogram levels during aqueous corrosion of Al alloys using diffusive gradients in thin films (DGT) with LA-ICP-MS - Mukhametzianova, Gulnaz; Wagner, Stefan; Eskinja, Magdalena; Moshtaghi, Masoud; Mori, Gregor Karl; Prohaska, Thomas (Analytical and bioanalytical chemistry, 2024)
A novel approach using diffusive gradients in thin films (DGT) with laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) for two-dimensional mapping of elemental solute release at sub-picogram levels during aqueous corrosion of Al alloys is presented. Evaluation of different DGT gels with mixed micro-sized binding phases (polyacrylamide-Chelex-Metsorb, polyurethane (PU)-Chelex-Metsorb, PU-Chelex-Zr(OH) 4) demonstrated the superior performance of PU gels due to their tear-proof handling, low shrinkage, and compliance with green chemistry. DGT devices containing PU-Chelex-Zr(OH) 4 gels, which have not been characterized for Al sampling before, showed quantitative uptake of Al, Zn, and Cu solutes over time (t = 4–48 h) with higher Al capacity (Γ DGT = 6.25 µg cm −2) than different gels. Application of PU-Chelex-Zr(OH) 4 gels on a high-strength Al-Cu alloy (Al2219) exposed to NaCl (w = 1.5%, pH = 4.5, T = 21 °C) for 15 min in a novel piston-type configuration revealed reproducible patterns of Al and Zn co-solubilization with a spatial expansion ranging between 50 and 1000 µm. This observation, together with complementary solid-state data from secondary electron microscopy with energy-dispersive X-ray spectroscopy, showed the presence of localized pitting corrosion at the material surface. Detection limits for total solute masses of Al, Zn, and Cu were ≤0.72 pg, ≤8.38 pg, and ≤0.12 pg, respectively, for an area of 0.01 mm 2, demonstrating the method’s unique capability to localize and quantify corrosion processes at ultra-trace levels and high resolution. Our study advances the assessment of Al alloy degradation in aqueous environments, supporting the design of corrosion-resistant materials for fostering technological safety and sustainability. Graphical Abstract: (Figure presented.)
Publisher Copyright: © The Author(s) 2024.
Keywords: Aluminium; Chemical imaging; Corrosion; Diffusion; Passive sampling

Informing deep geothermal reservoir rock mass properties from drilling data - experience from IDDP-1 - Villeneuve, Marlene C.; Kennedy, Ben; Mortensen, Anette; Saubin, Elodie; Hammoud, Aliaa (Krafla Magma Testbed Symposium, 2024)

A sequential lumped kinetic modelling approach for the co-pyrolysis of plastic mixtures with a heavy refinery intermediate product in a tubular reactor - Lorbach, Sebastian-Mark; Lechleitner, Andreas; Schubert, Teresa; Lehner, Markus (Reaction chemistry & engineering, 2024)
The knowledge of reaction rates and reaction pathways is essential for the upscaling of laboratory- and pilot-sized plants to full scale industrial processes. Over the last decades lumped kinetic modelling became the standard modelling approach for cracking reactions of hydrocarbon blends. In this paper a sequential nine-lump kinetic model is developed. The model allows for a fully automatic calculation of the kinetic parameters and efficient implementation in process simulation software like PetroSim. The kinetic parameters were calculated using experiments in a laboratory sized tubular reactor with a mass throughput between 600 g h−1 and 2500 g h−1 and temperatures between 440 °C and 530 °C at a pressure of 15 bar. A feedstock of 30 wt% plastic in different blends (PP, LDPE, HDPE) and 70 wt% carrier medium, a heavy refinery intermediate product, was used for the fitting and evaluation of the kinetic model. The results were evaluated with a set of experimental data, independent from the set used for the fitting. A residual analysis shows that the model has good predictive capabilities and can be used to simulate the cracking reaction of plastics in a plug flow reactor over a broad range of operating conditions.
Publisher Copyright: © 2024 The Royal Society of Chemistry.
Keywords: chemical recycling; plastic waste; plastic to oil; feedstock recycling; co-pyrolysis

Functionalization of PTFE substrates with quaternary ammonium groups - Bandl, Christine; Kern, Wolfgang; Ranz, Matthias; Grabner, Bianca (Applied surface science, 2024)
Hydrogen produced by electrolysis using renewable energy sources offers a zero-emission alternative to fossil-based sources providing high efficiencies in all energy sectors. Anion Exchange Membrane Water Electrolysis (AEM-WE) combines the advantages of the established technologies, alkaline (AEL) and proton exchange membrane (PEM) water electrolysis. However, AEM-WE still requires optimization, especially with regard to the membrane, catalysts and electrode structure. In this contribution we focus on the improvement of PTFE-based binders for AEM-WE membranes, which provide high chemical stability but lack the required ion conductivity. Thus, the functionalization of PTFE towards quaternary ammonium moieties (QAS) was investigated employing two approaches: (i) NH3-plasma treatment and (ii) O2-plasma with subsequent coupling of aminosilanes. Finally, the surface coupled amino groups were converted into QAS via alkylation with iodomethane (CH3-I), introducing ion conductivity. Successful functionalization was proved by X-ray photoelectron spectroscopy (XPS), displaying changes in the surface composition of PTFE surfaces such as the introduction of amino groups at the expense of fluorine, and the increase in surface carbon content upon alkylation. Furthermore, contact angle measurements revealed increased wettability with water due to the introduction of the polar surface functionalities, while zeta potential measurements confirmed the increase of positive surface charges along the modification processes.

Overview of application of automated SEM/EDS measurements for inclusion characterization in steelmaking - Ramesh Babu, Shashank; Michelic, Susanne Katharina (MetalMat, 2024)
The scanning electron microscope equipped with an energy dispersive spectroscopy (SEM/EDS) is considered as a state-of-the-art characterization tool to determine the morphological features and the chemical composition of non-metallic inclusions in steel. Such a characterization is pivotal to assessing the steel quality, which influences the properties of end products. This paper offers a comprehensive review of the SEM/EDS system, tracing its historical developments and methodological advancements by various research groups which have contributed to non-metallic inclusion analysis. Then the discussions transition to developments that have matured the SEM/EDS platform. The paper highlights selected examples utilizing the SEM/EDS to examine inclusions across various steel grades and at different stages of the metallurgical process. Finally, latest advancements in integrating machine learning techniques to expedite the analysis process were discussed.
Keywords: SEM; non-metallic inclusions; steel; review

Influence of corrosion fatigue on the stress gradient effect of the aluminium alloy EN AW-6082 T6 - Schönowitz, Markus; Maier, Bernd; Grün, Florian (International Journal of Fatigue, 2024)
This study investigates the influence of corrosion fatigue on the fatigue strength of the aluminium alloy EN AW-6082 T6 with regard to the stress gradient. The experimental design involves varying loading conditions and specimen geometries to facilitate testing under three distinct stress gradients: tension/compression (0 mm -1), rotary bending (0.2 mm -1), notched rotary bending (5.3 mm -1). Reference constant loading tests in air as well as continuously irrigated corrosion fatigue tests in a 5 wt% NaCl-solution are conducted with a constant stress ratio of R =−1. The results reveal a substantial reduction in fatigue strength due to corrosion fatigue across all three stress gradients. The slope of the S-N curves drops by a factor of at least two and no second slope of the S-N curves is found within the tested load cycle range (up to 10 7). The study demonstrates a significant increase in the support factor for tests conducted in the corrosive environment. This discrepancy becomes more pronounced towards higher stress gradients and lower load cycle numbers. The application of the support factor derived from tests in a non-corrosive atmosphere is shown to be conservative, emphasizing the significance of accounting for corrosion effects in assessing fatigue behaviour.
Publisher Copyright: © 2024

Microscopic fracture toughness of notched porous sintered Cu micro-cantilevers for power electronics packaging - Hu, Dong; Du, Leiming; Alfreider, Markus; Fan, Jiajie; Kiener, Daniel; Zhang, Guoqi (Materials Science and Engineering: A, 2024)
To fulfill the high-temperature application requirement of high-power electronics packaging, Cu nanoparticle sintering technology, with benefits in low-temperature processing and high-melting point, has attracted considerable attention as a promising candidate for the die-attach interconnect. Comprehensive mechanical characterization of the sintered layer at a microscale is necessary to deepen the understanding of the fracture behavior and improve the reliable design of materials. In this study, microscale cantilevers with different notch depths were fabricated in a 20 MPa sintered interconnect layer. Continuous dynamical fracture testing of the microcantilevers was conducted in situ in a scanning electron microscope to detail the failure characteristic of the porous sintered structure. The microscopic fracture toughness of different notched specimens was obtained from the J-integral in the frame of elastic-plastic fracture mechanics. Specimens with deeper notches presented higher resistance to crack extension, while geometry factors of notch-to-width ratio between 0.20 and 0.37 exhibited a relatively stable microscopic fracture toughness ranging from 3.2 ± 0.3 to 3.6 ± 0.1 MPa m1/2.
Publisher Copyright: © 2024 The Authors
Keywords: Continuous stiffness testing; Cu nanoparticles sintering; Elastic-plastic fracture mechanics; Microscopic fracture toughness

Valorisation of metallurgical residues via carbothermal reduction - Krammer, Anna; Doschek-Held, Klaus; Steindl, Florian Roman; Weisser, Katharina; Gatschlhofer, Christoph; Juhart, Joachim; Wohlmuth, Dominik; Sorger, Christoph (Waste management & research, 2024)
The decarbonisation of the steel and cement industry is of utmost importance in tackling climate change. Hence, steel production in modern integrated steel mills will be shifted towards electric arc furnaces in the future, in turn causing dwindling supplies of blast furnace slag, which is used as a supplementary cementitious material inter alia to reduce the CO2 emissions of cement production. Achieving a sustainable circular steel and building material economy requires the valorisation of currently landfilled steel slags and investigating utilisation options for electric arc furnace slag, which is increasingly being generated. For this purpose, different metallurgical residues and by-products were treated by carbothermal reduction in an inductively heated graphite crucible and then rapidly cooled by wet granulation, yielding a slag fraction similar to granulated blast furnace slag and a metal fraction valuable as a secondary raw material. A spreadsheet-based model was developed to calculate residue combinations to accomplish target compositions of the slag and metal fractions to fulfil previously identified requirements of the targeted cementitious and ferrous products. The results demonstrate the high accuracy of the model in predicting the properties (e.g. main oxide composition) of the generated slag and metal fraction, which fulfil the needed requirements for their use as (i) a supplementary cementitious material and (ii) a secondary raw material in steel production.
Publisher Copyright: © The Author(s) 2024.
Keywords: carbothermal reduction; circular economy; CO-reduced cement; industrial residue; metal recovery; metallurgical residues; steel slags; Supplementary cementitious material

A Comprehensive Numerical Study of a Wedge-Shaped Textured Convergent Oil Film Gap - Scharf, Raphael; Maier, Michael; Pusterhofer, Michael; Grün, Florian (Lubricants, 2024)
The modification of surface geometries to reduce friction is an omnipresent topic of research. In nature, different low-friction surfaces, such as fish skins, exist. To transfer this knowledge to technical applications, for example, to journal or plain bearings, many numerical and experimental studies of textured surfaces have been performed. In this work, the influence of the geometric parameters (texture length , width , angle and start position ) of a wedge-shaped texture on three different convergent oil film gaps was analyzed in full-film lubrication and compared with untextured oil film gaps. With the aid of a CFD (computational fluid dynamics) model, a comprehensive variation study was conducted, and the best-performing wedge-shaped texture was determined. The results show that an open texture at the inlet provides the largest improvement. Furthermore, it can be observed that the optimal relative texture width and absolute inlet height for the three investigated oil film gaps are similar. In contrast to the volume flow of the untextured geometry, the volume flow of the textured one is significantly higher, especially that perpendicular to the movement direction.

Types and quantities of Critical Raw Materials needed to meet growing demands in the European Union and worldwide - Melcher, Frank (2024)

Too much consumption – too little resources?! Types and quantities of Critical Raw Materials needed to meet growing demands on the globe - Melcher, Frank (2024)

MetamaterialFinder - Fleisch, Mathias; Thalhamer, Andreas; Schlögl, Sandra; Fuchs, Peter Filipp; Pinter, Gerald; Berer, Michael (Advances in Engineering Software, 2024)
Mechanical metamaterials have gained a lot of research interest over the last years due to their unusual mechanical properties and potential use for structural applications. However, the design and analysis of mechanical metamaterials remains challenging and time-consuming. Herein, we present a software framework for automated generation, finite element modeling and analysis of extruded mechanical metamaterials based on simple closed curves. By generalizing extruded unit cells with pores defined by simple closed curves, a wide variety of existing and novel metamaterials can be created and analyzed. Each pore can either be empty or filled with one or more materials, resulting in single- or multi-material metamaterials. Since part of the mechanical response of a metamaterial is defined by the geometric parameters of a unit cell, parameter studies are directly integrated into the framework. Examples of well-established mechanical metamaterials were used as benchmark structures and compared to their analytical solutions. We also demonstrate how generalized curves can further improve the mechanical properties of these structures, for example the load bearing capabilities and range of Poisson's ratios. Furthermore, newly developed single- and multi-material designs of mechanical metamaterials with tunable Poisson's ratio are presented and analyzed with the proposed framework. The framework is implemented in Python, executed via ABAQUS and allows for unit-cell based homogenization and full-size 2D and 3D simulations. The scripts are made open source and publicly available.
Publisher Copyright: © 2024
Keywords: Automated design; Cellular material; Finite element analysis; Mechanical metamaterials; Poisson's ratio

Methanoldampfreformierung mittels Perowskit-basierter Oxide: Transformation des Energiesektors für eine nachhaltige Zukunft - Berger, Tobias (2024)

NOx Postprocessing for industrial combustion processes - Spijker, Christoph; Swaminathan, Senthilathiban; Raonic, Zlatko; Raupenstrauch, Harald (2024)

Nanoparticles bearing germanium based photoinitiators at their surface: Preparation and use in grafting-from photopolymerization reactions - Müller, Matthias; Drusgala, Manfred; Fischer, Roland C.; Kern, Wolfgang; Haas, Michael; Bandl, Christine (Applied surface science, 2024)
In recent decades, there has been a growing interest in surface modifications utilizing “grafting-from” techniques within both industrial and academic fields. Among others, this technology continues to drive innovation in biomedicine, enabling the design and fabrication of advanced materials and devices with tailored properties for a wide range of applications, from regenerative medicine and drug delivery to diagnostics and therapeutics. This strategy relies on the covalent attachment of (photo)initiating species to surfaces. The coupled initiators are exploited to produce reactive sites such as radicals upon exposure to heat or light. Subsequently, polymerization reactions are induced, leading to surface coupled polymer brushes. In order to provide new perspectives in surface modification techniques, we present a novel and unique method for producing mesoporous organic/inorganic hybrid nanoparticles via the “grafting-from” method. This was accomplished by immobilizing a novel, low-toxic and visible light sensitive photoinitiator (based on triacylgermanium moieties) onto silica nanoparticles. Surface-initiated photopolymerizations of styrene and acrylate monomers were conducted to produce polymer shells on the surface of the nanoparticles. The grafted layers had a thickness in the range of 6–12 nm. Furthermore, the polymer grafting density is discussed in detail ranging between 0.17 and 0.23 chains per square nanometer.
Publisher Copyright: © 2024 The Authors
Keywords: Germanium-based photoinitiators; Initiator immobilization; Low-toxic initiators; Organic–inorganic hybrid materials; Polymeric shell; Silica nanoparticle modification; Surface-initiated photopolymerization

Recovery of Cobalt, Nickel, and Lithium from Spent Lithium-Ion Batteries with Gluconic Acid Leaching Process: Kinetics Study - Gerold, Eva; Lerchbammer, Reinhard; Antrekowitsch, Helmut (Batteries, 2024)
The demand for lithium-ion batteries (LIBs) is driven by environmental concerns and market growth, particularly in the transportation sector. The EU’s push for net-zero emissions and the European Green Deal accentuates the role of battery technologies in sustainable energy supply. Organic acids, like gluconic acid, are explored for the eco-friendly leaching of valuable metals from spent batteries. This study investigates leaching kinetics using gluconic acid (hydrolyzed glucono-1.5-lacton), analyzing factors such as temperature, acid concentration, particle size, and reaction time. Results reveal the temperature’s influence on leaching efficiency for cobalt, nickel, and lithium. The mechanism for Co follows a surface chemical reaction model with an activation energy of 28.2 kJ·mol −1. Nickel, on the contrary, shows a diffusion-controlled regime and an activation energy of 70.1 kJ·mol −1. The reaction of leaching Ni and Co using gluconic acid was determined to be first-order. The process within this environmentally friendly alternative leaching agent shows great potential for sustainable metal recovery.
Publisher Copyright: © 2024 by the authors.
Keywords: gluconic acid; kinetics study; lithium-ion batteries; recycling; sustainability

ConForce - Rettl, Matthias; Frankl, Siegfried Martin; Pletz, Martin; Tauscher, Markus; Schuecker, Clara (SoftwareX, 2024)
ConForce is a tool for evaluating nodal configurational forces (CF) from FEM results. ConForce supports 2D plane strain and 3D volume elements in a solver-independent manner. Furthermore, large displacements in static load cases are considered. ConForce accesses previously generated and compiled C code from Python via a C code binding. This compiled C code is provided for predefined element types, but can be regenerated for other element types. ConForce also includes an Abaqus plug-in with a graphical user interface. This Abaqus plug-in allows to easily add CF to the Abaqus output file.
Publisher Copyright: © 2024 The Authors
Keywords: Abaqus; Configurational forces; Finite element method; Fracture mechanics

Brittleness reduction of low-carbon Al2O3-C refractories with in-situ formation MgAl2O4/CNTs layer between aggregate and matrix - Luo, Jiyuan; Jin, Shengli; Chong, Xiaochuan; Ding, Donghai; Xiao, Guoqing (Journal of the European Ceramic Society, 2024)
This research was supported by the National Natural Science Foundation of China (NO. 52272027, 52372034); Key R&D Project in Shaanxi Province (2022GY-421); Outstanding Doctorate Dissertation Cultivation Fund of Xi'an University of Architecture and Technology (2021XYBPY014); and the China Scholarship Council. The authors would like to thank Dr. Chaowei Guo in Center for Advancing Materials Performance from the Nanoscale of Xi'an Jiaotong University for helping in the SEM observations.
Keywords: In-situ interfacial layer; Low-carbon AlO-C refractories; MgAlO/CNTs; Wedge splitting test

Building Information Modeling in the Execution Phase of Conventional Tunneling Projects - Huymajer, Marco; Melnyk, Oleksandr; Wenighofer, Robert; Huemer, Christian; Galler, Robert (Tunnelling and Underground Space Technology, 2024)
Building Information Modeling (BIM) has become the key technology for the digital transformation of the architecture, engineering, and construction (AEC) sector. The Industry Foundation Classes (IFC), as an open and vendor-neutral data model, play an essential role in this transformation. Despite all the recent advances of BIM, tunneling needs to catch up with other AEC sectors adopting digital technologies. Currently, IFC is mainly used to capture information directly connected to the structural elements of the final tunnel but rarely as a means to document the tunnel excavation and support. This article proposes an IFC-driven process for the execution phase of conventional tunneling projects by extending the usage of IFC to information about the process, labor, equipment, and employed material. The proposed process is evaluated by a case study demonstrating how to represent data from a conventional tunneling project by IFC. The results show that IFC provides the necessary concepts to express the data of the execution phase of conventional tunneling projects. Implementing an IFC-driven process in this phase significantly contributes to the digital transformation of tunneling projects.
Publisher Copyright: © 2024 The Author(s)
Keywords: Building Information Modeling; Tunneling; Industry Foundation Classes; Construction phase; Digitalization; BIM; IFC; Drill and blast; Conventional tunneling

Digitale Abfallanalytik: Online-Bestimmung der Materialzusammensetzung und Qualität - Kandlbauer, Lisa; Sarc, Renato (Österreichische Abfallwirtschaftstagung, 2024)

Dual-Wavelength Vat Photopolymerization 3D Printing with Hybrid Acrylate-Epoxy Resins - Cazin, Ines; Plevová, Kateřina; Alabiso, Walter; Vidović, Elvira; Schlögl, Sandra (Advanced Engineering Materials, 2024)
Dual-wavelength vat photopolymerization 3D printing represents a convenient technology for the fabrication of objects with heterogeneous and locally controlled mechanical properties. By using two λ-orthogonal cross-linking reactions, it is possible to produce soft and stiff photopolymers with a single resin vat by switching the light source. Herein, hybrid acrylate-epoxy resins are selectively cured by using either visible or UV light. At 405 nm, a free radical curing of the acrylate monomers is induced while irradiation with 365 nm triggers an additional cationic ring opening reaction of the epoxy monomer yielding interpenetrating photopolymer networks. In a comprehensive approach, the influence of the resin composition and the applied wavelength on cure kinetics, film morphology, (thermo)mechanical properties, and printability are studied. Fully separated as well as homogenous network morphologies are obtained depending on the ratio between acrylate and epoxy monomers, cure rate and applied light source (405 vs 365 nm). In general, glass transition temperature, stiffness, and tensile strength of the photopolymers increase with rising epoxy content. In contrast, a higher epoxy concentration in combination with a higher amount of the cationic photoinitiator compromises on the system's orthogonality, giving rise to the important role of the resin composition in dual-wavelength vat photopolymerization 3D printing.
Publisher Copyright: © 2024 Wiley-VCH GmbH.
Keywords: dual-wavelength vat photopolymerization 3D printings; heterogeneous properties; hybrid radical/cationic photopolymers; multi-materials; polymer morphologies

Strategische Flexibilität im Fokus - Zawodnik, Vanessa; Pfleger, Jasmin; Reiter, Jana; Pfleger-Schopf, Kerstin; Zaversky, Martin; Kienberger, Thomas (EnInnov 2024 | 18. Symposium Energieinnovation: "Europas Energiezukunft: Sicher, leistbar, sauber?!", 2024)
Conference code: 18

Strategische Flexibilität im Fokus - Zawodnik, Vanessa; Pfleger, Jasmin; Reiter, Jana; Pfleger-Schopf, Kerstin; Zaversky, Martin; Kienberger, Thomas (Eine qualitative Analyse energieintensiver Industriestandorte in Österreich, 2024)

Subduction zone-related metasomatism of Devonian oceanic lithosphere - Ahmed, Ahmed H.; Hamdy, Mohamed M.; Meisel, Thomas C. (Lithos, 2024)
The serpentinized peridotite bodies found in gneisses of the Sowie Mountains Block (SMB) in the Central Sudetes of SW Poland (NE segment of the Bohemian massif) are significanly metasomatized. Mineral chemical and whole-rock geochemical data combined with Rb-Sr-Sm-Nd-O-H isotope data suggest that these peridotites are refractory oceanic mantle relics from supra-subduction zone to mid-ocean ridge. They and the nearby Devonian (∼400 Ma) ophiolitic ultramafic rocks most probably came from the same mantle source. The studied peridotites are all rich in Ti, LREE and FME, except for a few that are slightly depleted in LREE. Mineralogical changes include formation of metasomatic poikilitic amphiboles and olivine, as well as metamorphic Cpx and Opx. Mixing with metasomatic sulfide-rich liquids and PPGEs (Rh, Pt, and Pd) enrichment are also supposed. The εNd and 87Sr/86Sr ratios are similar to the compositions of HIMU, EM2, and continental basalt, indicating that the depleted mantle protolith was commonly mixed with components of subducted oceanic crust and rare continental crust input. Also, the δ18O values of separated amphiboles are comparable to metasomatic fluids derived from subducted oceanic slab. The contrasting δ18O and δD values of amphibole and serpentine minerals show that serpentinization fluids are not the amphibole-forming agent. The metasomatism of the investigated peridotites most likely occurred as a result of their emplacement in the SMB, concurrently with the SMB's HT-HP metamorphism.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Amphibole-bearing peridotites; Metasomatism; Rb-Sr-Sm-Nd-O-H isotope; Sowie Mountains Block (SMB); SW Poland

Towards 3D-printed alumina-based multi-material components with enhanced thermal shock resistance - Schlacher, Josef Christian; Geier, Sebastian; Schwentenwein, Martin; Bermejo, Raul (Journal of the European Ceramic Society, 2024)
A novel architectural design is introduced which utilizes the layer-by-layer capabilities of the vat photopolymerization 3D printing process to fabricate multi-material ceramic components with improved thermal shock resistance. The combination of 3D-printed alumina-zirconia (ZTA) with alumina (A) layers generates compressive residual stresses in the embedded alumina regions during cooling down from sintering. Thermal shock tests in water are performed on samples at different maximum temperatures and the strength degradation of the multi-material design is investigated and compared to the reference monoliths. Experimental results show that the retained strength of the multi-material ceramic after thermal shock is twice as high as that of the monoliths, associated with the crack arrest capability of the embedded layers. The concept is demonstrated on 3D-printed multi-ceramic blades for potential high temperature applications, showing enhanced “damage-tolerance” against thermal shock cracks. These findings open the path for fabricating reliable ceramic components using the vat photopolymerization process.
Publisher Copyright: © 2023 The Authors
Keywords: Additive manufacturing; Multi-material; Residual stresses; Thermal shock; Vat photopolymerization

Tübbinggroßversuche mit optimierter Krafteinleitung - Kühbacher, Manuel; Evangelatos, Alexandros; Galler, Robert (Beton- und Stahlbetonbau, 2024)
Abstract Beim Tunnelbau mittels geschildeter Vortriebsmaschinen dienen Tübbinge zur Sicherung des Hohlraums. Es ist daher unerlässlich, Kenntnis über deren statische Tragfähigkeit und Verhalten bei Belastung vorweisen zu können. Die einzelnen Tübbinge bilden im eingebauten Zustand einen Ring aus, auf welchen die unterschiedlichsten Belastungen aus dem umliegenden Gebirge einwirken. Für die an der Montanuniversität Leoben durchgeführten Großversuche im Realmaßstab wurde eine kombinierte Krafteinleitung nachgebildet, um eine realistische Belastung eines Tübbings zu simulieren. Um die aus dem Ringschluss resultierenden Normalkräfte im Querschnitt hervorzurufen, wird eine Kraft in horizontaler Richtung aufgebracht. Bei Erreichen dieses Belastungsniveaus wird in weiterer Folge die Vertikalkraft bis zum Versagen des Bauteils gesteigert, wobei die horizontale Einspannung konstant gehalten wird. Aufgrund der spezifischen Tübbinggeometrie ist während des Einleitens der Horizontalkraft auch gleichzeitig eine Vertikalkraft notwendig, um ein Ausknicken des Tübbings zu verhindern. Diese erforderliche Kraft kann mit einer numerischen Simulation oder alternativ dazu mittels herkömmlicher statischer Berechnung in vereinfachter Form ermittelt werden, welche in der vorliegenden Arbeit aufgezeigt wird. Es werden unterschiedliche Überlegungen dazu aufgezeigt und anschließend gegenübergestellt.
Publisher Copyright: © 2023 Ernst & Sohn GmbH.
Keywords: Biegemoment; optmierte Versuchsdurchführung; Tübbinge; Tübbinggroßversuch; Tunnelauskleidung

WEGE ZUR KLIMANEUTRALITÄT IN ÖSTERREICHS INDUSTRIE - Gradwohl, Christopher; Kienberger, Thomas (2024)

Impact Characteristics and Repair Approaches of Distinct Bio-Based Matrix Composites: A Comparative Analysis - Ravindran, Bharath; Agathocleous, Timotheos; Oswald-Tranta, Beata; Fauster, Ewald; Feuchter, Michael (Journal of composites science, 2024)
Increasing global concerns regarding environmental issues have driven significant advancements in the development of bio-based fiber reinforced polymer composites. Despite extensive research on bio-composites, there remains a noticeable gap in studies specifically addressing the challenges of repairing bio-composites for circular economy adoption. Traditional repair techniques for impacted composites, such as patching or scarf methods, are not only time-consuming but also require highly skilled personnel. This paper aims to highlight cost-effective repair strategies for the restoration of damaged composites, featuring flax fiber as the primary reinforcement material and distinct matrix systems, namely bio-based epoxy and bio-based vitrimer matrix. Glass fiber was used as a secondary material to validate the bio-based vitrimer matrix. The damage caused specifically by low impact is detrimental to the structural integrity of the composites. Therefore, the impact resistance of the two composite materials is evaluated using instrumented drop tower tests at various energy levels, while thermography observations are employed to assess damage evolution. Two distinct repair approaches were studied: the resin infiltration repair method, employing bio-based epoxy, and the reconsolidation (self-healing) repair method, utilizing the bio-based vitrimer matrix. The efficiency of these repair methods was assessed through active thermography and compression after impact tests. The repair outcomes demonstrate successful restoration and the maintenance of ultimate strength at an efficiency of 90% for the re-infiltration repair method and 92% for the reconsolidation repair method.
Publisher Copyright: © 2024 by the authors.
Keywords: bio-based polymers; bio-composite; compression after impact (CAI); resin reinfiltration; self-healing; vacuum assisted resin infusion (VARI)

Consumers confused ‘Where to dispose biodegradable plastics?’: A study of three waste streams - Mhaddolkar, Namrata; Tischberger-Aldrian, Alexia; Vollprecht, Daniel; Astrup, Thomas Fruergaard (Waste management & research, 2024)
Biodegradable plastics, either fossil- or biobased, are often promoted due to their biodegradability and acclaimed environmental friendliness. However, as demonstrated by previous literature, considerable confusion exists about the appropriate source separation and waste management of these plastics. Present study investigated this confusion based on manual sorting analyses of waste sampled from packaging waste (P), biowaste (B) and residual waste (R) in an urban area of Austria. The results were evaluated relative to near-infrared sensor-based sorting trials conducted in a German urban area. Although existing literature has focused on waste composition analyses (mostly in stand-alone studies) of the three waste streams, the present study focused on identifying the specific types of biodegradable plastic items found in each of these streams. Supermarket carrier bags (P = 90, B = 14, R = 33) and dustbin bags (P = 2, B = 46, R = 6) were found in all three waste streams in the Austrian urban area. Similarly, in the German urban area dustbin bags (P = 1, B = 106, R = 3) were the common items. The results indicate that certain bioplastic items were present in more than one bin; thus, hinting that consumers are not necessarily aware of how-to source-separate the biodegradable plastics. This suggests that neither consumers nor current waste management systems are fully ‘adapted’ to bioplastics, and the management of these plastics’ waste is currently not optimal.
Publisher Copyright: © The Author(s) 2024.
Keywords: Bioplastics waste management; biodegradable plastics; consumer confusion; EU legislation; waste sorting analyses; waste sorting guidelines; waste collection and sorting

Deep reinforcement learning algorithm for wellbore cleaning across drilling operation - Keshavarz, Sahar; Elmgerbi, Asad; Thonhauser, Gerhard (2024)
We propose a novel framework for real-time drilling operation planning updates using deep reinforcement learning algorithm, enabling drilling process reactions to be automated. The framework includes a decision tree algorithm to represent the environment dynamic changes based on the imposed actions parallel to a Gaussian process algorithm to quantify the safe operating window in real-time. Combining these two algorithms leads to mounting a Markov Decision Process (MDP) environment for a decision-making system.We demonstrate the effectiveness of our framework by implementing an off-policy deep reinforcement learning algorithm, using a deep Q-learning network to create experiences, and employing synchronous updates on the agent. Given the essence of reinforcement learning, the framework can be efficiently implemented for on-the-spot decision-making, allowing the driller to receive an effective sequence of actions considering company policies.Our algorithm achieves state-of-the-art performance on weight-to-slip hole conditioning operation, a wellbore cleaning operation after drilling a stand before connecting to the next pipe. The performance evaluation exhibits its efficiency in real-time operation overhaul, eliminating non-value-added activities. Our framework thus opens the door for automating the process based on the operating parameters obtained in real-time

Elucidating effects of Eu and P on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by Ta and TiB2 - Spáčil, Ivo; Gehringer, Dominik; Holec, David; Albu, Mihaela; LI, Jiehua (Journal of alloys and compounds, 2024)
Effects of Eu (up to 500 ppm) and P (up to 40 ppm) on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by solute Ta (0.12 wt%) and stochiometric Al-2.2Ti-1B grain refiner were investigated using optical microscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as well as density functional theory (DFT) calculations. It was found that (i) solute Ta can refine α-Al grains and is unaffected by the addition of Eu and/or P. (ii) 200 ppm Eu is eligible enough to modify eutectic Si although its modification effect can be enhanced with higher Eu additions (up to 500 ppm). (iii) A high P concentration (40 ppm) counteracts the modification effect in the alloy modified with 200 ppm Eu and therefore unmodified structure is obtained. (iv) Even with the addition of Eu and P, the activation energy of stable β-Mg 2Si is calculated to be very low (60–70 kJ/mol), indicating a short time for the precipitation of β-precipitates. Furthermore, one possible nucleation sequence in Al-Si-Mg based alloys modified with Eu or Sr has been proposed based on the lattice mismatch calculation and thermodynamic stability. Finally, DFT calculations suggest that Eu is energetically favourable for TPRE growth mechanism. The present investigation provides new insights into controlling solidification microstructure (mainly for the grain refinement of α-Al and eutectic grains) and precipitation microstructure (mainly for β-MgSi precipitate) of Al-7Si-0.3Mg based alloys via the addition of Ta and TiB 2 as a refiner of α-Al and the addition of Eu and P as a modifier of eutectic Si.
Publisher Copyright: © 2024 The Authors
Keywords: AlSiMg based alloys; DFT; DSC; Grain refinement; Heat treatment; Modification; TEM

Advancements and Challenges in Photovoltaic Cell Recycling: A Comprehensive Review - Gerold, Eva; Antrekowitsch, Helmut (Sustainability, 2024)
This review examines the complex landscape of photovoltaic (PV) module recycling and outlines the challenges hindering widespread adoption and efficiency. Technological complexities resulting from different module compositions, different recycling processes and economic hurdles are significant barriers. Inadequate infrastructure, regulatory gaps and limited awareness are also hampering progress. In addition, this analysis draws parallels between the development of PV module recycling and recycling technologies for other high-tech products, such as lithium-ion batteries, highlighting similarities in regulatory and technical feasibility challenges. Amid these challenges, however, lie opportunities for a sustainable future. Technological advances, stakeholder collaboration and the adoption of circular economy principles emerge as key ways forward. This review highlights the need for concerted action to overcome barriers and drive the development of efficient and sustainable PV module recycling practices.
Publisher Copyright: © 2024 by the authors.
Keywords: environmental impact of PV module recycling; photovoltaic cell recycling; photovoltaic technology; sustainable technology for energy production

From abandoned mines to carbon sinks - Safaei Farouji, Majid; Misch, David; Sachsenhofer, Reinhard F.; Rauscher, Max; Kostoglou, Nikolaos (International journal of coal geology, 2024)
This study represents the first assessment of CO2 storage potential in Austrian coal seams. Coal samples were taken from Fohnsdorf and Leoben abandoned coal mines, with particular emphasis on the Fohnsdorf coal since Leoben coal reserves were largely mined during previous coal production. Several methods were used to compare coal characteristics, including Rock-Eval pyrolysis (RE), organic petrography, and low-pressure N2 and CO2 sorption measurements. Both Fohnsdorf and Leoben coal samples show low sulfur and ash yields, as well as correspondingly high total organic carbon (TOC) contents. The pyrolysis Tmax and vitrinite reflectance values agree with a low coal rank for both sites. According to the N2 adsorption measurements at 77 K, low-lying mire coals from Fohnsdorf show a higher BET-specific surface area (BET-SSA) and BJH pore volume compared to raised-mire coals from Leoben. However, sapropelic shales and high-ash coals from Leoben show the highest BET-SSA and BJH pore volumes of all investigated samples and considerably exceed the N2 adsorption volumes of pure coals from both locations (N2 uptake up to 16 cm3/g; avg. for all samples 5.4 cm3/g). In contrast, the mean adsorbed CO2 uptake measured at 273 K and ∼ 1 bar followed the order of Fohnsdorf low-lying mire coals > Leoben raised-mire coals > Leoben sapropelic coals and shales, ranging at ∼0.8 mmol/g, ∼0.7 mmol/g, and ∼ 0.2 mmol/g, respectively. This shows that BET-SSA and BJH equations did not allow for adequate estimation of CO2 adsorption capacity trends in the investigated sample set. Furthermore, based on the existence of a hysteresis loop between CO2 adsorption and desorption branches for all investigated samples, the occurrence of weak chemisorption phenomena during CO2 adsorption is indicated. This effect helps to increase CO2 uptake and storage safety since the chemisorption process is not fully reversible upon pressure decrease. Ultimately, the theoretical CO2 sequestration potential of the remaining unmined Fohnsdorf coal reserves was estimated at 4.65 million tons, with an additional potential for enhanced coal bed methane production due to the gas-rich nature of Fohnsdorf coals with an estimated 1.2 billion m3 of CH4 in place.
Publisher Copyright: © 2024 The Authors
Keywords: CO adsorption; Coal; Fohnsdorf; Leoben; Nanopores; Nitrogen adsorption

Industry 4.0 Technologies and their Implications for Environmental Sustainability in the Manufacturing Industry - Kopeinig, Jacob; Woschank, Manuel; Olipp, Nadine (Procedia computer science, 2024)
The advent of Industry 4.0 has revolutionized the manufacturing industry by incorporating interconnectivity, decentralized decision-making, resource optimization, and automation. This transformation has been made possible through the integration of advanced technologies such as Artificial Intelligence, Cyber-Physical Systems, the Internet of Things, Big Data Analytics, and Blockchain Technology. However, while Industry 4.0 has primarily focused on production efficiency and real-time transparency, the need for the transition toward a holistically sustainable environment has become increasingly urgent. As a result, the term Industry 5.0 was devised, merging the concept of Industry 4.0 with sustainability, resilience, and human-centric goals. This paper explores the potential areas of influence these technologies have on the environmental dimension of sustainability. The findings indicate that various Industry 4.0 technologies can contribute to environmental sustainability in manufacturing. These technologies offer opportunities to optimize supply chain performance, improve product traceability, reduce waste, enhance resource management, and minimize overall environmental impact. By understanding the implications of Industry 4.0 for environmental sustainability, researchers, policymakers, and industry practitioners can collaborate to develop strategies that integrate advanced technologies and sustainable practices in the manufacturing sector. The research provides insights into the potential benefits of these technologies for environmental sustainability and calls for further investigation to fully explore their environmental dimensions.
Publisher Copyright: © 2024 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0)
Keywords: Circular Economy; Digitalization; Green Logistics; Industrial Logistics; Industry 4.0; Industry 5.0; Sustainability

The Impact of Competence on Performance in Industrial Engineering and Management - Pacher, Corina; Woschank, Manuel; Zunk, Bernd M. (Procedia computer science, 2024)
Industrial companies are constantly confronted with a variety of challenges caused by competitive pressure, globalization, and changing customer behavior. The discipline of Industrial Engineering and Management (IEM) aims to educate the engineers for tomorrow that balance economic competitiveness, environmental protection, and social acceptance towards facing grand issues of the world, such as climate change, resource scarcity, and energy transition. However, the critical success factors of engineering education remain insufficiently studied. A realignment of engineering education and training requires, on the one hand, a deep understanding of the necessary competences and, on the other hand, an empirically based investigation of the relationship between competences and performance in the actual working environment. This paper conceptualizes a preliminary research model for measuring the impact of competence on the performance of IEM professionals. After discussing the IEM job profile and the core working areas of IEM professionals, the preliminary research model is presented, and future implications are derived.

Investigations on the hydrogen embrittlement tendency of K55 for underground storage applications using hollow probe specimens - Eichinger, Matthias; Zwittnig, Dino; Mori, Gregor Karl (Materials letters, 2024)
The susceptibility of ferritic pearlitic steel K55 to hydrogen embrittlement in high pressure gas atmospheres was investigated using slow strain rate tests with hollow probe specimens. Therefore, the specimens were charged with an internal hydrogen pressure of up to 20 MPa according to planned conditions for underground gas storages. The results show a significant decrease in ductility caused by hydrogen embrittlement yielding a loss in fracture strain of 46 % at 10 MPa and 63 % at 20 MPa hydrogen partial pressure compared to a specimen tested in nitrogen atmosphere. Furthermore, observations on the cross-sections of the tested specimens reveal that pearlite acts as obstacle for hydrogen enhanced crack growth.

Wong–Zakai approximation of a stochastic partial differential equation with multiplicative noise - Hausenblas, Erika; Randrianasolo, Tsiry Avisoa (Applicable Analysis, 2024)
In this article, we derive the convergence rate for the Wong–Zakai equation of some approximation of stochastic evolution equations with multiplicative noise. To be more precise, the diffusion coefficient in front of the noise is the multiplication operator, and, is therefore not bounded, a situation not treated in the literature. Since our motivation comes from problems in numerical ling, we consider a finite, high-dimensional problem approximating a stochastic evolution equation on a random time grid. By imposing suitable stability conditions on the drift term and the time grid, we achieve a convergence rate in the mean square of order (Formula presented.), for some (Formula presented.) and (Formula presented.).
Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 60J65; 65C30; multiplicative noise; partial differential equations with randomness; Primary 35R60; Secondary 65M15; Stochastic partial differential equations; time-discretization scheme; Wong–Zakai approximation

New strategies to improve Recycling and reduce CO2-emission of Aluminum production and processing - Samberger, Sebastian; v. Czarnowski, Peter; Pogatscher, Stefan; Hirsch, Jürgen (Keikinzoku-yōsetsu = Journal of light metal welding, 2024)
https://doi.org/10.11283/jlwa.62.119

M5 — Mars Magnetospheric Multipoint Measurement Mission - Larkin, Cormac J.K.; Lundén, Ville; Schulz, Leonard; Baumgartner-Steinleitner, Markus; Brekkum, Marianne; Cegla, Adam; Dazzi, Pietro; Iuliis, Alessia De; Gesch, Jonas; Lennerstrand, Sofia; Nesbit-Östman, Sara; Castro Pires, Vasco Daniel; et al. (Advances in Space Research, 2024)
Mars, lacking an intrinsic dynamo, is an ideal laboratory to comparatively study induced magnetospheres, which can be found in other terrestrial bodies as well as comets. Additionally, Mars is of particular interest to further exploration due to its loss of habitability by atmospheric escape and possible future human exploration. In this context, we propose the Mars Magnetospheric Multipoint Measurement Mission (M5), a multi-spacecraft mission to study the dynamics and energy transport of the Martian induced magnetosphere comprehensively. Particular focus is dedicated to the largely unexplored magnetotail region, where signatures of magnetic reconnection have been found. Furthermore, a reliable knowledge of the upstream solar wind conditions is needed to study the dynamics of the Martian magnetosphere, especially the different dayside boundary regions but also for energy transport phenomena like the current system and plasma waves. This will aid the study of atmospheric escape processes of planets with induced magnetospheres. In order to resolve the three-dimensional structures varying both in time and space, multi-point measurements are required. Thus, M5 is a five spacecraft mission, with one solar wind monitor orbiting Mars in a circular orbit at 5 Martian radii, and four smaller spacecraft in a tetrahedral configuration orbiting Mars in an elliptical orbit, spanning the far magnetotail up to 6 Mars radii with a periapsis just outside the Martian magnetosphere of 1.8 Mars radii. We not only present a detailed assessment of the scientific need for such a mission but also show the resulting mission and spacecraft design taking into account all aspects of the mission requirements and constraints such as mass, power, and link budgets. Additionally, different aspects of the mission programmatics like a possible mission timeline, cost estimates, or public outreach are shown. The common requirements for acceptance for an ESA mission are considered. The mission outlined in this paper was developed during the Alpbach Summer School 2022 on the topic of “Comparative Plasma Physics in the Universe”.
Publisher Copyright: © 2023 COSPAR
Keywords: Atmospheric escape; Induced magnetospheres; Magnetic reconnection; Mars; Mission concept proposal; Multi-spacecraft constellation

Mineral diagenesis in lacustrine organic-rich shales - Yan, Yu; Wang, Min; Misch, David; Sachsenhofer, Reinhard F.; Wu, Yan; Li, Jinbu (Journal of Asian earth sciences, 2024)
Publisher Copyright: © 2024 Elsevier Ltd
Keywords: Clay-rich shale; Diagenesis; Organic matter porosity; Qingshankou Formation; Shale oil; Songliao Basin

Device Having a Guide Unit for Guiding a Conveyor Belt - Prenner, Michael; Dünnwald, Wilfried; Koth, Thorsten (2024)
A device for guiding a conveyor belt, having a guide unit with an outer and an inner hollow-cylindrical body, the inner hollow-cylindrical body having a first central axis and being arranged in the outer hollow-cylindrical body, which has a second central axis, and both hollow-cylindrical bodies each have a central axis, with at least one bearing for rotatably mounting the outer hollow-cylindrical body on the inner hollow-cylindrical body and with an articulation body designed for mounting the inner hollow-cylindrical body on a central axle, wherein the articulation body is further designed to allow a horizontal and/or vertical change in angle of the first and/or second central axis relative to a central axis of the central axle. In order to increase the service life of the conveyor belt, the device is equipped according to the invention with a measuring and evaluating system including a sensor unit arranged inside and/or outside the guide unit, wherein the measuring and evaluating system is designed to detect the change in angle. The invention is based on the consideration that from a control behavior of the device, the causes of a fault of the belt run can be identified, deduced or narrowed down. Furthermore, a system for monitoring and guiding a conveyor belt using a device according to the invention is described.

Multimodal Human-Autonomous Agents Interaction Using Pre-Trained Language and Visual Foundation Models - Nwankwo, Linus; Rückert, Elmar (19th ACM/IEEE International Conference on Human-Robot Interaction (HRI 2024), 2024)
In this paper, we extended the method proposed in [17] to enable humans to interact naturally with autonomous agents through vocal and textual conversations. Our extended method exploits the inherent capabilities of pre-trained large language models (LLMs), multimodal visual language models (VLMs), and speech recognition (SR) models to decode the high-level natural language conversations and semantic understanding of the robot's task environment, and abstract them to the robot's actionable commands or queries. We performed a quantitative evaluation of our framework's natural vocal conversation understanding with participants from different racial backgrounds and English language accents. The participants interacted with the robot using both spoken and textual instructional commands. Based on the logged interaction data, our framework achieved 87.55% vocal commands decoding accuracy, 86.27% commands execution success, and an average latency of 0.89 seconds from receiving the participants' vocal chat commands to initiating the robot's actual physical action. The video demonstrations of this paper can be found at https://linusnep.github.io/MTCC-IRoNL/

Österreichischer Bergbau und Klimawandel: Umfrage zur Perzeption und Positionierung von im österreichischen Bergbau tätigen Personen - Forstinger, Franziska; Meyer, Anna; Tost, Michael (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Over 30 years ago, the United Nations concurred that urgent action was needed to counteract anthropogenic climate change. The mining industry can make a major contribution to climate protection. Austrian mining operators were surveyed on current actions taken in their companies. Moreover, attitudes towards climate change, personal actions, and knowledge about the climate were examined. Findings show that more than half of the companieshave implemented or planned 70% of the operational measures listed in the survey. These include calculation of energy consumption, implemented by 94%, as well as rather planned measures that are currently rarely realised, such as drawing energy from entirely renewable sources, implemented by 6%. Moreover, about two-thirds of polled people can derive business advantages from climate change.
Keywords: Climate change, Mining, Knowledge, Climate action

Tackling Uncertainty: Forecasting the Energy Consumption and Demand of an Electric Arc Furnace with Limited Knowledge on Process Parameters - Zawodnik, Vanessa; Schwaiger, Florian; Sorger, Christoph; Kienberger, Thomas (Energies : open-access journal of related scientific research, technology development and studies in policy and management, 2024)
The iron and steel industry significantly contributes to global energy use and greenhouse gas emissions. The rising deployment of volatile renewables and the resultant need for flexibility, coupled with specific challenges in electric steelmaking (e.g., operation optimization, optimized power purchasing, effective grid capacity monitoring), require accurate energy consumption and demand forecasts for electric steel mills to align with the energy transition. This study investigates diverse approaches to forecast the energy consumption and demand of an electric arc furnace—one of the largest consumers on the grid—considering various forecast horizons and objectives with limited knowledge on process parameters. The results are evaluated for accuracy, robustness, and costs. Two grid connection capacity monitoring approaches—a one-step and a multi-step Long Short-Term Memory neural network—are assessed for intra-hour energy demand forecasts. The one-step approach effectively models energy demand, while the multi-step approach encounters challenges in representing different operational phases of the furnace. By employing a combined statistic–stochastic model integrating a Seasonal Auto-Regressive Moving Average model and Markov chains, the study extends the forecast horizon for optimized day-ahead electricity procurement. However, the accuracy decreases as the forecast horizon lengthens. Nevertheless, the day-ahead forecast provides substantial benefits, including reduced energy balancing needs and potential cost savings.
Publisher Copyright: © 2024 by the authors.
Keywords: electric arc furnace; electric steel industry; forecast modelling; Markov chain; neural network; time series forecasting

In situ study and assessment of the phosphorus-induced solute drag effect on the grain boundary mobility of austenite - Kern, Maximilian; Bernhard, Michael Christian; Kang, Youn-Bae; Bernhard, Christian (Acta Materialia, 2024)
The solute drag effect of phosphorus (P) in the single-phase austenite (γ-Fe) region was studied under isothermal annealing conditions at temperatures of 1050 °C, 1150 °C, 1250 °C and 1350 °C. High-temperature laser scanning confocal microscopy (HT-LSCM) was used to observe and quantify in situ grain growth on the surface of three different samples containing 0.026 wt.-% P, 0.044 wt.-% P and 0.102 wt.-% P. The dependence of the arithmetic mean grain sizes on time and temperature were modeled mathematically using a simple ordinary differential equation (ODE) according to normal grain growth (NGG) theory. As no other major effects, i.e., Zener-pinning by precipitates, occurred under the selected experimental conditions, grain growth interference was only considered by grain boundary (GB) segregation of P. Thus, the total grain boundary mobility (M) was directly determined depending on the P content and isothermal annealing temperature. The fitted GB mobility values enabled the determination of an average binding energy value between impurity P atoms and grain boundaries (E0 = -1.1 - -0.6 eV) in the system. Finally, the GB segregation of P in γ-Fe was derived from the observed grain growth kinetics. The results showed reasonable agreement with calculations using segregation enthalpies from the literature.

Automatic Texture Alignment by Optimization Method - Ott, Alois C; Weißensteiner, Irmgard; Arnoldt, Aurel; Österreicher, Johannes A; Papenberg, Nikolaus Peter (Microscopy and microanalysis, 2024)
Microstructure analysis via electron backscatter diffraction has become an indispensable tool in materials science and engineering. In order to interpret or predict the anisotropy in crystalline materials, the texture is assessed, e.g. via pole figure diagrams. To ensure a correct characterization, it is crucial to align the measured sample axes as closely as possible with the manufacturing process directions. However, deviations are inevitable due to sample preparation and manual measurement setup. Postprocessing is mostly done manually, which is tedious and operator-dependent. In this work, it is shown that the deviation can be calculated using the contour of the crystal orientations. This can also be utilized to define the axis symmetry of pole figure diagrams through an objective function, allowing for symmetric alignment by minimization. Experimental textures of extruded profiles and synthetically generated textures were used to demonstrate the general applicability of the method. It has proven to work excellently for deviations of up to 5 ◦, which are typical for careful manual sample preparation and mounting.
Publisher Copyright: © The Author(s) 2024.
Keywords: aluminum; electron backscatter diffraction; material science; optimization method; pole figure; texture analysis

Investigating the Potential of a Transparent Xanthan Polymer for Enhanced Oil Recovery - Hublik, Gerd; Kharrat, Riyaz; Mirzaalian Dastjerdi, Ali; Ott, Holger (Energies, 2024)
This study delThis study delves into the properties and behavior of xanthan TNCS-ST, a specialized variant designed for enhanced oil recovery (EOR) purposes. A notable aspect of this polymer is its transparency and capability to dissolve in high salt concentrations, notably up to 18% total dissolved solids. Various laboratory methods are employed to assess the polymer’s distinctive traits, including transparency, salt tolerance, and high pyruvylation. These methods encompass preparing xanthan solutions, conducting filtration tests, assessing energy consumption, and measuring rheological properties. The findings highlight the influence of salt concentration on xanthan’s filterability, indicating increased energy requirements for dissolution with higher salt and xanthan concentrations. Additionally, this study observes temperature-dependent viscosity behavior in different solutions and evaluates the shear stability of xanthan. A significant and novel characteristic of TNCS-ST is its high salt tolerance, enabling complete dissolution at elevated salt concentrations, thus facilitating the filterability of the xanthan solution with sufficient time and energy input. Core flooding experiments investigate fluid dynamics within porous rock formations, particularly sandstone and carbonate rocks, while varying salinity. The results underscore the substantial potential of the new xanthan polymer, demonstrating its ability to enhance oil recovery in sandstone and carbonate rock formations significantly. Remarkably, the study achieves a noteworthy 67% incremental recovery in carbonate rock under the high salinity level tested, suggesting promising prospects for advancing enhanced oil recovery applications.
Publisher Copyright: © 2024 by the authors.
Keywords: enhanced oil recovery (EOR); filtration; rheological properties; salt tolerance; xanthan

Multi-Layer Palladium Diselenide as a Contact Material for Two-Dimensional Tungsten Diselenide Field-Effect Transistors - Murastov, Gennadiy; Aslam, Muhammad Awais; Leitner, Simon; Tkachuk, Vadym; Plutnarová, Iva; Pavlica, Egon; Rodriguez, Raul D.; Sofer, Zdenek; Matkovic, Aleksandar (Nanomaterials, 2024)
Tungsten diselenide ((Formula presented.)) has emerged as a promising ambipolar semiconductor material for field-effect transistors (FETs) due to its unique electronic properties, including a sizeable band gap, high carrier mobility, and remarkable on–off ratio. However, engineering the contacts to (Formula presented.) remains an issue, and high contact barriers prevent the utilization of the full performance in electronic applications. Furthermore, it could be possible to tune the contacts to (Formula presented.) for effective electron or hole injection and consequently pin the threshold voltage to either conduction or valence band. This would be the way to achieve complementary metal–oxide–semiconductor devices without doping of the channel material.This study investigates the behaviour of two-dimensional (Formula presented.) field-effect transistors with multi-layer palladium diselenide ((Formula presented.)) as a contact material. We demonstrate that (Formula presented.) contacts favour hole injection while preserving the ambipolar nature of the channel material. This consequently yields high-performance p-type (Formula presented.) devices with (Formula presented.) van der Waals contacts. Further, we explore the tunability of the contact interface by selective laser alteration of the (Formula presented.) under the contacts, enabling pinning of the threshold voltage to the valence band of (Formula presented.), yielding pure p-type operation of the devices.
Publisher Copyright: © 2024 by the authors.
Keywords: palladium diselenide; tungsten diselenide; tungsten selenium oxide; semi-metal; laser treatment; contact engineering; field-effect transistor; pMOS; van der Waals electronics; 2D Materials; 2D materials

Prospects in the application of a frontally curable epoxy resin for cured-in-place-pipe rehabilitation - Malik, Muhammad Salman; Wolfahrt, Markus; Domínguez Pardo, Juan J.; Bublitz, Dirk; Schlögl, Sandra (Journal of applied polymer science, 2024)
Publisher Copyright: © 2023 Wiley Periodicals LLC.
Keywords: photopolymerization; radical polymerization; ring-opening polymerization; thermosets

The geodynamic significance of UHP exhumation - Bidgood, Anna; Parsons, Andrew; Roberts, Nick; Waters, David; Tapster, Simon; Gopon, Phillip (Tectonics, 2024)
The burial and exhumation of continental crust to and from ultrahigh-pressure (UHP) is an important orogenic process, ofteninterpreted with respect to the onset and/or subduction dynamics of continent-continent collision. Here, we investigate thetiming and significance of UHP metamorphism and exhumation of the Tso Morari complex, North-West Himalaya. We presentnew petrochronological analyses of mafic eclogites and their host-rock gneisses, combining U-Pb zircon, rutile and xenotimegeochronology (high-precision CA-ID-TIMS and high-spatial resolution LA-ICP-MS), garnet element maps, and petrographicobservations. Zircon from mafic eclogite have a CA-ID-TIMS age of 46.91 ± 0.07 Ma, with REE profiles indicative of growthat eclogite facies conditions. Those ages overlap with zircon rim ages (48.9 ± 1.2 Ma, LA-ICP-MS) and xenotime ages (47.4 ±1.4 Ma; LA-ICP-MS) from the hosting Puga gneiss, which grew during breakdown of UHP garnet rims. We argue that peakzircon growth at 47-46 Ma corresponds to the onset of exhumation from UHP conditions. Subsequent exhumation throughthe rutile closure temperature, is constrained by new dates of 40.4 ± 1.7 and 36.3 ± 3.8 Ma (LA-ICP-MS). Overlapping agesfrom Kaghan imply a coeval time-frame for the onset of UHP exhumation across the NW Himalaya. Furthermore, our regionalsynthesis demonstrates a causative link between changes in the subduction dynamics of the India-Asia collision zone at 47-46Ma and the resulting mid-Eocene plate network reorganization. The onset of UHP exhumation therefore provides a tightlyconstrained time-stamp significant geodynamic shifts within the orogen and wider plate network.

H2020-ROBOMINERS Prototype Field Test - Berner, Michael; Sifferlinger, Nikolaus August (Berg- und hüttenmännische Monatshefte : BHM, 2024)

Advancing Interactive Robot Learning: A User Interface Leveraging Mixed Reality and Dual Quaternions - Feith, Nikolaus; Rückert, Elmar (IEEE International Conference on Ubiquitous Robots, 2024)
Keywords: Human-Robot Interaction; Mixted Reality; Robot Learning

Integrating Human Expertise in Continuous Spaces: A Novel Interactive Bayesian Optimization Framework with Preference Expected Improvement - Feith, Nikolaus; Rückert, Elmar (IEEE International Conference on Ubiquitous Robots, 2024)
Keywords: Interactive Learning; Reinforcement Learning

M2CURL: Sample-Efficient Multimodal Reinforcement Learning via Self-Supervised Representation Learning for Robotic Manipulation - Lygerakis, Fotios; Dave, Vedant; Rückert, Elmar (IEEE International Conference on Ubiquitous Robots, 2024)
Keywords: Contrastive Learning; Manipulation; Multimodal Reinforcement Learning; Multimodal Representation Learning; Reinforcement Learning; Robot Learning

Semi-Autonomous Fast Object Segmentation and Tracking Tool for Industrial Applications - Neubauer, Melanie; Rückert, Elmar (IEEE International Conference on Ubiquitous Robots, 2024)
Keywords: computer vision; Deep Learning; Recycling

Comprehensive approach for assessing, managing, and Monitoring Asphaltene Deposition and inhibitor utilization in oil wells - Jafari, Farshad; Karambeigi, Mohammad Ali; Hejri, Shahab; Kharrat, Riyaz (Geoenergy science and engineering, 2024)
This study addresses the challenges of managing asphaltene precipitation in oil well production, aiming to establish a rapid computational approach for production management based on individual well productivity. The methodology involves modeling the impact of inhibitors on tubing diameter and incorporating well and reservoir performance. Validation using real-world data reveals optimal production conditions related to Asphaltene Onset Pressure (AOP) and Bubble Point Pressure (Pb) in relation to inhibitor location. The study emphasizes the importance of positioning AOP above the perforation interval for operable conditions and observes the impact of asphaltene deposition on wellhead pressure. To address increased bottomhole drawdown pressure, a production rate regulatory program is developed. The research offers a novel computational approach for managing asphaltene precipitation, grounded in real-world data, and provides insights into optimizing production rates while ensuring flow assurance in oil well operations. Additionally, strategic recommendations for field development are proposed, including acid/hydraulic fracturing and deviated horizontal/bilateral wells drilling to mitigate bottomhole drawdown pressure.
Publisher Copyright: © 2023 The Authors
Keywords: Asphaltene deposition; Formation plug-in; Asphaltene inhibitor; Flow assurance; Rate regulation; Field management

Demand Side Management: Entscheidung leicht gemacht - Pfleger, Jasmin; Reiter, Jana; Zawodnik, Vanessa (EW : Magazin für die Energie-Wirtschaft, 2024)

Demand Side Management: Entscheidung leicht gemacht - Pfleger, Jasmin; Reiter, Jana; Zawodnik, Vanessa (Öko+ : das Fachmagazin für Ökonomie + Ökologie, 2024)

Effect of different weft-knitted structures on the mechanical performance of bio-based flexible composites - Schwaiger, Markus; Bender, Marcel; Schirmer, Heiko; Taesler, Johannes; Feuchter, Michael; Resch-Fauster, Katharina (Composites Part C: Open Access, 2024)
This work investigates composites from renewable resources that exhibit high flexibility. The effect of three different weft-knitted structures on the tensile properties, flexural properties, tear resistance and puncture impact properties is analyzed in combination with two different flexible matrix materials. Furthermore, the potential of the knitted structures in flexible composites is compared to a woven fabric and comprehensively discussed. The tear resistance and the total absorbed energy in puncture impact tests were unaffected by the matrix material. Among the knitted structures, the highest tensile strength, tear resistance and impact properties were achieved with the interlock structure, whereas the double jersey with tuck stitch structure resulted in the lowest flexural modulus. However, a much higher tensile strength was achieved with the woven fabric, at the expense of a higher flexural modulus. Overall, knitted structures proved promising to be used in bio-based flexible composites for applications requiring high flexibility without the need for high tensile strength.
Publisher Copyright: © 2024
Keywords: Bio-composite; erneuerbare Stoffe; Epoxid; Leinöl; mechanische Eigenschaften; Bio-composite; Epoxy resin; Flexibility; Linseed oil; Mechanical properties; Renewable

Impact crusher kinematics - Kemper, Dietmar; Fimbinger, Eric; Antretter, Thomas; Egger, Matthias; Flachberger, Helmut (Results in Engineering, 2024)
This study presents an analytical-mathematical model that elucidates the mechanics/kinematics of an impact crusher’s impact swing mechanism. Essentially, this model comprises a series of mathematical descriptions and equations that are leveraged from established mechanical principles, such as rigid body kinematics, multibody dynamics, and collision laws, thus enabling comprehensive analytical exploration of the complex mechanical-kinematical system underlying the impact swing’s mechanism, particularly focusing on the system-critical activation of this mechanism when triggered by an impacting non-fragile particle. The developments presented in this paper, supportively illustrated through detailed diagrams, provide relevant insights into the operational behaviour of modern impact crushers. This research therefore not only advances the theoretical understanding of system-critical crusher kinematics but also holds significant implications for the design and optimisation of future equipment. The resulting model’s ability to analytically and mathematically delineate the complex mechanical-kinematical system of an impact swing mechanism not only facilitates efficient analyses but also circumvents the extensive and resource-intensive demands typically associated with numerical simulations of such systems. Consequently, this approach thereby forms substantial added value, particularly in the realm of engineering analysis.
Publisher Copyright: © 2023 The Authors
Keywords: Impact crusher; mineral processing; impact swing; mathematical model; analytical model; kinematics; rigid body kinematics; multibody dynamics; impact dynamics; crusher design; crankshaft system; Impact dynamics; Impact swing; Mechanical model; Crusher design; Mineral processing; Analytical model; Rigid body kinematics; Crankshaft system; Kinematics; Multibody dynamics; Mathematical model

Nanomechanical characterization - Kiener, Daniel; Misra, Amit (MRS Bulletin, 2024)
Recent developments in test methodologies for nanoindenter-based small-length-scale mechanical characterization are overviewed, such as micropillar compression, cantilever beam bending, and tensile tests. Emphasis is placed on the possibilities offered by in situ testing in transmission and scanning electron microscopes, as well as examining strain rate and temperature dependence of mechanical strength. The versatility and growing impact of new nanomechanical characterization tools is highlighted through selected recent examples, such as indentation (sample) size effect, crack-tip plasticity, radiation damage, indentation creep, laser additive manufacturing, and crystalline/amorphous high-entropy alloys. Graphical abstract: (Figure presented.)
Publisher Copyright: © The Author(s) 2024.
Keywords: Dislocations; Electron microscopy; Mechanical behavior; Metallurgy; Nanomechanics

Neue Wege in der Leichtverpackung (LVP)-Sortierung - Innovative Identifikationstechnologien revolutionieren das Recycling in Deutschland - Guo, Jinyang; Kuchta, Kerstin; Woidasky, Jörg; Auer, Maximilian; Schmidt, Jannick; Pomberger, Roland; Tischberger-Aldrian, Alexia; Kuhn, Nikolai Emanuel (Müll und Abfall, 2024)
Keywords: Kunststoffsortierung; Sortiertechnik

Phase composition and proton uptake of acceptor-doped self-generated Ba(Ce,Fe)O3-δ – Ba(Fe,Ce)O3-δ composites - Nader, Christina; Lammer, Judith; Egger, Andreas; Berger, Christian; Sitte, Werner; Grogger, Werner; Merkle, Rotraut; Maier, Joachim; Bucher, Edith (Solid State Ionics, 2024)
Self-generated Ba(Ce,Fe,In)O 3-δ composites were prepared by one-pot sol-gel synthesis. They consist of Ce-rich and Fe-rich phases, and are intended to supply the required protonic and electronic transport for air electrode materials in protonic ceramic fuel and electrolysis cells (PCFC, PCEC). Crystal structure, lattice parameters, and the relative phase amounts of the composites were obtained from X-ray diffraction. The local chemical composition and distribution of cations within the individual phases were characterized by scanning transmission electron microscopy and energy-dispersive X-ray spectroscopy. Annealing experiments indicate that the miscibility gap of the BaCe 0.8-xFe xIn 0.2O 3-δ system ranges from [Ce]/([Ce] + [Fe]) ratios of ~ 0.2 to ~ 0.9. The In 3+ acceptor shows a tendency to accumulate in the Fe-rich phase, with the ratio In(Ce-rich phase)/In(Fe-rich phase) being in the range of 0.3–0.7. The proton uptake capacity of the materials, which was analyzed by thermogravimetry, increases with an increasing amount of In and decreasing amount of Fe in the precursor. Proton concentrations are in the range of 1–4 mol% at 400 °C. Further measurements on BaCe 0.4Fe 0.4Acc 0.2O 3-δ (Acc = Y, Yb, Gd, Sm, Sc) composites show that proton uptake is generally increased compared to the undoped system BaCe 0.5Fe 0.5O 3-δ. However, variations in the acceptor ion can tune the proton uptake only to a limited extent.
Publisher Copyright: © 2024 The Authors
Keywords: Barium indium cerate; Barium indium ferrate; Crystal structure; Miscibility gap; Proton uptake capacity; Self-generated composite

Schurrensimulationen für eine Waggonbeladeeinrichtung - Prenner, Michael (2024)

The Impact of the Bohemian Spur on the Cooling and Exhumation Pattern of the Eastern Alpine Wedge of the European Alps - Heberer, Bianca; Salcher, Bernhard C.; Tari, Gabor; Wessely, Godfrid; Dunkl, István; Sachsenhofer, Reinhard F.; Wagreich, Michael; von Hagke, Christoph (Tectonics, 2024)
Publisher Copyright: © 2024. The Authors.
Keywords: basement step; Bohemian Spur; Eastern Alps; exhumation; fold and thrust belt; thermochronology

The ball-on-three-balls strength test: In-situ testing through X-ray radiography and tomography - Staudacher, Maximilian; Pinzón, Gustavo; Adrien, Jérôme; Lachambre, Joël; Maire, Eric; Chevalier, Jérôme; Lube, Tanja (Open ceramics, 2024)
Over the past two decades, the Ball-on-Three-Balls-test (B3B) has been increasingly used due to its low systematic error and simple execution. A limiting factor for a more wide-spread use of the B3B-test is the lack of an accurate analytical solution. This demands the use of numerical methods, such as Finite-Element-Analysis (FEA). In a recent work, FEA has been used to assess the influence of non-linear effects on the measured strength. To validate the utilized FEA-model, the experimental measurement of the specimen's deflection can be drawn on. Due to the design of the fixture for the B3B-test, common deflection-measurement methods are not straightforward. Therefore, X-ray tomography is employed in this paper to track the displacement of the load and support balls for thin plates of a high-strength glass and Ce-doped zirconia presenting transformation-induced plasticity. Furthermore, the ball displacement is also determined from two-dimensional radiographs and shows good agreement with FEA results.
Publisher Copyright: © 2023 The Authors

UV lamp spectral effects on the aging behavior of encapsulants for photovoltaic modules - Heidrich, Robert; Barretta, Chiara; Mordvinkin, Anton; Pinter, Gerald Gerhard; Oreski, Gernot; Gottschalg, Ralph (Solar energy materials and solar cells, 2024)
Polymer encapsulants used in photovoltaic (PV) modules experience severe UV aging during more than 25 years of module’s operation. However, the current standard qualification tests cannot provide a sufficient solution able to mimic the UV exposure in the field. IEC 61215 defines the requirements for UV stability of PV modules with very low cumulative UV dosage. While the new IEC 62788-7-2 imposes higher UV dosages on polymers films, the used UV testing procedure allows the use of either UV-A fluorescence lamps or xenon lamps, yielding different spectra. The given work compares the effect of different lamp spectra, based on IEC 62788-7-2, on the aging behavior of the encapsulant. For this purpose, coupons (glass/encapsulant/busbar/encapsulant/backsheet) using the common encapsulant ethylene-vinyl acetate copolymer (EVA) and the emerging encapsulants polyolefine (POE) and thermoplastic polyolefine (TPO) were manufactured. The samples were weathered under different UV conditions for a total duration of 2500 h with extraction times of 250 h. Photodegradation was observed for all encapsulants and weathering types. However, in general the weathering with UV-A lamps inflicted significantly less damage. The formation of unsaturated carbon bonds because of polymer backbone decomposition was only reported for xenon lamp weathering. The carried out experiments suggest that xenon lamps, providing more realistic accelerated aging, should be predominately used in the UV weathering standards in the PV industry, whose current versions are to be accordingly reconsidered.
Funding Information: We acknowledge support by the German Research Foundation (Deutsche Forschungsgemeinschaft DFG) - project number 491460386 - and the Open Access Publishing Fund of Anhalt University of Applied Sciences. Furthermore, we acknowledge funding by TotalEnergies. Publisher Copyright: © 2023 The Author(s)
Keywords: EVA; IEC 62788; POE; Spectroscopy; TPO; UV degradation

Determining the critical Reynolds number for suppressing Marangoni convection of alumina in silicate melt - Burhanuddin, Burhanuddin; Harmuth, Harald; Vollmann, Sandra (Ceramics International : CI, 2024)
Ceramic dissolution within silicate melts is often caused by Marangoni convection arising from surface tension gradients, unless it is counteracted by forced convection, which typically occurs beyond a specific critical Reynolds number (〖Re〗_c). This study presents a method for determining the 〖Re〗_c required to suppress Marangoni convection at the alumina (Al2O3)/slag/air triple point. This approach utilizes a modified finger test device equipped with a high-resolution laser for dimensional measurement, allowing accurate determination of mass flux densities from the grove and mantle separately. Subsequently, we examined the dissolution of Al2O3 fine ceramics in a quaternary silicate melt of calcium oxide (CaO)–Al2O3–silicon dioxide (SiO2)–MgO (or magnesium oxide), featuring a CaO/SiO2 weight ratio of 0.65. The experiments were conducted at 1550 °C for speeds of 0, 50, 100, and 200 rpm. The findings revealed a critical rotational speed of 127 rpm for Al2O3-dissolution in this silicate slag at 1550 °C using the aforementioned device, corresponding to an 〖Re〗_c of 6.46. These results contribute to a deeper understanding of the factors influencing ceramic dissolution in silicate melts and offer valuable insights for materials and process engineering applications.
Publisher Copyright: © 2024 Elsevier Ltd and Techna Group S.r.l.
Keywords: Alumina; Marangoni convection; Corrosion; Silicate slag; Critical Reynolds number

Leverage demand-side policies for energy security - Bento, Nuno; Gruebler, Arnulf; Boza-Kiss, Benigna; De Stercke, Simon; Krey, Volker; McCollum, David L; Zimm, Caroline; Alves, Tiago (Science, 2024)

A mathematical study of the Braess's Paradox within a network comprising four nodes, five edges and linear time functions - Poulios, Nikolaos; John Leventides; C. Poulios; M. Livada; E. Melas (Springer, 2024)

Polyphase stratabound scheelite-ferberite mineralization at Mallnock, Eastern Alps, Austria - Altenberger, Florian; Krause, Joachim; Wintzer, Niki E.; Iglseder, Christoph; Berndt, Jasper; Bachmann, Kai; Raith, Johann G. (Mineralium deposita, 2024)
A peculiar type of stratabound tungsten mineralization in metacarbonate rocks was discovered and explored at Mallnock (Austria) during the late 1980s. It is the only tungsten occurrence in the Eastern Alps in which scheelite is associated with wolframite (96 mol% ferberite). The tungsten prospect is located in the Austroalpine Drauzug-Gurktal Nappe System recording polyphase low-grade regional metamorphism. Raman spectroscopy of carbonaceous material yield maximum metamorphic temperatures of 296 ± 27 °C and 258 ± 27 °C, which are assigned to Variscan and Eoalpine metamorphism, respectively. Scheelite and ferberite occur as polyphase stockwork-like mineralization in Fe-rich magnesite in the northern ore zone (Mallnock North), whereas in the western ore zone (Mallnock West), scheelite-quartz veinlets are exclusively hosted in dolomitic marbles.LA-ICP-MS analyses of scheelite and ferberite yield low contents of Mo, Nb, Ta, and rare earth elements, but high contents of Na and Sr. Uranium is particularly high in scheelite (up to 200 µg/g) and makes this mineral a suitable target for U-Pb dating. In-situ U-Pb dating of scheelite yielded an early Permian age (294 ± 8 Ma) for Mallnock West and a Middle Triassic age (239 ± 3 Ma) for Mallnock North. A monzodioritic dike close to Mallnock yielded a U-Pb apatite date of 282 ± 9 Ma and supports the polyphase formation of this mineralization.The U-Pb scheelite ages indicate that a model for tungsten metallogeny in the Eastern Alps must also consider remobilization of tungsten by metamorphic fluids. In the Alps, the Permian to Triassic period (ca. 290-225 Ma) is characterized by an overall extensional geodynamic setting related to the breakup of Pangea. Lithospheric thinning caused higher heat flow, low-P metamorphism, and anatexis in the lower crust, which led to enhanced crustal fluid flow in the upper crust. These processes were not only responsible for the formation of metasomatic hydrothermal magnesite and siderite deposits in the Eastern Alps but also for this unique magnesite-ferberite-scheelite mineralization at Mallnock.
Publisher Copyright: © The Author(s) 2024.
Keywords: Scheelite; Wolframite; LA-ICP-MS trace element analyses; Raman spectroscopy; U-Pb dating; Eastern Alps; U–Pb dating

DISPOSITIVO CON UNIDAD DE GUIA PARA GUIAR UNA CINTA TRANSPORTADORA - Prenner, Michael (2024)
] Dispositivo (1) para guiar una cinta transportadora, con una unidad de guia (2) con un cuerpo cilindrico hueco exterior y otro interior (3,4), en donde el cuerpo cilindrico hueco interior (4) tiene una primera linea central y esta dispuesto en el cuerpo cilindrico hueco exterior (3) que tiene una segunda linea central y ambos cuerpos cilindricos huecos presentan en cada caso una linea central (Xl, X2j) con al menos un cojinete (5) para el alojamiento giratorio del cuerpo cilindrico hueco exterior sobre el cuerpo cilindrico hueco interior y con un cuerpo de articulacion (6) preparado para el alojamiento del cuerpo cilindrico hueco interior (4) sobre un eje central (7), en donde el cuerpo de articulacion (6) esta preparado adicionalmente para permitir un cambio de angulo horizontal y/o vertical de la primera y/o segunda linea central (X|, Xz) con respecto a una linea central (X3) del eje central, en donde el dispositivo esta equipado con un sistema de medicion y evaluacion (8) que presenta una unidad de sensor (9) que esta dispuesta dentro y/o fuera de la unidad de guia (2), en donde el sistema de medicion y evaluacion (8) esta preparado para detectar el cambio de angulo.

Effect of ZrO2 in the activity of Cu/CeO2 catalysts for reverse water gas shift reaction - Palma, Mireia; Schröder, Christian; Schrenk, Florian; Rameshan, Christoph; Barrabés, Noelia; Sanchez-Sanchez, Maricruz (FemChem Scientific Workshop, 2024)

Gutachten zur Dissertationsschrift - Galler, Robert (Neue Methoden zur Untersuchung bindiger und nicht-bindiger Böden beim maschinellen Tunnelvortrieb mit Erddruckstützung, 2024)

Perovskite-type Oxides in Methanol Steam Reforming: Overcoming the Challenges of Conventional Catalytic Systems - Berger, Tobias; Drexler, Hedda; Ruh, Thomas; Schrenk, Florian; Lindenthal, Lorenz; Rameshan, Raffael; Rameshan, Christoph (12th NESY Winterschool & Symposium, 2024)

Neural Network Supported Microscale In Situ Deformation Tracking: A Comparative Study of Testing Geometries - Keckes, Julius; Jelinek, Alexander; Kiener, Daniel; Alfreider, Markus (JOM, 2024)
Micro- and nanomechanical testing techniques have become an integral part of today’s materials research portfolio. Contrary to well-studied and majorly standardized nanoindentation testing, in situ testing of various geometries, such as pillar compression, dog bone tension, or cantilever bending, remains rather unique given differences in experimental equipment and sample processing route. The quantification of such experiments is oftentimes limited to load-displacement data, while the gathered in situ images are considered a qualitative information channel only. However, by utilizing modern computer-aided support in the form of the recently developed Segment Anything Model (SAM), quantitative mechanical information from images can be evaluated in a high-throughput manner and adds to the data fidelity and accuracy of every individual experiment. In the present work, we showcase image-assisted mechanical evaluation of compression, tension and bending experiments on micron-scaled resin specimens, produced via two-photon lithography. The present framework allows for a determination of an accurate sample strain, which further enables determination of quantities such as the elastic modulus, Poisson’s ratio or viscoelastic relaxation after fracture.
Publisher Copyright: © The Author(s) 2024.

On the applicability of carbon steels K55 and L80 for underground hydrogen storage - Loder, Bernd; Bhosale, Saurabh; Eichinger, Matthias; Mori, Gregor Karl; Rokosz, Krzysztof; Fournier, Cyriane; Réveillère, Arnaud; Bulidon, Nicolas; Moli-Sanchez, Laura; Mendibide, Christophe (International Journal of Hydrogen Energy, 2024)
To evaluate the possibility of hydrogen storage in depleted gas reservoirs, natural gas storage facilities, aquifers and salt caverns, the applicability of ferritic pearlitic K55 and tempered martensitic L80, both very frequently used as casings and tubings, has been investigated. Materials were investigated by means of high-pressure, high-temperature autoclave tests and analyses of the hydrogen uptake. The autoclave tests were performed on tensile specimens loaded with a spring at 90 % of the specified minimum yield strength, additionally the samples were analysed to determine the hydrogen uptake. Different gas compositions were considered (pure hydrogen, with or without the presence of CO2/H2S) under a hydrogen partial pressure of 120 bar. The tests were conducted in dry or wet environments. From the results, it can be seen that the hydrogen uptake is low even under the most severe conditions. However, from the mechanical test conducted in this study, it appears that the ferritic pearlitic K55 steel seems to be a suitable pipe material for underground hydrogen storage, and the higher strength steel L80 steel can be used only in non-sour environments (no significant amount of H2S in the reservoir, which is a priori the case of underground storages).
Publisher Copyright: © 2023 The Authors
Keywords: Carbon steel; Constant load tests; Hydrogen embrittlement; Hydrogen storage; Ripple load tests

Comparative analysis of binder systems in copper feedstocks for metal extrusion additive manufacturing and metal injection moulding - Sadaf, Mahrukh; Cano Cano, Santiago; Bragaglia, Mario; Schuschnigg, Stephan; Kukla, Christian; Holzer, Clemens; Vály, Lilla; Kukla, Christian; Kitzmantel, Michael; Nanni, Francesca; Gonzalez-Gutierrez, Joamin (Journal of Materials Research and Technology, 2024)
In the realm of material innovation, the remarkable versatility of thermoplastic-based highly filled composites emerges as a pivotal advantage for fabricating metal parts, seamlessly integrating design flexibility. This study delves into the fusion of design and manufacturing, spotlighting the convergence of material extrusion additive manufacturing (MEX) and metal injection moulding (MIM) processes through the adept utilization of three distinct in-house developed copper-feedstocks. Each feedstock had a different composition that influenced their processability; two feedstocks were for solvent and thermal debinding, and one was only for thermal debinding. The sintering was carried out under the same conditions for all produced specimens to assess the effect of binder composition on the properties of the sintered components. Structural integrity evaluations of sintered specimens encompassed 3-point bending, hardness tests, and metallography. It was possible to perform MEX with all produced filaments and MIM with the pellets of the same feedstocks and to obtain acceptable-quality specimens. Regardless of the shaping method, specimens shaped with binders containing a soluble binder survived the thermal and sintering steps. The specimens produced from the feedstock intended solely for thermal debinding experienced a nearly complete loss of shape during the debinding process. For the specimens that could be debound and sintered without defects, a relative density between ∼88 and 94 % was measured for MEX components and ∼93 and 95 % for MIM components after sintering. All sintered components showed the same diffraction peaks as pure copper powder, confirming that the reductive hydrogen atmosphere provided protection from contamination and reduced the oxides that could have appeared during thermal debinding in air. Moreover, adequate shrinkage of ∼10–18 % was observed in the sintered specimens. Vickers microhardness of the MEX and MIM sintered components were ∼32 HV and ∼36 HV, respectively. Compared to MEX, MIM-produced sintered components showed a higher maximum stress (i.e., σmax = 79 ± 3.2 MPa). These results demonstrate that the binder composition plays a crucial role in determining the success of metal MEX and MIM processes. Having the possibility to choose between MEX and MIM allows for greater design flexibility for copper parts.
Publisher Copyright: © 2024 The Authors
Keywords: Additive manufacturing; Copper; Debinding; Material extrusion (MEX); Metal injection moulding (MIM); Sintering; Feedstock; Copper; Polymer processing; Material Extrusion; Additive Manufacturing

Tensile properties of flexible composites with knitted reinforcements from various yarn materials - Schwaiger, Markus; Röper, Florian; Wolfahrt, Markus; Taesler, Johannes; Schirmer, Heiko; Salzmann, Moritz; Feuchter, Michael; Resch-Fauster, Katharina (Polymer Composites, 2024)
The tensile behavior of a flexible epoxy resin reinforced with knitted reinforcements from various fiber materials was comprehensively studied in the wale and course direction. By measuring dry yarns, temperature-treated yarns, dry knitted fabrics and flexible composites, the effect of the fiber material and the knitted fabric on the tensile properties was analyzed. The interlock knit structure strongly affected the deformation behavior of the flexible composites which differed significantly from the dry knitted fabrics. The deformation behavior of the flexible composites was monitored using digital image correlation which revealed the formation of cracks and high local strain differences in the course direction for all fiber materials. This was linked to fiber-matrix debonding by scanning electron microscope observations. In the wale direction, the deformation of the knitted structure under tensile load led to plastic deformation of the matrix material. Overall, with yarns from recycled thermoplastic fibers, a higher maximum stress and strain at break was achieved compared to bio-based fibers. However, irreversible damage occurred for all fiber materials at similar strain values. Highlights: Tensile tests on yarns, knitted fabrics and flexible composites. Investigation of the effect of fiber material on mechanical properties. High local strain differences in composites due to knitted structure. Fiber-matrix debonding in course direction. Plastic deformation of the matrix material in the wale direction.
Publisher Copyright: © 2023 The Authors. Polymer Composites published by Wiley Periodicals LLC on behalf of Society of Plastics Engineers.
Keywords: Verbundwerkstoff; flexibel; Zugprüfung

New method for determining the Mode-I fracture toughness of shotcrete: edge notched partial disc test - Manesh, Mohammad Omidi; Sarfarazi, Vahab; Babanouri, Nima; Rezaei, Amir; Moayedi Far, Arsham (Magazine of concrete research, 2024)
The fracture toughness (mode I) of shotcrete specimens was obtained using edge-notched partial disc (ENPD) specimens. Notched Brazilian discs (NBDs) were also tested to validate the results of the ENPD experiments. Numerical analysis was also conducted on the ENPD results to compare the measured and numerically obtained fracture toughness values. The notch lengths in the ENPD specimens were 15, 30, 45 and 60 mm, while the notch lengths in the NBD specimens were 10, 20, 30, 40, 50 and 60 mm. It was found that the flat joint model accurately predicted the potential crack growth path and crack initiation stress as compared with the experimental results. It was also deduced that the fracture toughness was roughly the same with an increase in the notch length. The tensile strength (σ t) and fracture toughness (K IC) of the shotcrete specimens were found to be meaningfully correlated (σ t = 7.92K IC). The ENPD tests yielded the lowest fracture toughness values because of the pure tensile stress distribution on the failure surface. It was also found that the derived fracture extension patterns from the laboratory investigations were in acceptable agreement with the outputs of numerical simulations.
Publisher Copyright: © 2023 ICE Publishing. All rights reserved.
Keywords: Mining & environmental issues; Numerical modeling; Toughness; numerical modelling; mining & environmental issues; toughness

Rapid tooling for rubber extrusion molding by digital light processing 3D printing with dual curable vitrimers - Höller, Rita; Hrbinič, Katja; Reisinger, David; Alabiso, Walter; Schuschnigg, Stephan; Fleisch, Mathias; Waly, Christoph; Rossegger, Elisabeth; Schlögl, Sandra (Applied research, 2024)
For the manufacture of extrusion dies, three-dimensional (3D) printing with photopolymers offers numerous advantages including flexibility, high surface quality, decent build speed, low costs and a reduced amount of waste. However, the majority of photocurable resins used in vat photopolymerization 3D printing rely on acrylates, which entail 3D-printed objects with poor mechanical properties. In particular, the high brittleness limits their application in rapid tooling, for which tough materials with high glass transition temperatures (Tg) are required. In the present study, we highlight the use of dual curable acrylate-epoxy resins with dynamic covalent bonds for the direct fabrication of extrusion dies. During digital light processing (DLP) 3D printing the acrylate network is formed, whose toughness and thermal stability are significantly enhanced by the thermoactivated formation of a second network. By following a postbaking procedure, aminoglycidiyl monomers are cured with an anhydride hardener bearing bulky norbornene groups yielding interpenetrating polymer networks with a Tg > 100°C. The tertiary amine groups present in the structure of the aminoglycidyl derivatives do not only accelerate the ring-opening reaction but also act as internal catalysts and activate bond exchange reactions between free –OH groups and ester moieties available in the photopolymer. This is confirmed by rheometer studies showing a distinctive stress relaxation at elevated temperature and giving rise to a possible reprocessability of the 3D-printed dies. With a selected resin formulation, a set of dies is printed by DLP 3D printing, with which a highly filled rubber compound is successfully extruded. The results clearly show that dual curable resins with dynamic covalent bonds are a promising class of material for rapid tooling and pave the way towards a customized and convenient fabrication of extrusion dies for rubber processing.
Publisher Copyright: © 2024 Wiley-VCH GmbH.
Keywords: dies; dynamic photopolymers; extrusion molding; rapid tooling; transesterification

Hydrogen densification in carbon nanopore confinement - Stock, Sebastian; Seyffertitz, Malina; Kostoglou, Nikolaos; Rauscher, Max; Presser, Volker; Demé, Bruno; Cristiglio, ‪Viviana; Kratzer, Markus; Rols, Stéphane; Mitterer, Christian; Paris, Oskar (Carbon, 2024)
This study reports on the low-pressure hydrogen (H2) and deuterium (D2) physisorption processes in nanoporous activated carbon cloth at supercritical temperatures. In-situ small-angle neutron scattering (SANS) is employed as a hydrogen-sensitive method to determine the pore-size-dependent and isotope-dependent adsorbate densification for different gas pressures up to 1 bar. The changes of the SANS signal resulting from the physisorption of adsorbate molecules in the pore space is described by analytical pore scattering functions resembling slit-like pores. Analysis based on a hierarchical pore model allows quantifying the pore-size-dependent physical density of the confined adsorbate for three pore classes, resembling roughly the IUPAC classes of ultramicropores, supermicropores, and mesopores. While the adsorbate density within the very smallest pores approaches the bulk solid density of H2 for pressures of about 1 bar at 77 K, it remains much lower for larger pores. A high density is also found for D2 within ultramicropores, but these results are hampered by a subtle effect of an exchange of chemically bound hydrogen by deuterium in the sample. These findings contribute to a fundamentally better understanding of confinement effects on hydrogen densification, and affect materials design for efficient hydrogen storage devices working at realistic cryogenic conditions and low pressures.

Characterization of fracture behavior under impact-like loading conditions of elastomeric grades for high-pressure gas applications - Balasooriya, Winoj; Kaiser, Andreas; Fasching, Michael; Hausberger, Andreas; Schwarz, Thomas; Pinter, Gerald Gerhard (Polymer, 2024)
Funding Information: The PCCL is funded by the Austrian Government and the State Governments of Styria , Lower Austria and Upper Austria . Funding Information: The authors thank Jürgen Grosser and Philipp Arno Franz Huber for the assistance provided in experimental aspects. The research work was performed within the COMET-project “Polymers4Hydrogen” (project-no.: 21647053) at the Polymer Competence Center Leoben GmbH (PCCL, Austria) within the framework of the COMET-program of the Federal Ministry for Climate, Action, Environment, Energy, Mobility, Innovation and Technology and the Federal Ministry for Digital and Economic Affairs with contributions by Montanuniversität Leoben (Department Polymer Engineering and Science, Chair of Chemistry of Polymeric Materials, Chair of Materials Science and Testing of Polymers), Politecnico di Milano, Technical University of Munich, Tampere University of Technology. Bundesanstalt für Materialforschung und -prüfung (BAM) and Arlanxeo Deutschland GmbH, ContiTech Rubber Industrial Kft. Peak Technology GmbH, SKF Sealing Solutions Austria GmbH, Faurecia. The PCCL is funded by the Austrian Government and the State Governments of Styria, Lower Austria and Upper Austria. Publisher Copyright: © 2024 Elsevier Ltd
Keywords: Elastomers; High-pressure H gas; High-rate fracture; Rapid gas decompression (RGD); Tearing energy

A rapid heat treatment for nanocrystallization of amorphous Fe75.1Cu1Nb1.5Si15.5B6.9 and Fe83Cu1Nb4B12 tape wound cores - Plutta, Niklas; Spieckermann, Florian; Polak, Christian; Marsilius, Mie; Zehetbauer, Michael J.; Eckert, Jürgen (Journal of magnetism and magnetic materials, 2024)
A rapid annealing technique for soft magnetic Fe75.1Cu1Nb1.5Si15.5B6.9 and Fe83Cu1Nb4B12 tape wound cores is presented. Its effectiveness for creating a fine-grained nanocrystalline structure is demonstrated by measurements of the magnetic hysteresis loops as well as by structural investigations done by X-ray diffraction. The results show that the technique reduces the average crystallite sizes from about 27 nm to 17 nm for Fe75.1Cu1Nb1.5Si15.5B6.9, and from about 52 nm to 15 nm for Fe83Cu1Nb4B12. The coercivity after the rapid annealing is about three times lower for the Fe75.1Cu1Nb1.5Si15.5B6.9 alloy and up to one order of magnitude lower for the Fe83Cu1Nb4B12 alloy compared to the coercivity after the standardized long-time heat treatment. The improved heat treatment is outstanding in the way that it produces better soft magnetic properties in high-performance alloy cores within much shorter time than the standard core heat treatments.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Heat treatment; Nanocrystallinity; Soft magnetic; Tape wound core

Influence of multiple detection events on compositional accuracy of TiN coatings in atom probe tomography - Schiester, Maximilian; Waldl, Helene; Hans, Marcus; Thuvander, Mattias; Primetzhofer, Daniel; Schalk, Nina; Tkadletz, Michael (Surface & coatings technology, 2024)
The accuracy of composition measurements by atom probe tomography is often dependent on the selected operation mode as well as the applied measurement parameters. The detected hit characteristics, distinguishing between single and multiple events, along with the electric field, are also affected by parameter selection. In this study, atom probe tomography experiments were performed on a stoichiometric TiN coating in voltage as well as in laser-assisted mode with systematically varied laser pulse energies. The observed elemental compositions were compared with complementary ion beam analysis measurements. The influence of multiple detection events was investigated by two approaches: I) A modified local electrode served as a hardware filter, reducing multiple detection events from 78.8 % to 41.9 % and from 40.9 % to 5.6 % using voltage mode and laser-assisted APT (0.6 nJ), respectively, and II) unfiltered datasets were analyzed by data post processing. The latter allowed the study of ion species, particularly of emerging complex molecular ions associated with dissociation processes. Additionally, average electric fields were estimated and spatial considerations were made to investigate the evolution of charge state ratios and hit characteristics during the measurement. Filtering the measurements significantly improved the elemental accuracy. In voltage mode, hardware and software filtering reduced the discrepancy between reference and observed composition from 3.8 at.% to 2.1 at.% and 0.1 at.% within uncertainty limits. In laser-assisted mode, higher laser pulse energy increased the difference between unfiltered data and the reference composition, from 1.4 at.% (0.1 nJ) to 8.1 at.% (2.0 nJ). Ion species analysis of the datasets shows an increasing presence of complex ions (Ti 2N) with raising laser pulse energy. Electric field studies reveal a decline from 40 V/nm in voltage mode to 36 V/nm applying a high laser pulse energy of 2.0 nJ, indicating insufficient field strength for neutral nitrogen re-ionization.
Publisher Copyright: © 2023 The Authors
Keywords: Atom probe tomography; Compositional accuracy; Electric field strength; Multiple detection events; TiN

Reversibel und räumlich getrennte Elektrolyse- Brennstoffzellensysteme im Energienetz mit erneuerbarer Erzeugung - Banasiak, David (EnInnov 2024 | 18. Symposium Energieinnovation: "Europas Energiezukunft: Sicher, leistbar, sauber?!", 2024)
Der europäische Green Deal und das Erneuerbaren-Ausbau-Gesetz legen in Österreich die Grundsteine für die Entwicklung der zukünftigen Energieversorgung. Der steigende Anteil an fluktuierender Einspeisung aus PV- und Windkraft und deren räumliche Verteilung führen zu Lastsituationen im elektrische Leitungsnetz, die sowohl einen Ausbau von Leistungen als auch Flexibilitäten erfordern. Die Sektorkopplung von Strom und Gas kann Flexibilitäten für kurz und Langzeitausgleich bereitstellen. In diesem Kontext werden in der gegenständlichen Arbeit Systeme mit Elektrolyse- und Brennstoffzellenfunktion in derselben Einheit (reversible EC/FC-Systeme) und räumlich getrennten EC- und FC-Systeme als Technologien zur Sektorkopplung untersucht und miteinander verglichen. Damit ermöglichen wir die Einschätzung der Anwendungspotentiale dieser beiden Ausführungen mit Hilfe von technoökonomischen Analysen und können Anwendungsszenarien vorschlagen.
Conference code: 18

Ternary low-friction coatings on thermoplastics by plasma spraying - Kopp, Dietmar; Gleirscher, Milena; Stummer, Maximilian; Major, Lukasz; Hausberger, Andreas; Schlögl, Sandra; Lackner, Jürgen Markus; Kaindl, Reinhard; Prethaler, Thomas; Coclite, Anna Maria; Waldhauser, Wolfgang (Surface and Coatings Technology, 2024)
Thermally sprayed MoS2/graphite/Zn coatings were developed by the atmospheric pressure plasma jet technique to investigate the process-structure-relationship of the low-friction coatings. The fine-tuning of the powder carrier gas flow to the plasma jet was supported by computational fluid dynamics and revealed the impact on the powder particles within the coating process i.e. ideal powder particle temperature for transferring the solid Zn powder into the liquid state as main requirement for a successful embedding process of the dry lubricants. MoS2/graphite/Zn composite coatings were deposited on polyamide 4.6 (PA4.6) substrates to evaluate the adhesion/cohesion properties and tribological performance by tuning the current of the atmospheric pressure plasma jet (APPJ) from 125 A to 150 A. In particular, the plasma spraying distribution of the composite feedstock and the resulting coating architecture are strongly dependent on the plasma process setting, which are investigated by scanning electron microscopy and transmission electron microscopy in combination with an energy-dispersive x-ray spectrometer. Tribological characterisation indicates that coating composition and thickness influence the coating performance significantly. According to the 125 A plasma current setting, the low frictional compounds MoS2 and graphite are embedded in a Zn matrix in contrast to plasma current settings of 150 A, where Zn is embedded in a MoS2 and graphite matrix and demonstrates excellent low frictional properties.
Publisher Copyright: © 2023 The Authors
Keywords: Atmospheric pressure plasma jet; Composite coating; Polyamide 4.6 (PA4.6); Process-structure-relation

Analysing the Impacts of an External Power Supplier in a Renewable Energy Community - Feichtinger, Gerald; Ringhofer, Samuel; Posch, Wolfgang (2024)
Renewable energy communities (REC) offer the possibility of joint production and supply of renewable energy sources. This article presents the framework conditions of REC in Austria and comprehensively analyses the financial and ecological effects of an REC using a newly developed analysis tool. The results show positive financial and ecological effects of the REC being investigated by introducing an external power supplier. A sensitivity analysis was applied to evaluate all parameters used in the simulation model and to identify the key influencing variables which are the grid electricity price, the inflation rate and the discount rate.
Keywords: Renewable energy community; External power supplier; Net present value; NPV; Financial feasibility

Waste-Based Geopolymer Construction Materials - Ratz, Bettina; Sedlazeck, Klaus Philipp; Sattler, Theresa Magdalena; Steindl, Florian Roman; Raič, Sara; Rudic, Ognjen; Grengg, Cyrill (13. DGAW-Wissenschaftskongress: Abfall- und Ressourcenwirtschaft, 2024)
The building and construction industry generates enormous amounts CO2 emissions. To counteract this impact and to reduce the quantity of landfilled mineral waste in Austria,the Christian Doppler Laboratory GECCO2 attempts to generate highly resistant environmentally friendly waste-based geopolymer building and construction materials. These geopolymers, also referred to as alkali-activated materials, are utilized based on the specific material properties. One example is their use in chemically aggressive waste systems. Therefore, potential unexploited Austrian mineral waste and secondary raw material (SRM) streams are examined by various chemical, mineralogical and environmental characterization methods and techniques. The results are then used to compare the mineralogical and geochemical patterns of the waste and SRMs. These patterns define respective material categories and enable the development of a portfolio of Austrian mineral waste materials and SRMs. Subsequently, their suitability and recycling potential through geopolymerization are reviewed.

Investigation on strategies for optimizing process definition in rubber processing: A study on mechanical and chemical properties of vulcanizates as basis for the development of a new calculation model for quality prediction - Traintinger, Martin; Kerschbaumer, Roman C.; Hornbachner, Michaela; Lechner, Bernhard; Lucyshyn, Thomas (Journal of applied polymer science, 2024)
Rubber compounds may exhibit significant batch variations due to multiple different ingredients mixed in one compound. Hence, defining the manufacturing process for constant part quality can be challenging. Common strategies in considering batch variations in rubber processing include the determination of reaction kinetics, and the definition of process parameters according to normalized vulcanization isotherms. Thereby, maintenance of the degree of cure is targeted. With this path, information on the mechanical properties of vulcanizates is lost, despite its visibility from the kinetic data and part quality assurance is missed. This contribution points out the differences obtained for parts produced to the same degree of cure at various temperatures and intends to emphasize new strategies in process definitions. Therefore, compression molded parts were produced from styrene-butadien rubber, which was then characterized with mechanical and chemical methods. Each of the methods revealed a significant difference in part behavior, which were manufactured to the same degrees of cure but at different temperatures. It was concluded that a temperature-dependent reaction rate should be considered when quality maintenance is targeted in the production. Only then will it be possible to predict the properties adequately, with simultaneous effect of enhancing sustainability policies in rubber processing.
Publisher Copyright: © 2023 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals LLC.

Critical Examination of the Representativeness of Austenite Grain Growth Studies Performed In Situ Using HT-LSCM and Application to Determine Growth-inhibiting Mechanisms - Kern, Maximilian; Bernhard, Michael Christian; Presoly, Peter; Brandl, Dominik; Bernhard, Christian (Berg- und hüttenmännische Monatshefte : BHM, 2024)
This contribution critically addresses the potential of HT-LSCM experiments for in situ observations of austenite grain growth (AGG). By quantifying AGG for various alloys, the impact of impurity induced solute drag effects (SDE) and second phase precipitation Zener pinning forces (PZ) on AGG can be estimated. Also the grain boundary mobility (GBM) can be determined. The measured arithmetic mean of the time-resolved grain size distributions as a function of temperature and chemical composition is the most important value for quantification. The obtained data is then used to contribute to mathematical models of classical grain growth theory and to allow conclusions on parametrization of SDE and PZ. In this contribution, grain size measurements at the sample surface (in situ and ex situ) are compared with ex situ bulk measurements and experiments on grain growth in the single-phase austenite region (γ-Fe) under isothermal annealing conditions at different temperatures are presented. Grain growth results include high-purity Fe (Fe > 99.98%), binary Fe‑P, Fe‑C, and quaternary Fe-C-Nb‑N systems. For the alloys investigated, it is assumed that grain growth in high-purity Fe occurs without the influence of solute drag or precipitation mechanisms. In Fe‑P, it is shown that grain growth is inhibited by the segregation of impurity atoms at the grain boundaries (GB), which allows conclusions to be drawn about the influence of SDE. In the case of Fe-C-Nb‑N systems, the influence of Nb(C,N) precipitation on grain growth due to Zener pinning forces is presented.

Delamination prevention of composite joints with asymmetric carbon-fiber reinforced plastic adherends - Castro Pires, Vasco Daniel; Carbas, Ricardo JC; Marques, Eduardo AS; Silva, Lucas FM da (Journal of composite materials, 2024)

Application Of Production Simulation Combined With Site-Specific Data To Quantify The Environmental Performance Of Aggregate Products At Five Pilot Sites - Lee, Christina; Sánchez, Felipe; Asbjörnsson, Gauti; Evertsson, Magnus (Conference in Minerals Engineering, 2024)

A Modified Rotating-Finger Test Aiming to Quantify Refractory Wear Based on Fundamental Equations Governing Refractory Dissolution and Erosion - Burhanuddin, Burhanuddin; Harmuth, Harald (Springer, 2024)
Design of wear-resistant refractories necessitates an in-depth under-standing and accurate quantification of the continuous wear. However, the experimental methods reported in the literature are mostly phenomenological and unable to reveal the physicochemical background of continuous wear. Main goals of this work are scientific investigation of continuous refractory wear and acquisition of data for quantitative simulation of continuous wear to design wear-resistant refractories. A modified rotating-finger test (RFT) device was equipped with high-resolution laser to scan the sample surface for dimension measurement. Generally, refractory dissolution in molten slag is controlled by diffusion through a boundary layer and diffusivity is the most important parameter to quantify dissolution. The data obtained from modified RFT studies were applied to accurately determine effective binary diffusivity using simulation method or mass transfer equation. Also, results of erosion studies were applied for inverse calculation of erosion parameters. Continuous wear of alumina in silicate slag will be exemplified here.
Keywords: Refractory; Dissolution; Diffusivity; Erosion; Rotating finger test

Dispositivo com uma unidade de guia, para a guia de uma correia transportadora - Prenner, Michael; Dünnwald, Wilfried; Koth, Thorsten (2024)
dispositivo com uma unidade de guia, para a guia de uma correia transportadora. a invenção se refere a um dispositivo (1) para a guia de uma correia transportadora, com uma unidade de guia (2) com um corpo cilíndrico oco exterior e um corpo cilíndrico oco interior (3, 4) sendo que, o corpo cilíndrico oco interior (4) tem um primeiro eixo central, e está disposto no corpo cilíndrico oco exterior (3) que tem um segundo eixo central, e ambos os corpos cilíndricos ocos apresentam respectivamente um eixo central (x1, x2j), com pelo menos um mancal (5) para o apoio giratório do corpo cilíndrico oco exterior no corpo cilíndrico oco interior, e com um corpo articulado (6) colocado em um eixo central (7), sendo que, o corpo articulado (6) é projetado, além disso, para possibilitar uma alteração de ângulo horizontal e/ou vertical do primeiro e/ou segundo eixo central (x1, x2j), em relação a um eixo central (x3) do eixo central, sendo que, o dispositivo está equipado com um sistema de medição e de avaliação (8), que apresenta uma unidade de sensor (9), que está disposta fora da unidade de guia (2), sendo que, o sistema de medição e de avaliação (8) foi projetado para a recepção da alteração de ângulo.

Evaluierung der Unterschiede zwischen sequenzieller chemischer und elektrolytischer Extraktion anhand von Seltene Erden (SE)-haltigen Einschlüsse - Schickbichler, Manuel; Thiele, Kathrin; Michelic, Susanne Katharina (Berg- und hüttenmännische Monatshefte : BHM, 2024)
In metallurgischen Anwendungen nimmt der Einsatz von Seltenen Erden (SE) eine zunehmend größere Rolle ein. Diese werden in modernen Herstellungsprozessen nicht nur als Kornfeinungsmittel eingesetzt, sondern auch zur Markierung von Desoxidationsprodukten. Durch das Tracen der Einschlüsse (NME) ist es möglich, die Modifikation von beispielsweise Aluminiumoxiden über den Prozess zu verfolgen und zu erforschen. Aufgrund der teilweisen Reduktion der bestehenden NME kommt es zur Veränderung dieser hinsichtlich der chemischen und physikalischen Eigenschaften, sowie ihrer Morphologie.Die Modifikation der Einschlüsse mittels SE kann ebenfalls ihre Löslichkeit in verschiedenen Chemikalien beeinflussen. Daher liegt ein Fokus der durchgeführten Studie darauf, die Stabilität der gebildeten komplexen mehrphasigen SE-Al-Oxide mithilfe häufig angewandter Extraktionsmethoden zu untersuchen.Dabei kommt es zur Evaluierung der Anwendbarkeit von elektrolytischer und sequenzieller chemischer Extraktionstechnik für SE-haltige Einschlüsse. Bei den Proben für diese Studie handelt es sich um Ultra-Low Carbon (ULC)-Stähle, die durch Ce modifizierte Aluminiumoxide beinhalten. Ziel ist es, zusätzlich zur Überprüfung der Stabilität dieser mehrphasigen Einschlüsse bei verschiedenen Extraktionsmethoden auch die Anzahl an Einschlüssen pro Volumen zu prognostizieren. Dazu findet eine Berechnung der NME-Konzentration mittels des Modells nach Woodhead statt und anschließend werden die Ergebnisse dieser Modellrechnung mit der gemessenen Anzahl an NME pro Volumen verglichen.

Influence of Solidification Rate and Impurity Content on 5/7-Crossover Alloys - Samberger, Sebastian; Stemper, Lukas; Uggowitzer, Peter; Tosone, Ramona; Pogatscher, Stefan (2024)
In view of an upcoming scrap wave and the need for products with lower carbon footprint, there is an urgent need to increase the recycled fraction in wrought aluminum alloys. However, due to the narrow compositional limits of conventional aluminum wrought alloys and the higher impurity levels in scrap material, the applicable recycling content is limited. Therefore, new approaches need to be identified to increase the recycled content. The introduction of the AlMgZn(Cu) Crossover alloy concept may prove to be a step forward in escaping the corset of conventional alloying systems. The 5/7-Crossover alloy not only overcomes the long-standing trade-off between the excellent formability of 5xxx-series alloys and the outstanding strength of 7xxx-series alloys by combining both properties but may also tolerate a higher content of impurity elements. The scope of this study is to properly address the 5/7-Crossover alloy’s sustainability in terms of its ability to be manufactured from secondary raw materials. AlMgZn(Cu) alloys with different tramp element concentrations were investigated.
https://doi.org/10.1007/978-3-031-50308-5_28

Influence of Water Vapor on the Oxidation Behavior of Molten Aluminum Magnesium Alloys - Tichy, Stefan; Doppermann, Simon; Pucher, Philip; Prillhofer, Bernd; Wibner, Stefan; Antrekowitsch, Helmut (2024)
To achieve the goal of climate neutrality in aluminum casthouses, all furnaces currently heated with fossil fuels should be able to be switched to hydrogen burner technologies in the future. This primarily entails a change in the furnace atmosphere. In addition to the elimination of CO2 emissions, increased water vapor contents must inevitably be expected when combusting H2. While the oxidation-inhibiting effect of carbon dioxide on aluminum-magnesium melts is well known and extensively studied, the effects of water vapor on oxidation behavior are still largely unexplored. Depending on the burner setup, H2O contents can range from 17 vol.% (CH4 + Air) to theoretically over 95 vol.% (H2 + O2). In this work, an isolated examination of the influence of H2O on the oxidation behavior of molten AlMg alloys takes place. In addition to gravimetric analyses, an optical investigation of the resulting oxide layers is also carried out. It can be shown that high H2O contents in the furnace atmosphere have a similar oxidation-inhibiting effect compared to CO2.
Keywords: Aluminum; Magnesium; Hydrogen; Atmosphere; Decarbonization; Water vapor

Production of carbon and hydrogen by methane pyrolysis: Assessment of chemical properties of carbon produced via methane pyrolysis in a liquid metal bubble column reactor. - Neuschitzer, David; Scheiblehner, David; Wibner, Stefan; Antrekowitsch, Helmut (SIPS 2023, 2024)
In the context of the growing interest in hydrogen as an energy carrier and reducing agent, numerous industries, including the iron and steel sector, are contemplating an increased adoption of hydrogen. Expanding and developing hydrogen production is imperative to meet the escalating demand in energy-intensive industries. However, the present hydrogen production methods heavily rely on fossil fuels, resulting in a substantial environmental burden, with approximately 10 tons of CO2 emissions per ton of hydrogen generated [1, 2]. To address this challenge, methane pyrolysis has emerged as a promising approach to produce clean hydrogen with reduced CO2 emissions. This process involves the dissociation of methane into hydrogen and solid carbon, leading to a substantial reduction in the carbon dioxide footprint associated with hydrogen production [3, 4]. The Montanuniversitaet Leoben (Austria) is actively researching methane pyrolysis and developing a liquid metal bubble column reactor (LMBCR) specifically dedicated to this purpose. On the one hand, the resulting H2-rich product gas from methane pyrolysis may have potential applications in various processes, such as iron ore reduction. On the other hand, carbon products have stricter requirements in terms of impurities, depending on their intended field of use. Many applications demand shallow threshold values for impurities in the carbon product [5]. Therefore, the main objective of this study is to investigate the chemical properties of carbon produced via methane pyrolysis in an LMBCR concerning impurities and to propose process technological improvements to enhance the overall product quality.

Studies of Layer Growth During the Disintegration of Cemented Carbides with Vaporous Zinc - Luznik, Lea Theres; Gerold, Eva; Weirather, Thomas; Czettl, Christoph; Karhumaa, Teemu; Antrekowitsch, Helmut (TMS 2024, 2024)

Mn-promoted MoS2 catalysts for CO2 hydrogenation - Alves, Gustavo A.S.; Pacholik, Gernot; Pollitt, Stephan; Wagner, Tobias; Rameshan, Raffael; Rameshan, Christoph; Föttinger, Karin (Catalysis science & technology, 2024)
Considering the alarming scenario of climate change, CO2 hydrogenation to methanol is considered a key process for phasing out fossil fuels by means of CO2 utilization. In this context, MoS2 catalysts have recently shown to be promising catalysts for this reaction, especially in the presence of abundant basal-plane sulfur vacancies and due to synergistic mechanisms with other phases. In this work, Mn-promoted MoS2 prepared by a hydrothermal method presents considerable selectivity for CO2 hydrogenation to methanol in comparison with pure MoS2 and other promoters such as K and Co. Interestingly, if CO is used as a carbon source for the reaction, methanol production is remarkably lower, which suggests the absence of a CO intermediate during CO2 hydrogenation to methanol. After optimization of synthesis parameters, a methanol selectivity of 64% is achieved at a CO2 conversion of 2.8% under 180 °C. According to material characterization by X-ray Diffraction and X-ray Absorption, the Mn promoter is present mainly in the form of MnO and MnCO3 phases, with the latter undergoing convertion to MnO upon H2 pretreatment. However, following exposure to reaction conditions, X-ray photoelectron spectroscopy suggests that higher oxidation states of Mn may be present at the surface, suggesting that the improved catalytic activity for CO2 hydrogenation to methanol arises from a synergy between MoS2 and MnOx at the catalyst surface.
Publisher Copyright: © 2024 The Royal Society of Chemistry.

Additive manufacturing of 3D yttria-stabilized zirconia microarchitectures - Winczewski, J.P.; Zeiler, Stefan; Gabel, S.; Maestre, D.; Merle, Benoit; Gardeniers, J.G.E.; Susarrey-Arce, A. (Materials and Design, 2024)
The additive manufacturing (AM) of yttria-stabilized zirconia (YSZ) microarchitectures with sub-micrometer precision via two-photon lithography (TPL), utilizing custom photoresin containing zirconium and yttrium monomers is investigated. YSZ 3D microarchitectures can be formed at low temperatures (600 °C). The low-temperature phase stabilization of ZrO 2 doped with Y 2O 3 demonstrates that doping ZrO 2 with ≈ 10 mol% Y 2O 3 stabilizes the c-ZrO 2 phase. The approach does not utilize YSZ particles as additives. Instead, the crystallization of the YSZ phase is initiated after printing, i.e., during thermal processing in the air at 600 °C – 1200 °C for one and two hours. The YSZ microarchitectures are characterized in detail. This includes understanding the role of defect chemistry, which has been overlooked in TPL-enabled micro-ceramics. Upon UV excitation, defect-related yellowish-green emission is observed from YSZ microarchitectures associated with intrinsic and extrinsic centers, correlated with the charge compensation due to Y 3+ doping. The mechanical properties of the microarchitectures are assessed with manufactured micropillars. Micropillar compression yields the intrinsic mechanical strength of YSZ. The highest strength is observed for micropillars annealed at 600 °C, and this characteristic decreased with an increase in the annealing temperature. The deformation behavior gradually changes from ductile to brittle-like, correlating with the Hall–Petch strengthening mechanism.
Publisher Copyright: © 2024 The Author(s)
Keywords: 3D printing; Additive manufacturing; Micromechanics; Photoluminescence; Yttria-stabilized zirconia

Influence of high-frequency lake level fluctuations on organic matter accumulation in the northern Qaidam Basin, NW China - Hu, Fei; Misch, David; Zhang, Penglin; Meng, Qingtao; Sachsenhofer, Reinhard F.; Xu, Yinbo; Shi, Xiangyun; Liu, Zhaojun; Bechtel, Achim (Journal of Asian earth sciences, 2024)
Publisher Copyright: © 2023 Elsevier Ltd
Keywords: Coal; Lake level fluctuations; Organic geochemistry; Qaidam Basin; Shale; Shimengou formation; Spectral attribute analysis

Numerical modeling of clog fragmentation during SEN clogging in steel continuous casting - Barati, Hadi; Wu, Menghuai; Ilie, Sergiu; Kharicha, Abdellah; Ludwig, Andreas (Powder Technology, 2024)
In the study of clogging during steel continuous casting, less attention was paid to the clog fragmentation, although it always accompanies the clogging process. This paper introduces a sub-model for the clog fragmentation integrated into a comprehensive transient clogging model. In this sub-model, the intricate network of the clog is simplified as a bunch of fictitious cylinders. Each cylinder, called ‘clog finger’, contains a column of spherical non-metallic inclusions (NMIs), which are mechanically bound by sintering at contact points. The mechanical stress acting at the sintering neck between NMIs due to hydraulic forces of the melt flow is evaluated. Simulation of clogging/fragmentation in a real-scale SEN was conducted using the integrated clogging model. Comparing the simulation results with the as-clogged SEN observed in steel plants revealed a qualitative agreement. The effects of different parameters were discussed. The importance of the fragmentation and necessity to have such a sub-model were affirmed.
The authors gratefully acknowledge the funding support of K1-MET GmbH, metallurgical competence center. The research program of the K1-MET competence center is supported by COMET (Competence Cen- ter for Excellent Technologies), the Austrian program for competence centers. COMET is funded by the Federal Ministry for Climate Action, Environment, Energy, Mobility, Innovation, and Technology; the Fed- eral Ministry for Digital and Economic Affairs; the Federal States of Upper Austria, Tyrol, and Styria; and the Styrian Business Promotion Agency (SFG). In addition to the public funding from COMET, this research project was partially financed by scientific partners (Mon- tanuniversit¨at Leoben and Johannes Kepler University Linz) and in- dustrial partners (voestalpine Stahl Linz GmbH, voestalpine Stahl Donawitz GmbH, and RHI Magnesita GmbH). The authors also thank voestalpine Stahl Linz GmbH for providing topography of the as-clogged SEN. Publisher Copyright: © 2023 Elsevier B.V.
Keywords: Clogging; Continuous casting; Non-metallic inclusions; Fragmentation; Detachment

Slurry transport system of the ROBOMINERS prototype - Berner, Michael; Pinkse, Tobias; Riaz, Sadia; Aaltonen, Jussi; Koskinen, Kari (2024)

The Effects of Different Motor Teaching Strategies on Learning a Complex Motor Task - Kunavar, Tjasa; Jamšek, Marko; Avila-Mireles, Edwin Johnatan; Rueckert, Elmar; Peternel, Luka; Babič, Jan (Sensors, 2024)
Publisher Copyright: © 2024 by the authors.
Keywords: human–robot interaction; motor learning; motor teaching; robot tutoring; skill learning; tracking task; visuomotor perturbation

A carbon-stabilized austenitic steel with lower hydrogen embrittlement susceptibility - Khanchandani, Heena; Zeiler, Stefan; Strobel, Lucas; Göken, Mathias; Felfer, Peter (Steel research international, 2024)
High-strength steels are susceptible to H-induced failure, which is typically caused by the presence of diffusible H in the microstructure. The diffusivity of H in austenitic steels with face-centered cubic (fcc) crystal structure is slow. The austenitic steels are hence preferred for applications in the hydrogen-containing atmospheres. However, the fcc structure of austenitic steels is often stabilized by the addition of Ni, Mn, or N, which are relatively expensive alloying elements to use. Austenite can kinetically also be stabilized using C. Herein, an approach is applied to a commercial cold work tool steel, where C is used to fully stabilize the fcc phase. This results in a microstructure consisting of only austenite and M 7C 3 carbide. An exposure to H by cathodic hydrogen charging exhibits no significant influence on the strength and ductility of the C-stabilized austenitic steel. While this material is only a prototype based on an existing alloy of different purposes, it shows the potential for low-cost H-resistant steels based on C-stabilized austenite.
Publisher Copyright: © 2023 The Authors. Steel Research International published by Wiley-VCH GmbH.
Keywords: atom probe tomography; austenite stabilizations; diffusible hydrogen; electron backscatter diffractions; hydrogen embrittlements

Agglomerating behavior of in-situ TiB2 particles and strength-ductility synergetic improvement of in-situ TiB2p/7075Al composites through ultrasound vibration - Wu, Yihong; Li, Linwei; Kang, Huijun; Guo, Enyu; LI, Jiehua; Du, Guohao; Chen, Zongning; Wang, Tongmin (Materials characterization, 2024)
Agglomerates of in-situ particles are the key detrimental defects in particulate reinforced aluminum matrix composites (PRAMCs) by acting as Achilles' heel leading to the premature failure of the materials. Effective methods to disperse/eliminate these agglomerates rely on in-depth understanding of the agglomeration mechanism of the in-situ particles. In this work, the agglomerating behavior of TiB 2 particles in Al-Ti-B system was investigated through the thermit reactions between mixed fluorides and molten aluminum. The results indicate that the morphological patterns of TiB 2 agglomerates are inherited from the preformed Al 3Ti intermedium. The formation of flocculent, shell and flaky TiB 2 agglomerates are the results of the diffusing boron atoms continuously reacting with Al 3Ti. The in-situ Al-TiB 2 was used as a precursor to prepare TiB 2p/7075 Al composites. In particular, ultrasound vibration treatment was applied to explore if a locally forced oscillation can deagglomerate the TiB 2 agglomerates. Microstructural observations strongly support such speculation. Thanks to the deagglomeration and dispersion of TiB 2 particles, both the strength and ductility of the PRAMC have been improved drastically. The fracture surface of the composites was transformed from particle debonding to the dominance of ductile fracture.
Publisher Copyright: © 2024
Keywords: Al Ti; Aluminum matrix composites; Strength-ductility; TiB agglomerates; Ultrasound vibration

Cavitation-induced particle engulfment via enhancing particle-interface interaction in solidification - Zhao, Kai; Li, Xinchen; Liu, Xiangting; Guo, Enyu; Kang, Huijun; Hao, Zhigang; LI, Jiehua; Zhang, Yubo; Chen, Zongning; Wang, Tongmin (Ultrasonics sonochemistry, 2024)
Particle engulfment plays a vital role in the application of particulate reinforced metal matrix composites fabricated by ingot metallurgy. During solidification, particles are nevertheless pushed by an advancing front. As a model system, TiB2p/Al composites were used to investigate the particle engulfment facilitated by acoustic cavitation. The implosion of bubbles drives the particles plunging towards the solid/liquid interface, which increases the engulfment probability. The secondary dendrite arms are refined from 271.2 μm to 98.0 μm as a result of the forced movements of TiB2 particles. Owing to the particle engulfment and dendrite refinement, the composite with ultrasound vibration treatment shows a more rapid work-hardening rate and higher strength.
Publisher Copyright: © 2024 The Authors
Keywords: Metal matrix composites; Particle dispersion; Ultrasonic vibration

Comment on: Evolutionary paths for the formation of different types of fluid inclusions in the H2O-NaCl system by Mao et al. (2023) - Bakker, Ronald Jack (Ore geology reviews, 2024)
Mao et al. (2023) illustrate phase assemblages in a variety of H 2O-NaCl-rich fluid inclusions, and the “evolution” of these assemblages at temperatures below homogenization conditions. A fundamental knowledge of the application, merits and weakness of microthermometry seems to be absent. The authors do not clearly indicate which H 2O-NaCl fluid model is used to calculate the “evolutionary paths”, but the results are identical to the results from the software AqSo_NaCl (Bakker, 2018, 2019). The claimed “first time” presented evolutionary path was already included in AqSo_NaCl, that contain all possible “evolutionary paths”, and offers abundant calculation procedures in the H 2O-NaCl system. The suggested application to recognize or understand post-entrapment modifications does not contribute to our knowledge of re-equilibration processes, and does not offer a comprehensible method. The selected evolutionary paths (isochores) of relatively high-density inclusions must be corrected for host mineral expansivity and compressibility, that result in completely different homogenization temperatures and dissolution temperatures. The presence of abundant errors, deficiencies, and misplaced and omitted references highly reduces the quality of this manuscript.
Publisher Copyright: © 2024 The Author(s)
Keywords: Fluid immiscibility; Fluid inclusion; H O-NaCl; Isochore; Microthermometry; Phase diagram

Development of a Dross Build-Up Growth Process Model for Hot-Dip Galvanizing Considering Surface Reaction Kinetics - Reiss, Georg; Eßl, Werner; Trasca, Raluca Andreea; Mugrauer, Claudia; Stefan-Kharicha, Mihaela; Kharicha, Abdellah; Gerold, Eva; Goodwin, Frank (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)
The minimization of unwanted dross build-up formation on the sink rolls in continuous hot-dipgalvanizing lines is a key goal of the industry. In this study, the CFD multi-physics modeling ofthe surface reaction kinetics for dross build-up growth and the coupling to the mass transfer isthe basis for the evaluation of relevant process parameters. The results of a virtual Design ofExperiments were processed by neural network approaches, as well as linear regressionmodeling to build a surrogate process model. It was found that the bath Al concentration hasthe highest effect (> 80 pct) on the dross build-up rate on the sink rolls. Operating the zinc bathat higher Al concentrations decreases the dross build-up reaction rate. Furthermore, it wasfound by the CFD multi-physics model that the local dross build-up rate increases toward theedges of the roll grooves which might lead to the occurrence of strip surface defects.
Publisher Copyright: © 2023, The Minerals, Metals & Materials Society and ASM International.
Keywords: Dross Build-Up; Grwoth Process Model; Hot-Dip Galvanizing

Digital Transformation in Tunneling - Bednar, Thomas; Galler, Robert; Huemer, Christian; Huymajer, Marco; Stefan, Klikovits; Melnyk, Oleksandr; Paskaleva, Galina; Steiner, Bernhard; Wenighofer, Robert; Wimmer, Manuel (Zeitschrift für Hochschulentwicklung : ZFHE, 2024)
The digital transformation has significantly affected many industries. Recently, it has gained momentum in the Architecture, Engineering, and Construction (AEC) sector in general and tunneling in particular. To support these developments, TransIT represents an inter-university and interdisciplinary research initiative with the goal of advancing digitalization in tunneling. This article discusses the challenges connected with the digital transformation of the tunneling sector. We examine this topic with different use cases demonstrating solutions to those challenges.
Keywords: Tunneling; Digitalization; Digital transformation

Engineering surface dipoles on mixed conducting oxides with ultra-thin oxide decoration layers - Siebenhofer, Matthäus; Nenning, Andreas; Rameshan, Christoph; Blaha, Peter; Fleig, Jürgen; Kubicek, Markus (Nature Communications, 2024)
Publisher Copyright: © The Author(s) 2024.

Estimating the compressive strength of plastic concrete samples using machine learning algorithms - Alishvandi, Ali; Karimi, Javad; Damari, Siavash; Far, Arsham Moayedi; Pour, Mohammad Setodeh; Ahmadi, Morteza (Asian journal of civil engineering, 2024)
Publisher Copyright: © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Compressive strength; Machine learning algorithm; Plastic concrete; Regression

Evaluation of Mixing Effects and Particle Breakage on a Cross Flow Turbine with DEM - Denzel, Michael; Prenner, Michael; Sifferlinger, Nikolaus August (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Various effects during conveying and storage processes lead to size segregation of bulk material, but many applications require a mostly constant particle size distribution. Especially during bunker filling, segregation effects are noticed, which are further intensified by possible core flow effects. In order to reduce segregation effects during bunker filling, a cross flow turbine is installed at a bunker used for storage of blast furnace sinter. In this contribution, discrete element simulations were performed to analyze mixing effects and possible particle breakage due to the cross flow turbine. Significant mixing effects during bunker filling are noticed due to the cross flow turbine. The results show a more evenly distributed bunker outflow in terms of particle size.Particle breakage is analyzed by means of a newly developed breakage model for the Discrete Element Method (DEM). The model is based on a probabilistic particle replacement with voronoi-tessellated fragments. The validated breakage model allows high accuracy in prediction of fragment size distribution. Fragments are further breakable, which allows simulation of processes with several damaging effects. The breakage model was calibrated with a specially developed automated single particle impact tester for rapid analysis of breakage characteristics of bulk materials.
Keywords: Size segregation; Particle size distribution; Mixing equipment; Blending equipment; Discrete element method; Bunker filling; Bulk storage; Blast furnace sinter

Fracture toughness of Ca-, Sr-, and Ba-aluminoborosilicate glasses - Fry, Aubrey L.; Krug, Christian; Ladinger, Lukas; Lube, Tanja; Kim, Seong H.; Mauro, John C. (Journal of the American Ceramic Society, 2024)
Publisher Copyright: © 2023 The Authors. Journal of the American Ceramic Society published by Wiley Periodicals LLC on behalf of American Ceramic Society.
Keywords: aluminoborosilicate; brittleness; field strength; fracture toughness; glass; plasticity

High-capacity CO/CO2 methanation reactor design strategy based on 1D PFR modelling and experimental investigation - Krammer, Andreas; Salbrechter, Katrin; Lehner, Markus (Journal of CO2 utilization, 2024)
An in-depth analysis of oil-cooled and naturally ambient air-cooled fixed bed reactors for catalytic methanation of a feedgas containing CO and CO2 has been performed. Combined investigation of modelling and experiments showed, that small tube-to-pellet diameters ratios and optimized reactor cooling are beneficial for high-capacity CO/CO2 methanation. Very good model accuracy was proven with a 1D approach for small diameter reactor pipes. It is shown that the reactor design sweet spot under consideration of input gas capacity, methane output concentration, catalyst degradation and pressure loss can be assessed by the experimentally validated reactor model. The study reveals insights to the mechanism of combined CO and CO2 methanation showing that initial CO methanation is kinetically limited, while subsequent CO2 methanation is ruled by the kinetics of the reverse water gas shift reaction. Finally, this works aim is to provide a design strategy for effective and cheap high-capacity CO/CO2 methanation reactors for industrial scale using commercial pellet catalysts in oil-cooled tube-bundle-reactors.
Publisher Copyright: © 2024 The Authors
Keywords: Plug flow model; CO/CO methanation; Co-SOEC syngas methanation; Reactor design; Tube-bundle reactor

Methodenentwicklung zur digitalen Abfallanalytik für nicht gefährliche gemischte Gewerbeabfälle - Kandlbauer, Lisa; Sarc, Renato (2024)

Methodenentwicklung zur digitalen Abfallanalytik für nicht gefährliche gemischte Gewerbeabfälle - Kandlbauer, Lisa (2024)

Multiscale in-situ observations of the micro- and nanostructure of a PH 13-8 Mo maraging steel during austenitization - Rosenauer, Andreas; Brandl, Dominik; Ressel, Gerald; Hönigmann, Thomas; Stadler, Manfred; Turk, Christoph; Gammer, Christoph; Wiessner, Manfred; Gamsjäger, Ernst; Stockinger, Martin; Schnitzer, Ronald (Materials characterization, 2024)
The aim of the present work is to elaborate on the microstructural evolution of a PH 13-8 Mo maraging steel during austenitization by using multiscale in-situ techniques, which range from high-temperature electron backscatter diffraction and high-energy X-ray diffraction to high-temperature transmission electron microscopy. In order to supplement these in-situ experiments, samples quenched from different temperatures after isochronal heating are subjected to an in-depth microstructural characterization by means of atom probe tomography. The results indicate diffusion-dominated kinetics for the α’ to γ transformation in the investigated heating rate range. Moreover, high-temperature electron backscatter diffraction experiments confirm the occurrence of the austenite memory effect. In addition to the inheritance of grain size and crystallographic orientation of the prior austenite grains, a lath-like substructure remains in austenite, which consists of thermally stable, geometrically necessary dislocations. It is suggested that these dislocations play the key role for enabling recrystallization at higher temperatures without prior cold deformation. This phenomenon is evidenced for the first time in a PH 13-8 Mo maraging steel. However, it is believed that excessive amounts of carbides at austenite grain boundaries or an alteration of the dislocation structure could impede this abnormal recrystallization.
Publisher Copyright: © 2023 The Authors
Keywords: In-situ electron backscatter diffraction; In-situ high-energy X-ray diffraction; In-situ transmission electron microscopy; Maraging steel; Phase transformation; Recrystallization

Optimizing synthetic core plugs - Khoramian, Reza; Pourafshary, Peyman; Golshokooh, Saeed; Kharrat, Riyaz (Geoenergy science and engineering, 2024)
Keywords: Synthetic cores; Sintering; Sand-glass beads; Porosity-permeability; Core strength; Pore size distribution

Optimizing synthetic core plugs: Sintered glass beads and sand particles for natural rock property replication in fluid flow and reservoir studies - Khoramian, Reza; Pourafshary, Peyman; Golshokooh, Saeed; Kharrat, Riyaz (2024)
Developing reliable synthetic cores that accurately mimic natural rock properties is crucial forstudying fluid flow and reservoir processes. This paper presents a novel study for fabricatingsynthetic core samples by fusing glass beads and sand particles within cylindrical molds. Varioussynthetic core production and characterization factors were explored, including material selection,fabrication parameter optimization, pore size distribution, and capillary behavior analysis.Ceramic tubes were ideal for core fabrication due to their high-temperature tolerance, durability,and reusability. Quartz glass beads were preferred for their transparency and enhanced heatstability. Varying the size and shape of the glass beads influenced porosity, with round particleshaving lower porosity and angular particles showing higher porosity. The packing procedure andfurnace type affected porosity and permeability, with tightly packed arrangements resulting inlower values. Optimal sintering conditions were identified at 680°C for 15 minutes, resulting inhigh porosity and permeability. Incorporating sand particles at a 1:6 sand-to-glass-bead ratioenhanced core stability under challenging conditions (740°C), achieving high-pressure resistance(≈15,000 psi) and tighter cores with lower porosity (≈11%) and permeability (≈5 mD) comparedto cores made solely of glass beads, which had lower pressure resistance (≈2,300 psi) and higherporosity (≈31%) and permeability (≈3,190 mD). Synthetic cores demonstrated exceptionalstability under fluid flow conditions, with minimal property changes (≈<1%) and wettabilityalterations comparable to natural cores. The capillary pressure study confirmed the similarity ofsynthetic cores to real cores, revealing variations in pore sizes and residual mercury saturations.Overall, this innovative study highlights the potential of sintered glass beads for producing bettersynthetic core plugs. Including sand particles at elevated temperatures and extended retentiontimes enables the production of tighter synthetic core plugs. The findings confirm the essential roleof sintered glass beads in replicating natural rock properties and studying fluid flow at reservoirconditions.
Keywords: Synthetic cores; sintering; sand-glass beads; porosity-permeability; core strength; pore size distribution

Redox cationic frontal polymerization - Malik, Muhammad Salman; Wolfahrt, Markus; Pinter, Gerald; Schlögl, Sandra (Monatshefte fur Chemie, 2024)
Publisher Copyright: © The Author(s) 2024.
Keywords: Cations; Composites; Epoxy; Frontal polymerization; Radicals; Redox reactions

Salinity-Driven Structural and Viscosity Modulation of Confined Polar Oil Phases by Carbonated Brine Films: Novel Insights from Molecular Dynamics - Mirzaalian Dastjerdi, Ali; Kharrat, Riyaz; Ott, Holger; Niasar, Vahid (Journal of physical chemistry (B, Condensed matter, materials, surfaces, interfaces, & biophysical chemistry), 2024)
The structural and dynamic properties of fluids under confinement in a porous medium differ from their bulk properties. This study delves into the surface structuring and hydrodynamic characteristics of oil/thin film carbonated brine two-phase within a calcite channel upon salinity variation. To this end, both equilibrium and non-equilibrium molecular dynamics simulations are utilized to unveil the effect of the carboxylic acid component (benzoic acid) in a simple model oil (decane) confined between two thin films of carbonated brine on the oil–brine–calcite characteristics. The salinity effect was scrutinized under four saline carbonated waters, deionized carbonated water (DCW), carbonated low-salinity brine (CLSB, 30,000 ppm), carbonated seawater (CSW, 60,000 ppm), and carbonated high-salinity brine (CHSB, 180,000 ppm). An electrical double layer (EDL) is observed at varying salinities, comprising a Stern-like positive layer (formed by Na+ ions) followed by a negative one (formed by Cl– ions primarily residing on top of the adsorbed sodium cations). By lowering the salinity, the Na+ ions cover the interface regions (brine–calcite and brine–oil), depleting within the brine bulk region. The lowest positive surface charge on the rock surface was found in salinity corresponding to seawater. Two distinct Na+ peaks at the oleic phase interface have been observed in the carbonated high-salinity brine system, enhancing the adsorption of polar molecules at the thin brine film interfaces. There is a pronounced EDL formation at the oleic phase interface in the case of CSW, resulting in a strong interface region containing ions and functional fractions. Likewise, the oil region confined by CSW exhibited the lowest apparent viscosity, attributed to the optimized salinity distribution and inclination of benzoic acid fractions uniformly at the brine–oil interface, acting as a slippery surface. Moreover, the results reveal that the presence of polar fractions could increase the oil phase’s apparent viscosity, and introducing ions to this system reduces the polar molecules’ destructive effect on the apparent viscosity of the oil region. Therefore, the fluidity of confined systems is modulated by both composition of the brine and oil phases.
Keywords: Calcite; Ions; Lipids; Molecule

Thermal volume expansion as seen by Temperature-modulated optical refractometry, Oscillating dilatometry and Thermo-mechanical analysis - Klingler, Andreas; Gilberg, Maurice; Reisinger, David; Schlögl, Sandra; Wetzel, Bernd; Krüger, Jan Kristian (Polymer Testing, 2024)
Publisher Copyright: © 2024 The Authors
Keywords: Dilatometry; Epoxy thermoset; Temperature-modulated optical refractometry; Thermal volume expansion; Thermo-mechanical analysis

Numerical and experimental assessment of liquid metal embrittlement in externally loaded spot welds - Prabitz, Konstantin Manuel; Antretter, Thomas; Rethmeier, Michael; El-Sari, Bassel; Schubert, Holger; Hilpert, Benjamin; Gruber, Martin; Sierlinger, Robert; Ecker, Werner (Welding in the world, 2024)
Zinc-based surface coatings are widely applied with high-strength steels in automotive industry. Some of these base materials show an increased brittle cracking risk during loading. It is necessary to examine electrogalvanized and uncoated samples of a high strength steel susceptible to liquid metal embrittlement during spot welding with applied external load. Therefore, a newly developed tensile test method with a simultaneously applied spot weld is conducted. A fully coupled 3D electrical, thermal, metallurgical and mechanical finite element model depicting the resistant spot welding process combined with the tensile test conducted is mandatory to correct geometric influences of the sample geometry and provides insights into the sample’s time dependent local loading. With increasing external loads, the morphology of the brittle cracks formed is affected more than the crack depth. The validated finite element model applies newly developed damage indicators to predict and explain the liquid metal embrittlement cracking onset and development as well as even ductile failure.
Publisher Copyright: © 2024, The Author(s).
Keywords: Advanced high-strength steel; Damage prediction; Finite element simulation; Liquid metal embrittlement; Resistance spot welding; Tensile resistance spot welding experiment

Complexity in Action: Inter- and Transdisciplinarity in EURECA-PRO - Gritzner, Karoline; Kollnig, Sarah (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Integrated approaches to research set a common goal, which, in the case of the EURECA-PRO programme, is to work towards realising Sustainable Development Goal (SDG) 12, Responsible Consumption and Production (RCP). However, the diversity of perspectives, expectations, and work methods within all types of cross-disciplinary work can be challenging. Based on the work of the RE-EURECA-PRO project, which develops the research and innovation agenda of EURECA-PRO, this contribution provides an insight into the complexity, challenges, and opportunities of interdisciplinary research collaboration and transdisciplinary actions.

Mitverbrennung von Abfällen mit geringem Schadstoffpotenzial in der Zementindustrie - Lorber, Karl; Sarc, Renato; Pomberger, Roland (2024)

Report on an open dataset to constrain the Balmuccia peridotite body (Ivrea-Verbano Zone, Italy) through a participative gravity-modelling challenge - Hetényi, György; Baron, Ludovic; Scarponi, Matteo; Subedi, Shiba; Michailos, Konstantinos; Dal, Fergus; Gerle, Anna; Petri, Benoit; Zwahlen, Jodok; Langone, Antonio; Greenwood, Andrew; Ziberna, Luca; et al. (Swiss journal of geosciences, 2024)
The Balmuccia peridotite exposes relatively fresh mantle rocks at the Earth’s surface, and as such it is of interest for geologists and geophysicists. The outcrop is a kilometre-scale feature, yet its extent at depth is insufficiently imaged. Our aim is to provide new constraints on the shape of the density anomaly this body represents, through 3D gravity modelling. In an effort to avoid personal or methodology bias, we hereby launch an invitation and call for participative modelling. We openly provide all the necessary input data: pre-processed gravity data, geological map, in situ rock densities, and digital elevation model. The expected inversion results will be compared and jointly analysed with all participants. This approach should allow us to conclude on the shape of the Balmuccia peridotite body and the associated uncertainty. This crowd effort will contribute to the site surveys preparing a scientific borehole in the area in frame of project DIVE.
Keywords: Gravimetry; Gravimetry anomaly; Modelling; Open science; Alps; Balmuccia peridotite

Multimodal Visual-Tactile Representation Learning through Self-Supervised Contrastive Pre-Training - Dave, Vedant; Lygerakis, Fotios; Rückert, Elmar (Proceedings / IEEE International Conference on Robotics and Automation, 2024)

Achievements of the European University on Responsible Consumption and Production - Kircher, Volkmar (Berg- und hüttenmännische Monatshefte : BHM, 2024)
The editorial introduces the European University on Responsible Consumption and Production - EURECA-PRO and explains some of the important achievements of the alliance since its foundation. In particular, the ambitions in terms of joint study programmes and educational activities, joint interdisciplinary research collaboration, Third Mission, Science Communication and interaction with society are discussed. These areas reflect the subject areas of this issue and thus introduce it.
Keywords: European University; EURECA-PRO; Verantwortungsvoller Konsum; Verantwortungsvolle Produktion; SDG 12; SDG 4; Interdisziplinäre Forschung; Wissenschaftskommunikation; European University; EURECA-PRO; Responsible consumption and production; SDG 12; SDG 4; interdisciplinary research; Science Communication

LIDAR sensors and methods for LIDAR sensors - Thurner, Thomas; Brunner, David; Hennecke, Marcus; Schitter, Georg; Yoo, Han Woong (2024)
A light detection and ranging (LIDAR) sensor includes a first reflective surface configured to oscillate about a first rotation axis to deflect a light beam into an environment; and a second reflective surface configured to oscillate about a second rotation axis to guide light received from the environment onto a photodetector of the LIDAR sensor. The first rotation axis and the second rotation axis extend parallel to one another. The LIDAR sensor also includes a control circuit configured to drive the first reflective surface to oscillate with a first maximum deflection angle about the first rotation axis, and to drive the second reflective surface to oscillate with a second maximum deflection angle about the second rotation axis, the first maximum deflection angle being greater than the second maximum deflection angle, and an area of the first reflective surface is less than an area of the second reflective surface.

In situ and ex situ quantification of nanoparticle fluxes in magnetron sputter inert gas condensation - Knabl, Florian; Bandl, Christine; Griesser, Thomas; Mitterer, Christian (Journal of vacuum science & technology / A (JVST), 2024)
Magnetron sputter inert gas condensation was coupled with quadrupole mass spectrometry for the in situ characterization of a nanoparticle beam. The proposed method allows us to determine the size distribution and the mass flux of the nanoparticles. The measured quadrupole mass spectrometer grid current is converted into a nanoparticle flux and subsequently into a mass flux. Cu nanoparticles were deposited onto Si substrates using different filtering modes of the quadrupole mass spectrometer. Characterization was carried out using a combination of x-ray photoelectron spectroscopy and scanning electron microscopy. Quantitative analysis of the elemental composition of the Si surface revealed a Gaussian distribution of the deposited nanoparticles over the diameter of the rotating substrate holder with a good quantitative agreement with the predictions made from the in situ quantification method.
Publisher Copyright: © 2024 Author(s).

Cost-Driven Assessment of Technologies’ Potential to Reach Climate Neutrality in Energy-Intensive Industries - Nagovnak, Peter; Mobarakeh, Maedeh Rahnama; Diendorfer, Christian; Thenius, Gregor; Böhm, Hans; Kienberger, Thomas (Energies, 2024)

The Conversation is the Command: Interacting with Real-World Autonomous Robot Through Natural Language - Nwankwo, Linus; Rückert, Elmar (Association for Computing Machinery (ACM), 2024)

Investigating the Origin of Non-Metallic Inclusions in Ti-Stabilized ULC Steels Using Different Tracing Techniques - Thiele, Kathrin; Truschner, Christoph; Walkner, Christoph; Meisel, Thomas C.; Ilie, Sergiu; Rössler, Roman; Michelic, Susanne Katharina (Metals : open access journal, 2024)
Since steel cleanness comes to the fore of steel producers worldwide, it is necessary to understand the formation mechanism and modification of non-metallic inclusions (NMIs) in more detail. One central point is the identification of the source of especially interfering NMIs to prevent their evolution in the future. The present study applies two approaches to determine the source of NMIs in Ti-stabilized ultra-low carbon (ULC) steels—the active and the passive tracing. Both approaches are applied to an industrial experiment. The active tracing technique is focused on investigating the clogging layer formation in submerged entry nozzles and, hence, the origin of alumina particles. This method adds rare earth elements (REEs) directly to the melt to mark pre-existing deoxidation products at a certain point of the steelmaking process. The main concern of the passive method, the so-called REE fingerprint, is the determination of the source of mesoscopic NMIs. For the REE fingerprint, the pre-existing concentration of REEs in different potential sources and the investigated NMIs are measured by using an inductively coupled plasma mass spectrometer (ICP-MS). The resulting patterns are compared after normalizing the contents to chondrites, and the NMIs’ origins are identified. Concerning the EDS analysis and the resulting patterns from the REE fingerprint, the mold slag and, respectively, the casting powder were the sources of the investigated NMIs.
Publisher Copyright: © 2024 by the authors.
Keywords: Non-metallic inclusions; tracing techniques; rare earth elements; rare earth element fingerprint; non-metallic inclusions; rare earth element fingerprint; rare earth elements; tracing techniques

Influence of Anion and Cation Structures on Ionic Liquid Epoxy-Based Vitrimers - Wanghofer, Florian; Trausner, Carina; Reisinger, David; Wolfahrt, Markus; Schlögl, Sandra (ACS applied polymer materials, 2024)
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.
Keywords: anhydride; epoxy; ionic liquid; self-healing; transesterification; vitrimer

Short-Time Magnetron Sputtering for the Development of Carbon–Palladium Nanocomposites - Knabl, Florian; Kostoglou, Nikolaos; Terziyska, Velislava; Hinder, Steven J.; Baker, Mark; Bousser, Etienne; Rebholz, Claus; Mitterer, Christian (Nanomaterials, 2024)
In recent nanomaterials research, combining nanoporous carbons with metallic nanoparticles, like palladium (Pd), has emerged as a focus due to their potential in energy, environmental and biomedical fields. This study presents a novel approach for synthesizing Pd-decorated carbons using magnetron sputter deposition. This method allows for the functionalization of nanoporous carbon surfaces with Pd nano-sized islands, creating metal–carbon nanocomposites through brief deposition times of up to 15 s. The present research utilized direct current magnetron sputtering to deposit Pd islands on a flexible activated carbon cloth substrate. The surface chemistry, microstructure, morphology and pore structure were analyzed using a variety of material characterization techniques, including X-ray photoelectron spectroscopy, X-ray diffraction, Raman spectroscopy, gas sorption analysis and scanning electron microscopy. The results showed Pd islands of varying sizes distributed across the cloth’s carbon fibers, achieving high-purity surface modifications without the use of chemicals. The synthesis method preserves the nanoporous structure of the carbon cloth substrate while adding functional Pd islands, which could be potentially useful in emerging fields like hydrogen storage, fuel cells and biosensors. This approach demonstrates the possibility of creating high-quality metal–carbon composites using a simple, clean and economical method, expanding the possibilities for future nanomaterial-based applications.
Publisher Copyright: © 2024 by the authors.
Keywords: activated carbon cloth; magnetron sputtering; metal–carbon composites; palladium; physical vapor deposition; surface functionalization

The reduction of stress concentrations in adhesive joints with the use of curved aluminum adherends - Pires, Vasco D. C.; Ribeiro, Francisco C. C.; Carbas, Ricardo; Marques, Eduardo A. S.; Silva, Lucas F. M. da (Mechanics of advanced materials and structures, 2024)

A Comparison of 90° Bending for Foldable Electronics - Cordill, Megan J.; Kreiml, Patrice; Köstenbauer, Harald; Mitterer, Christian (Coatings, 2024)
In order to assess the longevity of foldable electronics, folding or bending tests on model systems need to be performed. However, not all bending tests are created equal in that different configurations lead to different amounts of mechanical damage and thus different electrical responses. Two 90° bending instruments were compared using two model metallic thin film systems on polyimide to establish if the two seemingly similar bending tests yield the same results. The two film systems, namely 300 nm Mo and 130 nm Al on 50 nm Mo, were magnetron-sputtered on polyimide substrates and tested in the custom-built FLEX-E-TEST and the commercially available YUASA test that is capable of in situ resistance measurements. For statistics, 10–12 samples were tested of each film system on each folding device using the same applied bending strain and number of cycles. Samples were intermittently characterized with confocal laser scanning microscopy and electrical resistance to correlate the amount of mechanical damage (crack density) with the electrical normalized resistance ratio of the damaged area. The results show that even with the same bending radius, a similar but not identical amount of mechanical damage forms for both bending devices. Additionally, the resistance as a function of cycles also differs after 10,000 cycles. A closer examination of the damage, especially in the Al/Mo film system, indicates that the speed of the bending, and if the samples experience spring back, can alter the received mechanical damage. The in situ resistance data of the YUASA test were further examined and a suggestion of standardizing how folding or bending test results are reported is provided.
Publisher Copyright: © 2024 by the authors.
Keywords: bending; cycles; folding; lifetime; thin films

Operando probing of the surface chemistry during the Haber–Bosch process - Goodwin, Christopher M.; Lömker, Patrick; Degerman, David; Davies, Bernadette; Shipilin, Mikhail; Garcia-Martinez, Fernando; Koroidov, Sergey; Mathiesen, Jette Katja; Rameshan, Raffael; Rodrigues, Gabriel L.S.; Schlueter, Christoph; Amann, Peter; et al. (Nature, 2024)

Simulation techniques and 3D modeling of TBM tunneling in soft and shallow grounds: A case study of Tehran metro line 6 - Tarafrava, Mostafa; Khan, Arif; Shokri, Sahand; Shokati Beyrag, Behzad; Emadi, Amin; Far, Arsham Moayedi; Hajivand Dastgerdi, Rashid (Engineering and applied science research, 2024)
In modern urbanized areas, the increasing demand for underground structures has led to an increase in the number of tunnelling projects in soft and shallow grounds. Tunneling in such conditions poses significant challenges, primarily due to the ground's low shear capacity and high deformation potential, leading to tunnel face instability and surface settlement. Accurate calculation of surface settlement is crucial in order to prevent probable damage to nearby structures. Consequently, various field measurement techniques and analytical solutions have been developed to estimate the maximum surface settlement resulting from tunneling activities in urban areas. These methods provide valuable insights to mitigate the risks associated with excessive settlement, ensuring the integrity and safety of surrounding infrastructure. Therefore, this study employs the numerical approach to gain a comprehensive understanding on surface settlement and the tunneling operation with tunnel boring machines. The analysis considers various performance parameters, including applying pressure around the shield, grout pressure, face pressure, parameters of machine advancement, and shield conicity. The aim of this research is to compare the results obtained from the numerical model with those obtained from precision instruments. Firstly, a comprehensive background on the importance of the considered subject is outlined, and the procedure of numerical modeling is elaborated in detail which is followed by outputs, comparisons, discussion and conclusions. The findings of this study demonstrate that the difference between surface settlement obtained from the results of instrumentation and numerical modeling for the eight investigated sections was an average of 11%, which was deemed negligible. These results highlight the potential of three-dimensional modeling and simulation techniques to support accurate estimation of surface settlement in tunneling operations, thereby minimizing potential damage to the surrounding structures. The reliable assumptions and simulation techniques used in this research can be useful for future tunneling projects to reduce the construction costs.
Publisher Copyright: © 2024, Paulus Editora. All rights reserved.
Keywords: Numerical modeling; Soft grounds; Surface settlement; Tunneling

A Chemo-Mechanically Coupled Model for the Prediction of Phase Segregation and Pore Formation in Microelectronic Solders - Antretter, Thomas (28th International Conference on Plasticity, Damage and Fracture, 2024)
Keywords: Chemo-Mechanically Coupled Model; Prediction of Phase Segregation; Pore Formation; Microelectronic Solders

Dual-vat photopolymerization 3D printing of vitrimers - Shaukat, Usman; Thalhamer, Andreas; Rossegger, Elisabeth; Schlögl, Sandra (Additive Manufacturing, 2024)
Publisher Copyright: © 2023 Elsevier B.V.
Keywords: Dual-vat photopolymerization 3D printing; Multi-material; Photopolymers; Soft active devices; Vitrimers

Effects of polar fractions on interfacial and bulk properties at the oil/carbonated aqueous solution interface: Insight from molecular dynamics simulation - Mirzaalian Dastjerdi, Ali; Kharrat, Riyaz; Niasar, Vahid; Ott, Holger (Colloids and surfaces A: Physicochemical and Engineering Aspects, 2024)
This study utilized molecular dynamics simulations to understand the liquid/liquid interfaces in a natural environment involving carbon dioxide and various acidic components. The aim is to unravel the impact of polar fractions with various chemical structures and functional groups, namely benzoic acid, decanoic acid, phenol, and decanol, on the interfacial phenomena of the oleic phase (decane) in contact with water or CO 2-rich water at the molecular resolution. The findings indicate that carbon dioxide molecules enrich at the decane/water interface before dissolving into the oleic phase. When polar molecules are introduced to the oleic phase, there is a competition between carbon dioxide and acidic components to accumulate at the interface. The functional hydrocarbon fractions displace carbon dioxide at the interface and bridge the oleic and aqueous phases, reducing interfacial tension. Polar components change the charge distribution of water molecules in the biphasic system, signifying that the organized water layer at the interface with the non-aqueous phase has been disrupted. In contrast to the polar molecules, the carbon dioxide tends to diffuse into the oleic phase and changes the bulk properties like oil fluidity. Accordingly, the fluidity of the decane exhibited significant enhancement by CO 2 diffusion throughout the bulk oil phase, which might lead to substantial viscosity reduction.
Publisher Copyright: © 2023

The simple microsegregation model for steel considering MnS formation in the liquid and solid phases - You, Dali; Bernhard, Christian; Bernhard, Michael Christian; Michelic, Susanne Katharina (Journal of Materials Research and Technology, 2024)
A simple microsegregation model for steel considering MnS formation in the liquid and solid phases is proposed. The concentration of the solutes during the solidification is calculated using the discretized Scheil-Gulliver model for steel (SGS). In the calculation, the planar dendrite is divided into a finite number (n) of elements to record the local solid concentrations and calculate the mass fraction of MnS precipitation during further cooling. The solidification part of the model is validated by measured solidification temperatures and the MnS formation amount predicted by the FactSage thermochemical software. The model was applied to valuate the hightemperature ductility of the selected steel. The optimum Mn content of the assumed steel was obtained based on the simulation.

Electrified/charged aqueous interfaces - Advincula, Xavier R.; Backus, Ellen H. G.; Bonn, Mischa; Cox, Stephen J.; Diebold, Ulrike; Fellows, Alexander; Finney, Aaron R.; Goel, Gaurav; Hedley, Jonathan; Jiang, Ying; Jin, Di; Kapil, Venkat; et al. (Faraday Discussions, 2024)

Tunnelausbruchverwertung: Nachhaltigkeit beim Bau des FCC des CERN - Hauzinger, Elisabeth; Galler, Robert; Schneider, Daniel (Stein & Kies (Mitgliederzeitung - Forum mineralische Rohstoffe), 2024)
Keywords: tunnel excavation utilization; sustainability

AI assisted steel cleanness evaluation: Predicting the morphology of La-traced non-metallic inclusions using backscattered-electron images - Thiele, Kathrin; Musi, Robert; Prohaska, Thomas; Irrgeher, Johanna; Michelic, Susanne Katharina (Journal of Materials Research and Technology, 2024)
This study shows how computer vision, a field of artificial intelligence (AI), can be used to gain access to morphological information for a better process understanding and furthermore, how it can be implemented in the evaluation of active tracing experiments. Non-metallic inclusions (NMIs) play a crucial role in determining the chemical and physical properties of the final steel product. The active tracing technique allows for tracking the formation and modification mechanisms of detrimental NMIs throughout the steelmaking process by adding rare earth elements (REEs) to the melt. The interaction of REEs with NMIs results in the formation of traced multiphase particles and, therefore, lead to challenges for accurate evaluation by automated scanning electron microscopy with energy-dispersive spectroscopy (SEM/EDS). However, obtaining information about the REE distribution in traced NMIs without extensive, time-consuming human effort is not feasible using the existing method. A two-step classification process with AI was established, which included training and testing of two random forest classifiers (RFC). The first RFC achieved for the binary NMI/non-NMI classification an accuracy of 94.8 %. Four different morphology-based classes were considered in the second classification, whereas traced homogeneous NMIs and NMIs with a high La content got classified with a precision exceeding 90 %. However, caution is required in interpreting results for traced heterogeneous NMIs, as they have a higher prediction error of 37.2 %.
Publisher Copyright: © 2023 The Authors

IFC concepts in the execution phase of conventional tunneling projects - Huymajer, Marco; Peskalova, Galina; Wenighofer, Robert; Huemer, Christian; Mazak-Huemer, Alexandra (Tunnelling and Underground Space Technology, 2024)
The documentation process of conventional tunneling projects is time-consuming and costly. Building Information Modeling (BIM) has enabled substantial productivity gains in the Architecture, Engineering, & Construction (AEC) sector. However, BIM has only been marginally adopted in the execution phase of conventional tunneling projects. For this purpose, we propose a BIM model that facilitates fully digital and automated data exchange between project stakeholders. We use the Industry Foundation Classes (IFC) as a basis and identify concepts potentially useful to represent data from the execution phase of construction projects. We demonstrate how IFC concepts are utilized to represent a shift report of a conventional tunneling project. Thereby, we deliver a reference model as an implementation guide for software developers in this domain. This may serve as a blueprint for handling construction management data in a machine-readable format, laying the foundations for Big Open BIM in the execution phase of construction projects.
Publisher Copyright: © 2023 The Author(s)
Keywords: Building Information Modeling; Tunneling; Industry Foundation Classes

The contribution of ceramography to the development of ceramic spark plug electrode materials for large gas engines ergab keine Übereinstimmung mit Publikationen - Gruber, Manuel; Melcher, Verena; Harrer, Walter Stefan; Tilz, Anton; Engelmayer, M.; Fimml, Wolfgang; Wimmer, A.; Bermejo, Raul (Practical Metallography, 2024)
Publisher Copyright: © 2024 Walter de Gruyter GmbH, Berlin/Boston, Germany.
Keywords: Ceramic spark plug electrodes; ceramography; erosion; metal/ceramic joining; oxidation

3D Seismic Tomography of DT-1B Drill Site - Spriggs, Lucas Crozier Sutek (2024)
Travel time tomography has been utilized to delineate the boundary between crystalline metamorphic lower crustal rocks and quaternary sediments of a site. The area investigated is approximately 50x50m within the Ivrea Verbano Zone (IVZ). The IVZ is a region of significant geological interest due to deep crustal segments that have been uplifted to shallow depths. DIVE (Drilling the Ivrea-Verbano zonE) is an international scientific collaboration, funded by the ICDP, which aims to unravel fundamental inquiries of the IVZ. This is done through drilling 3 drill-holes, one of which is DT-1B located in Ornavasso Italy. In order to characterize the DT-1B drill site, geophysical investigations were conducted prior to the start of drilling activities including Ground Penetrating Radar (GPR), Electrical Resistivity Tomography (ERT), and active-source seismic surveys. The seismic data was acquired as a tightly spaced 3-D rolling spread with the source lines offset from the geophone lines. This source-receiver geometry is not optimal for 2-D seismic refraction profiling and a 3-D refraction travel-time tomography scheme was subsequently used to derive a subset of 2.5-D profiles that span the drilling site. An Eikonal solver was used to generate velocity models and produce theoretical travel-time curves. The starting velocity model utilized velocities derived from first-break analysis and subsurface geometry assumed from the ERT and GPR data results. An RMS error of 4.97ms between the observed and calculated travel-times is achieved after 12 iterations. The final velocity models compare well with the ERT and GPR profiles and the 3D-velocity cube serves as a good starting model for improved seismic reflection imaging.
no embargo
Keywords: Bohrungen in der Ivrea-Verbano-Zone; Laufzeittomographie; Seismik aktiver Quellen; Geophysikalische Standortcharakterisierung; Drilling the Ivrea-Verbano zonE; Travel-time Tomography; Active-Source Seismics; Geophysical Site Characterization

3D-printed alumina-based ceramics with spatially resolved porosity - Nohut, Serkan; Schlacher, Josef; Kraleva, Irina; Schwentenwein, Martin; Bermejo, Raul (International journal of applied ceramic technology, 2024)
The interest on porous ceramics has increased in the last years with the developments in additive manufacturing methods, enabling design of components with complex geometries for membranes, filters, catalytic converters, or biostructures. In this study, porous alumina samples were produced by using different concentrations of poly(methyl methacrylate) (PMMA) as pore-forming agent (PFA) in a photocurable slurry via vat photopolymerization (VPP). The effect of layer thickness, PMMA particle size, and sintering temperature on the mechanical properties and microstructural features of the samples was investigated as a function of PMMA concentration. It is shown that the mechanical properties of 3D-printed porous alumina are comparable with those fabricated by conventional processes. The Young modulus, fracture toughness as well as the biaxial strength decreased with increasing weight concentration of PFA (resulting in an increased total porosity). Specially using smaller PMMA particles has a positive effect, resulting in higher Young's modulus as well as fracture toughness. The feasibility of VPP for fabricating novel parts with more complex porosity regions is explored by printing multi-material samples and porosity-graded architectures. The counterbalance effect between porosity and mechanical properties may be optimized by tailoring material composition and processing parameters.
Publisher Copyright: © 2023 Lithoz Gmbh and The Authors. International Journal of Applied Ceramic Technology published by Wiley Periodicals LLC on behalf of American Ceramics Society.
Keywords: additive manufacturing; alumina; mechanical properties; pores/porosity; Vat photopolymerization

A DSMS approach to support surveillance data based services in U-space - Pfisterer, Daniel (2024)
The market for UAS (Unmanned Aerial System) holds a lot of potential for growth in the near future, both in industrial and consumer applications. With an increasing rate of adoption, standardized regulations and technical developments are crucial to enable safe UAS operations. One initiative that blends both is the deﬁnition of a U-space that provides digital services for a safe access to airspace. In order to provide these services in real-time, with 1Hz as reference value, the implementation of a prototype of a DSMS (Data Stream Management System) is proposed.The developed DSMS is speciﬁed based on a combination of regulatory and problemspeciﬁc requirements. For deﬁning the technical speciﬁcations the system is divided into three parts (ingestion, processing, and storing). According to the speciﬁcations a DSMS should be fault-tolerant and scalable while providing tools for stateful computations and SQL-compatibility. These speciﬁcations serve as basis for selecting the frameworks for the implementation of the prototype. For the data ingestion Apache Kafka is utilized, the stream processing is done with Kafka Streams, and all data is stored in a PostgreSQL database. Based on these frameworks the architecture of the whole system is designed. As Kafka is responsible for most of the data handling, designing the data ﬂow within, from and to Kafka proved to be crucial for a successful implementation. To simplify testing and deployment of the prototype, all frameworks are implemented as containerized applications using Docker. Yet, even as containerized applications, applying these frameworks is not trivial. A smooth data exchange between the di!erent components, is only possible with consistent schema deﬁnitions. Coordinating the partitioning logic from Kafka with the stream processors for scalability requires careful adjustment of all parameters. Overcoming these challenges demands a deep understanding of the whole system with all its components and the interactions between them.The ﬁnished DSMS prototype implements a selection of U-space services which are tested with a customized simulator. Although results have to be viewed with care, as all tests are conducted in a controlled environment, the results demonstrate the feasibility of using a DSMS to provide U-space services.
no embargo
Keywords: U-space; Apache Kafka; DSMS; SQL; Datenstromverarbeitung; Kafka Streams; data engineering; Docker; Datenstrom; Log-basierter Nachrichten- broker; stateful processing; exactly once; idempotence; PostgreSQL; Kafka Connect; Java; Echtzeitdatenverarbeitung; U-space; Apache Kafka; DSMS; SQL; stream processing; Kafka Streams; data engineering; Docker; unbounded data; log-based message broker; stateful processing; exactly once; idempotence; PostgreSQL; Kafka Connect; Java; real-time processing

A Decomposition Method for the Deterministic Flow Refueling Location Problem (DFRLP) - Höller, Marcel (2024)
The transport sector is a significant driver of climate change and is responsible for a substantial proportion of global CO2 emissions. Battery electric vehicles offer a promising solution for reducing emissions, but require a well-developed charging network for widespread acceptance. The Deterministic Flow Refueling Location Problem (DFRLP) deals with optimizing the placement of charging stations considering traffic flows in order to maximize the coverage of charging demand. This thesis addresses the combination of two existing extensions of the DFRLP. These consider the sizing of charging stations with limited capacity, as well as the cost heterogeneity in urban, suburban and rural areas. A problem-specific decomposition method is developed and applied to efficiently solve this extended DFRLP. The developed decomposition method decomposes a given graph by removing the edges with the smallest traffic volume until the graph is decomposed into smaller clusters to which the extended DFRLP can be efficiently applied. The effectiveness of the decomposition method is demonstrated through extensive numerical experiments. The results show that the solution quality is close to the optimal solution of the full data sets with a significant reduction in runtime. This work contributes to the optimization of electric vehicle charging infrastructure and provides a practical tool for decision making in the field of transportation planning. The proposed method can assist decision makers, infrastructure planners and private investors in optimizing the placement and sizing of charging stations to enable a sustainable transportation future.
no embargo
Keywords: Electromobility; E-Mobility; Charging Stations; Deterministic Flow Refueling Location Problem; DFRLP; Decomposition; ILP; Elektromobilität; E-Mobilität; Ladestationen; Deterministic Flow Refueling Location Problem; DFRLP; Dekomposition; ILP

A Study of a concept geothermal ERD well for the South German Molasse Basin - Minihold, Maximilian (2024)
To ensure energy supply for Munich in the future, Stadtwerke München Services GmbH (SWM) is planning to utilize extended reach drilling (ERD) wells for resource development. With ERD wells it is possible to increase the potential from one well site, by producing heat in locations with a high demand. Complicated and cost-intensive connections to the heating network can thus be avoided. Several wells have already been drilled in the South German Molasse Basin and drilling processes have been timely improved. Wells in this area have been realized at around 3.000 m horizontal departure (HD) for shallow depths and 2.500 m for deeper depths, but potential for more horizontal reach is available. In geothermal projects within the Molasse Basin in southern Germany, several wells are usually drilled from one well site. To ensure sufficient spacing between boreholes in the reservoir, boreholes are drilled horizontally away from each other. Firstly, with increasing horizontal distance of the target point to the drilling site, the technical effort, costs and risks increase. Secondly, increasing the horizontal distance allows a significantly larger reservoir area to be developed from one drilling site. The ultimate goal of this thesis is to design a new well concept that focuses on a horizontal departure of at least 3.500 m up to 6.000 m in shallow depths of less than 2.500 m true vertical depth (TVD), taking into consideration solutions to overcome the current limitations, such as Torque/Drag, Hydraulics and Drag during Casing/Liner running. The final well design concepts established in this thesis should act as a foundation for future geothermal ERD wells in South German Molasse Basin. The basis for this thesis is a conceptual project selected in the northern region of Munich. Based on the most demanding well path of this project, various well path variations are developed using constant parameters to ensure comparability. This approach also allows the simulation of various difficulty levels, inclusive potential limitations. A full well design is established for all wells, taking into account existing SWM guidelines, literature, and expert insights from various industry disciplines. The developed well design is explained using one exemplary well. From the simulations can be concluded that, due to the implemented technology and expertise, all wells can be technically feasible simulated regardless of the length of the well, with only small operational changes (e.g., no rotation necessary during drill string tripping in) needed. A singular exception occurs during drilling simulations in Section 4 for well Var 3, which necessitates a top drive with higher torque capability. The well design established in this thesis encompasses selection and optimization of challenging well paths, collaboration with industry experts for the development of drilling fluids formulations, a casing design aligned with SWM guidelines that incorporates insights from manufacturers for the selection of proven ERD casing connections, and the incorporation of floating equipment for a 9.5/8¿ liner as well as a drill string configuration based on companies¿ recommendations. Furthermore, comprehensive simulations, including torque, drag, hydraulics during drilling and running liner as well as cementation modeling are conducted.
no embargo
Keywords: geothermal well; extended reach drilling; horizontal departure; well trajectory design; casing design; drilling fluid design; drill string design; running loads simulation; Geothermiebohrung; Bohrungen mit großer Reichweite; horizontale Distanz; Bohrpfad-Design; Rohrtouren-Design; Bohrspülungs-Design; Bohrstrang-Design; Schleiflasten Simulation

A green future from a contentious past - Hiller, Jasmin Mareen (Gold and critical metals in a historic arsenic mining district Straßegg (Styria), 2024)
To reach Europe’s ambitious goals for the “Green Deal”, the supply of resources to build the Green Energy Infrastructure needs to be assured. At this moment, recycling is not able to handle the exponential increase in demand for precious and critical raw materials. Therefore, it is still necessary to explore new and alternative sources of these metals. At Straßegg (Styria, Austria) an abandoned medieval As-Ag-Au mining district contains several mine waste dumps with up to 14,000 tonnes of material. The main sulfide minerals in the deposit are arsenopyrite, chalcopyrite, and pyrite as well as several sulfosalts such as boulangerite, bournonite, and galena. Due to the limited ore processing ability in previous centuries, the deposit and its waste still contain abundant precious metals and critical raw materials.The potential of sulfide minerals to host critical and precious metals is already known from Carlin-type Au-deposits, orogenic gold and epithermal deposits. These elements are incorporated as inclusions, nanoparticles, or in the crystal structures of the sulfide mineral. Pyrite is especially known for its ability to incorporate Au, Ag, As Co, Cu, Ga, Ge and Ni into the crystal structure by the substitution of S2- or Fe2+ with As2+/2-. A distortion of the lattice as well as partial charge imbalances allow the incorporation of metals. Arsenopyrite is also capable of incorporating various metals, when the ratio of Fe:As:S is disturbed and Au, Co, Mn, Ni, Sb, Se and Te might be incorporated. Chalcopyrite is a potential host for Ag, Bi, Cd, Co, Ga, Hg, In, Mn, Pb, Se, Sb, Sn, Tl and Zn.This thesis applies a combination of whole rock geochemistry and trace element mapping to identify element correlations and zonation patterns to better understand the evolution of the deposit and its potential as a source of critical metals. Arsenopyrite appears to be a host for Au, Co, Ni, Pb and Sb. Pyrite contains appreciable Au, As, Co and Ni. The trace metal content is generally related to an elevated amount of As in arsenopyrite and pyrite. Chalcopyrite is enriched in Ag, In, Pb and Zn.The thesis highlights several ore stages for Straßegg, beginning with an Fe-rich fluid, followed by an As-rich fluid, and finally a Pb-Sb-Ag rich one. Each of these main stages has been subdivided into a series of substages depending on the element correlations noted in the element maps.Additionally, U/Pb age dating was conducted on calcite veins from Straßegg and Flatschach, another historical mining district in the Eastern Alps, to compare the temporal evolution of mineralization in the Eastern Alps. Due to the high content of common Pb in Straßegg calcite, the age dating was unsuccessful, while those from Flatschach provided ages spanning from the Oligocene to the Pliocene.
no embargo
Keywords: Critical metals; Arsenic; Arsenopyrite; Pyrite; Eastern Alps; Straßegg; Mine waste; historic mining district; Kritische Metalle; Arsen; Arsenopyrit; Pyrit; Ostalpen; Straßegg; Bergbauhalden; historischer Bergbaubezirk

A laboratory total scattering approach for studying short-range order in a novel precipitation-strengthened compositionally complex alloy - Bauer, Nicolas Erwin (2024)
Precipitation-strengthened compositionally complex alloys (CCAs), which are derived from the novel material class of high-entropy alloys (HEAs), show high potential for demanding high strength high temperature applications, but some of their properties such as serrated plastic flow are peculiar. The local ordering phenomenon termed short-range order (SRO) of different elements such as Ni and Ti may explain these peculiar properties. One method for studying such local phenomena that has risen to remarkable importance over the past few years is X-ray total scattering (XTS), or pair distribution function (PDF) analysis. In the present thesis, first, a robust laboratory approach for PDF analysis devised at Materials Center Leoben Forschung GmbH (MCL) is presented and applied to Ni powder. The generated laboratory PDF data of Ni is then validated against benchmark data generated with high-energy synchrotron radiation as well as data from literature. The second aim of the present thesis is the investigation of ordering phenomena, in particular SRO, in a Ni 11 wt.% Ti binary alloy and a precipitation-strengthened CCA manufactured at MCL using the total scattering approach. Using Rietveld refinement and PDF refinement of both laboratory and synchrotron data in combination with scanning electron microscopy (SEM) and energy-dispersive X ray spectroscopy (EDX), the evolution of ¿¿ precipitation in the CCA is investigated in detail. The findings indicate that in the most rapidly quenched states of the CCA, early stages of ¿¿ precipitation can be observed in the form of SRO, extending over only a few nanometers and acting as a precursor for subsequent ¿¿ formation. In PDF analysis of laboratory and synchrotron data, indirect evidence of the transition from SRO to long-range ordered (LRO) ¿¿ precipitation in the investigated CCA is found. Hence, the present thesis proves that the presented laboratory total scattering approach is a valuable tool for investigating the local atomic structure in polycrystalline materials of varying chemical complexity up to CCAs.
no embargo
Keywords: Chemisch komplexe Legierung; Nahordnung; lokale atomare Struktur; totale Röntgenstreuung; Paarverteilungsfunktion; Labor-Ansatz; ¿¿-Ausscheidung; Compositionally complex alloy; short-range order; local atomic structure; X-ray total scattering; pair distribution function; laboratory approach; ¿¿ precipitation

A phase-field fracture model in thermo-poro-elastic media with micromechanical strain energy degradation - Liu, Yuhao; Yoshioka, Keita; You, Tao; Li, Hanzhang; Zhang, Fengshou (Computer methods in applied mechanics and engineering, 2024)

Ab initio study of oxygen vacancy filament formation at Ta/HfO2 interface - Zhang, Donglan; Wang, Jiong; Wu, Qing; Du, Yong; Holec, David (Surfaces and Interfaces, 2024)

Accoustic Tool Condition Monitoring with Angular Resolution on the Cutting Edges - Ninevski, Dimitar; O'Leary, Paul; Pisowicz, Thomas; Thaler, Julia; Hagendorfer, Elias Jan (2024)

Achieving Superior Strength-ductility-conductivity Combination in TiB2p 6201 Composites via Particle Rotation and Sub-grain Refinement - Zhao, Kai; Li, Xinchen; Liu, Xiangting; Shi, Shuyan; Guo, Enyu; Kang, Huijun; Hao, Zhigang; LI, Jiehua; Zhang, Yubo; Chen, Zongning; Wang, Tongmin (Advanced engineering materials, 2024)

Adaptive Heavy End Control Optimization - Novak, Philipp (2024)
The optimization of production processes using machine learning models is an important step towards more efficient and cost-effective production processes. The aim of this thesis is to formulate a strategy for the adaptive optimisation of parameters for Heavy End Control (HEC) based on input parameters for a specified minimum target length of the thickened tail of the tube. For this purpose, various machine learning regression models and a feed forward neural network are used, which are trained and tested with a provided data set. These models are tested for plausibility and evaluated by predicting the parameters for two different thickened tail lengths of two different materials. The Random Forest model achieves the best results in predicting the input parameters for small and medium lengths of the thickened tail based on known values. The feed forward neural network also shows a good prediction for some parameters, such as the number of scaffolds used and the stress factor. Subsequently, the median of the distribution of the values for temperature and mean wall thickness before the stretch reducing block (SRB) are selected, with which the models generate the optimised parameter values for a specified target length of the thickened tail. The random forest model and the feed forward neural network are used for this purpose. These results will be verified experimentally on the system in the future.
embargoed until 31-01-2029
Keywords: Heavy End Control; Streck-Reduzierwalzwerk; Maschinelles Lernen; Random Forest; Neurales Netz; K-Nearest Neighbor; Polynominale Regression; Regression; Heavy End Control; Stretch Reducing Block; Machine Learning; Random Forest; Neural Network; K-Nearest Neighbor; Polynomial Regression; Regression

Advanced characterization of nanoporous materials - Kostoglou, Nikolaos (Science 4 Technology @MUL, 2024)

Advancements in elemental analysis of Ti(C,N) coatings using atom probe tomography - Schiester, Maximilian (2024)
Atom probe tomography (APT) has emerged as a crucial tool in materials science, offering near-atomic resolution and enabling to investigate the three-dimensional distribution of elements. However, the accuracy of elemental composition observed via APT is significantly influenced by acquisition parameters, in particular the effective electric field and laser pulse energy (LPE). Within this study, the impact of these parameters on compositional biases is systematically investigated using a series of Ti(C,N) coatings, ranging from TiN to TiC. Advanced acquisition parameters, available in modern atom probes were utilized, revealing improved evaporation conditions and a higher specimen survival rate. For this purpose, measurements were carried out with active constant field control, auto pulse rate control and auto pulse energy control. The subsequent comparison with the results obtained with the conventional standard parameters made it possible to analyze the advantages of the advanced acquisition parameters. Customized software scripts were developed to enhance data analysis, including peak decomposition for accurate elemental composition determination. The investigation illuminated various compositional biases dependent on the C/(C+N) ratio and LPE. At low LPEs, preferential retention of carbon and nitrogen was observed. Carbides exhibited tendencies to evaporate as adjacent groups or large molecules, with dissociation effects becoming pronounced at very high LPEs. These findings highlight the significance of optimized electric field strength for achieving a high elemental accuracy. In conclusion, this work provides comprehensive insights into the evaporation behavior of nitrides and carbides in atom probe tomography, facilitating improved elemental analysis for future investigations. Utilization of advanced acquisition parameters is recommended for enhanced measurement efficiency and accuracy. By understanding and controlling acquisition parameters, researchers can mitigate compositional biases and advance the capabilities of atom probe tomography in materials science research.
no embargo
Keywords: Atomsondentomographie; Elementanalyse; Elektrische Feldstärke; Chemische Zusammensetzung; Atom probe tomography; Elemental accuracy; Electric field strength; Compositional biases

Advancements in metal additive manufacturing: In-situ heat treatment of aluminium alloys during the laser powder bed fusion process - Schimbäck, David; Kaserer, Lukas; Mair, Philipp; Mohebbi, M.S.; Staron, Peter; Maier-Kiener, Verena; Letofsky-Papst, Ilse; Kremmer, Thomas; Palm, Frank; Montes, I.; Höppel, Heinz Werner; Leichtfried, Gerhard J.; et al. (Materials science and engineering: A, Structural materials: properties, microstructure and processing, 2024)

Alternatives stetiges Fördersystem - Geier, Gerald (2024)
Im Zuge dieser wissenschaftlichen Arbeit wird versucht, ein innovatives stetiges Fördersystem zu entwickeln und auf seine Tauglichkeit als ökonomische Alternative zum konventionellen Gurtbandförderer hin zu überprüfen. Ziel ist es, Verbesserungen im Hinblick auf die Kurvengängigkeit, Flexibilität sowie Energieeffizienz im Vergleich zu bereits im Einsatz befindlichen Anlagen zu erreichen. Dafür werden zuerst die bekannten Einschränkungen unterschiedlicher stetiger Förderer genau untersucht, um danach, auf dieser Grundlage, erste Überlegungen zu möglichen Entwürfen anstellen zu können. Nach der Festlegung auf ein vielversprechendes Konzept wird nach tauglichen Berechnungsmethoden für die Auslegung der einzelnen Anlagenkomponenten gesucht, auf dessen Basis anschließend eine vollständige CAD-Konstruktion des finalen Entwurfs erstellt wird. Zur Validierung des vorgeschlagenen Konzepts werden abschließend noch relevante Schüttguttransportsimulationen nach der „Diskreten Elemente Methode“ durchgeführt, deren Ergebnisse in die Verbesserung der Konstruktion einfließen. Nach sorgfältiger Auswertung aller vorliegenden Berechnungs- und Simulationsergebnisse kann festgestellt werden, dass der finale Entwurf, speziell in den Bereichen Kurvengängigkeit und Flexibilität, durchaus Potential zeigt. Um diese Resultate in der Realität zu überprüfen und weitere Erkenntnisse zu gewinnen, sollte anschließend in die Prototypenphase übergegangen werden, indem mit angefertigten Modellen ausgewählter Abschnitte der Anlage im verkleinerten Maßstab experimentiert wird.
gesperrt bis 15-02-2029
Keywords: Gurtbandförderer; Kreisförderer; alternativer Förderer; Energieeffizienz; belt conveyor; overhead conveyor; alternative conveyor system; energy efficiency

Analyse der Feuchtigkeitseinflüsse auf 316L und Ti6Al4V Pulver für den Laser Powder Bed Fusion Prozess - Schlemmer, Gerhard (2024)
Additive Fertigungsverfahren bieten die Möglichkeit, hochkomplexe Bauteile mit optimaler Materialausnutzung herzustellen. Im Laser Powder Bed Fusion Prozess (L-PBF) wird metallisches Pulver mittels Laserstrahlung aufgeschmolzen, um schichtweise das finale Bauteil zu produzieren. Die Anwendungsbereiche dieser Bauteile erstrecken sich von Themen mit hoher Gestaltungsflexibilität wie der Medizintechnik über den Rennsport mit Leichtbauanwendungen bis hin zur Raumfahrt mit Hochtemperaturanwendungen. Aufgrund der hohen Qualitätsanforderungen in all diesen Bereichen ist es von hoher Relevanz, das Rohmaterial zu verstehen. Im Rahmen dieser Arbeit sollen Aussagen über die Auswirkungen feuchter Pulverlagerung auf die Pulvereigenschaften sowie die Eigenschaften des fertigen Bauteils analysiert werden. Die untersuchten Werkstoffe sind die Titanlegierung Ti6Al4V sowie der austenitische Edelstahl 316L. Für die Analyse wurden möglichst realitätsnahe Umgebungsbedingungen eingestellt, um etwaige Qualitätsunterschiede festzustellen. Durch die Wiederverwendung des Pulvers in der industriellen Anwendung kommt es zu zusätzlichen Änderungen der Eingangsparameter. Daher wurden sowohl frische, als auch wiederverwendete, sogenannte Mischpulver analysiert. Aufgrund der geringen Partikelgröße des Pulvers im L-PBF-Prozess (unter 60 µm) stehen verschiedene Analysemethoden zur Verfügung. In dieser Arbeit wurden einige Methoden angewandt, die die Pulverdichte, die Partikelgrößenverteilung sowie die chemische Zusammensetzung untersuchen. Zusätzlich wurden Zugproben und Dichtewürfel gefertigt und getestet, um Unterschiede in den mechanischen Eigenschaften sichtbar zu machen. Die Aussagen dieser Arbeit sollen ein grundlegendes Verständnis der Einflüsse der Pulverlagerung und der Unterschiede durch das Pulveralter vermitteln. Aufgrund der durchgeführten Untersuchungen sollen zukünftige Entscheidungen im Pulvermanagement fundiert getroffen werden, um höchstmöglichen Qualitätsansprüchen gerecht zu werden.
gesperrt bis 18-03-2029
Keywords: Additive Manufacturing; Laser Powder Bed Fusion; Powder Characterization; Powder humidity; Additive Fertigung; Laser Powder Bed Fusion; Pulver Charakterisierung; Pulverfeuchtigkeit

Analyse der Gebirgsdrucksituation für einen querschlägigen und streichenden Abbauzuschnitt im Revier VI des Magnesitbergbaus Breitenau - Moosbacher, Benedikte (2024)
Aufgrund der zunehmenden Rohstoffnachfrage infolge des Wachstums der Bevölkerung und der Erschöpfung oberflächennaher Lagerstätten, ist es unumgänglich verstärkt tieferliegende Lagerstätten abzubauen. Mit dem Vordringen in die Teufe erhöhen sich jedoch auch die primären Spannungen, und die Kontrolle des Gebirgsdrucks wird zentral. Um die Gesellschaft adäquat mit Rohstoffen zu versorgen und gleichzeitig einen wirtschaftlichen, möglichst nachhaltigen und vor allem sicheren Abbau zu gewährleisten, ist es unerlässlich, die spezifischen Gegebenheiten und Herausforderungen, die mit zunehmender Teufe einhergehen, zu bewältigen. In dieser Arbeit wird der Magnesit Bergbau Breitenau, welcher seinen Abbau weiter in die Teufe ausweitet, betrachtet. Mit der Erhöhung der Teufe nimmt auch die Komplexität des Verhiebs im Bergbau Breitenau zu. Der Abbau im Westfeld erfolgt über einen schwebend geführten Teilsohlenkammerbau. Ein besonderes Augenmerk in dieser Arbeit liegt auf der projektierten Erweiterung im Revier VI. Eine Rotation der Kammerorientierung von 75° (querschlägige Abbauzuschnitt), welche der derzeitigen Orientierung des Westfeld entspricht, auf 140° (streichender Abbauzuschnitt) wird untersucht. Der streichende Abbauzuschnitt wird mit dem querschlägigen verglichen, um die Auswirkungen hinsichtlich der Spannungen und Zustände der Strecken zu betrachten. Dazu wurden zu Beginn dieser Arbeit die in-situ Zustände der Strecken im Westfeld aufgenommen. Folgend darauf wurden linear elastische numerische Simulationen des Westfeldes durchgeführt. Dabei wurde eine Kammer nach der anderen gemäß der realen Sequenz abgebaut. Im Zuge des Abbaus werden die Baufeldfesten überlastet und entspannen sich. Um diesen Effekt in der numerischen Analyse wiederzugeben, wurden die Baufeldfesten ¿weich¿ gemacht, das heißt die Spannungen der Baufeldfesten wurden Null gesetzt und ein neues Elastizitätsmodul (im Zuge einer Kalibrierung ermittelt) wurde aufgegeben. Die Adjustierung der Primärspannungen und des E-Moduls erfolgte über die Rückanalyse bzw. Kalibrierung. Dabei wurde der RCF-Wert aus den Hauptnormalspannungen der numerischen Simulationen berechnet und mit den aufgenommenen Streckenzuständen abgeglichen. Dieser Vorgang der Adjustierung wurde wiederholt, bis die Gegebenheiten vor Ort durch die numerischen Simulationen wiedergespielt wurden und die passenden Zustände bzw. Werte der Primärspannungen und des E-Moduls gefunden wurden. Hierbei ist zu beachten, dass lediglich der Endzustand der Strecken betrachtet wurde. Darauf folgte die Vorwärtsanalyse, sprich die gewonnenen Erkenntnisse wurden auf die beiden Varianten der Erweiterung, der streichenden und querschlägigen Abbauführung angewandt und simuliert. Es wurden dieselben Materialparameter und Simulationsvorgang gewählt. Hinsichtlich der Sequenzen wurden verschiedene Varianten betrachtet. Die zwei Abbauvarianten wurden im Hinblick auf die Veränderung der Spannungen und Zustände in den Strecken im Verlauf der einzelnen Abbauetappen betrachtet. Zusätzlich erfolgte eine detaillierte Betrachtung sensibler Bereiche der langfristigen Infrastruktur und Barrierefesten. Die Kombination von numerischer Simulation und Kalibrierung ermöglicht die Prognose der Spannungszustände, Spannungsumlagerungen und zu erwartenden Streckenzustände. Dies wiederum gibt die Möglichkeit, frühzeitig Modifikationen vorzunehmen und den Abbau an die vorgefundenen Gegebenheiten anzupassen bzw. zu optimieren.
gesperrt bis 15-04-2029
Keywords: Gebirgsmechanik; Numerische Simulationen; Tiefer Bergbau; Gebirgsspannungen; Spannungsumlagerungen; Rock Mechanics; Numerical Simulations; Deep Mining; Rock Stress; Stress Changes

Analyse der notwendigen Niederspannungsnetzentwicklung bei Ausschöpfung der Photovoltaik-Dachflächenpotenziale - Murbacher, Anna (2024)
Der Anstieg an Erzeugern aus Erneuerbaren Energien stellt Netzbetreiber in Österreich vor die Herausforderung, die zusätzlichen Leistungen in die bestehende Infrastruktur zu integrieren. Dabei spielt die Photovoltaik eine wesentliche Rolle, aufgrund der aktuellen Vielzahl an möglichen Förderungen und der damit einhergehenden Option dem Anstieg von Strom- und Gaspreisen entgegenzuwirken. Die Integration von PV-Anlagen in das vorhandene Verteilernetz führt zu einem beträchtlichen Aufwand in der Beurteilung geeigneter Anschlusspunkte. Die vorliegende Masterarbeit untersucht das Potenzial der Photovoltaik auf den Dächern im Land Salzburg, insbesondere im Versorgungsgebiet des Verteilernetzbetreibers Salzburg Netz GmbH. Basierend auf der Globalstrahlung je Dachfläche wird die potenzielle Leistung für die Einspeisung ins Niederspannungsnetz berechnet. Um die Versorgung für die Zukunft sicherzustellen, wird anhand des Potenzials der Handlungsbedarf in der Niederspannungsnetzebene aufgezeigt. Die zentralen Forschungsfragen sind die Auswirkungen des Dachflächenpotenzials auf das Niederspannungsnetz und die notwendigen Veränderungen zur Einbindung der zukünftig anfallenden Einspeiseleistungen. Um diese zu beantworten, wird die derzeitige Auslastung durch die Analyse von Messdaten für das aktuelle Niederspannungsnetz im Programm MATLAB® bestimmt. Dies gibt Einblicke in den Ausgangszustand in der Niederspannung. Durch die Bestimmung des PV-Potenzials für Dachflächen mithilfe von Werten aus dem Solarkataster für Salzburg sowie untersuchten Literatur kann eine Vorhersage für künftige Einspeiselasten abgegeben werden. Die Wiederholung der Kapazitätsberechnung und die Feststellung von Engpässen ermöglicht es, durch die strategische Netzplanung und die Erstellung von beispielhaften Ortsnetzen das Potenzial für den Ausbau des Niederspannungsnetzes im Versorgungsgebiet der Salzburg Netz GmbH zu ermitteln. Die Ortsnetze werden durch Lastflussberechnungen in NEPLAN® modelliert und der wirtschaftliche Aufwand verschiedener Ausbaustrategien bewertet. Die Analyse des PV-Dachflächenpotenzials zeigt eine Verachtfachung der derzeitigen Leistung im Niederspannungsnetz der Salzburg Netz GmbH. Dies führt zu einer erhöhten Auslastung bei den Transformatoren, die den Energietransport zwischen Mittel- und Niederspannungsnetz sicherstellen. Bei knapp einem Fünftel der Transformator-Stationen im Niederspannungsnetz muss mindestens ein zusätzlicher Transformator gebaut werden, um die Leistung übertragen zu können. Die Modellierung von Ortsnetzen, bei denen zumindest ein Tausch des Transformators notwendig ist, um die Leistung zu übertragen, zeigt die verschiedenen Möglichkeiten des Ausbaus und die Schwierigkeit der Standortsuche für zusätzliche Stationen. Bei der wirtschaftlichen Betrachtung dieser Ortsnetze sticht besonders der Einsatz von regelbaren Ortsnetztransformatoren (rONT) positiv heraus. Ähnliches gilt für den kombinierten Einsatz von rONT und Längsregler, der sich ebenfalls in einem Ortsnetz als die wirtschaftlichste Lösung erweist. Währenddessen führt die Verlegung von Parallelkabeln bei einer derart großen Zunahme an Leistung zu einem hohen Kostenaufwand.
nicht gesperrt
Keywords: Potovoltaics; Distribution Grid; Grid; Expansion; Photovoltaik; Verteilernetz; Netzausbau

Analyse und Prognose des elektrischen und thermischen Energiebedarfs der Produktion in der PCB Industrie - Bohslavski, Stefan (2024)
Die Zielsetzungen dieser Masterarbeit sind eine umfassende Analyse der Energieverbräuche der Firma AT&S und eine Erstellung von Prognosemodellen, um den Bedarf an Energie in der Zukunft möglichst genau vorhersagen zu können. Dies dient der Abschätzung für den zukünftigen Energiebedarf hinsichtlich der Menge und der damit verbundenen Kosten. Aufbauend auf den Stromzählerständen und dem thermischen Energiebedarf des Unternehmens war es möglich, die vorliegenden Daten zuerst für Analysen vorzubereiten und anschließend Prognosen zur Vorhersage des Energieverbrauchs zu erstellen. Um diese Ziele erreichen zu können, wurden anfangs unterschiedliche Prognoseverfahren ausgewählt und untersucht, unter welchen Voraussetzungen die unterschiedlichen Prognoseverfahren am besten geeignet sind. Dafür wurde zu Beginn dieser Arbeit eine umfassende Literaturrecherche durchgeführt, in der verschiedene Prognoseverfahren analysiert wurden. Aus den Untersuchungen ergab sich, dass besonders Regressionsverfahren und Neuronale Netzwerke gute Eigenschaften für die Prognose haben. Für die Anwendung von Regressionsverfahren wurden Informationen über den Verbrauch einzelner Energieverbraucher verwendet. Die Nutzung des Neuronalen Netzwerkes ermöglicht es zusätzlich zu den Messwerten Zusatzinformationen mit diesen Messwerten verknüpfen zu können. Durch den Vergleich der Verbrauchszeitreihen mit zusätzlichen Daten, wie zum Beispiel die Außentemperaturen oder Wartungsplänen, ist es möglich, die Genauigkeit eines Forecasts deutlich zu steigern. Die Regressionsmethoden wurden mithilfe des Programmes Visplore umgesetzt. Dazu wurden die verwendeten Daten anfangs von Messfehlern bereinigt. Anschließend wurden die Daten auf sich wiederholende Verhaltensmuster analysiert. Durch diese Muster konnten die Daten in Abschnitte aufgeteilt werden, um für jeden dieser Abschnitte eine eigene Funktion zu ermitteln. Diese Funktionen konnten dann zu einer Prognose zusammengeführt werden, durch die, basierend auf den Messwerten in der Vergangenheit, eine Vorhersage für den Energiebedarf getroffen werden konnte. Für die Anwendung des Neuronalen Netzwerkes wurde ein Programmcode in Python entwickelt. Zuerst musste das Neuronale Netzwerk die vorliegenden Daten anlernen. Dazu war es wichtig, Parameter für beispielsweise die Größe der Testabschnitte und der Stapelgrößen im Programm anzugeben. Diese Parameter mussten für jede Prognose an die vorliegenden Daten angepasst werden. Anschließend war es möglich, die Erstellung eines Forecasts aufbauend auf diesem Lernprozess durchzuführen. Durch die Verknüpfung der Messwerte in der Vergangenheit mit zusätzlichen Daten wie Wartungsplänen konnten noch genauere Prognosen als mit dem Regressionsverfahren erstellt werden. Für besonders kleine Verbraucher sowie Verbraucher, die sich mit den erwähnten Verfahren nicht ausreichend prognostizieren ließen, war es zudem möglich, einfachere Prognoseverfahren anzuwenden. Dafür eignete sich das statistische Verfahren der linearen Regressionsmethode basierend auf den Mittelwerten des Verbrauches. Waren für die Anwendung des Regressionsverfahrens und des Neuronalen Netzwerkes die vorhandenen Daten nicht ausreichend genau aufgrund fehlender Daten oder die Prognose zu aufwändig, konnte mit diesem Verfahren eine Annäherung für den Energiebedarf getroffen werden. Der Energieverbrauch der Firma wurde aufgeteilt in Wärme, Kälte, Druckluft und elektrischen Strom, wovon im Rahmen dieser Masterarbeit Wärme, Kälte und Strom analysiert und prognostiziert wurden. Die Betrachtung des Verbrauches von elektrischem Strom der Firma AT&S lässt keine genaue Vorhersage zu. Daher wurde einzelne Bereiche separat betrachtet. Dabei wurde für diese Bereiche untersucht, welche Prognoseverfahren jeweils am besten geeignet sind.
gesperrt bis 05-02-2029
Keywords: Energiebedarf; Energieverbrauch; Forecast; Energieprognose; Regressionsverfahren; Multivariate Regression; Neuronales Netzwerk; elektrischer Stromverbrauch; Energy demand; Energy consumption; Forecast; Energy forecast; Regression method; Multivariate Regression; Neural network; Electrical power consumption

Analysis of economic and sustainable haulage systems for the proceeding mining operation in the limestone and marl quarries in Wietersdorf - Glaser, Sebastian (2024)
Since the 1960s limestone and marlstone have been extracted from two open pits in the vicinity of Klein St. Paul for the clinker and cement production in the cement plant Wietersdorf of Alpacem Zement Austria GmbH. For the last decades, the materials were hauled by diesel-powered dump trucks to the stationary primary crusher, positioned between the two open pits. The planned expansion of the two mining sites will supply the cement plant in Wietersdorf for the next 37 years with limestone and 44 years with marlstone. Regarding the time ranges of ongoing production, 17 million t limestone and 41 million t marl will be extracted and that will need to be hauled to the stockpiles and storage silos. As the open pits get deeper with every blast and every dig from the excavator, the distances that the material needs to be hauled will increase. The advancement of the mining activity and the extension of the haulage routes from the pit to crusher result in a higher energy demand to overcome the vertical distances from the pit to the crusher. An increased energy expenditure means a higher diesel consumption to operate the currently utilised dump trucks and therefore higher CO2 emissions. Simultaneously the efforts to reduce CO2 emissions are rising in every sector of the economy. Additionally, fuel and electricity price fluctuations are a complex challenge in a mining operation. The current haulage method of using fuel-powered dump trucks will inevitably reach a point, at which the economic and sustainable performance will decline. These problems concerning both economic and sustainable aspects could be targeted and improved by implementing an appropriate alternative to the current haulage system that is used. Different hauling methods like in-pit crushing and conveying systems, or electrified truck haulage were assessed and compared to the currently applied system in terms of economic feasibility and sustainable performance. Trolley assisted haulage systems have the potential to significantly reduce the consumption of diesel, therefore also the operating costs, a great method in terms of sustainability. However, the capital investments of trolley assisted systems are too high to be considered as an economical method, for the scope of the mining operations in the vicinity of Klein St. Paul. The results of the assessment showed that one hauling method performs well both in economic and sustainable terms. The implementation of a fully mobile in-pit crushing and conveying system could achieve reductions of operating costs and capital costs and a substantial decrease of emitted CO2, which makes this hauling method a suitable substitute to haulage by diesel-powered dump trucks.
embargoed until 08-05-2029
Keywords: Haulage optimisation; economic; sustainable; IPCC; diesel-powered trucks; trolley assisted system; emission reduction; Fördersystemoptimierung; wirtschaftlich; Nachhaltigkeit; IPCC; dieselbetriebene Muldenkipper; Trolley Assisted System; Emissionsreduktion

Analysis on the use of a new explosive and geological condition with a mine-to-mill approach for a limestone quarry located in the vicinity of Madrid, Spain - Gurrea Matus, Gabriel Ismael (2024)
The main objective of this work is the analysis of the use of a new explosive and geological condition with a mine-to-mill approach for limestone in Valdilecha, Spain. Initially, a general description of the mine site is provided, where the focus is on the unitary process: Drill & Blast, Load & Hauling, and Processing stage. A group of 15 blasts is analyzed, and of these several KPIs are defined to create a Base Line for the quarry. Then this information is contrasted with data gathered collected by the team and is processed using different tools, through this is possible to contrast the data and evaluate the use of different technologies. Then, the impact of a new explosive is evaluated on 3 blasts. Through this, a New Design scenario allows a comparison between downstream process KPIs. Finally, the drill-to-mill approach seeks to digitally integrate the processes of drilling, blasting, loading, transport, and processing in the plant. It is expected that the information collected will allow the modeling of different scenarios and study their impact on the main production indicators, becoming a decision support tool for the management and administration of the daily operation of the quarry.
no embargo
Keywords: Mine to Mill; Mine Digitalization; Bergbau; Digitalisierung

Annealing activated substrate element diffusion and its influence on the microstructure and mechanical properties of CVD TiN/TiCN coatings - Konstantiniuk, Fabian; Schiester, Maximilian; Tkadletz, Michael; Czettl, Christoph; Schalk, Nina (Surface & coatings technology, 2024)
TiN/TiCN deposited by chemical vapor deposition (CVD) is widely used as hard coating system for cemented carbide cutting tools, typically under an Al2O3 top layer. During the deposition of the Al2O3 top layer, the underlying TiN and TiCN layers are exposed to high temperatures. Therefore, the present study focuses on the influence of this Al2O3 deposition step, which is mimicked by a vacuum-annealing treatment, on the microstructure and mechanical properties of the TiN/TiCN coating. By applying advanced characterization techniques such as scanning electron microscopy, scanning transmission electron microscopy, transmission Kikuchi diffraction, atom probe tomography, and micro-mechanical bending tests on both, as-deposited and annealed coatings, changes in the microstructure and mechanical properties were studied. It was found that W and Co diffusion occurs along the TiN and TiCN grain boundaries from the substrate into the coating. While the hardness, Young's modulus, and fracture toughness remained unaffected by the annealing treatment, a significant decrease of the fracture stress with increasing annealing time was observed. The present study provides a fundamental understanding of substrate element diffusion in CVD TiN/TiCN coatings deposited on cemented carbide substrates.

Anreicherung von aus Trübwasser rückgewonnenem Ammonium zur Gewinnung eines ammoniakhaltigen Treibstoffs für Brennstoffzellen - Schobesberger, Clemens (2024)
Ziel dieser Arbeit ist es, im Rahmen des Forschungsprojekts „GreenAmmoniaFUEL“ die Möglichkeiten zur Rückgewinnung von Ammonium aus Trübwasser einer Kläranlage und die Anreicherung in einer Produktlösung zu überprüfen. Dabei wird Ammonium mittels Ionentauscher (Klinoptilolith) abgetrennt. Die Regeneration erfolgt mit einer natriumhaltigen Lösung. Die dabei entstehende ammoniumreiche Lösung soll in weiterer Folge durch eine Vakuummembrandestillation zu einem Treibstoff für Brennstoffzellen weiterverarbeitet werden.Die Versuche werden in verschiedenen Variationen an einer vorhandenen Technikumsanlage durchgeführt. Dabei wird das Verhältnis von Flüssigkeit und Zeolith variiert und untersucht, wie sich die Zugabe von Natriumchlorid zur Regenerationslösung auf deren Gleichgewichtskonzentration auswirkt.Die Ergebnisse zeigen, dass sich ein großer Teil des abgetrennten Ammoniums aus dem Trübwasser in der Regenerationslösung wiederfinden lässt und sich während der Regeneration ein Gleichgewicht zwischen Zeolith und Regenerationslösung einstellt. Ohne zusätzliche NaCl-Zugabe nähert sich die Ammoniumkonzentration einem Maximalwert (ca. 520 mg L-1). Der Anteil an Ammonium in der Lösung kann durch Zugabe von Natriumchlorid (entspricht einer Natriumkonzentration von 4,25 g L-1, 8,5 g L-1 und 17 g L-1) bis auf einen Wert von etwa 2200 mg L-1 gesteigert werden.
gesperrt bis 12-02-2029
Keywords: Ammonium; Abwasser; Ionenaustausch; Brennstoffzelle; ammonium; wastewater; ion exchange; fuel cell

Anteil an für die getrennte Sammlung vorgesehenen Alttextilien im Restmüll - Tatschl, Lisa Fiona (2024)
Die Kreislaufwirtschaft ist ein zentrales Thema der Europäischen Union auf dem Weg ambitionierte Klimaziele zu erreichen. Der Textilsektor wird dabei auch immer mehr in den Fokus gerückt. Für eine nachhaltige Gestaltung der Abfallwirtschaft ist eine ausgereifte Sammlung unumgänglich. Für Alttextilien gibt es bereits ein bestehendes System für tragbare Textilien, das derzeit jedoch überdacht wird. Ein Großteil der haushaltsüblichen Textilien wird momentan noch über den Restmüll mitgesammelt und das Potential geht damit so gut wie verloren, da dieser Anteil keiner Wiederverwendung zugeführt wird. Ziel dieser Arbeit war es den Anteil an tragbaren Alttextilien im Restmüll zu erfassen und zu quantifizieren. Dazu wurden Abfallanalysen in mehreren Regionen mit unterschiedlichen abfallwirtschaftlichen Kriterien, wie einer zentralen oder dezentralen Altkleidersammlung, durchgeführt. So wurden vier Regionen gewählt, die sich hinsichtlich sozioökonomischer Faktoren in ländliche, intermediäre und städtische Gebiete unterscheiden. Teil der Untersuchung war es, alle Alttextilien aus einer definierten Probe an Restmüll herauszuklauben und im Anschluss mittels Handsortierung in unterschiedliche Fraktionen zu sortieren. Daraus ergaben sich sechs Kategorien, die sich in Altkleider, Schuhe und Accessoires sowie sonstige Textilien und jeweils in tragbar und nicht-tragbar gliederten. Basierend auf den Daten der Analyse wurde das Potential an tragbaren Textilien im Restmüll berechnet und die verschiedenen Faktoren diskutiert. Die Ergebnisse dieser Arbeit zeigen, dass im Durchschnitt pro Kopf 5,1 Kilogramm Alttextilien aus dem Restmüll erfasst werden, und mehr als die Hälfte davon noch tragbar und somit für die Wiederverwendung geeignet wären. Als Unterschiede der einzelnen Gebiete lässt sich zum Beispiel ableiten, dass die Menge der Fehlwürfe an tragbaren Alttextilien in der ländlichen Region geringer ist als im städtischen oder intermediären Raum.
nicht gesperrt
Keywords: seperate textile waste collection; textile waste; Wearability; textiles; Altkleidersammlung; Altkleider; Tragbarkeit; Textilien

Anwendung von Process Mining auf logistische Prozesse: Vorgehensweise im produzierenden Umfeld - Steinwiedder, Daniel (2024)
In der vorliegenden Arbeit wird die Anwendung von Process Mining zur Verbesserung logistischer Prozesse produzierender Unternehmen untersucht. Process Mining verbindet Elemente der Data Science mit Prozessmanagement, um reale Prozesse durch Analyse von Ereignisprotokollen zu identifizieren und zu verbessern. Die Arbeit beinhaltet eine umfassende theoretische Einführung in die Themen Logistik, Geschäftsprozessmanagement und Data Science, gefolgt von einem detaillierteren Einblick in die Grundlagen von Process Mining. Ein wesentlicher Teil der Arbeit ist die Entwicklung eines praktischen Leitfadens für den Einsatz von Process Mining, basierend auf einer systematischen Literaturrecherche. Dieser Leitfaden wird in einer Fallstudie angewendet, in der die Methodik in einem Produktionsunternehmen implementiert wird, um logistische Abläufe zu verbessern. Dabei wird detailliert auf die Vorbereitung, Durchführung und Nachbereitung der Fallstudie eingegangen, was einschließt, wie Daten gesammelt, verarbeitet und analysiert werden, um Optimierungspotenziale bei Prozessen zu identifizieren. Die Ergebnisse der Fallstudie zeigen, dass mittels der Anwendung des entwickelten Leitfadens, eine Verbesserung der Transparenz logistischer Prozesse erreicht werden kann. Es werden auch Herausforderungen und Limitationen der Technologie diskutiert, insbesondere die Qualität und Verfügbarkeit von Daten. Die Diskussion der Ergebnisse führt zu konkreten Empfehlungen, wie Process Mining effektiv eingesetzt werden kann, um die Leistungsfähigkeit der logistischen Prozesse zu steigern. Dies umfasst eine sorgfältige Datenpflege, die Auswahl geeigneter Process Mining Werkzeuge und die fortlaufende Schulung der Mitarbeiter, um die Potenziale der Technologie vollständig ausschöpfen zu können.
gesperrt bis 16-05-2029
Keywords: Process Mining; Prozessmanagement; Logistik; Produktion; Leitfaden; Process Mining; Process Management; Logistics; Manufacturing; Guideline

Application of Printable Electronics to Improve Tubular Integrity Monitoring - Gorshenin, Artyem (2024)
With the development of the oil and gas industry, the health of the wells always stays in focus. Well, integrity is a critical matter throughout the entire well life cycle. The failure of the wellbore integrity can result in not only adverse financial outcomes and stability of an organization but also significant environmental consequences, including the pollution of groundwater, the release of gas into the atmosphere, and leakage and spillage of fluids on the surface. Tubular monitoring, in terms of well integrity, enables early detection of potential damage, especially in ageing wells. The structural integrity of wells may deteriorate over a certain period, increasing the likelihood of tubular failure. During the well production phase, tubulars are most susceptible to cyclic loads (axial loads, radial loads, bending loads), corrosion, temperature, pressure changes, etc. For instance, external casing corrosion is a common problem in the oil and gas industry, which can compromise the safety and productivity of the well. However, predicting the corrosion rate can be difficult due to the uncertainty of various factors. Since the accuracy of theoretical models to indicate the corrosion rate is questionable, inspection tools are frequently utilized to monitor the remaining wall thickness of the casing to prevent potential leaks and other hazardous incidents. However, different logging tools and sensors have some limitations when it comes to continuous measurements. Wireline logging jobs are periodic operations and can only be used when the well is in a shut-in state and when the tubing has been removed to enable logging in the casing string. On the other hand, fiber optic sensors are commonly utilized for acoustic, temperature, and strain measurements. These types of measurements are not capable of identifying localized corrosion types, and they come with high costs. A similar situation is identified in the tubular surface applications (pipeline). The pipeline inspection tools provide periodical health information and other monitoring technologies primarily based on existing leak detection. The thesis work aims to investigate mechanical changes in tubular, which are subjected to high pressures, temperatures, and exposure to corrosive fluids causing mechanical stress and deformation over time. To address the limitations of conventional logging tools and fiber optic sensors, the study proposes using new strain sensors for detecting tubular mechanical deformations. The proposed research aims to compare existing strain measurement technologies from a market point of view and define the most suitable applications for tubular integrity monitoring within the oil and gas industry.
embargoed until 14-05-2029
Keywords: Well integrity; tubular; strain; temperature; pressure; corrosion; mechanical deformation; fiber optics; 3D-printed strain gauges; pipeline; casing; Rohrüberwachung; Ölaustritt; Alternde Bohrlöcher; Zyklische Belastungen; Korrosion; Temperaturschwankungen; Druckschwankungen; Wandstärke; Faseroptische Sensoren; 3D-Druck; Öl- und Gasindustrie

Application of frontal polymerization on an industrial scale - challenges and solutions - Malik, Muhammad Salman (2024)
The aim of this thesis was to address various challenges in the cationic frontal curing of epoxy monomers for composites used in technical carbon fiber reinforced laminates and cured-in-place pipe rehabilitation technology (CIPP). Two types of epoxy resins were investigated throughout the thesis namely bisphenol A diglycidyl ether (BADGE) and 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (CE), that are often used as polymer matrix in numerous industrially relevant composites. To develop a frontally curable epoxy resin suitable for thick-walled carbon fiber reinforced composites, a major challenge was to initiate the curing front with ultraviolet (UV) light since fibers are intrinsic UV blockers and surface irradiation was not sufficient to sustain an autocatalytic curing front.In the first part of this thesis, varying contents of CE as epoxy diluent were used to increase the reactivity of a BADGE monomer in frontal polymerization by employing a diaryliodonium salt and benzopinacol as classical photoinitiator/thermal initiator pair. The results showed an increase in front velocity and a negligible effect on temperature of the propagating front. In addition, the resins were stable with a pot life of at least eight months. Whilst glass transition temperature and degree of cure of the frontally cured resins decreased with higher CE content, tensile strength and storage modulus increased up to a CE concentration of 25 wt%.However, it was found that the addition of CE to BADGE was not enough to increase the exothermicity of the curing front when initiated by UV light only. As an alternative approach, triggering the frontal polymerization via heat was studied. For this the neat resins and the composites were subjected to medium temperature (150 °C) in a conventional oven. As the curing yielded composites with a low glass transition temperature, a new strategy namely redox cationic frontal polymerization (RCFP) was introduced. In RCFP, a reducing agent (stannous octoate) is used in combination with the diaryliodonium salt, that allowed the generation of an increased number of radicals and cations at 150 °C. The results showed a glass transition temperature and degree of cure that were equal to those obtained via a classical anhydride cured BADGE monomer.The RCFP technique was also used to address another significant challenge observed in the frontal curing of cycloaliphatic epoxies. The addition of stannous octoate to a composition of diaryliodonium salt and thermal radical initiator (benzopinacol or even benzoyl peroxide) prevented the decarboxylation of CE-based resin during curing. RCFP was further utilized to develop a frontally curable CE resin suitable for CIPP composites, which are initiated with LEDs emitting at 405 nm. The results showed a successful frontal curing of CE composition on a polyester knitted glass fiber liner with a PVC host pipe without any degradation signs. The thermomechanical properties were compared against acrylate and vinyl ester resins benchmarks cured via classical free radical photopolymerization. It was found that the glass transition temperature and degree of cure of the CE frontal cured resin was higher than in acrylate and vinyl ester resin counterparts. The frontal cured liner exhibited exceptionally high bonding strength to the PVC host pipe in comparison to acrylate and vinyl ester resins, and it was found that host pipes could be safely prevented from heat deformation during on-site operation buried in soil.In the final chapter of this thesis, a unidirectional (UD) carbon fiber reinforced composite was cured with the RCFP technique, and its thermomechanical properties compared with the classical anhydride cured counterpart. The results showed a lower glass transition temperature of the neat resin but competitive tensile, compression and interlaminar shear properties in comparison to an anhydride cured composite. The results of this study showed that the RCFP cured composite exhibit a slightly brittle behavior in comparison to the anhydride cured composite accounting to the differences in the cure kinetics of the two resins. The newly developed RCFP technique was able to reduce the cure time of a classical anhydride cured BADGE based UD composite from 8 h to only an hour, while being fully intact and free of any microscopic defects. The work presented in this thesis provides an exceptionally significant example for the full utilization of frontal polymerization in various technical applications. Reporting for the very first time, this work demonstrates various solutions to frontal polymerization challenges incurred from industrially relevant composites.
no embargo
Keywords: frontal polymerization; cationic polymerization; carbon fiber reinforced composites; cured-in-place pipe rehabilitation; epoxy resin; Frontalpolymerisation; kationische Polymerisation; kohlenstofffaserverstärkte Verbundwerkstoffe; vor Ort ausgehärtete Rohrsanierung; Epoxidharz

Application of machine learning for predicting shallow geothermal temperatures - Skosareva, Viktoriia (2024)
Nowadays, the energy sector is experiencing the transition towards clean energy sources that reduce carbon emissions. Geothermal energy can cover the demand for energy grid stability and contribute to decarbonisation. The heat extracted from underground can be used directly as heat for space cooling and heating without any conversion. The extraction of heat from shallow underground depths (up to 200 m) is the basis of this research. To provide long-term sustainability of projects involving geothermal deployment and heat extraction, it is necessary to carefully monitor and manage the geothermal resources. Groundwater temperature (GWT) is a critical environmental parameter influencing the utilisation of geothermal systems. Accurate prediction of GWT is essential for assessing the efficiency and optimising the performance of geothermal installations. This thesis investigates the predictive modelling of GWT using machine learning (ML) techniques. To accurately predict GWT with the help of ML algorithms, a comprehensive dataset with selected features was assembled, incorporating measurements from the eHYD database, along with weather data from Visual Crossing. The data from 1996 to 2016 of shallow geothermal wells in Vienna, district 22, was used for this purpose. Steps for dataset preprocessing are described, and ML algorithms are applied and evaluated to predict the temperature. The analysis revealed the K-Nearest Neighbors model to be the model providing the highest accuracy in predicting GWT, as well as showed the importance of additional accounting for urban factors when investigating geothermal applications on the city scale.
no embargo
Keywords: Maschinelles Lernen; Temperaturvorhersage; Oberflächengeothermie; Dekarbonisierung; Machine learning; temperature prediction; shallow geothermal energy; decarbonisation

Assessment of URANS-Type Turbulent Flow Modelling of a Single Port Submerged Entry Nozzle (SEN) for Thin Slab Continuous Casting (TSC) Process - Vakhrushev, Alexander; Karimi Sibaki, Ebrahim; Wu, Menghuai; Ludwig, Andreas; Nitzl, Gerald; Tang, Yong; Hackl, Gernot; Watzinger, Josef; Bohacek, Jan; Kharicha, Abdellah (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)
The numerical methods based on the unsteady Reynolds-averaged Navier–Stokes (URANS)equations are robust tools to model the turbulent flow for the industrial processes. They allowan acceptable grid resolution along with reasonable calculation time. Herein, the URANSapproach is validated against a water model experiment for the special single port submergedentry nozzle (SEN) design used in the thin slab casting (TSC) process. A 1-to-2 under-scaledwater model was constructed, including the SEN, mold, and strand Plexiglas segments.Paddle-type sensors were instrumented to measure the submeniscus velocity supported byvideorecording of the dye injections to provide both qualitative and quantitative verification ofthe SEN flow simulations. Two advanced URANS-type models (realizable k–e and shear stresstransport k–x) were applied to calculate velocity pattern on meshes with various resolutions. Anoscillating single jet flow was detected in the experiment, which the URANS simulations initiallystruggled to reflect. The dimensionless analysis of the mesh properties and correspondingadjustment of the boundary layers inside the SEN allowed to resolve the flow pattern. Theperformed fast Fourier transform (FFT) verified a good numerical prediction of the flowfrequency spectrum. The corresponding simulation strategy is proposed for the industrial CCprocess using the URANS approach.
On behalf of all authors, the corresponding author states that there is no conflict of interest. The Author(s) 2024
Keywords: URANS; urbulent Flow Modeling; Single Port Submerged Entry Nozzle; SEN; Thin Slab Continuous Casting; TSC

Assessment of conceivable CCU technologies for Austria - Knaak, Alexander (2024)
The utilization of carbon dioxide in production processes, targeted for implementation by 2030 or 2040, necessitates timely technological readiness and a substantial impact on greenhouse gas reduction compared to conventional manufacturing methods. Within this context, a comprehensive literature review has identified ten distinct CCU technologies, presenting their methodologies and possible operational conditions. Aligned with national objectives, climate target compatibility criteria are formulated for comparative analysis and to determine technology-specific emission factors. These factors, in conjunction with emissions data from domestic operators, highlight the value of CO2 as an alternative raw material and potential GHG emission savings through a substitution approach. Furthermore, this thesis explores considerations and challenges involved in selecting suitable CCU pathways, tracing the journey of carbon dioxide from its origin to its re-release at the end of a product's lifecycle.
no embargo
Keywords: climate change mitigation; GHG emissions; CCU; LCA; technology readiness level; industry; Austria; Klimaschutz; Treibhausgasemissionen; CCU; Industrie; Österreich; LCA; TRL

Assessment of heavy metals in river ecosystems: a geochemical approach to support biodiversity for the Ombrone Grossetano River Basin (Italy) - Gianetti, Francesca; Gozzi, Caterina; Venturi, S; Natali, C; Rimondi, V; Morelli, G; Vaselli, O; Tassi, F; Maccelli, C; Capecchiacci, F; Meloni, F; Cabassi, J; et al. (Forum Nazionale della Biodiversità 2024, 2024)

Asymmetric supercapacitors based on biomass-derived porous activated carbon (PAC)/1D manganese oxide (MnO2) electrodes with high power and energy densities - Lee, Young-Seok; Selvaraj, Aravindha Raja; Kostoglou, Nikolaos; Rebholz, Claus; Rajendiran, Rajmohan; Raman, Vivekanandan; Kim, Heeje; Rajesh, John Anthuvan; Nagulapati, Vijay Mohan; Oh, Tae Hwan; Jerome, Peter; Kim, Sung-Shin (Materials science and engineering B (Solid-state materials for advanced technology), 2024)

Aufbereitung von Rückständen aus Müllverbrennungsanlagen - Lechner, Michael (2024)
Die Abfallverbrennung wird in der Zukunft mehr und mehr an Bedeutung gewinnen, somit auch das Recycling der daraus entstehenden Rückstände. Diese Arbeit ist Teil des K1-MET Projektes Project 1.3 ¿Ressource efficient copper refining process¿ und konzentriert sich primär auf die Anreicherung von Kupfer und kupferhaltigen Metallen aus Rückständen von Müllverbrennungsanlagen. Um die Sortierung von Müllverbrennungsschlacken mit sensorgestützten Sortiersystemen möglich zu machen, muss zuvor ein hinreichender Aufschluss der Probenoberfläche vorliegen. Der Ausdruck ¿hinreichend¿ deutet an, dass der für effiziente Trennung notwendige Aufschluss je nach nachgeschaltetem Sortiersystem unterschiedlich sein kann. Um diesen hinreichenden Aufschluss zu erzielen, muss die Schlackenoberfläche vor dem Sortierschritt behandelt, der erzielte Aufschluss aber auch hinsichtlich beschrieben werden. Ziel dieser Arbeit ist es, ein Oberflächenbehandlungsverfahren sowie eine Methodik zur Bewertung des dabei erzeugten Aufschlussgrades zu entwickeln. Es werden verschiedene Oberflächenreinigungsverfahren im Labormaßstab getestet. Methoden zur Effizienzbewertung des erzielten Aufschlusses werden entwickelt und miteinander verglichen. Neben den am Lehrstuhl für Aufbereitung durchgeführten Untersuchungen wird in Kooperation mit der Firma LINETECHNOLOGY GmbH (BlueLine) ein Sortierversuch an einem LIBS-Sortiersystem durchgeführt, um die gewonnenen Erkenntnisse aus den Laborversuchen im Industriemaßstab umzusetzen. Im Rahmen der Arbeit wurde ein Aufschlussverfahren entwickelt. Ein Verfahren auf Basis digitaler Bildverarbeitung erwies sich neben der Messung der Masseabnahme der Schlackenkörnungen als objektivierbare Beschreibung des Aufschlusses und der Aufschlussrate. Die ersten Ergebnisse mit der Sensorik industrieller Sortiersysteme belegen die verbesserte Erkennung von Kupfer.
gesperrt bis 06-05-2027
Keywords: Müllverbrennungsschlacke; Oberflächenbehandlung; LIBS-Sortiersystem; Kupferanreicherung; Waste incineration slag; Copper enrichment; Waste incineration plant; surface treatment; Sensor-based-sorting

Aufbereitungstechnische Rohgutcharakterisierung und Kleinversuchstechnik an einem pyrometallurgischen Blei-/Zink-Rückstand - Schober, Martin (2024)
In der vorliegenden Diplomarbeit wurden Untersuchungen zur Aufbereitbarkeit von Rückständen aus der pyrometallurgischen Blei-/Zink-Gewinnung durchgeführt. Dabei wird zu Beginn auf die Entstehung eines solchen Rückstandes, vereinfacht als Schlacke bezeichnet, eingegangen. Dazu wird zunächst erklärt, welche primären Rohstoffe zum Einsatz gelangen und wie diese bis zu einem marktfähigen Konzentrat verarbeitet werden, welches für die Metallurgie nutzbar ist. Darauffolgend wird der Röstungsschritt vor dem Imperial-Smelting-Verfahren (IS-Verfahren) erläutert. Das IS-Verfahren ist das einzige pyrometallurgische Verfahren, in dem Blei und Zink in einem Prozessschritt hergestellt werden können. Zentrales Aggregat des IS-Verfahrens ist der Blei-/Zink-Schachtofen, dessen Funktionsprinzip erläutert wird. Im Speziellen wird darauf eingegangen, welche Rückstände beim IS-Verfahren anfallen. Für die Aufarbeitung dieser deponierten Rückstände, die zum Teil hohe Gehalte an wirtschaftlich relevanten metallischen Elementen aufweisen, gibt es bereits energieintensive metallurgische Prozesse. Im Zuge dieser Arbeit wurde nun der forschungsrelevanten Fragestellung nachgegangen, ob aufbereitungstechnische Prozessschritte zu einer Entlastung der metallurgischen Prozesse führen können. Die Rohgutcharakterisierung wie auch die Aufbereitungsversuche erfolgten überwiegend an einer Schlacke stammend aus Veles, Nordmazedonien. Die Rohgutcharakterisierung erfolgte nach der Leobener Schule der aufbereitungstechnischen Merkmalsklassenanalyse, die Sortierversuche wurden mittels aufbereitungstechnischer Kleinversuchstechnik durchgeführt. Der Fokus der Sortierversuche wurde auf die Nutzung der Trennmerkmale ¿Dichte¿, ¿magnetische Suszeptibilität¿ sowie ¿Benetzbarkeit¿ gelegt. Zwar konnten bei den durchgeführten Versuchen An- und Abreicherungseffekte in den erzeugten Trennprodukten eruiert werden. Für eine Umsetzung sind diese allerdings als zu gering zu bewerten. Die intensive Verwachsung der beteiligten Phasen in der Schlacke verunmöglicht aus heutiger Sicht den wirtschaftlichen Einsatz aufbereitungstechnischer Prozesse zur Entlastung metallurgischer Prozesse.
nicht gesperrt
Keywords: Aufbereitung; Schlacke; Blei-/Zink-Schlacke; Imperial-Smelting-Verfahren; Veles; Processing; Slag; lead-/zinc-slag; Imperial-Smelting-process; Veles

Aufbereitungstechnische Untersuchungen an Quarz-/Feldspat-Sandfraktionen der KAMIG GmbH & Co. KG - Schaffer, Alexander (2024)
In der vorliegenden Masterarbeit wurden umfangreiche aufbereitungstechnische Untersuchungen an zwei, in unterschiedlichen Dispersitäten anfallenden Quarz-/Feldspat-Sandfraktionen der KAMIG GmbH & Co. KG durchgeführt. Ziel war dabei, in Ergänzung zur Erhebung der Möglichkeiten der Ausnutzung unterschiedlicher Zerkleinerungseigenschaften für nachfolgende Trennschritte, vor allem die möglichst vollständige Abreicherung von Störstoffen mittels Magnetscheidung und Dichtesortierung. Die Qualitätsanforderungen an die erzeugten Quarz- und Feldspat-Konzentrate sollten jenen für den Einsatz in der Glasproduktion genügen.Im ersten Teil der Arbeit wurden die beiden Quarz-/Feldspat-Sandfraktionen mittels eines Vertikalprallbrechers zerkleinert und gemäß der aufbereitungstechnischen Merkmalsklassenanalyse analysiert. Für die anschließenden Sortierversuche nach den Merkmalen „Magnetisierbarkeit“ und „Dichte“ wurden die zerkleinerten Aufgabegüter mittels Taumelsieb in vier Kornfraktionen klassiert.An zwei der vier Zerkleinerungsfraktionen fanden im Anschluss umfangreiche Sortierversuche mit verschiedenen Versuchsreihen auf zwei Magnetscheidern statt. Hier lag das Ziel vor allem auf der möglichst vollständigen Abreicherung von eisenhältigen Schwermineralphasen wie z.B. Ilmenit.Im dritten Teil der Arbeit wurden an der Kornfraktion 315/100 µm systematische Versuche an einer Fliehkraft-Zentrifuge im Labormaßstab durchgeführt. Dabei erfolgte die Trennung in ein Leicht- und ein Schwergut, wobei wie bei der Magnetscheidung eine möglichst vollständige Abreicherung von färbenden Störstoffen angestrebt wurde.Dabei konnten sowohl bei der selektiven Zerkleinerung als auch bei den Versuchen auf den Trennaggregaten vielversprechende Ergebnisse erzielt werden.
gesperrt bis 11-02-2029
Keywords: raw material characterisation; mineral processing; quartz; feldspar; quartz sand; glass industry; magnetic separation; centrifuge; Rohgutcharakterisierung; Aufbereitung; Quarz; Feldspat; Quarzsand; Glasindustrie; Magnetscheidung; Zentrifuge

Aufschmelzexperimente mineralischer Materialien im Mikrowellenplasma - Trupina, Dominik (2024)
Beim Mikrowellenplasma dient Mikrowellenstrahlung als Energiequelle für die Zündung eines Plasmagases. Dies erzeugt eine Plasmaflamme, welche eine Temperatur von mehreren hundert bis mehreren tausend Grad Celsius aufweist. Da das Mikrowellenplasma keine exotherme chemische Reaktion benötigt und sich die geometrische Form des Plasmas beeinflussen lässt, kommt diese Art von Plasmabrennern für diverse Hochtemperaturanwendungen in der Metallurgie und der Hochtemperaturverfahrenstechnik in Betracht. Das Ziel der Arbeit ist die Implementierung einer Mikrowellenplasmabrennkammer am Lehrstuhl für Verfahrenstechnik des industriellen Umweltschutzes an der Montanuniversität Leoben (MUL-VTIU) für die partielle Aufschmelzung bzw. Sphäroidisierung von mineralischen Pulvern. Die Grundüberlegung dahinter ist das Energiesparpotential und eine mögliche Homogenisierung des Energieeintrages im Mikrowellenplasma gegenüber anderer Hochtemperaturbrenner. Es soll untersucht werden, mit welchen Anordnungen ein atmosphärisches Mikrowellenplasma mit Argon als Plasmagas realisiert werden kann. Dies wird in drei Teilschritten realisiert. Dazu wurden zuerst zwei unterschiedliche Mikrowellenplasma-Brennkammern gebaut. Die Zündfähigkeit dieser mit Mikrowellenkomponenten in 2,45 GHz-Technik wurde bewiesen. Als Anwendungstest wurde eine Korund-Pulverprobe sphäroidisiert. Basierend auf den Sphäroidisierungsversuch wurde die benötigte Energiemenge zum Schmelzen berechnet und ein grober, benötigter Leistungsfaktor der Brennkammer abgeschätzt.
nicht gesperrt
Keywords: microwave plasma; microwave plasma torch; resonator based plasma; Mikrowellenplasma; Mikrowellenplasmafackel; resonatorbasierte Plasmabrenner

Austrian Electricity Market Transformation - Brandstetter, Julia (Analysing effects of aFRR/mFRR LMOL Limits regarding Efficiency in Balancing Energy Markets and the Local Intraday Market, 2024)
European goals aiming for climate-neutrality demand an increase of renewable energy sources within the electricity system. The Austrian goal of achieving carbon-neutrality in its electricity generation by 2030 poses additional challenges to the country. An increase of renewable volatile energy sources goes along with an increase in forecast errors, resulting in a higher system imbalance. Real-time price signals, short-term market opportunities, and well-functioning balancing mechanisms are needed to accomplish energy transition. European interconnected balancing energy markets play a key role when it comes to increased market efficiency, thriving for welfare gains for all cooperation members. Nevertheless, balancing cross-border and national market elements is no easy task. By setting a limit to the local merit order list in balancing energy markets in Austria, both short-term markets, the balancing energy market, and the local intraday market, shall benefit. Whereas enough balancing energy shall be forwarded and shared with cooperation members, not-needed balancing energy shall be set free to be traded at the local intraday market, enabling to decrease open positions. This way, imbalances can be handled within the local intraday market by market participants themselves before the transmission system operator has to activate balancing energy, causing high costs which are in the end carried by consumers and producers likewise. Additional intraday trading does not only promise to reduce imbalance costs but also creates an option for balance service providers to increase their incomes. This thesis aims to evaluate the potential impact of short-term market participation of balancing service providers under the current energy market design on overall welfare. The main focus lies on the limit of the local merit order list within the balancing energy market. A simulation model is derived based on evaluations of the current market situation and applied to accomplish a scenario comparison. Different market behaviors of balancing service providers and their chances within the given balancing energy market framework are put into focus. Sensitivities of varied parameters and assumptions are tested, finding the lever to increase producer and consumer surplus. It is shown that short-term market participation is increasing significantly in the balancing energy market as in the intraday market. However, not all market participants apply short-term strategies, causing time periods with illiquid market situations. Nonetheless, intraday incomes could significantly be increased if more close-to-delivery trading is done. The impact is expected to increase even further if regular activities at the local intraday market are established. Yet, the impact onto consumer surplus is still marginal. Further developments and an increase in short-term market activity trends are needed to generate noticeable benefits. This work states the need and potential for short-term market participation within the balancing energy and intraday markets while providing a solid foundation for observing the recently started trend of almost real-time trading to deal with higher volatilities. Only by taking the chance and courage of short-term market actions will energy transition be accomplished technically and economically equally.
no embargo
Keywords: Electricity Market; Balancing Energy Market; Local Intraday Continuous Market; Short-Term Trading; Strommarktdesign; Regelenergie; Kurzfristiges Trading; Regelenergiekooperationen

Automatisierung des Backenwechsels an einer Schmiedepresse der voestalpine Railway Systems - Gruber, Lukas (2024)
Die vorliegende Masterarbeit beschreibt die Möglichkeiten der Arbeitserleichterung und der Steigerung der Wirtschaftlichkeit durch den Einsatz von Automatisierungstechnik. Dabei wird der Backenwechsel einer Schmiedepresse der voestalpine Railway Systems automatisiert. Nach einer umfassenden theoretischen Beschreibung der Umform- und Automatisierungstechnik sowie Industrie 4.0 erfolgt die Umsetzung der Automatisierung. Im praktischen Teil dieser Arbeiter wird zunächst auf den Schmiedeprozess und den damit verbundenen Backenwechsel eingegangen. Folgend werden verschiedene Möglichkeiten der Automatisierung aufgezeigt. Auf Basis einer Nutzwertanalyse in Kombination mit einem paarweisen Vergleich werden diese Automatisierungsmöglichkeiten miteinander verglichen, um die geeignetste Variante zu finden. Anschließend wird die Auslegung und Konstruktion des ausgewählten Konzepts detailliert beschrieben. Zur Prozessoptimierung werden die Teilprozesse evaluiert und in einem Flussdiagramm dargestellt, um den genauen Ablauf der Automatisierung zu definieren sowie weiterführende Kennwerte bestimmen zu können. Daraufhin wird die Vernetzung und Kommunikation zwischen den Komponenten der Automatisierungstechnik beschrieben. In Anlehnung an die Automatisierungspyramide wird für jede Ebene die notwendige Hard- und Software ausgewählt, so dass alle Komponenten miteinander kommunizieren bzw. harmonieren und die Automatisierung vollständig abgedeckt ist. Abschließend werden die Ergebnisse und Auswirkungen der Automatisierung bzw. dieser Arbeit diskutiert.
gesperrt bis 16-05-2029
Keywords: Automatisierung; Digitalisierung; Industrie 4.0; Konstruktion; Schmieden; Schmiedepresse; Automation; Digitalization; Industry 4.0; Construction; Forging; Forging press

Automatisierung einer Maschine zur Bestimmung der Schüttgutpartikelfestigkeit - Buchwalder, Christoph (2024)
Im Bergbau sind verschiedene Eigenschaften wie die Bruchkraft oder die Bruchenergie eines Schüttgutpartikels von großer Bedeutung. Die Firma Geopyörä hat eine Maschine entwickelt, welche die genannten Eigenschaften mittels eines Doppelradprinzips messen und analysieren kann. Dabei drehen sich zwei Räder in entgegengesetzte Richtungen. Diese befinden sich in einem definierten Abstand zueinander, sodass ein einstellbarer Spalt entsteht. Vor dem Bruch werden die Räder von der Stromversorgung getrennt und bremsen dadurch ab. Um den Partikel zu brechen, wird die kinetische Energie der Räder eingesetzt und verbraucht. Dadurch kommt es zu einem Geschwindigkeitsverlust und einer Verringerung der Drehzahl. Über die Differenz der Drehzahl vor und nach dem Bruch, ist es möglich die Bruchenergie zu berechnen. Im Rahmen der Diplomarbeit soll die Partikelzuführung zu dieser Maschine, die bisher manuell erfolgte, automatisiert und in die bereits bestehende Maschine integriert werden. Dies umfasst die Konzeptionierung, Steuerung und den Bau des Prototypen. Um mögliche Fehlerquellen auszuschließen und Verbesserungsmöglichkeiten zu erkennen, wird eine diskrete Elemente Simulation des gesamten Systems durchgeführt. Dabei sollen Informationen über das Bruchverhalten, mögliche Partikelverluste nach dem Bruch oder auch die Gesamtzeitdauer eines Versuchsdurchlaufs gewonnen werden. Anschließend soll eine Korngrößenanalyse der Partikel mittels Camsizer stattfinden. Für den Transport zwischen der Maschine und den Camsizer werden verschiedenen Konzeptideen entwickelt.
gesperrt bis 06-05-2029
Keywords: Automatisierung; Schüttgutpartikelfestigkeit; Bruchenergie; LabVIEW; Diskrete Elemente Simulation; Fördersysteme; Automation; Bulk solids particle strength; Breakage energy; LabVIEW; Discrete element simulation; Conveyor systems

Automatisierung im Lager von Kontraktlogistikdienstleistern: Treiber und Barrieren - Klampfer, Thomas (2024)
Die Einführung neuer Technologien im Lager hat nachweislich einen großen Einfluss auf die logistischen Abläufe, insbesondere im Hinblick auf automatisierte Lager und Lagersysteme. Zusätzlich kommen laufend neue, flexiblere Automatisierungslösungen für den Bereich Lager auf den Markt. Folglich wird dieses Thema auch für Kontraktlogistikdienstleister, welche besonderen Wert auf Flexibilität legen, zunehmend relevanter. Die Kontraktlogistik muss somit trotz ungünstiger äußerer Einflüsse, wie dem Fachkräftemangel, optimale und stabile Prozesse liefern. Ziel dieser Arbeit ist es, die Treiber und Barrieren für den Einsatz von Automatisierung im Lager von Kontraktlogistikdienstleistern zu identifizieren. Nach der Definition einiger Begriffe der Lagerlogistik wird auf die Besonderheiten der Kontraktlogistik und die Automatisierung der Logistik im Lager eingegangen. Im Hauptteil dieser Arbeit werden zunächst die Treiber und Barrieren aus der Wissenschaft mithilfe einer systematischen Literaturrecherche erhoben und anschließend aus Sicht der Praxis beleuchtet. Hierzu wurden Experteninterviews durchgeführt und diese mit einer qualitativen Inhaltsanalyse ausgewertet. Zum Abschluss wurden die Treiber und Barrieren aus Wissenschaft und Praxis gegenübergestellt.
nicht gesperrt
Keywords: Automation; Contract logistics service providers; Drivers; Barriers; Intralogistics; Automatisierung; Kontraktlogistikdienstleister; Treiber; Barrieren; Intralogistik

Beobachtung des Austenitkornwachstums in Nb-mikrolegierten Stählen und Rückschluss auf Zener-Pinning-Kräfte bei Temperaturen zwischen 950 und 1350 °C. - Hanifl, Lukas (2024)
Die Größe der Austenitkörner beeinflusst maßgeblich die Eigenschaften von Stahlprodukten. Dieser Einfluss wird durch gezielte Maßnahmen, wie die Zugabe von Mikrolegierungselementen, kontrolliert. In dieser Arbeit wird der Fokus auf den Einfluss von Niob und Stickstoff auf das Austenitkornwachstum gelegt, insbesondere durch die Bildung von Nb(C,N)-Ausscheidungen und die daraus resultierenden Zener-Pinning-Kräfte. Dies ist von großer Bedeutung für die Herstellung hochwertiger Stähle mit den gewünschten mechanischen Eigenschaften. Im experimentellen Teil wurden Laborschmelzen mit verschiedenen Gehalten an Niob (0.08 wt.-% und 0.02 wt.-%), Stickstoff (60, 80 und 120 ppm) und gleichen Kohlenstoffgehalt (0.15 wt.-%) hergestellt. Die Verwendung des Hochtemperatur-Laser-Scanning-Konfokalmikroskopie (HT-LSCM) war entscheidend für die experimentelle Analyse des Austenitkornwachstums. Diese fortschrittliche Mikroskopietechnik ermöglichte es, die Proben bei definierten Zeit-Temperatur-Verläufen zu untersuchen und hochauflösende Bilder der Probenoberfläche zu erhalten. Zusammenfassend zeigen die Ergebnisse, dass Nb(C,N)-Partikel das Austenitkornwachstum hemmen und Legierungen mit höherem Niob-Gehalt eine stärkere Kornfeinung aufweisen. Der Einfluss des Stickstoffgehalts ist weniger ausgeprägt, aber eine Tendenz zur Kornverkleinerung ist erkennbar. Dieses Verständnis ist entscheidend für die Optimierung der Stahlherstellungsprozesse und die Entwicklung hochwertiger Stähle mit den gewünschten mechanischen Eigenschaften.
gesperrt bis 11-06-2029
Keywords: HT-LSCM; Austenite grain growth; Nb(C; N) precipitations; Zener pinning; HT-LSCM; Austenitkornwachstum; Nb(C; N)-Ausscheidungen; Zener-Pinning

BiMg2/3Nb1/3O3-based thin films from Chemical Solution Deposition - Gindel, Theresa (A study on the influence of the process parameters on the structure and the electrical properties, 2024)
Enhancing the energy storage properties of lead-free dielectric capacitors is a key focus in today's microelectronic industry. This objective is gaining importance in the quest to develop lead-free devices that align with lead-based property standards while minimizing the toxicity associated with processing and the end products. BiMg2/3Nb1/3O3-based thin films show promising energy storage properties due to the disruption of the long-range ferroelectric order. The relaxor-like behavior results in slimmer polarization vs. electric field hysteresis loops (PE loops) compared to ferroelectrics and leading to a significant reduction in energy losses while maintaining a high permittivity. The use of thin film technology, as opposed to bulk ceramics, is a crucial step in the miniaturization of devices. In addition, this technique increases energy density and increases breakdown fields by improving microstructure and promoting texture.In this thesis, thin films based on (1-x)Bi(Mg2/3Nb1/3)O3–xBi0.5Na0.5TiO3 (BMN-BNT, x = 0.85) and (1-x)Bi(Mg2/3Nb1/3)O3–xNaNbO3 (BMN-NN, x = 0.78) systems were produced by chemical solution deposition (CSD) on Pt/TiO2/SiO2/Si substrates. All films have been successfully synthesized and the influence of different heating rates and crystallization temperatures on the microstructure and electrical properties have been investigated and characterized. Characterization analysis was carried out using Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and Energy-Dispersive X-ray (EDX) analysis. Electrical measurements (PE loops) were conducted to evaluate the energy storage properties and to gain insights into the temperature-dependent response and cyclic fatigue behavior of the various films. Both thin film systems show a phase pure and highly crystalline perovskite structure in both XRD and Raman spectroscopy. The BMN-BNT composition showed the most promising energy storage properties (Wrec ~ 20 J/cm3 and 69% efficiency), coupled with excellent thermal stability up to 140°C. However, superior cyclic fatigue stability, extending up to 10^6 unipolar cycles, and low leakage currents were observed for the BMN-NN system. In a broader context, it can be confirmed that varying process parameters significantly impact both the microstructure and the electrical properties of the two material systems. The complex interplay between structural characteristics and electrical behavior underscores the need of thorough exploration of processing conditions in achieving tailored material properties.
no embargo
Keywords: BMN; Thin films; Chemical Solution Deposition; Process parameters; BMN; Dünnschicht; CSD; Prozessparameter

Biobasierte Binder für Naturoberflächen - Watzenig, Martin (2024)
Binder sind Stoffe, die andere Materialien fügen und zusammenhalten beziehungsweise die Oberfläche modifizieren. Diese Masterarbeit behandelt Binder auf Basis nachwachsender Rohstoffe sowie deren Charakterisierung und Entwicklung für die Applikation auf Naturoberflächen. Momentan basieren die meisten Epoxid-Binder auf dem petrochemischen Bisphenol A, welches seit Jahrzehnten unter Verdacht steht, krebserregend zu sein. Polyester und Polyurethane werden ebenso üblicherweise aus fossilen Rohstoffen hergestellt. Einige alternativen Bindemittel wurden bereits gefunden: Epoxidierte Pflanzenöle, Kunststoffe auf Zuckerbasis oder mithilfe der Massenbilanzierung können biobasierte Bindemittel mit gleichen chemischen Eigenschaften und geringerem ökologischen Fußabdruck hergestellt werden. Es ist absehbar, dass die Nachfrage nach biobasierten Kunststoffen im Allgemeinen in den kommenden Jahren durch Umweltanforderungen oder technologische Fortschritte zunehmen wird. Ebenso wird die steigende Nachfrage nach natürlichen Dekorelementen für Innenräume durch diese innovative Lösung bedient. Diese Diplomarbeit ist Teil des Projekts SoftTOUCHwood, das sich auf die Entwicklung und Herstellung von kratzfesten und hochflexiblen naturnahen Dekoroberflächen spezialisiert. Im Rahmen dieser Arbeit sollen drei Bindersysteme (Epoxid, Polyester und Polyurethan) charakterisiert werden und anschließend ein Pressprozess entwickelt werden, um naturnahe Dekorplatten herzustellen. Die hergestellten Pressplatten werden diversen Möbeltests, welche an die ÖNORM A-1605 und A-1610 angelehnt sind, unterzogen und abschließend nach den Kriterien der Verarbeitung, Haptik und mechanischen Eigenschaften bewertet.
gesperrt bis 27-05-2029
Keywords: Biobasiert; Binder; Oberflächenchemie; biobased; binder; surface chemistry

Biomasse als alternatives Reduktionsmittel in der Nichteisenmetallurgie - Dornig, Christian (2024)
In den letzten Jahrzehnten hat der Ausstoß von anthropogen verursachtem CO2 zu einem Anstieg der durchschnittlichen globalen Temperatur geführt. Die dadurch entwickelten Maßnahmen gegen die Emission von Treibhausgasen, wie beispielsweise die Einführung von CO2-Zertifkitaten, betreffen auch die metallurgische Industrie. Aufgrund aktuell steigender Preise für die Zertifikate wächst das Interesse der Unternehmen an Alternativen zu fossilen Einsatzstoffen. Die vorliegende Dissertation befasst sich mit Biomasse als alternatives Reduktionmittel in der Nichteisenmetallurgie. Damit kann eine Möglichkeit zur Verringerung der Nutzung von fossilen Kohlenstoffträgern aufgezeigt werden. Die aus der Pyrolyse von Biomasse hergestellte Biokohle hat, verglichen mit Petrolkoks, neben der CO2-Neutralität den Vorteil eines sehr geringen Schwefelgehaltes. Speziell aus holzartiger Biomasse lässt sich ein Produkt mit besonders hohem Kohlenstoffgehalt produzieren. Daher wurden in dieser Arbeit sechs verschiedene Biokohlen aus diesem Typ Biomasse charakterisiert und hinsichtlich der Verwendung in unterschiedlichen metallurgischen Aggregaten getestet. Die Untersuchungen zum Einsatz von Biokohle im Wälzprozess zeigten, dass die Reaktivität eine große Rolle spielt. Der alternative Kohlenstoffträger erwies sich als effektiv bei der Reduktion von ZnO im Stahlwerkstaub. Allerdings stellte sich die Simulation der Aufheizphase als problematisch dar. Die Verwendung von Biokohle anstatt fossiler Kohlenstoffträger für das Recycling von Bleischlacken stellte sich als vielversprechend heraus, da mit der pyrolysierten Biomasse bessere Reduktionsergebnisse erzielt werden konnten. Pyrolysegas ist ein weiteres Produkt der thermischen Behandlung von Biomasse und wurde hinsichtlich einer Verwertung in einem Reaktor mit flüssigem Metall als Katalysator behandelt. Es konnte erfolgreich eine Umsetzung zu einem Gas mit hohen Anteilen an CO und H2 erreicht werden, womit ein Einsatz als Reduktionsgas denkbar ist. Zum jetzigen Zeitpunkt ist der Einsatz von Biokohle kostenintensiver als jener von Petrolkoks. Allerdings könnte die Subventionierung durch die Nutzung des aufbereiteten Pyrolysegases sowie den Handel mit CO2-Zertifikaten dazu beitragen, die wirtschaftliche Diskrepanz zwischen erneuerbaren und fossilen Kohlenstoffträgern zu verringern. Basierend auf den Recherchen und den hier durchgeführten Untersuchungen, ist Biokohle ein mit teilweisen Einschränkungen nutzbares Substitut und liefert somit einen wertvollen Beitrag zu einer CO2-neutralen Metallurgie.
gesperrt bis 19-02-2029
Keywords: biomass; biochar; alternative reducing agent; Biomasse; Biokohle; alternative Reduktionsmittel

Boron nitride nanotubes versus carbon nanotubes: A thermal stability and oxidation behavior study - Kostoglou, Nikolaos; Tampaxis, Christos; Charalambopoulou, Georgia; Constantinides, Georgios; Ryzhkov, Vladislav; Doumanidis, Charalabos C.; Matovic, Branko; Mitterer, Christian; Rebholz, Claus (2nd International Conference on Innovative Materials in Extreme Conditions (IMEC 2024), 2024)

Capability of microstructure simulation to study cyclic behaviour of aluminium cast alloys - Smit, Thomas (2024)
This master's thesis investigates the practical application of microstructure simulations using the DAMASK simulation software (Düsseldorfer Advanced Material Simulation Kit) for cyclic loads. The focus is on two aluminium casting alloys, EN AC 42100 and EN AC 46200, which were previously characterised in the Christian Doppler Laboratory for Manufacturing Process based Component Design. The study performs a comparative analysis between experimental and simulated samples. The material's consecutive parameters were approximated through literature research and parameter variation. Grain size and grain orientation were derived from physical samples. Changes in the microstructure, particularly plastic deformations resulting from introduced deformation, were analysed. EBSD measurements of the samples before and after loading processes were used to understand and visualize these changes. Although there have been remarkable successes, such as the convergence between experimental and simulated data in material approximation based on uniaxial tensile tests, it is important to note the limitations of this experimental procedure. As a result, there may be a discrepancy between experimental and simulated low-cycle fatigue tests.
no embargo
Keywords: Betriebsfestigkeit; Mikrostruktursimulation; EBSD-Auswertung; Zyklische Materialänderung; fatigue strength; microstructure simulation; EBSD evaluation; cyclic material response

CharAM - Mechanische Charakterisierung additiv gefertigter keramischer Bauteile - Scheithauer, Uwe; Staudacher, Maximilian (2024)

Characterization of short fiber reinforced polymers in the very high cycle fatigue regime - Puregger, Franz (2024)
The present work deals with the development of a test setup for investigating the fatigue behavior of short fiber-reinforced thermoplastics in the VHCF range (> 107 cycles). The main objective was to reduce the test duration for high cycle numbers by increasing the frequency and to assess the feasibility of high-frequency testing on the examined materials. A test concept involving the application of test force by an electrodynamic shaker was developed based on a test setup for metals. The mean stress is 0 MPa, and the stress ratio R = -1. The testing involves alternating tensile/compressive loading. The test concept utilizes the resonance principle. Three versions of the test setup were designed and implemented based on this concept, with each new version representing an improvement. Each version was systematically examined using various sensors and methods to identify deviations from the test concept. The final setup closely adheres to the test concept and allows testing at 230 Hz. With this testing frequency, 107 cycles can be achieved in half a day, while conventional testing methods require 115 days for the same test. In an initial test series, carbon- and glass-fiber-reinforced PEEK with 30% fiber volume content was investigated. To rule out unacceptable temperature increases due to hysteretic heating, the temperature was monitored during the test. The temperature increase was not critical across all tests. The generated S/N curves show a clear increase in fatigue strength with decreasing stress amplitude, as observed in conventional S/N tests for this material. This confirms the fundamental testability of this material at high frequencies. However, the position and slope of the S/N curves do not match conventional tests, requiring further investigation to explain this discrepancy.
no embargo
Keywords: Ermüdung; Wöhlerlinie; VHCF; kurzfaserverstärkte Thermoplaste; Shaker; Fatigue; SN-curve; VHCF; short fiber reinforced thermoplasitcs; Shaker

Characterization of the viscoelastic material properties of FR-4 materials - Zach, Daniel (2024)
Printed circuit boards (PCBs) are crucial in the packaging of electronic devices, providing structural support and electrical connectivity. The demand for smaller, lighter devices has led to the use of multilayer boards (MLBs) made from FR-4 materials, known for their excellent properties. However, harsh environmental conditions pose challenges, and thermally induced stresses impact the reliability of MLBs. This master's thesis focuses on determining the viscoelastic behavior of FR-4 materials, by the use of reliable and time-efficient methods. The specific aim is to characterize the viscoelastic properties of two different FR-4 resin materials, emphasizing accelerated creep characterization. A test methodology based on thermo-mechanical tests and short-term creep tests, coupled with polymer-physical extrapolation principles, was established. Experimental approaches included dynamic mechanical analysis (DMA) at various frequencies and temperatures, constructing time-dependent master curves according to the time-temperature superposition principle. Additionally, short-term tensile creep tests at different temperatures and load levels were conducted using digital image correlation (DIC), constructing creep modulus master curves up to 1000 hours following the stepped-stress method (SSM). For a reproducible and user-independent evaluation of the DMA results, special evaluation programs using the Python programming language were developed, which enable the automated generation of master curves for the viscoelastic property functions. The comparison between experiments provides detailed insights into the reliability of each test method, ensuring a meaningful characterization of viscoelastic behavior over a wide range of loading times. Particularly, the developed test and evaluation method based on temperature and frequency dependent DMA measurements was shown to be a useful tool for the efficient generation of creep modulus master curves. The additional determination of basic material properties, such as glass transition temperature (Tg), coefficient of thermal expansion (CTE), and mechanical short-term properties provided a comprehensive characterization of application relevant properties for the two FR 4 resins investigated. The developed test method, combined with automated evaluation routines, offers a time-efficient approach to estimate long-term viscoelastic behavior, supporting efficient material selection and product development.
embargoed until 19-02-2029
Keywords: FR4-Materialien; Epoxidharze; Viskoelastizität; Zeit-Temperatur Superpositionsprinzip; Beschleunigte Kriechversuche; SSM; FR4-Materials; Epoxy Resin; Viscoelasticity; Time-Temperature Superposition Principle; Accelerated creep test; SSM

Charakterisierung der Mikro- und Nanostruktur eines hochlegierten, martensitischen Cr-Stahls - Pferschy, Matthias (2024)
Durch die fortschreitende Abkehr von fossilen Energiequellen hin zu nachhaltigeren Ressourcen wird Wasserstoff als alternative Form der Energiespeicherung betrachtet. Da jedoch die meisten Stähle unter Wasserstoffatmosphäre unerwünschte Versprödung zeigen, ist eine genaue Kenntnis der Mikrostruktur von Stählen unerlässlich, um diesem Problem entgegenzuwirken. Der martensitische Cr-Stahl X30CrMoN15-1, der in der Vergangenheit vor allem durch seine hohe Härte und Verschleißbeständigkeit in Wälzlagern und tribologisch beanspruchten Bauteilen Anwendung fand, ist ein vielversprechender Werkstoff für den Einsatz in trockenlaufenden Kugellagern unter Wasserstoffatmosphäre Im Zuge dieser Masterarbeit wurden zwei Wärmebehandlungszustände des Stahls X30CrMoN15-1, welche sich lediglich in ihrer Anlasstemperatur unterschieden, hinsichtlich ihrer Mikro- und Nanostruktur untersucht und verglichen. Zur Charakterisierung der Matrixzusammensetzung, insbesondere des Restaustenitgehalts und etwaiger Ausscheidungen, kamen verschiedene Beugungsverfahren, wie Röntgenbeugung oder Elektronenrückstreubeugung, zum Einsatz. Durch Rasterelektronenmikroskopie und Rastertransmissionselektronenmikroskopie konnten der Ausscheidungsgehalt sowie deren Größenverteilung exakt bestimmt werden. Durch zusätzliche Atomsonden-Messungen sowie energiedispersive Röntgenspektroskopie konnten zusätzlich die chemischen Zusammensetzungen der Matrix und der Ausscheidungen bestimmt werden. Beide untersuchten Zustände zeigten eine sehr ähnliche Mikrostruktur mit einem hohen Restaustenitanteil von bis zu 30 %, sowie Ausscheidungen mit einem Phasenanteil bis 1,5 % in Form von trigonalen Karbonitriden mit einer Größe von einigen hundert Nanometern. Obwohl beide Mikrostrukturen in den beobachteten Größenskalen sehr ähnlich ausgebildet waren, führte das Anlassen bei höheren Temperaturen zu signifikant höheren Härtewerten Zusätzlich konnte durch HE-XRD-Messungen eine Verkleinerung der Gitterparameter von Martensit und Austenit vom Zustand 350°C zum Zustand 450°C ermittelt werden. Der Grund für die erhöhte Härte des Zustand 450°C ist demnach in Unterschieden kleinerer Größenordnungen wie Segregationen, Clusterbildungen oder Ausscheidungsbildung in Frühphasen zu vermuten. Insgesamt konnte eine gute Übereinstimmung der Phasenquantifizierung zwischen elektronenmikrokopiebasierten Methoden sowie röntgenbeugungsbasierten Methoden hergestellt werden.
gesperrt bis 12-03-2029
Keywords: X30CrMoN15-1; Kryobehandlung; Karbonitrid; korrosionsbeständiger Stahl; Stickstoff; Mikrostruktur; Restaustenit; X30CrMoN15-1; cryogenic treatment; carbonitride; corrosion-resistant steel; nitrogen; microstructure; retained austenite

Charakterisierung der Mikrostrukturentwicklung sowie dynamischer bzw. metadynamischer Rekristallisation eines PH 15-5 Stahls - Seitweger, Rupert (2024)
Untersucht wird die Mikrostruktur des PH 15-5 Stahls in Bezug auf den rekristallisierten Anteil und die ehemalige Austenitkorngröße nach durchgeführten Warmumformversuchen. Die Basis für die Definition der Versuchsparameter sind bereits durchgeführte, als gleichwertig geltende Versuche des Werkstoffes PH 15-5 aus einer anderen Materialcharge, die von demselben Unternehmen der voestalpine BÖHLER Aerospace GmbH & Co KG zur Verfügung gestellt worden sind. Die Experimente werden durch eine Gleeble-Prüfmaschine durchgeführt. Sie bestehen aus einer Austenitisierung gefolgt von einer Warmumformung in Vakuum und einer darauffolgenden Abschreckung mit Wasser. Bei den verwendeten Proben werden die Temperatur, die Dehnrate und die Haltezeit nach der Umformung variiert. Diese Proben werden dann hinsichtlich ihrer Mikrostruktur untersucht. Sie zeigen, dass sich die Mikrostruktur in Bezug auf den rekristallisierten Anteil und der ehemalige Austenitkorngröße durch die genannten Parameter und durch den unterschiedlichen lokalen Umformgrad über den Probenquerschnitt ergibt. Die Unterschiede zu den im Vorfeld durchgeführten Versuchen der anderen Probencharge werden aufgezeigt. Sie deuten darauf hin, dass das Rekristallisationsverhalten des Werkstoffes zusätzlich zu den bereits genannten Einflussparametern signifikant von der Ausgangskorngröße abhängen dürfte. Um die Rekristallisation einordnen zu können, werden die zusammenhängenden Prozesse der Erholung, Rekristallisation und Kornvergröberung untersucht. Es wird insbesondere auf die metadynamische und dynamische Rekristallisation eingegangen, der PH 15-5 Stahl charakterisiert und die Ergebnisse dargestellt, erläutert und diskutiert.
gesperrt bis 30-01-2029
Keywords: Microstructural evolution PH 15-5 steel; structure of grain boundaries; recovery; recrystallization; dynamic recrystallization; metadynamic recrystallization; grain coarsening; Ostwald ripening; characterization of the microstructure and texture of a metal; determination of grain size; ISO 643; ASTM E 112; Hot forming tests; Gleeble 3800; Forming simulation; Local degrees of deformation after hot forming; Determination of the former austenite grain size using the line section method; Determination of the recrystallized fraction; Resulting microstructure after hot forming tests of PH 15-5 steel; Mikrostrukturentwicklung PH 15-5 Stahls; Struktur der Korngrenzen; Erholung; Rekristallisation; dynamische Rekristallisation; Metadynamische Rekristallisation; Kornvergröberung; Ostwald-Reifung; Charakterisierung der Mikrostruktur und Textur eines Metalls; Bestimmung der Korngröße; ISO 643; ASTM E 112; Warmumformversuche; Gleeble 3800; Umformsimulation; lokale Umformgrade nach der Warmumformung; Bestimmung der ehemaligen Austenitkorngröße mittels dem Linienschnittverfahren; Bestimmung des rekristallisierten Anteils; Resultierende Mikrostruktur nach Warmumformversuchen des PH 15-5 Stahls

Charakterisierung und Optimierung eines zweistufigen Verfahrens zur Rückgewinnung von Graphit aus verbrauchten Lithium-Ionen-Batterien - Hauler, Caroline (2024)
Bei Graphit handelt es sich um eine Modifikation von Kohlenstoff, welche in vielfältigen Anwendungsbereichen wie Elektroden, Feuerfestmaterialien oder Schmiermitteln eingesetzt wird. Technisch von besonderer Bedeutung ist Graphit auch als Anodenmaterial in Lithium-Ionen-Batterien. Aufgrund seiner Einstufung als kritischer Rohstoff in der Europäischen Union und dem steigenden Bedarf im Bereich der Elektromobilität sowie weiterer Zukunftstechnologien rückt das Recycling immer stärker in den Fokus der Forschung. Dadurch kann der Rohstoff, alternativ zum primären Abbau, auch aus Reststoffen rückgewonnen werden. Hierbei erfolgt die verfahrenstechnische Einteilung in pyro- und hydrometallurgische Routen, außerdem existieren Mischprozesse, bei welchen eine Kombination von Methoden der beiden genannten Wege zum Einsatz kommen. Pyrometallurgisch findet die Aufarbeitung von Lithium-Ionen-Batterien häufig im Rahmen von Recyclingverfahren anderer metallischer Reststoffe statt. Mithilfe dieser Verfahren ist keine selektive Rückgewinnung der einzelnen Elemente möglich und Graphit dient als Energieträger und Reduktionsmittel, wird jedoch nicht stofflich verwertet. Hydrometallurgische Technologien ermöglichen die gezielte Abtrennung einzelner Metalle für weiterführendes Recycling. In der Hydrometallurgie verbleibt der Graphit großteils im Rückstand, welcher nach der Fest-Flüssig-Trennung anfällt. Gegenstand der vorliegenden Arbeit ist die Prozessentwicklung eines hydrometallurgischen Recyclingverfahrens, welches gereinigten Graphit als Produkt gewinnt. Ein zweistufiger Prozess entfernt Wertmetalle wie Kobalt, Nickel und Mangan sowie weitere Begleitelemente. Ziel ist die Herstellung einer Graphitfraktion mit hoher Reinheit und einem niedrigen Gehalt an metallischen und oxidischen Verunreinigungen. Um negative Umweltauswirkungen zu minimieren, finden die Versuche bei niedrigen Temperaturen und mithilfe von Citronensäure als Laugungsmittel statt. Das gewonnene feine Pulver durchläuft anschließend eine Charakterisierung zur Beurteilung des Prozesserfolgs. Bei einigen Experimenten traten Gelierungseffekte auf, wodurch sich auch Auswirkungen auf die weitere Verarbeitung der Rückstände zeigten. Die besten Ergebnisse konnten mit einer Laugung bei mittlerer Temperatur (32,5 °C), welche 24 Stunden dauerte, eine Säurekonzentration von 1,5 mol/L aufwies und unter Zugabe von 2,5 Vol.-% Wasserstoffperoxid als Reduktionsmittel erzielt werden.
nicht gesperrt
Keywords: lithium-ion-batteries; battery recycling; graphite; black mass; hydrometallurgy; critical raw materials; Lithium-Ionen-Batterien; Batterierecycling; Graphit; Schwarzmasse; Hydrometallurgie; Kritische Rohstoffe

Chemical recycling of plastic waste via production of ethylene from gasification syngas - Maier, Matthias (2024)
A plastic waste to ethylene (PtE) process through steam-oxygen gasification, methanation and oxidative coupling of methane was investigated. Gasification was modelled using a stochastic reactor model, while the downstream process was modelled using Aspen Plus. This study investigated two cases, one with venting of captured CO2 and one with CO2 compression and transport. In addition, two alternative feedstocks and their effect on the process were explored. The model was evaluated from a technical, economic, and ecological perspective. For the ecological evaluation, the investigated plastic recycling process was compared to naphtha steam cracking, and it was found that 5.7-18.4 kgCO2eq/kg ethylene can be avoided. The minimum ethylene sales price was found using a discounted cashflow calculation and is between 4.9-5.4 ¿/kg. This leads to costs of CO2 avoided between 230-666 ¿/tCO2eq. Moreover, a sensitivity analysis on costs of CO2 avoided using 20,000 random parameter values was conducted.
embargoed until 06-05-2025
Keywords: Chemisches Recycling; Dampf-Sauerstoff Vergasung; Oxidative Kopplung von Methan; Kosten von vermiedenem CO2; Chemical recycling; steam-oxygen gasification; oxidative coupling of methane; cost of CO2 avoided

Classification of Multivariate Time Series Data using Machine Learning and System Redundancy Analysis - Lang, Elliot (2024)
This thesis investigates the level of redundancy within batches of sensor data; the explicit goal of which being to evaluate the system's reaction to the inactivity of one or more sensor units. Moreover, this thesis explores the applicability and viability of different machine learning algorithms for classifying the state of the analysed machine based on batches of acceleration data. The redundancy within the data is measured by quantification of the inherent dimensional coverage; based on the result, the data dimensionality can be reduced. Possible permutations of the loss of one or two of the six available sensor units are analysed in the context of the remaining dimensional coverage. This gives an indication of the certainty with which analyses based on the reduced data can be evaluated. Furthermore, several possible supervised machine learning algorithms, capable of multi-class classification, are identified and their applicability to the labelled data batches is assessed. An array of promising classification methods were identified and applied to each batch of data. The successful classification is quantified by measuring each method's predictive accuracy, the number of correctly identified machine states, and the training time each method requires including the optimization of its hyperparameters. The results of both of these processes show a robustness to the loss of sensors within the system, independent of spatial location, as well as some promising machine learning classification algorithms, capable of identifying the machine's state.
no embargo
Keywords: Machine Learning; Classification; Redundancy; Decision Trees; Neural Networks; Discriminant Analysis; k-Nearest Neighbours; Ensemble Classification; Naive Bayes; Machinelles Lernen; Systemredundanz; Decision Trees; Neural Networks; k-Nearest Neighbours; Discriminant Analysis; Naive Bayes; Ensemble Classification; Classification

Comparative considerations of the recycling of aluminium-containing raw materials in the laboratory and industrial scale - Trippl, Michael (2024)
Aluminium is a highly recyclable material with special properties and remains an indispensable and future-oriented raw material for the transport, packaging and construction industries. To achieve environmental friendly recycling processes with the highest possible overall efficiency, new processing concepts and systems are continually being developed to improve conventional recycling methods. Contaminants, including metallic, non-metallic, organic (such as paints, varnishes, and oils), and inorganic substances (such as oxides), are often found as adhesions or free foreign substances on the scrap used. These can significantly impair the overall process and, therefore, the quality of the products. This thesis covers recycling methods, focusing on the different scrap categories: in-house, pre-consumer, and post-consumer. The literature review describes the main pre-treatment steps, including shredding, sorting, and pyrolysis, which remove impurities from the scrap and prepare it for remelting. Furthermore, various smelting technologies and the role of remelters based on the level of impurities in the scrap are described. Pyrolysis is particularly important for removing organic contaminants in the production of secondary aluminium. The review also examines the remelting process and its challenges, specifically dross formation and its impact on the melting yield. For the experimental study sample material from Alu Menziken SRL is used. To validate the findings on an industrial scale, experiments were conducted on a labratory scale under controlled conditions at the Chair of Nonferrous Metallurgy at the University of Leoben. The aim of this project is to develop a standardised method for predicting dross formation and melting yields in an industrial two-chamber furnace using various scrap input materials.
embargoed until 07-05-2029
Keywords: Aluminium; Nichteisenmetallurgie; Recycling; Industriemaßstab; Laborversuche; Vergleich; Krätzebildung; Schmelzausbeute; Aluminium; Recycling; Recycling of Aluminium; Industrial Scale; Dross; Melting; Casting; Nonferrous Metallurgy

Competitor Analysis of Railway Infrastructure Asset and Maintenance Management IT-Systems for voestalpine Digital Track Management GmbH - Schröck, Maximilian (2024)
This thesis aims to analyze the competition of voestalpine Digital Track Management GmbH. The company offers asset and maintenance management software for railway infrastructure. The most significant competitors have been investigated in detail, and a comparison of the functionalities of the individual software solutions was created. A matrix was created to determine which functionalities are covered and finally to evaluate the extent to which the individual systems cover the areas of asset and maintenance management. Internal interviews, a survey of competitors' customers, and extensive internet research were conducted to gather information. This made it possible to identify important aspects of the competition, the company's position in the market, unique selling points, and potentials for improvement. In addition, theoretical elements of asset and maintenance management systems for railway infrastructure and competitor analysis, to generate an understanding of the topic.
embargoed until 17-01-2029
Keywords: Wettbewerbsanalyse; Asset Management; Instandhaltungsmanagement; Eisenbahninfrastruktur; Funktionenvergleich; voestalpine; Competitor Analysis; Asset Management; Maintenance Management; Railway Infrastructure; Functionality Comparison; voestalpine

Concept development of a body-integrated battery housing - Riahi Samani, Arash (2024)
To seamlessly integrate the battery housing onto the Body in White (BIW), it is imperative to consider a concept that allows for the repair and replacement of battery housing components without the need to open the BIW again. This concept should be designed to be installed on the BIW without an upper cover, ensuring it is both waterproof and cost-effective. In the initial stages, a concept for the battery housing was formulated, with the aid of common CAD (Computer-Aided Design) software, taking into account the specific requirements set forth by the Magna company. To accommodate this battery housing concept, certain modifications were made to the existing platform. These adjustments included altering the height of the surface around the car's floor to create a level surface suitable for the battery housing installation. The frame of the battery housing and the components housed within it were designed to be both fixed and removable, with careful consideration given to their design and how they interconnect. Subsequently, the approach for assembly and the watertight sealing of the battery housing to the BIW were assessed. A comprehensive list detailing the weight of individual components and the production costs were compiled, facilitating a comparison between the conventional concept and the integrated concept. This comparative analysis enables a clear understanding of the advantages and disadvantages of the integrated concept. Compared to the old battery housing that were installed as a module and had a higher weight and manufacturer-specific sealing, the integrated model not only offers weight reduction but also allows for easier sealing during maintenance and convenient access for battery replacement due to its integration.
embargoed until 14-02-2027
Keywords: Battery housing of electric vehicle; Battery housing integration; Body in White; Battery fire protection; Batteriegehäuse für Elektrofahrzeuge; Integration des Batteriegehäuses; Body in White; Brandschutz für Batterien

Corporate Foresight Maturity in Oil and Gas Organisations - Siegmeth, Franz (2024)
This thesis aims to enhance organisational capabilities to improve the likelihood of survival, maintain the status quo, and excel at higher and sustainable growth within a VUCA environment. More specifically, this work aims to improve the organisational capacity of oil and gas organisations to detect and interpret weak and early signals by identifying the gap between the as-is and the should-be situation of their corporate foresight capabilities. This commences through the development and application of an enhanced capability maturity model for corporate foresight in accordance with an oil and gas context.
embargoed until 26-03-2029
Keywords: Öl- und Gasgeschäft; Chaos und Komplexität; Komplexitätstheorie; Komplexitätsdenken; Systeme; Systemtheorie; Systemdenken; Wert der Information; VUCA; VUCA-Umwelt; Organisation; Organisationstheorien; Strategisches Management; Strategische Konzepte; Schwache Signale; Infliction Points; Corporate Foresight; Oil and Gas Business Organisations; Chaos and Complexity; Complexity Theory; Complexity Thinking; Systems; Systems Theory; Systems Thinking; Value of Information; VUCA; VUCA Environment; Organisations; Organisation Theories; Strategic Management; Strategic Concepts; Weak Signals; Infliction Points; Corporate Foresight

Correlation of surface and laboratory methods for the determination of rock parameters underground - Kumertz, Dominik (2024)
The construction of underground structures in existing tunnel systems poses a number of challenges for planners. The construction records are often inadequate and an assessment must be carried out based on the existing condition. This thesis deals with a branch of the Presserstollen in the Styrian Erzberg, which is part of the Zentrum am Berg (ZaB). The objective is the geotechnical evaluation of an approximately 55 m long adit with a diameter of around 3.5 m, that is lined with steel arches and wood. The work focuses on the invert, because the unclear stability conditions prevented any measurements on or behind the lining. The methods used can be divided into three categories: laboratory tests on loose and solid rock samples, geophysics in the invert and evaluation of the deformation of the steel arches. Grain size distribution curves, abrasivity, electrical resistivity, p-wave velocity and strength parameters (triaxial test, point load test) were measured in the laboratory. In geophysics, electrical resistivity tomography (ERT) and refraction seismics were used to identify fault zones and the depth of the damaged zone. The tunnel deformation was assessed by closely observing and evaluating the deformation visible in the steel arches. The results of the laboratory testing show a clearly schistose rock, which has low strength and, depending on the orientation, shows strong anisotropy in behavior. The geophysical surveys show at least two fault zones that cross the tunnel and a damaged zone with a depth of around 4 m, which is less pronounced at both ends of the section. Two faults also appear in the evaluation of the deformation. These can also be assigned a Clar value. In addition, the lower stress in the footwall of the faults can be clearly seen, as can the transfer of the loads near the face. Overall, there is a high correlation between the methods used. In particular, the observation of the deformation provides a good indication of the geological structures encountered in relation to the effort required. On the other hand, the results are very dependent on personal assessment and experience, which requires a second method to verify the results. In this area in particular, further research results and more precise observation procedures could help to improve the quality of the data.
no embargo
Keywords: Erzberg; Subsurface; Tunnel; Geophysics; Seismics; ERT; Triaxial Test; Deformation; Point Load Test; Presserstollen; Erzberg; Untertage; Stollen; Geophysik; Seismik; ERT; Triaxialversuch; Deformation; Point Load Test; Presserstollen

Creep and creep strain recovery of a spinel forming refractory castable - measurement and simulation - Akbari, Behnam (2024)
Spinel forming (SF) and Pre-formed spinel (PS) castables are common materials in refractory linings of steel ladles in secondary steel metallurgy. In service, these materials are affected by thermo-mechanical stresses. At elevated temperatures, this leads to creep of the castables. For the optimum design of the lining, consideration of the creep behaviour is important. In the current study, the castables were characterized in dried and sintered state and compared in bulk and true density, apparent and true porosity, Young’s modulus up to 1500 °C and uniaxial compressive creep behaviour. The microstructure of both castables was investigated using SEM, additionally, mineralogical phases were analysed with XRD. For further investigation, only the SF castable was selected. During the sintering process, the SF castable showed volume expansion and formation of liquid phases. The liquid phase partially counterbalanced the volume expansion caused by the in-situ spinel formation. However, it was observed that the liquid phase formation decreases the castables Young’s modulus at high temperatures and reduces the creep resistance. Uniaxial compressive creep tests were performed at 1300, 1400, and 1500 °C for three loads per temperature. The separation of creep stages was performed with an in-house developed MATLAB code and the three-stage creep parameters were inversely evaluated using the Norton-Baily creep equation. Additionally, a statistical study was carried out to evaluate the creep parameters by different combinations of measurements. Furthermore, the material’s creep behaviour was investigated under loading/unloading (l/u) conditions. For this purpose, the experiments have been performed at 1300 °C under different loads. After defined periods, the load was reduced. In this way, several cycles were performed. It was observed that creep strain recovery occurs after load reduction. The recovery increases with holding time and the degree of unloading. It was identified that the internal stress (back-stress) was the driving force for the creep strain recovery. Finally, a non-linear kinematic hardening model (Chaboche) was applied to simulate the creep strain recovery behaviour. The model fits the experimentally observed creep strain for different creep periods and unloading degrees with one parameter series. However, further work is necessary to automatize the parameter determination.
no embargo
Keywords: Feuerfest; Spinellbildendes Gießmaterial; Kriechen; Kriechdehnungsserholung; Refractory; Spinel-forming castable; Creep; Creep strain recovery

Decarbonization of Industrial Logistics - Miklautsch-Breznik, Philipp (Understanding and Supporting Strategic and Operational Initiatives, 2024)
According to the recent report by the Intergovernmental Panel on Climate Change, the decisions made about reducing greenhouse gas emissions during the next decade will have a definitive impact on how severe the consequences of climate change will become. As all corners of the world have agreed that the worst-case scenarios presented by the IPCC and other research institutions are not desirable for human well-being, all countries, regions, sectors, companies, and other economic and non-economic entities have been or will be required to meet stringent emission reduction targets in the coming decades. One sector that will be hit hard by such reduction targets or emission taxes is transportation, since avoiding transportation is associated with the undesirable concept of sufficiency, and technological advances are costly and tedious. Particularly challenging is the freight transport sector, which due to its complexity and cost pressures, presents significant obstacles to decarbonization. As sustainable innovations were discovered to diffuse downstream the supply chain, one of the most important actors in the decarbonization of transportation is the transportation principal and buyer ¿ which is, for freight transportation, the freight owner. This entity determines the importance of logistics indicators such as costs, lead time, and emissions. It is exactly because of this reason that this thesis investigates the decarbonization of transportation from the industrial perspective which is commonly known as industrial logistics. Therefore, the aim of this thesis is to close the gap between the well-researched field of Green Supply Chain Management and the under-researched field of industrial logistics decarbonization. Answering four overarching research questions that were delineated from existing research contributes to the scientific body of knowledge regarding strategic and operational perspectives and provides industrial logistics practitioners with effective decision-support. Throughout the publications that emerged from this thesis, various in-depth research questions were answered, providing nuanced insights in the decision-making process in industrial logistics, thereby enhancing the understanding of these processes. Subsequently, this increased understanding of strategic and operational decisions that have already been made by industry practitioners was utilized to develop several tools that effectively support future decisions on this field by practitioners. Conclusivley, an approach on how to decarbonize industrial logistics most effectively was developed and based on the evidence gathered throughout this thesis. For the scientific community, the transdisciplinary studies conducted by the authors brought up research gaps and ideas for future directions. In brief, this thesis yields scholarly contributions that enable researchers to understand how industrial freight owners comprehend and implement decarbonization in transportation. It also provides benchmark data from Austria and offers several tools for practitioners to assess decarbonization possibilities in their Scope 3 upstream and downstream transportation activities. This thesis presents the research context and frame, delineates the overarching research questions, summarizes the scholarly publications and their contributions to answering the questions, and conclusively presents implications for practitioners and researchers.
no embargo
Keywords: Grüne Logistik; Industrie Logistik; Dekarbonisierung; Klimawandel; green logistics; industrial logistics; decarbonization; climate change

Deep Neural Energy Price Forecasting for the Hydrogen Industry - Lechner, Klemens (2024)
The HyCentA Research GmbH analyses, among other things, the technical and economic design of hydrogen plants. Since hydrogen plants are almost exclusively operated electrically, the price of electricity plays a major role in operating costs. Based on transformer models, the electricity price should be predicted for various scenarios. These scenarios consist of the electricity mix (what percentage of the electricity comes from which source), own generation and the gas price. The gas price was added to the electricity generation data because it has a major influence on the electricity price due to the merit order system. This could be observed, among other things within the Ukraine crisis (2022). In addition, these transformer models were used to identify electricity price trends depending on the type of electricity generation. As the energy system in Europe is moving towards more renewable energies, the electricity mix is also changing towards these. A strong positive trend towards lower electricity prices was observed for wind energy and biomass in particular. The opposite trend was observed for solar power generation: Electricity prices rose as solar power generation increased. However, it was observed that even small amounts of solar power in the electricity mix reduce the price of electricity. This means that the electricity price initially starts at a lower price and only rises later. The later increase could be explained by the increased need for balancing energy due to the volatile nature of solar power generation. However, this effect still is subject to further investigation.
no embargo
Keywords: Energy; Price; Forecasting; Transformer; LSTM; Long Short Term-Memory Network; Scenarioanalysis; ENTSO-E; Neural Network; Artificial Intelligence; Energy market; Day Ahead Price; Energy mix; Gas price; Energy; Price; Forecasting; Transformer; LSTM; Long Short Term-Memory Network; Scenarioanalysis; ENTSO-E; Neural Network; Artificial Intelligence; Energy market; Day Ahead Price; Energy mix; Gas price

Design and characterization of novel Zr-Al-Fe-Y metallic glasses with nanoscale phase separation - Singh, Devinder; Parthiban, Ramasamy; Jelinek, Anna; Bhattacharya, Rahul; Chen, Zhuo; Fellner, Simon; Gammer, Christoph; Zhang, Zaoli; Eckert, Jürgen (Materialia, 2024)

Detektion von CO, CO2, NO, NO2 und Schwebestaub im Rahmen des IGNITE-Projektes - Stocker, Philipp (2024)
Die Auswirkungen des Klimawandels sind global durch eine Zunahme und das Ausmaß von Naturkatastrophen zu beobachten. In Österreich kommt es im Zuge der Klimaerwärmung vermehrt zu Waldbränden, welche neben wirtschaftlichen auch weitreichende negative Folgen für die Tier- und Pflanzenwelt darstellen. Die vorliegende Arbeit entstand im Rahmen des IGNITE Projektes, das darauf abzielt, die Abschätzung der Entstehungsgefahr von Waldbränden in Österreich zu verbessern. Im Zuge des Projektes wurde ein großflächiger Waldbrand Versuch durchgeführt und die daraus resultierenden gesundheitlichen Gefahren von Waldbränden auf Menschen analysiert. Dazu wurden umfassende Messungen von Gasen (CO, CO2, NO, NO2) sowie vom für die Atemwege potenziell gefährlichen Schwebestaub vorgenommen. Diese Daten wurden zur Ermittlung der Gefährdung für den Menschen mit den jeweils zulässigen Grenzwerten abgeglichen. Zusätzlich wurden die Einflussfaktoren, welche für einen Waldbrand und dessen Ausbreitung eine essenzielle Rolle spielen, ermittelt, da diese wiederum direkte Auswirkungen auf die gemessenen Werte der Gase und des Schwebestaubes haben. Dabei zeigen die Auswertungen der Messergebnisse, dass vor allem die gesundheitlichen Grenzwerte von Kohlenmonoxid im unmittelbaren Umfeld des Brandes bei weitem überschritten wurden. Ebenfalls überschritten die gemessenen Werte der Schwebestaubkonzentrationen im Nahbereich des Brandes die zulässigen Schwellenwerte. Über den gesamten Brandverlauf war zu beobachten, dass sich mit der Entfernung zum Brandherd die gemessene Schadstoffkonzentration durch die Verdünnung der Schadstoffe mit der Umgebungsluft verringerte und somit keine Grenzwerte überschritten wurden.
nicht gesperrt
Keywords: Fire test; Pollutant measurement; CO2; CO; NO; NO2; Fire; Dust particles; Brandversuch; Schadstoffmessung; CO2; CO; NO; NO2; Brand; Staubpartikel

Development of Innovative Recycling Processes for Mineral Wool Waste - Sattler, Theresa Magdalena (2024)
The present doctoral thesis comprises recovery and recycling options for mineral wool waste along the waste hierarchy. The aim of this thesis was the development of innovative landfilling solutions through processing of the waste stream, recovery of mineral wool waste in backfilling and recycling in the cement industry, and a circular solution with a closed loop scenario for the waste in and glass/stone wool industries. Obtained results are presented in the five publications and the supplementary chapters found in the appendix. The recycling of mineral wool waste is not yet conducted in Austria due to economic inefficiency, technical challenges and suspected health issues. Some recycling and processing options already exist however; other options are investigated in the RecyMin project, which compares various recycling methods in regard to environmental and economic impact. In a study researching landfilling, three scenarios for the conditioning of rock wool for landfilling are compared. The performance of the different sample bodies under landfill conditions are simulated at the lab scale by cyclic loading along with the monitoring of the deformation during the experiment and the graphical derivation of the Young¿s modulus. The results show that a combination of comminution and cement-supported briquetting significantly increases the geotechnical performance of mineral wool waste with respect to landfilling. Mineral wool waste can be used together with an inorganic binder as backfill material. Corresponding recipes indicate the compliance with all requirements. Research on the recycling of mineral wool waste to produce a supplementary cementitious material shows that materials obtained from thermochemical treatment of mineral wool waste with other secondary raw materials fulfill the performance requirements regarding an alternative binder component. The circular route investigated to recycle mineral wool waste into new mineral wool showed that valuable and limited landfill volume can be conserved and the reduction of primary resource consumption and CO2 emissions is possible. The solubility-controlling mechanisms of mineral wools were investigated using pH-dependent leaching tests according to ÖNORM EN 14429 and hydrogeochemical models (LeachXS/Orchestra). For the Al-rich samples, the precipitation of the mineral phase wairakite is suggested to control the leaching, for the Al-poor sample, the precipitation of talc yields to leachable concentrations of Silicon at a pH value of 10. The thermochemical treatment using correction materials to adjust the chemical composition of the mineral wool that was followed by rapid cooling through a spinning process revealed the possibility of a closed loop scenario for mineral wool waste. The present doctoral thesis deepens the understanding regarding mineral wool waste in general and it´s recovery and recycling options in Austria on a broad and fundamental approach. The results gained through the RecyMin project open up numerous future paths facilitating recycling of mineral wool waste.
no embargo
Keywords: mineral wool waste; recycling; recovery; circular economy; waste management; closed loop scenario; Mineralwolleabfall; Recycling; Verwertung; Kreislaufwirtschaft; Abfallwirtschaft; Abfalltechnik

Development of a logistics concept for strategic plant development - Dehzani, Samira (2024)
Ramping up production capacity significantly influences a company's existing structures and logistics processes, often calling for necessary adaptations. Identifying the specific areas in need of change and devising cost-efficient ways to implement these modifications are crucial steps. This master thesis is founded on a real project at the Göss brewery, focusing on increasing the current production capacity for the bottle line. The reconstruction of the bottle line is scheduled to be completed by 2025, with a projected 38% production increase by 2027 compared to 2023. The study entails the development of a strategic concept for expanding the logistics area, adjusting the warehouse layout, optimizing processes and traffic flows, and adapting warehouse storage capacity. The initial phase involved compiling data on the current warehouse layout, logistics processes, and traffic flows. This data underwent analysis employing warehouse management techniques, aimed at identifying bottlenecks and addressing any issues in need of resolution. Subsequently, considering the projected production increase, modifications to the warehouse layout were proposed to accommodate the necessary capacity, alongside enhancements to logistics processes including traffic flows. Additionally, the introduction of alternative primary transport options via trains was recommended. Comparative assessments were made between these proposed changes and the current configurations. In instances with multiple proposed alternatives, a detailed evaluation of these options was conducted, to select the most effective scenario. The conducted work has been supported by relevant literature in the respective field.
no embargo
Keywords: Lagerlayout; Logistikprozesse; Verkehrsflüssen; ABC Analyse; XYZ Analyse; Warehouse layout; Logistics processes; Traffic flow; ABC analysis; XYZ analysis

Development of a quantitative risk assessment method to address the rock mechanics issues of applying TBMs in deep mines - Narimani Dehnavi, Roohollah (2024)
For fast roadway development in deep underground mining, Tunnel Boring Machines are sometimes brought into operation. However, such machines might get entrapped if squeezing behavior develops and the machine advance rate is not high enough because of breakdowns. This research investigates the suitability of different types of Tunnel Boring Machines for development of infrastructure in deep mines and tunneling projects, with an emphasis on geological risks including squeezing and rockburst. The main consequences linked to these hazards are identified as worker injuries and support system and equipment damage in regions susceptible to rockbursts, and occurrences of shield jamming, support system damage, and challenges related to gripper bracing in squeezing grounds. In pursuit of the primary objective of this research, a probabilistic approach is used to quantitatively assess these consequences, leading to the development of an index called the TBM Risk Index, which assesses the cumulative effect of geological risks and mitigating measures. To conduct an initial evaluation of shield jamming, as the most critical consequence in squeezing scenarios, a combination of parametric studies based on pre-conducted 3D numerical models and an approach derived from convergence confinement (CC) concept were used. The adapted convergence confinement method was also employed to assess the risk of support system damage. As for the rockburst consequences, the procedure highly relies on factors such as rockburst intensity and location, which are notably challenging to anticipate. To analyze these risks, preliminary rockburst prediction tools together with a probabilistic approach based on data from a relevant project were applied. The methodologies introduced in this research were implemented in two primary case studies, each focusing on a specific category of geological risks, leading to the following key findings: The case study with only squeezing consequences highlighted the effectiveness of a single-shielded TBM with shield lubrication in mitigating the risk. On the contrary, the case study with rockburst hazards demonstrated the higher risks associated with shorter shields in rockburst-prone areas. Recognizing the uniqueness of each individual project, the research considered multiple hypothetical scenarios with varying proportions of squeezing grounds, areas susceptible to rockbursts, and regions characterized as normal grounds. Using the introduced TBM risk index, insights were gained for an optimum decision to be made between different available machines and mitigating measures. In scenarios with both squeezing and rockburst risks of roughly the same percentage, a single-shielded TBM with lubrication and a gripper TBM with associated mitigating measures were shown to have the lowest extent of rock mechanics issues. When rockburst risk is predominant, shielded TBMs are the preferred option, reducing exposure to seismic events. In scenarios with predominant squeezing grounds, gripper TBMs had the lowest TBM risk index. However, it is noteworthy that in severely squeezing grounds with prevalent squeezing proportion, the application of TBMs are generally questionable and conventional tunneling must be considered instead.
no embargo
Keywords: TBM risk index; Squeezing; Rockburst; shield jamming; Probabilistic approach; TBM-Risikoindex; Bodenquetschung; Gebirgsschlag; Schildverklemmung; Probabilistischer Ansatz

Development of high entropy alloy thin films for hydrogen permeation barriers - Kirchmair, Magdalena (2024)
The central role of hydrogen in the ongoing global energy transition underlines the urgency of developing robust material concepts for the hydrogen economy and infrastructure to ensure a safe and efficient handling of hydrogen. Due to its remarkable strength and high toughness, steel is the most commonly used material in all areas of hydrogen technology, including generation, storage, transportation, and utilization. High alloyed steels such as austenitic stainless steels are favored for this kind of application due to their beneficial properties, but their high costs stimulate the search for alternative options. Low alloyed steels provide a more economical option regarding costs, but they suffer from increased susceptibility to hydrogen embrittlement (HE), a phenomenon that leads to degradation of the mechanical properties due to hydrogen diffusion. Hydrogen permeation barriers (HPBs) have emerged as promising solutions to reduce the risks of HE. Several materials, including metals, nitrides and oxides have been suggested as suitable HPBs. High entropy alloys (HEAs), representing a rather new material class, show also promising properties for the use as HPBs. HEAs, are gaining increased attention in the field of engineering and materials science, since as a result of their multi-principal element design concept they exhibit exceptional mechanical, physical and chemical properties. They benefit from their so-called HEA core effects, where for the application as HPB the sluggish diffusion effect is of particular importance. This thesis delves into the scope of HEA thin films, with special emphasis on MoNbTaW-based HEAs supplemented by a fifth element, Ti or Zr, termed as refractory high entropy alloys (RHEAs). The RHEA thin film HPBs are synthesized by two different physical vapor deposition (PVD) methods, direct current magnetron sputtering (DCMS) and high-power impulse magnetron sputtering (HiPIMS) with the aim to reduce HE in steel substrates. In addition, a TiN film grown by DCMS, representing an already well-established coating system, serves as reference material. The experimental results highlight the differences in terms of deposition rates, elemental composition, residual stresses, and microstructural features depending on the deposition technique, parameters and employed film system. The HPB efficiency of the films is evaluated by using a recently introduced in-situ electrochemical nanoindentation method, applying a side charging setup. The findings from the in-situ nanoindentation measurements indicate that the MoNbTaWZr thin film deposited via HiPIMS could be a promising prospect for HPB applications, since during hydrogen charging no hardness increase within the steel substrate can be observed. However, some RHEA films exhibit rather poor adhesion and thus show only limited HPB performance. This study provides the fundamental basis for future investigations to assess the full potential of HEA thin films for HPBs applications.
no embargo
Keywords: high entropy alloys; refractory high entropy alloys; hydrogen permeation barriers; physical vapor deposition; direct current magnetron sputtering; high-power impulse magnetron sputtering; in-situ electrochemical nanoindentation; side charging setup; MoNbTaTiW; MoNbTaWZr; TiN; thin film; Hochentropielegierung; Refraktär-Hochentropielegierungen; Wasserstoffpermeationsbarrieren; physikalischen Gasphasenabscheidung; Gleichstrom-Magnetronsputtern; Hochleistungsimpuls-Magnetronsputtern; in-situ elektrochemischen Nanoindentationsmethode; side charging setup; MoNbTaTiW; MoNbTaWZr; TiN; Dünnschicht

Digitalisierung der Abschlagskarten für den Bergbau Webing der Moldan GmbH mittels Surpac - Burgschmidt, Viktor (2024)
Die Moldan Baustoffe GmbH & Co KG betreibt im Gemeindegebiet von Abtenau in Salzburg den untertägigen Gipsbergbau Webing. Dieser ist historisch gewachsen; Die Art der Abschlagserfassung erfolgt noch traditionell auf Papier, obwohl jeder Abschlag beprobt und im Labor analysiert wird. Als Optimierungsmöglichkeit der erfahrungsbasierten Abbauplanung wird die Erstellung einer digitalen Datenbank mit dazugehörigem Blockmodell angestrebt. Jene erfolgte im Rahmen dieser Diplomarbeit. Die Dokumentation auf Papier wurde koordinatenreferenziert in eine Exceltabelle übertragen, somit besteht eine einfach zu pflegende Datenbasis, auf Grundlage derer diverse Auswertungen und Visualisierungen erfolgen können. Aus dieser wurde eine mit der verwendeten Software GEOVIA Surpac kompatible Datenbank erstellt. Weiters erfolgten die Erstellung eines Lagerstättenkörpers, einer Stringdatei, die die erfassten Daten repräsentiert, und mehrerer Variogramme. Diese bildeten die Grundlage zur Erstellung des finalen Blockmodells, in dem mittels Ordinary Kriging eine geostatistische Annäherung an die Wirklichkeit erfolgte. Dieses Modell korreliert in den relevanten Bereichen nahe des bestehenden Abbaus sehr gut mit der Wirklichkeit. Da am Standort wenig Erfahrung und keine Lizenz für GEOVIA Surpac vorhanden sind wurden zusätzlich nach Gehalten gefärbte Grafiken der einzelnen Sohlniveaus erstellt. Mithilfe dieser kann das Ergebnis der Lagerstättenmodellierung beispielsweise in AutoCAD hinterlegt werden. Abschließend wurde noch eine rein datenbasierte Interpretation des Lagerstättenmodells angestellt. Hier konnten einige relevante Bereiche identifiziert werden, jedoch erfolgte dies ohne Rücksicht auf die tatsächlichen geologischen Gegebenheiten vor Ort.
gesperrt bis 29-01-2029
Keywords: Bergbaukarten; Digitalisierung; Surpac; Markscheidewesen; Mine mapping; Digitalisation; Surpac; Surveying

Digitalization of Displacement of non-Newtonian and Newtonian Fluids in Horizontal Annuli - Shams Eshaghi, Sahand (2024)
The fluid displacement is being assessed and evaluated via digital sensing of involved parameters such as flow rate and pressure in lab-scale apparatus known as a flow loop. Flow loop replicates the geometry of the borehole and the casing/drill pipe in a lab scale (5 meters) manner. The thesis has 1 major objective and 1 minor objective. The major objective is to compare experimental results with a commercial software. The series of tests included 6 different non-Newtonian fluids at 4 selected flow rates and 3 selected standoffs leading to 72 experimental tests. During the test, parameters such as flow rate and pressure were recorded by sensors in real time and the processed results were compared with software simulation. Since a picture is more than a thousand words, the interface between fluids is tracked and digitalized by digital cameras (2 high-speed and 1 GO PRO). The visual tracking of the interface provides a better understanding of interaction between two fluids during displacement process in real time. The displacing fluids are designed and provided by a client and the displaced fluid at this phase of the experiment is water. Because horizontal well has more complexity than vertical and inclined, the horizontal was selected for the first phase, but in the next phases, other inclinations will be included for tests. Amongst the 6 fluids selected for displacement, 3 of them have translucent optical properties and 3 others are opaque (Barite as weight up). The water as displaced fluid was placed in the annulus and displacing fluid was pumped from the bottom of the flow loop to the annulus. The fluids had a density ranging from 8.6 to 12.8 ppg, from low to high viscosity and yield point. As a minor objective, the digitalized interface tracking was compared with available literature to investigate the validity of the observed interface. The content of the thesis is summarized in 6 chapters. The first chapter gives an overview of the issue and the objective. The second chapter describes the available literature review and previous studies. In the third chapter, the flow loop technical setup and configuration and capability are put forward. The methodology and calibration of sensors and digital tools were described in the fourth chapter. Results are discussed in the fifth chapter and the conclusion and alternative solutions are explained in the sixth chapter.
embargoed until 10-05-2029
Keywords: digitalization; flow loop; displacement; digitalization; flow loop; displacement

Digitalization of an Underground gypsum mine and generation of a 3D model using QGIS under the supervision of Moldan Baustoffe GmbH & CO Kg - Kovacic, Jurica-Boris (2024)
Digitalization is a vital factor for mining efficiency, safety and sustainability. Emerging new technologies come in the form of autonomous haulage, drilling, and conveying, and in almost every new integrated trend there is often major linking with GIS technology. Since mining operations cannot operate without georeferenced data the keen first step is to preserve the data that we have and transform it in a form, suited for simpler day to day usage. The aim of this thesis in collaboration with Moldan Baustoffe GmbH &Co KG is to help gather and transform data sets and underground maps with material content of their mine into digital. In order to have a better understanding, GIS history and applications will also be explained. After obtaining data sets we use various freely available software to try and display or manipulate data. The goal of this thesis is to combine the data obtained from the ¿Webing¿ underground mine and to display the mine in 3D combined with its core drillings. This will be performed in QGIS software. The simplicity of the software as well as its open-source platform provides a wide range of properties. For the sake of future use of the demonstrated system, a handbook manual with all the necessary steps needed for the program and visualization of the 3D model will be incorporated within the thesis. Serving future purposes for all operating staff members.
no embargo
Keywords: Digitalisierung; Bergbau; Bergbau Planung; QGIS Software; Digitalization; Mining; Mine planing; QGIS software

Direct fabrication of tailored metal-carbon nanocomposites made by two-photon polymerization - Jahn, Marco Paul (2024)
Additive manufacturing, also widely referred to as 3D printing, is an emerging and innovative manufacturing process that differs fundamentally from conventional manufacturing processes. In research and industry, it opens up completely new possibilities for scientists. 3D printing using two-photon polymerization is one of the photopolymerization processes, whereby extremely small components can be produced. In this work, two-photon polymerization is used to produce nanoscale deformation structures as well as nanocomposite materials. The deformation structures show very good deformation behavior and offer the possibility of testing a large number of samples in a short time. Other processes, such as pyrolysis, were used in the successful production of composite materials. The work shows that two-photon polymerization is an ideal tool for producing defined model systems.
no embargo
Keywords: Two-photon polymerization; Two-photon absorption; PVD; Magnetron sputtering; Pyroylsis; High throughput TEM testing; In situ TEM testing; Zwei-Photonen-Polymerisation; Zwei-Photonen-Absorption; PVD; Magnetron Sputtern; Pyrolyse; Hochdurchsatz-TEM-Prüfung; In-situ-TEM Prüfung

Disruption und Resilienz - Renner, Renate (Subjektives Erleben der Amokfahrt in Graz aus Sicht der psychosozialen Notfallversorgung, 2024)
Keywords: Resilienz; Psychosoziale Notfallversorgung; Krisenmanagement; Amok; Katastrophe; Disruption

Dynamic wetting phenomena of CaO-SiO2-Al2O3-Li2O slag on magnesia - Ijaz, Muhammad Usama (2024)
This thesis aims to investigate the wetting behavior of CaO-SiO2-Al2O3-Li2O slags on magnesia refractory, studying the impact of slag compositions and temperatures on the wetting behavior. The study focuses on the influence of Li2O on wetting behavior of the slag. In the initial phase, slag samples were prepared in the laboratory with varying Li2O content while keeping the basicity and alumina content fixed. The powders of the slag components were mixed using a Turbula mixer. For pre-melting of the samples, a vertical tube furnace at elevated temperatures was used. Simultaneously, substrates were prepared by cutting and polishing magnesia chromite refractory materials. The viscosities of the slags as a function of lithium oxide content and temperature were calculated using the FactSage 8.2 viscosity module. Additionally, the melting temperatures of the slag systems were determined through thermodynamic simulations of FactSage 8.2. A further comparative study between the melting temperatures obtained from thermodynamic simulations and derived from the drop profiles of the slags was carried out. To conduct in-situ measurements of contact angle, smaller slag pieces were precisely deposited on the substrate through the sessile drop method. The experiment was carried out using a Thermo-Optical Dynamic Wetting Apparatus (TODWA). A high-speed camera for the recording and analysis of drop profiles was attached. The experiments involved heating the samples to a temperature of 1350°C. The spreading of the slags was observed and recorded for analysis of melting temperature, and wetting behavior of slags at higher temperatures. Subsequently, high-speed camera images were subjected to detailed analysis using the image processing software SCA-20, to accurately measure contact angles. The increasing of lithium oxide content enhanced the wettability of the slags. Across all slag systems, a consistent wetting phenomenon was observed as characterized by higher contact angles at lower temperatures, followed by drastic spreading at higher temperatures. Also, higher Li2O content marked notable change in contact angle and slag spreading at lower temperatures. Slag A (0% Li2O) initiated spreading at 1235°C, while Slag B (2% Li2O) exhibited spreading at an even lower temperature of 1180°C. Further increases in Li2O content resulted in even earlier slag spreading, e.g. Slag F (10% Li2O) showed spreading at approximately 1100°C. Following in-situ TODWA analysis, the slag samples were prepared for subsequent microstructural and compositional analysis. Detailed analysis was carried out using scanning electron microscopy (SEM) and compositional analysis using an EDS detector. Increasing lithium oxide content enhanced the wettability of the slags. Deposition of slag A (0% Li2O) on the refractory resulted in an intermediate layer of 405 µm thickness, while the deposition of slag B (2% Li2O) resulted in a layer of just 120 µm. As lithium oxide content increased further, the thickness of the intermediate layer showed a consistent decrease. An increase in lithium oxide content also intensified slag penetration into the refractory and the dissolution of refractory components along its grain boundaries.
no embargo
Keywords: Schlacken; Basizität; Benetzbarkeit; (BSE)Rückgestreutes Elektron; (EDS)Energiedispersive Röntgenspektroskopie; (FTIR)Fourier-Transformations-Infrarot; (LIBs)Lithium-Ionen-Batterien; (SEM)Rasterelektronenmikroskop; (TODWA)Thermo-optisches dynamisches Benetzungsgerät; (θ)Kontaktwinkel; (θa)Fortschreitender Kontaktwinkel; (θr)Zurückweichender Kontaktwinkel; (ρ)Dichte; (g)Erdbeschleunigung; (H)Kontaktwinkel-Hysterese; (pO2)Partialdruck von Sauerstoff; (σ)Oberflächenfreie Energie; (σsv)Oberflächenfreie Energie des Festkörpers; (σlv)Oberflächenfreie Energie der Flüssigkeit; (σsl)Oberflächenfreie Energie der Fest-Flüssigkeits-Grenzfläche; (Wsl)Arbeit der Adhäsion; Slags; Basicity; Wettability; (BSE)Back Scattered Electron; (EDS)Energy Dispersive X-ray Spectroscopy; (FTIR)Fourier Transform Infrared; (LIBs)Lithium-Ion Batteries; (SEM)Scanning Electron Microscope; (TODWA)Thermo-Optical Dynamic Wetting Apparatus; (θ)Contact Angle; (θa)Advancing Contact Angle; (θr)Receding Contact Angle; (ρ)Density; (g)Gravitational acceleration; (H)Contact Angle Hysteresis; (pO2)Partial pressure of Oxygen; (σ)Surface Free Energy; (σsv)Surface Free Energy of solid; (σlv)Surface Free Energy of liquid; (σsl)Surface free Energy of Solid-Liquid Interface; (Wsl)Work of Adhesion

Economic-Technical Evaluation of Insulated Tubings for Completions in Geothermal Energy Applications - Mark, Daniel (2024)
Energy that is obtained from geothermal sources is considered as renewable energy and therefore one of the technologies that will enable us in the future to largely or, in the best case, completely replace climate-damaging fossil energy sources, which are oil, natural gas and coal. Since geothermal energy competes with other renewable energy sources, it is necessary to achieve a technical and economic optimum for the system components. The master's thesis deals with the question of whether the use of insulated pipes in the borehole offers economic added value compared to the generally used, uninsulated standard pipes, which are also used in the oil and gas industry. For this purpose, different insulation solutions are considered regarding heat transfer behavior and friction losses. The master's thesis is divided into a theoretical and a practical part. In the first section of the theoretical part, geothermal energy is described in a technical manner, and the basics of heat transfer are discussed. The particular focus here is on the description of the technologies currently most used to generate geothermal energy and the derivation of losses through heat transfer mechanisms and pipe friction. The second section of the theoretical part takes a look at the market for alternative energy sources, in particular geothermal energy. Economic indicators are also mentioned that can be linked to the potential increase in efficiency resulting from the insulation of pipes. In the first section of practical part, different insulation solutions are examined technically and economically in two different theoretical models. The former model is an application in which the production probe is separated from the injection probe. The other model represents a "single borehole" solution in which the injection probe and production probe are the same. Some fictitious but realistic values were used as input values, which is due to the aim of achieving results that are as general as possible. It turns out that certain insulations can deliver significant added value in terms of technical performance and economic outputs, despite considerable additional costs. The second section of the practical part deals with the question of whether pipes made of steel have added value compared to those made of plastic in near-surface geothermal energy applications. An evaluation scheme was used for this purpose, which in the end clearly negated the question.
embargoed until 17-10-2028
Keywords: Geothermal energy; optimization; heat loss; insulation; tubings; economic consideration; Geothermie; Optimierung; Wärmeverlust; Isolation; Rohre; Wirtschaftlichkeitsbetrachtung

Effect of Nb incorporation in Mo2BC coatings on structural and mechanical properties—Ab initio modelling and experiment - Zenisek, Jaroslav; Soucek, P.; Ondračka, Pavel; Czigány, Zsolt; Buršíková, V.; Holec, David; Balazsi, K.; Vasina, Petr (Acta materialia, 2024)

Effect of airborne particle abrasion and regeneration firing on the strength of 3D-printed 3Y and 5Y zirconia ceramics - Mirt, Tadej; Kocjan, Andraž; Hofer, Anna-Katharina; Schwentenwein, Martin; Ivekovic, Aljaz; Bermejo, Raul; Jevnikar, Peter (Dental Materials, 2024)
Objectives: This study aimed to assess the effect of airborne particle abrasion (APA) and regeneration firing (RF) on the subsurface damage and strength distribution of 3D-printed 3Y-TZP and 5Y-PSZ zirconia parts for dental applications. Methods: Disc-shaped specimens were prepared using vat photopolymerization (VPP) technology from 3Y and 5Y zirconia ceramics, followed by thermal debinding and sintering. APA treatment with 50 µm Al 2O 3 particles and RF at 1000 °C for 15 min were applied. Microstructural analysis was conducted using FIB-SEM, and XRD analysis determined crystalline phase content. Biaxial flexural strength was measured using the ball on three balls method and analyzed with Weibull statistics. ANOVA and Tukey HSD test were employed to compare strength differences between groups. Results: APA treatment increased the flexural strength of the 3Y specimens but decreased it for the 5Y specimens. RF treatment reversed the effect, restoring the strength to as-sintered levels for both materials. APA-treated 3Y specimens exhibited characteristic strength values above 1400 MPa, attributed to phase-transformation toughening. As sintered 5Y specimens showed strength values above 600 MPa. APA treatment increased the Weibull modulus of the 5Y specimens, indicating a narrower defect size distribution. Significance: The study demonstrates that the impact of APA and RF treatments on the mechanical properties and reliability of VPP-fabricated 3Y-TZP and 5Y-PSZ ceramics is comparable to conventionally prepared zirconia. VPP technology for 3D printing provides a viable approach for future manufacturing of dental restorations with potential clinical applications.
Publisher Copyright: © 2023 The Authors
Keywords: Airborne-particle abrasion; Biaxial flexural strength; Dental zirconia; Regeneration firing; Vat photopolymerization

Effect of intercritical annealing on the microstructure and mechanical properties of a PH 13-8 Mo maraging steel - Rosenauer, Andreas; Teusl, Sebastian; Landefeld, Andreas; Brandl, Dominik; Ressel, Gerald; Hönigmann, Thomas; Stadler, Manfred; Turk, Christoph; Maawad, Emad; Stockinger, Martin (Materials science and engineering: A, Structural materials: properties, microstructure and processing, 2024)

Effect of local loading on microstructure and enhanced mechanical property of large complex castings prepared by Al–Si–Fe–Mn–Mg–Cu alloy during squeeze casting - Meng, Shuancheng; Gao, Minqiang; Liu, Yan; Yang, Li; Ma, Huan; LI, Jiehua; Wang, Jianjun; Guan, Renguo (JOURNAL OF MATERIALS SCIENCE & TECHNOLOGY, 2024)

Effects of Printing Direction and Multi-material on Hardness of Additively Manufactured Thermoplastic Elastomers for Comfortable Orthoses and Prostheses - Michalec, Paweł; Varsavas, Sakine Deniz; Arbeiter, Florian; Weidner, Robert; Faller, Lisa-Marie (Springer International Publishing, 2024)
Medical assistive devices such as orthoses and prostheses (O P) are essential for people with physical limitations to provide them with more active, productive and independent lives. However, studies show that the rejection rate of O P is high, mostly due to the lack of comfort caused by improper fitting and the usage of rigid materials. Additive manufacturing makes possible development of a fully customized O P with soft materials what can result in better fitting and more homogeneous distribution of loads on the limb. Therefore, in this study, the effects of printing direction on the hardness, and the thickness ratio between soft materials in multi-material printed samples on the combined hardness are investigated. The following materials are used to produce samples with the extrusion-based 3D-printer Pollen New PAM Series P: PLA, TPE 45 Shore-A and TPE 30 Shore-00. Furthermore, 12 specimens are printed and tested with the Shore hardness method. As a result, the printing direction does not cause a significant change in the final hardness of the soft materials. The increased TPE 30 Shore-00 layer's height in combined materials changes hardness from 68.9 to 48.0 Shore-00. In addition, the increased TPE 45 Shore-A thickness increases combined hardness from 60.9 to 76.4 Shore-00. The change in thickness of both materials causes almost linear change in combined hardness. These results can be used to achieve the optimum comfort for individuals and a rise in the acceptance rate of O P.

Ein mineralisches Bindemittel auf Basis Olivin - Lackner, Lena (2024)
Die CO2-Bilanz von Prozessen und Produkten ist in den letzten Jahren durch die anhaltende Klimaproblematik vermehrt in den Fokus gerückt. Die Herstellung der für die moderne Bauindustrie essenziellen Zemente und Zementprodukte ist mit einem erheblichen Energieaufwand und CO2-Emissionen verbunden. Um Alternativen für die herkömmlichen Produktionswege und Produkte zu finden, wird die Eignung von Olivin ((Mg,Fe)2SiO4) und Oxalsäure Dihydrat (C2H2O4 · 2 H2O) als Rohstoffe für Säure-Base Zemente untersucht. Der verwendete Olivin wurde gebrochen, gemahlen und die Mahlfeinheit mittels Blaine-Gerät und lasergranulometrischer Messung überprüft. Die Dichte des Olivins wurde mittels Gaspyknometer bestimmt. Der Chemismus und die Mineralzusammensetzung des Rohstoffes wurde röntgendiffraktometrisch und durch energiedispersive Röntgenspektroskopie ermittelt und das Gefüge im Auflichtmikroskop und Rasterelektronenmikroskop untersucht. Im weiteren Verlauf wurden Mischungen aus Olivin, Oxalsäure und deionisiertem Wasser hergestellt, die in einer folierten Stahlform zu 20x20x20 mm großen Würfeln geformt wurden. Durch Veränderung der Parameter (spezifische Oberfläche, Massenverhältnis Olivin zu Oxalsäure und W/C-Wert) wurden unterschiedliche Mischungen hergestellt. Der Einfluss der Mischungsreihenfolge der Komponenten sowie der Einfluss der Lagerungsbedingungen auf die Ergebnisse wurden analysiert. Das Erstarrungsende der einzelnen Mischungen wurde mittels Vicat-Nadelversuch bestimmt und die Würfel hinsichtlich ihrer Druckfestigkeit und Volumen- sowie Längenänderungen bei der Trocknung und Lagerung untersucht. Zusätzlich zu den Versuchen mit Olivin wurden Wollastonit (CaSiO3) und Schlacke als Rohstoffe erprobt, eine Mörtelmischung aus Olivin und Quarzsand hergestellt und ein Vergleichsversuch zur Wasserbeständigkeit mit CEM II durchgeführt. Im Verlauf dieser Arbeit wurden darüber hinaus Formen aus unterschiedlichen Materialien getestet, da sich eine Stahlform (unfoliert) nicht für diese Art von Bindemittel eignet. Die Versuchsplanung basierend auf dem Box-Behnken Design wurde mittels MATLAB durchgeführt und die Ergebnisse der Versuchsreihe graphisch dargestellt. Zur weiteren Analyse der Ergebnisse wurde eine Korrelationsmatrix in Microsoft-Excel erstellt. Folgende Erkenntnisse konnten gewonnen werden: Vor allem bei einem niedrigen Olivin zu Oxalsäure Verhältnis kann eine hohe Volums- / Längenzunahme der Würfel beim Erstarren beobachtet werden. Die Druckfestigkeit wird von den konkurrierenden Einflüssen der auftretenden Porosität und der Menge an gebildetem Magnesiumoxalat beeinflusst. Die Druckfestigkeit steigt mit steigender spezifischer Oberfläche der basischen Komponente (Olivin), da das Reaktionsausmaß und die bindende Komponente gesteigert wird. Die Erstarrungszeit wird insbesondere von der spezifischen Oberfläche und dem W/C-Wert beeinflusst. Der Einfluss des W/C-Werts auf die Druckfestigkeit und Erstarrungszeit ist abhängig von den anderen Parametern und es besteht keine lineare Abhängigkeit. Die höchsten Werte der Druckfestigkeit können bei hoher spezifischer Oberfläche, einem mittleren Ol/Ox-Verhältnis und einem niedrigen W/C-Wert erreicht werden.
gesperrt bis 01-02-2026
Keywords: Bindemittel; Säure-Base-Zement; Olivin; Oxalsäure; Oxalsäurezement; Alternative Baustoffe; Binders; Acid-base cement; Olivine; Oxalic acid; Oxalic acid cement; Alternative building materials

Einfluss der Rotationsparameter auf die Erstarrungsbedingungen bei mechanischem Rühren - Holzgruber, Thomas Michael (2024)
Stähle erstarren unter technischen Bedingungen, wie sie beim Block- und Stranggießen vorkommen, nahe der Oberfläche gerichtet dendritisch, das heißt, mit bevorzugter Wachstumsrichtung, entgegengesetzt zum Wärmestrom und unter Bildung von tannenbaumartigen Primärkristallen und nahe dem Kern üblicherweise aufgrund der vorherrschenden Erstarrungsbedingungen ungerichtet globulitisch. Dieses dendritische Wachstum kann zu Gunsten ungerichtet globulitischen Wachstums, infolge von Konvektionsströmungen verursacht durch Rühren, zurückgedrängt werden. Generell führt eine Fluidströmung auch zur Verringerung von Seigerungen und Porositäten infolge eines höheren Anteils globulitischer Erstarrungsstruktur. Aktueller Stand der Technik beim Stranggießen von Stahl ist das mittlerweile weit verbreitete elektromagnetische Rühren (EMS-System). Bei der Produktion sehr großer Dimensionen stößt dieses allerdings technisch an seine Grenzen, da zum Erzielen einer ausreichenden Rührwirkung extrem hohe elektrische Leistungen installiert werden müssen, insbesondere wenn man eine Rührwirkung im Kern erreichen will. Eine andere Variante stellt mechanisches Rühren dar. Thema dieser Masterarbeit ist es den Einfluss der mechanischen Rotationsbedingungen auf die Erstarrungsstruktur zu untersuchen und zu evaluieren, ob ein zumindest ähnlicher oder größerer positiver Effekt wie durch elektromagnetisches Rühren erreichbar ist. Der große Vorteil des mechanischen Rühreffekts im Vergleich zum EMS-System liegt darin, dass es an jeder Stelle im Strang oder Block zu einer erzwungenen Konvektion an der Fest-Flüssig-Grenzfläche über die gesamte Länge, unabhängig der Größendimensionen, bis ins Zentrum kommt. Im praktischen Teil wurden zwei Versuchsreihen mit zwei unterschiedlichen Werkstoffen und insgesamt zwölf Versuchen durchgeführt. Die Versuche unterschieden sich in Rotationsart (nicht rotierend, kontinuierlich rotierend, alternierend rotierend), Rotationsgeschwindigkeit und Periodendauer. Zumal sowohl Abstichtemperatur als auch Überhitzung bei allen Versuchen gleich waren, konnte der Einfluss der beiden Rotationsparameter Geschwindigkeit und Periodendauer hervorragend herausgearbeitet werden. Die Schmelzversuche wurden in Zusammenarbeit mit der Firma INTECO melting and casting GmbH am Lehrstuhl für Eisen- und Stahlmetallurgie auf der Montanuniversität Leoben abgewickelt. In der ersten Versuchsreihe wurde der Werkstoff 1.4301 untersucht. Die Ergebnisse zeigten, dass bei allen fünf Versuchen der erhoffte Effekt des Rotierens auf die Bildung einer globulitischen Zone ausblieb. Dies lässt sich darauf zurückführen, dass der Austenit, unabhängig davon, ob der Primärferrit globulitisch oder kolumnar gebildet wird, ein kolumnares Korn bildet. Die Zusammenschau der gewonnenen Erkenntnisse lässt dennoch den Schluss zu, dass durch alternierendes Rotieren ein deutlich feineres Gefüge als bei den beiden Referenzversuchen eingestellt werden kann. Der größte positive Effekt kann durch die höchste Rotationsgeschwindigkeit und niedrigste Periodendauer erzielt werden. Um die Ergebnisse der ersten Versuchsreihe zu verifizieren und den Einfluss des Rotierens auf die Bildung einer globulitischen Zone analysieren zu können, war eine zweite Versuchsreihe notwendig. In der zweiten Versuchsreihe wurde der Werkstoff 1.4547 untersucht. Im Unterschied zur ersten Versuchsreihe kommt es bei der zweiten Versuchsreihe schon bei den beiden Referenzversuchen erwartungsgemäß zur Ausbildung einer globulitischen Zone mit groben Körnern im Zentrum. Infolge des alternierenden Rotierens sind sowohl eine erhebliche Verbesserung der Makrostruktur als auch ein sehr feines globulitisches Gefüge der Rundscheiben und Längsproben festzustellen. Der größte positive Effekt ¿ hoher Anteil an globulitischer Erstarrung, kein Auftreten von Rührstreifen und Porositäten ¿ wird durch die niedrigste Rotationsgeschwindig
gesperrt bis 20-03-2029
Keywords: mechanical stirring; rotating ingot; alternating rotation; solidification structure; mechanisches Rühren; rotierender Block; alternierende Rotation; Erstarrungsstruktur

Einfluss der Zusammensetzung von Mineralfaserabfällen auf die Recyclingfähigkeit als Sekundärzumahlstoff - Seywerth, Rebecca (2024)
Durch die geänderte Deponieverordnung von 2021 wird ein österreichweites Deponierungsverbot von künstlichen Mineralfasern ab dem Jahr 2027 in Aussicht gestellt. Zu den künstlichen Mineralfasern zählt unter anderem Mineralwolle, die in erster Linie als Dämmmaterial in der Bauindustrie eingesetzt wird. Abfälle aus Mineralwollen, zu denen Glas- und Steinwolle gehören, werden in Österreich derzeit wegen mangelnder Alternativen überwiegend deponiert. Daher müssen bis 2027 Verwertungs- oder Recyclingverfahren für diesen Abfallstrom entwickelt werden. In diesem Bereich wird an der Montanuniversität Leoben im Zuge des Projektes ¿BitKOIN¿ geforscht. Ein Arbeitspaket sieht dabei vor, dass die Möglichkeit der Verwertung dieser Abfälle in der Zementindustrie untersucht wird. Dabei ist die Idee, diese durch eine thermochemische Behandlung zu einem Sekundärzumahlstoff umzuwandeln, der ähnliche Eigenschaften wie Hüttensand aufweist. Aus diesem Grund werden in der vorliegenden Arbeit Glas- und Steinwolle mit Korrekturstoffen vermengt, geschmolzen und abschließend nass granuliert. Durch diese Herangehensweise wird ein glasig erstarrtes Granulat hergestellt, das auf dessen chemische Oxidzusammensetzung und bautechnologische Anforderungen analysiert wird. Die Ergebnisse der Analysen zeigen, dass die Voraussetzungen für das Outputmaterial in Hinblick auf die chemische Zusammensetzung, den Glasgehalt und der hydraulischen Reaktivität erfüllt sind. Eine granulierte Mischung aus Flugasche, Glas- und Steinwolle mit modifizierter chemischer Zusammensetzung kann somit potenziell als Sekundärzumahlstoff in der Zementindustrie eingesetzt werden.
nicht gesperrt
Keywords: mineral fibre waste; recyclability; secondary cementitious material; glass wool; stone wool; dynamic viscosity; thermochemical treatment; binder suitability; circular economy; Mineralfaserabfälle; Recyclingfähigkeit; Sekundärzumahlstoff; Glaswolle; Steinwolle; Dynamische Viskosität; Thermochemische Behandlung; Bindemitteleignung; Kreislaufwirtschaft

Einfluss verschiedener Zwischenglühstrategien auf die Biegeeigenschaften von Al-Mg-Si-Fe-Legierungen - Mutschlechner, Stefan (2024)
Im Rahmen dieser Masterarbeit werden verschiedene Zwischenglühstrategien auf die Biegeeigenschaften von Al-Mg-Si-Fe-Legierungen untersucht, deren Basis das Legierungssystem EN-AW 6016 darstellt. Die Herstellung der zu untersuchenden Legierungen erfolgt durch das Umschmelzen der Al-Mg-Si-Legierung 6016 und dem Legieren mit Eisen, Silizium und Mangan. Ein erhöhter Gehalt an Fe bewirkt die Bildung spröder intermetallischer Primärphasen (AlFeSi-Phasen), geschuldet durch dessen geringe Löslichkeit im Al-Gitter, welche im Walzprozess fragmentieren. Jene Primärphasen des Typs AlFeSi binden bei Ihrer Bildung Silizium, weswegen in einem Teil der zu untersuchenden Systeme zusätzliches Silizium zulegiert wird. Mangan wird typischerweise eingesetzt, um die Morphologie Fe-reicher Primärphasen bei ihrer Ausbildung im Guss zu beeinflussen. Außerdem bewirkt Mangan die Bildung von Dispersoiden während der Homogenisierung. Weitere Gefügebestandteile sind die löslichen Phasen Mg2Si und Si, die eine wichtige Rolle für die Festigkeit der Legierungen spielen. Die verwendeten Zwischenglühstrategien beeinflussten die Bildung und die resultierende Morphologie von Silizium stark, was wiederum einen erheblichen Einfluss auf die Biegefähigkeit hatte. Die Mikrostruktur wurde mittels Rasterelektronenmikroskop-Aufnahmen und dem Bildbearbeitungsprogramm ImageJ analysiert, sowie durch das Computerprogramm FactSage 8.3 auf Basis der chemischen Zusammensetzung der Legierungen berechnet. Unter der Anwendung von 3-Punkt-Biegeversuchen ließen sich unterschiedlich starke Einflüsse der Gefügebestandteile auf die Biegbarkeit feststellen. Zusätzlich kam die Methode der kleinsten Quadrate zum Einsatz, um Formeln für die Vorhersage des Biegewinkels basierend auf der Phasenzusammensetzung zu entwickeln. Darüber hinaus ließ sich aus der Größe der Formelparameter die Einflussstärke jeder einzelnen Phase ableiten. Hierbei zeigte sich, dass Silizium den stärksten negativen Einfluss auf den Biegewinkel hatte.
gesperrt bis 18-05-2029
Keywords: aluminium; aluminum; EN-AW 6016; bendability; bending angle; intermediate annealing; primary phases; dispersoids; magnesium; silicon; manganese; pores; bending test; hardness measurement; scanning electron microscopy; optical microscopy; ImageJ; FactSage; method of least squares; Aluminium; EN-AW 6016; Biegbarkeit; Biegewinkel; Zwischenglühung; Primärphasen; Dispersoide; Magnesium; Silizium; Mangan; Poren; Biegeprüfung; Härtemessung; Rasterelektronenmikroskopie; Lichtmikroskopie; ImageJ; FactSage; Methode der kleinsten Quadrate

Einfluss von Farb-Masterbatches auf adhäsive, elektrische sowie flammhemmende Eigenschaften ausgewählter technischer Thermoplaste - Wehinger, Philip (2024)
Die in der Automobilindustrie eingesetzten Materialien müssen hohen Standards entsprechen. Um verschiedene Steckverbinder oder Kontaktierungen optisch zu unterscheiden, werden Bauteile unterschiedlich eingefärbt. Herkömmlicherweise werden hierfür Farb-Masterbatches verwendet, welche direkt bei der Verarbeitung an der Spritzgießmaschine dem Grundpolymer beigemischt werden. In der Vergangenheit hat sich bereits gezeigt, dass diese einen signifikanten Einfluss auf die mechanischen Eigenschaften haben. Im Zuge dieser Arbeit wird der Einfluss von Farb-Masterbatches auf die Adhäsion, die elektrischen Eigenschaften sowie die flammhemmenden Eigenschaften an verschiedenen technischen Grundpolymeren untersucht. In den Versuchsplänen wird neben dem Einfluss des Gehalts, in dem das Farb-Masterbatch zugegeben wird, auch der Einfluss des Trägermaterials untersucht. Für die Untersuchung der Adhäsion werden anhand eines Prüfplans halbe Zugstäbe hergestellt, welche in einem zweiten Schritt umspritzt werden. Die Verbundfestigkeit wird mittels Zugprüfung bestimmt. Für die elektrischen Tests werden plattenförmige Prüfkörper hergestellt, woran die elektrische Durchschlagfestigkeit sowie die Kriechstromfestigkeit getestet werden. Die Brennbarkeit wird nach UL94 (vertikal) durchgeführt. Neben dem Einfluss des Farb-Masterbatchgehalts wird ein vollfaktorieller Versuchsplan aufgestellt, mit welchem der Einfluss ausgewählter Prozessparameter auf die Brennbarkeit untersucht wird. Bei der Auswertung der Ergebnisse hat sich gezeigt, dass das Farb-Masterbatch auf die Adhäsion mit den untersuchten Gehältern nur einen untergeordneten Einfluss hat, relevanter ist die Fließfähigkeit und Materialpaarung. Auf die elektrischen Eigenschaften haben sowohl die Farbe, der Gehalt an Farb-Masterbatch als auch das Trägerpolymer, beziehungsweise die enthaltenen Pigmente, einen Einfluss gezeigt. Auch für die Brennbarkeit wurde eine Abhängigkeit vom Gehalt und den Inhaltsstoffen des Farb-Masterbatches festgestellt.
gesperrt bis 23-02-2029
Keywords: Kunststofftechnik; Thermoplaste; Flammschutz; Adhäsion; Haftung; elektrische Eigenschaften; CTI; Durchschlagfestigkeit; Kriechstromfestigkeit; technische Thermoplaste; Automobilindustrie; Werkstoffprüfung; einfärben; Masterbatches; Farbeinfluss; Polymer engineering; Thermoplastics; flame-retardant properties; adhesion; Adherence; electrical properties; CTI; dielectric strength; tracking resistance; engineering polymers; Automotive industry; material testing; coloring; masterbatches; Color influence

Einfluss von markt- und netzorientierten Ladevorgängen auf die steigende Netzbelastung verursacht durch E-Mobilität - Rock, Maximilian (2024)
Die Elektromobilität ist eine vielversprechende Technologie für die Dekarbonisierung unserer Gesellschaft, um die hoch gesteckten Klimaziele zu erreichen. Durch den steigenden Durchdringungsgrad der Elektromobilität steigt jedoch die Netzbelastung zunehmend an. Das Ziel dieser Arbeit ist aufbauend darauf die Untersuchung der Auswirkungen von markt- und netzorientierten Ladestrategien auf zwei ausgewählte Verteilnetze in der Netzebene 7. Ein ländliches Netz mit nur wenigen Verbrauchern und ein suburbanes Netz mit einer dichteren Besiedelung und mehr Verbrauchern. Die Untersuchung stützt sich auf zwei unterschiedliche Szenarien, ein marktorientiertes Szenario und ein netzorientiertes Szenario. Das marktorientierte Szenario hat das Ziel die Kosten am Hausanschlusspunkt zu minimieren, wobei die Auswirkungen auf das Netz während der Optimierung gänzlich unberücksichtigt bleiben. Im Gegensatz dazu wird im netzorientierten Szenario auf eine optimale Netzsituation hin optimiert, wobei die dabei entstehenden Kosten während der Optimierung keinen Einfluss auf das Ergebnis nehmen. In einem ersten Schritt wird die Ausgangssituation in den beiden Netzen für das Jahr 2030 und 2040 analysiert und jeweils die Woche des Jahres mit den größten Spannungsproblemen für die weiterführende Optimierung ausgewählt. Im Anschluss erfolgen die markt- und netzorientierten Optimierungen. Hierfür wird mithilfe von Pyomo in Python ein lineares Optimierungsmodell entwickelt das sowohl die markt- als auch die netzorientierte Optimierung durchführen kann und als Multi-Objective Optimierungscode mit Summengewichtungsverfahren verwirklicht wird. Auf Basis der Verfügbarkeit des Elektroautos, gemeinsam mit Zeitreihen zum Hausverbrauch und der Photovoltaikerzeugung, wird anschließend die Optimierung durchgeführt. Die marktorientierte Optimierung orientiert sich dabei am Day-Ahead Marktpreis und die netzorientierte Optimierung an der Gesamtleistung, die am Transformator anliegt. Bei der netzorientierten Optimierung wird zudem ein iterativer Ansatz verfolgt, bei dem sich die Gesamtleistung am Transformator nach jeder Optimierung eines Haushalts aktualisiert, um so die gegenseitige Beeinflussung der Haushalte zu berücksichtigen. Das Optimierungsergebnis wird für jeden Haushalt durch eine Zeitreihe der Ladeleistung repräsentiert. Mithilfe dieser Zeitreihen, in einminütiger Auflösung, wird im Anschluss eine Lastflussberechnung durchgeführt. Das Ergebnis der Lastflussberechnungen stellen Zeitreihen zu Knotenspannungen und Leitungsauslastungen dar. Zudem werden die veränderten Energiekosten auf Basis des Day-Ahead Preises berechnet. Das Ergebnis des marktorientierten Szenarios sind reduzierte Kosten von bis zu 9,7% und eine verbesserte Netzsituation im Vergleich mit dem Basisszenario in den betrachteten Verteilnetzen. Die verbesserte Netzsituation zeigt sich im Jahr 2040 durch reduzierte maximale Leitungsauslastungen, mit bis zu 150%, und geringere Einbrüche der Knotenspannungen, mit bis zu +20 V. Dies liegt am günstigen Zusammenspiel von geringen Day-Ahead Preisen in den Nächten und gleichzeitig geringer Gesamtbelastung durch nichtflexible Verbraucher, wodurch der Ladevorgang der Elektroautos von den Abendstunden in die Nachtstunden verschoben wird. Im netzorientierten Szenario wird eine Verbesserung der Netzsituation mit reduzierten maximalen Leitungsauslastungen von bis zu 250% und geringeren Einbrüchen der Knotenspannungen um bis zu +90 V im Jahr 2040 in den betrachteten Verteilnetzen erreicht. Aus Peaks der Leitungsauslastungen und Tälern der Knotenspannungen werden dadurch im netzorientierten Szenario vergleichsweise konstante Bänder. Zudem reduzieren sich die Energiekosten für Haushalte mit Elektroauto im Durchschnitt um bis zu 6,3%, was ebenso eine Folge der günstigen Kombination aus billigem Nachtstrom und gleichzeitig geringer Gesamtbelastung durch nichtflexib
nicht gesperrt
Keywords: Smart Charging; Vehicle-To-Grid; Elektromobilität; Smart-Charging; Vehicle-To-Grid; E-Mobility

Einflussparameter einer Fallstufe auf die optische Detektion von Batterien in gemischten Abfallströmen - Grath, Elias (2024)
Die Steigerung der jährlichen Menge an in Verkehr gebrachten Gerätebatterien zeigt den Drang zur Entwicklung batteriebetriebener Geräte. Infolge des hohen Ressourcenverbrauches und Kreislaufpotenzials stehen Batterien im Fokus gesetzlicher Novellierungen. Trotz der Bereitstellung von Sammelinfrastrukturen finden Batterien vermehrt den Weg in diverse Abfallströme. Unsachgemäß entsorgte Batterien gefährden nicht nur die ökonomische Behandlung von Abfällen, sondern führen im Brandfall zur Gefährdung der Umwelt und des Betriebspersonals. Diese Herausforderungen erfordern die Entwicklung von Systemen zur Detektion von Batterien in Abfallströmen, um das Risiko für die nachhaltige Bewirtschaftung von Abfällen zu minimieren. Die Entwicklung zuverlässiger Systeme erfordert jedoch die Bereitstellung von umfassenden, fehlerlosen Datensätzen. Die vorliegende wissenschaftliche Betrachtung setzt sich in diesem Kontext zum Ziel, grundlegende Kenntnisse über Einflüsse auf die optische Detektion und Datenverarbeitung zu erarbeiten. Um verschiedene Einflüsse auf die optische Erkennung von Batterien zu eruieren, erfolgte die Erstellung einer Batterie-Bilddatenbank durch die Aufnahme von qualitativ beprobten Altbatterien im Flug. Die Untersuchung der Beeinflussung von Kameraeinstellungen und der Komponentenanordnung auf die Bildqualität wurde in Versuchsreihen betrachtet. Die Variation der Trainingsparameter ermöglichte die Analyse der Einflüsse auf die Klassifikation von Batterien mittels künstlicher neuraler Netzwerke. Das Training eines YOLOv8-Modelles und die Vorhersage von Batterien in künstlich beimpften Abfallströmen lieferte Erkenntnisse über die Einsatzfähigkeit eines KI-gestützten Systems zur Detektion von Batterien. Die Ergebnisse dieser wissenschaftlichen Arbeit zeigen die Möglichkeit der Detektion von Batterien in Abfallströmen, und bilden die Basis für weitere Optimierungen eines Detektionsalgorithmus.
gesperrt bis 15-05-2026
Keywords: Artificial intelligence; YOLO; Artificial neural network; Image recognition; Area scan camera; Line scan camera; Accumulators; Sorting; Künstliche Intelligenz; YOLO; Künstliche neurale Netzwerke; Bilderkennung; Flächenkamera; Zeilenkamera; Akkumulatoren; Sortierung

Einsatz von 3D-Renderings zur Generierung von digitalen Trainingsdaten für die Abfallcharakterisierung mithilfe künstlicher Intelligenz - Rizvan, Alisa (2024)
Die Implementierung von Digitalisierung und Industrie 4.0 in der Abfallwirtschaft steckt noch in den Anfängen. Zukünftig werden Echtzeitüberwachung, Datenanalyse, Management und Prozesssteuerung für Abfallbehandlungsanlagen höchste Priorität haben. Die Behandlung von gemischten Abfällen stellt eine Herausforderung dar, bedingt durch Unterschiede in Abfallqualität und Schwankungen durch materielle und maschinelle Faktoren. Das Hauptziel dieser Masterarbeit ist die Charakterisierung fester Abfallpartikel in einer Schüttung auf einem Förderband, mit besonderem Fokus auf die Informationsverarbeitung des Schüttguts. Die Echtzeit-Charakterisierung von Abfällen auf Förderbändern ist von grundlegender Bedeutung für die laufende Anlagenoptimierung. Ziel ist es, autonome und dynamische Anpassungen vorzunehmen, um mit Abfallschwankungen umzugehen. Sensoren, die für eine umfassende Charakterisierung notwendig sind, sind zwar vorhanden, aber mit beträchtlichen Kosten und hohen Anforderungen an Arbeitssicherheit verbunden. Daher sind alternative Methoden wie die Klassifizierung durch künstliche Intelligenz und Kameras äußerst wünschenswert. Allerdings erfordern diese Ansätze große Mengen an hochwertigen und gelabelten Trainingsdaten, die vor allem im Bereich der festen gemischten Abfälle schwierig zu finden sind. Die Erstellung solcher Trainingsdaten über digitale Methoden wie 3D-Renderings werden daher als mögliche Lösung in Betracht gezogen sowie die Entwicklung einer Methodik zur Ermittlung der befindlichen Partikel in einer Schüttung.
nicht gesperrt
Keywords: 3D-Rendering; künstliche Intelligenz; 3D Modelle von Abfallpartikeln; Abfallcharakterisierung; 3D-Rendering; artificial intelligence; waste characterization; 3D Models of waste particles

Enhanced simulation methodology and assessment for efficient Ti-6Al-4V WAAM component manufacturing - Springer, Sebastian (2024)
The utilization of innovative manufacturing technologies, such as wire arc additive manufacturing (WAAM), presents advantages in production of large, functional structures, reducing lead time and material consumption. However, to integrate WAAM parts into failure-critical aerospace applications, a comprehensive understanding of design factors influencing manufacturing quality is imperative. This thesis focuses on advancing simulation methodologies for WAAM, targeting the titanium alloy Ti-6Al-4V. The main objective is to improve simulation accuracy of process factors like residual stress and distortion, considering the layer-wise nature of the WAAM process itself. Additionally, to enhance the obtained quality of WAAM structures, a thorough investigation into fatigue strength and tailoring of WAAM-process applicable assessment methodologies is conducted. The development of the enhanced simulation methodology involves an in-depth exploration of material intrinsic WAAM properties, such as creep and strain rate. Comprehensive material tests, including tensile, creep, and low-cycle fatigue experiments, are conducted to study both the complex creep and the cyclic elasto viscoplastic behavior of Ti-6Al-4V WAAM and titanium substrate. Implementable material models are rated, leading to the integration of an advanced Norton-Bailey creep and cyclic Chaboche model. Validation through experimental manufacturing of complex representative structures reveals a substantial improvement over conventional approaches, for example, reducing mean error of distortion compared to experimental measurements from 60% to 6%. In regard to the fatigue strength assessment of WAAM structures, this thesis focuses on understanding the impact of process-induced porosity. Detailed experimental characterizations, including fatigue and low-cycle fatigue tests, coupled with fractographic and microstructural investigations, are conducted. As both surface and inner pores were found on the fractured surfaces, a probabilistic stress-intensity equivalent transformation approach is developed. Summing up, this work presents an engineering-feasible simulation methodology for the thermo-mechanical simulation of Ti-6Al-4V WAAM, providing accurate results of residual stress, distortion, and temperature distribution for each WAAM layer. Furthermore, a probabilistic fatigue assessment concept is introduced to assess for the presence of defects in WAAM material. These advancements enhance the understanding of the WAAM process settings and open avenues for the application of WAAM parts in dedicated aerospace applications.
embargoed until 21-12-2028

Entwicklung einer Rotationsschwingsiebanlage - Mellacher, Stefan (2024)
Diese Arbeit beschäftigt sich mit der Entwicklung eines zuverlässigen Siebsystems für die automatisierte Bestimmung der Korngrößenverteilung von Schüttgütern. Gegenwärtige Standardanalysesiebe sind anfällig für das Verlegen der Siebeinlagen durch Klemmkörner im Betrieb, wodurch die Siebfunktion negativ beeinflusst wird. In dieser Arbeit wird untersucht, wie ein selbstreinigendes Siebsystem realisiert werden kann, welches dieser Problemstellung entgegenwirkt. Ein besonderer Schwerpunkt liegt auf der Idee eines rotierenden Schwingsiebes, dessen Potenzial für die Anwendung in diesem Zusammenhang genauer betrachtet wird. An dieser Stelle sei erwähnt, dass die Grundidee von Herrn Dipl.-Ing. Dr.mont. Michael Prenner stammt. Die Arbeit umfasst sowohl theoretische Überlegungen als auch praktische Untersuchungen, um die Machbarkeit und Wirksamkeit eines solchen Systems zu belegen. Hierzu werden Simulationen durchgeführt. Die Erkenntnisse aus diesen Simulationen werden genutzt, um Konstruktions- und Betriebsparameter für das selbstreinigende Siebsystem zu erhalten und zu optimieren. Dabei stehen die partikelschonende Siebfunktion und der selbstreinigende Effekt während des Betreibens der Anlage im Vordergrund. Durch die Entwicklung eines betriebssicheren und effizienten Siebsystems für die Korngrößenbestimmung von Schüttgütern trägt die Arbeit dazu bei, die Zuverlässigkeit und Genauigkeit von Standartanalysesiebverfahren zu verbessern.
gesperrt bis 07-03-2029
Keywords: Schüttgutanalyse; Rotierendes Schwingsieb; Verfahrensoptimierung; Korngrößenverteilung; Klassiervorgang; Selbstreinigung; bulk material analysis; rotating oscillating sieve; process optimization; particle size distribution; classification process; self-cleaning

Entwicklung eines Kalkulationsmodells zur Berechnung des CO2-Fußabdrucks eines Betonzusatzstoffes - Butter, Philipp (2024)
Diese Masterarbeit behandelt den CO2-Fußabdruck eines neuartigen Zusatzstoffes für die Betonherstellung. Nach einer Einführung in die Produktion von Beton und Zement und die damit verbunden Emissionen von Treibhausgasen, werden der Greenhouse Gas Protocol Product life cycle accounting and reporting standard sowie der Entwurf der ISO 14068 vorgestellt. Ziel dieser Arbeit ist die Entwicklung eines Kalkulationsmodells zur Berechnung des CO2-Fußabdrucks eines Typ-II-Zusatzstoffes auf der Grundlage der beiden genannten Normen, sowie die Erhebung aller dazu benötigten Daten. Die mit diesem Modell berechneten Ergebnisse sollen künftig für den Anspruch und Nachweis der CO2-Neutralität des Produktes nach ISO 14068 herangezogen werden. Nach einer Beschreibung der erhobenen Daten werden die Berechnungsmethoden für jeden Schritt des Herstellungsprozesses beschrieben.
gesperrt bis 10-01-2029
Keywords: Klimaneutralität; Zement; Beton; ISO 14068; CO2-Fußabdruck; Kalkulationsmodell; Betonzusatzstoff; Emissionen; Baustoffe; Greenhouse Gas Protocol; Bauindustrie; Zementersatzprodukt; Typ-II Zusatzstoff; carbon neutrality; concrete additive; carbon footprint; cement; concrete; ISO 14068; Greenhouse Gas Protocol; building materials; emissions; cement replacement; construction industry; type-II additive

Entwicklung eines Konzeptes für den Einsatz von Mehrwegladungsträgern und -verpackungen im Rahmen des Lieferantenmanagements - Neumayr, Gregor (2024)
Mehrwegladungsträger und -verpackungen gewinnen zunehmend an Bedeutung, da sie die Möglichkeit zur Kosten- als auch Emissionsreduktion bieten. In diesem Zusammenhang beschäftigt sich die vorliegende Masterarbeit mit der Entwicklung eines Konzeptes für einen nutzbringenden Einsatz von Mehrwegsystemen im Rahmen des Lieferantenmanagements in der Fahrzeugindustrie. Dies umfasst sowohl eine qualitative Analyse der Einflussfaktoren auf die bereichsübergreifenden Prozesse von Mehrwegverpackungen als auch ein quantitatives Bewertungskonzept. Zu Beginn werden im Theorieteil durch eine strukturierte Aufarbeitung der Zusammenhänge relevante Einflussfaktoren für das Konzept identifiziert. Darauf aufbauend werden im empirischen Teil der Arbeit interdisziplinäre Experteninterviews zur Vertiefung des Konzeptes durchgeführt. Durch die Diskussion der theoretischen und praktischen Erkenntnisse wird eine ganzheitliche und praxisnahe Sichtweise erreicht. Zum Abschluss erfolgt eine anwendungsorientierte Ableitung des entwickelten Konzeptes, um ein Fallbeispiel der KTM AG sowohl einer ökonomischen als auch ökologischen Betrachtung zu unterziehen. Das Ziel ist es, dadurch die Praxistauglichkeit des Konzeptes zu überprüfen und gleichzeitig eine mögliche Vorgehensweise zur Quantifizierung von Kosten und Emissionen aufzuzeigen. Diese soll als Entscheidungsgrundlage dienen und dabei helfen, eine fundierte Entscheidung zwischen Einweg- und Mehrwegverpackungen zu treffen. Das Konzept umfasst eine strukturierte Aufarbeitung der Potentiale und Herausforderungen im Zusammenhang mit Mehrwegsystemen sowie deren Bewertungsmethodik. In der Fallstudie wird eine Lebenszyklusbetrachtung im Sinne der Total Cost of Ownership angewendet, um versteckte Kosten zu berücksichtigen und eine ganzheitliche Emissionsabschätzung vorzunehmen. Das Ergebnis zeigt, wie eine vereinfachte Berechnung zur Kosten- und Emissionsabschätzung in der Praxis durchgeführt werden kann. Für das vorliegende Fallbeispiel ist die Verwendung von Mehrwegverpackung sowohl kostengünstiger als auch nachhaltiger.
gesperrt bis 07-02-2029
Keywords: Logistik; Mehrweg; Konzept; Lieferantenmanagement; Verpackung; Ladungsträger; Logistics; Reusable; Concept; Supplier management; Packaging; Load carriers

Entwicklung eines Teststandes zur Bestimmung der Permeabilität poröser Materialien in Protonenaustauschmembran-Elektrolyseuren - Rubasch, Simon (2024)
In Elektrolyseuren wird Wasser mithilfe von elektrischer Energie in die Bestandteile Sauerstoff und Wasserstoff aufgespalten. Wasserstoff gilt als Schlüsselelement in der Energiewende, um erneuerbaren Strom aus Windenergie, Sonnenenergie, Wasserkraft, etc. zwischenzuspeichern, um die Erzeugung vom Verbrauch zu entkoppeln. Eine Technologie, die sich für diese Anwendung besonders eignet, ist die Protonenaustauschmembran-Wasserelektrolyse. Das Wasser gelangt über poröse Transportschichten zur Zellmembran, an der die Spaltung in Wasserstoff und Sauerstoff abläuft. Die porösen Transportschichten haben die Aufgabe, das Wasser durch deren inneren Widerstand über die gesamte Membranfläche zu verteilen. Weiters sind sie zuständig, um die produzierten Gase aus der Zelle abzutransportieren und die elektrische Leitfähigkeit zwischen der Elektrode und der Membran herzustellen. Durch den inneren Widerstand der porösen Transportmaterialien stellt sich ein Druckverlust ein, der in dieser Arbeit näher untersucht werden soll. Dadurch soll der Druckverlust von Stacks und Zellen besser verstanden und schlussendlich der Gesamtwirkungsgrad einer Protonenaustauschmembran-Elektrolyse optimiert werden. Dazu werden die gängigsten Materialien, die derzeit in Elektrolyseuren anoden- und kathodenseitig zum Einsatz kommen, näher betrachtet und deren Druckverlust bei Durchströmung der Medien mit Fluiden gemessen. Um die porösen Materialen hinsichtlich ihres Druckverlustes bei unterschiedlichen Strömungsgeschwindigkeiten beschreiben zu können, wird ein Testblock entwickelt. Auf Basis der Ergebnisse werden mathematische Funktionen aufgestellt, um die Permeabilität, den viskosen und den kinetischen Widerstand der unterschiedlichen porösen Materialen abschätzen zu können. Durch eine Auflistung möglicher Fehlereinflüsse zu Beginn der Arbeit kann auf deren Vermeidung bzw. Minderung bei der Durchführung der Versuche geachtet werden. Die Haupteinflüsse stellen dabei der Zuschnitt der Proben und die Reihenfolge der Proben dar, wenn mehrere Proben übereinander im Testblock eingebaut werden. Durch die Beachtung möglicher Fehlereinflüsse ist es möglich, reproduzierbare Daten zu generieren. Die Untersuchungen zeigen, dass beispielsweise die Anzahl der Proben einen wesentlichen Einfluss auf den Druckverlust darstellt, ebenso die Anpresskraft auf die Proben, welche sich vor allem jenen Proben mit höherer Elastizität einstellt. Aus den aufgenommenen Druckverlustpunkten der getesteten Materialien kann eine Trendlinie herausgelesen werden, mithilfe derer sich die Permeabilität, der viskose und kinetische Widerstand berechnen lässt.
gesperrt bis 30-12-2028
Keywords: PEM-Elektrolyse; poröse Transportschichten; poröse Materialien; Druckverlust; PEM electrolysis; porous transport layers; porous materials; pressure loss

Entwicklung und Konstruktion einer vakuumtauglichen Gieß- und Abkühleinheit zur Herstellung dünner Metallbänder - Pichler, Daniel Martin (2024)
Die Firma INTECO melting and casting technologies führt die Planung und Konstruktion einer Anlage zur Herstellung einer Titan-Eisen-Mangan-Legierung (TiFeMn) in der Form von Metallplättchen (Flakes) durch. Teil dieser Anlage ist das Gießrad, an welchem mit Dünnbandgießen (Strip casting) die Schmelze der Legierung abgekühlt und erstarrt wird. Das Metallband wird nachfolgend zerkleinert und zur weiteren Nutzung als Wasserstoffspeicher aufbereitet. Die Kühlung des Gießrades erfolgt durch das Durchleiten von Kühlwasser unter der Oberfläche der Mantelfläche. Um die Einflussfaktoren auf den Prozess und das Abkühlverhalten herauszuarbeiten, wurde eine Literaturrecherche durchgeführt. Es wurde in COMSOL Multiphysics ein grundlegendes Simulationsmodell erstellt, welches für die Simulation des Wärmeübergangs und des Abkühlverhaltens der Schmelze verwendet wurde. Zusätzlich wurde die thermische Spannung im Gießrad dargestellt. Als Einflussfaktoren auf den Gießprozess wurden die Gestalt und der Werkstoff des Gießradmantels sowie die Eigenschaften des Kühlwassers identifiziert. Darauf aufbauend wurde eine Baugruppe des Gießrades konstruiert, wobei der Gießradmantel als abziehbare Hülse auf dem Radkörper ausgeführt wurde. Die relevanten Bauteile wurden rechnerisch dimensioniert und die Baugruppe einer Simulation der mechanischen Belastung unterzogen.
gesperrt bis 06-05-2029
Keywords: Gießrad; Dünnbandgießen; Kühlwalzen; Einzelwalzengießanlage; Wärmeübergang; Gieß- und Abkühleinheit; strip casting; casting wheel; cooling rolls; single-roll strip caster; heat transfer; casting and cooling unit

Environmental assessment of an industrial site with special consideration of regional sustainability factors & biodiversity - Knapp, Christina (2024)
In addition to climate protection, measures for the protection of biodiversity are an important part of future-oriented sustainability management and an expression of responsible business. In the future, industrial companies will need to increasingly address issues such as biodiversity and regional sustainability factors to make a more significant contribution to Sustainable Development Goal 15, "Life on Land¿. Biodiversity is analysed throughout all sites and the entire value chain as part of corporate environmental management. This Master's thesis provides an in-depth examination of biodiversity in relation to the industrial site of voestalpine Böhler Edelstahl GmbH & Co KG in Kapfenberg. The aspects of biodiversity covered in this thesis, including definitions, legal frameworks, measurement methods, and strategies for promoting biodiversity, are of great importance, not only for the company under study but also for the general public. Through a holistic approach, the industrial site can contribute to local and regional biodiversity while reducing its ecological footprint. By evaluating the current and target status regarding biodiversity at the industrial site and throughout the entire value chain, along with its legal context, opportunities for promotion can be identified and implemented.
embargoed until 09-02-2029
Keywords: biodiversity; sustainability; environmental management; ecological footprint; Green Business; non-native species; Biodiversität; Neobiota; Biodiversitätscheck; Biodiversity Monitoring-System; biologische Vielfalt; EU-Biodiversitätsstrategie

Environmental impact assessment of a car door panel using recycled carbon fibers: Relevance of different life stages and influence of modelling choices - Kirschnick, Ulrike; Duchamp, Boris; Fick, Gael (21st European Conference on Composite Materials for Academia and Industry, 2024)

Erhebung einer potentiellen Energieunabhängigkeit Österreichs - Hofstätter, Maximilian (2024)
Die heimische Energiewirtschaft bildet das Rückgrat der Gesellschaft und steht angesichts der anvisierten Dekarbonisierung bis 2040 vor der grundlegenden Herausforderung, die Energiebereitstellung zu transformieren. Neben den Bestrebungen nach einer möglichst nachhaltigen Energieversorgung ist aufgrund der globalen geopolitischen Verwerfungen der letzten Jahre die Frage nach einer potenziellen Energieunabhängigkeit aktueller denn je. Um die Abhängigkeiten der Versorgungsströme aufzuzeigen wird daher im Rahmen der vorliegenden Masterarbeit zunächst die Primär- und Sekundärenergiebereitstellung in Österreich untersucht. Hierbei wird insbesondere auf die Erdöl- und Gasversorgung sowie die Zusammensetzung des Strommixes nach den jeweiligen Energieträgern genauer eingegangen. Im zweiten Kapitel erfolgt eine detaillierte Untersuchung der Potenziale an erneuerbaren Energien in Österreich, wobei hier klar zwischen theoretischen und technisch-wirtschaftlichen Potenzialen unterschieden wird. Diese Analyse dient als Grundlage zur Bewertung der Möglichkeiten einer Energieautarkie durch Gegenüberstellung verschiedener Energiebedarfsmodelle und dem Ermitteln einer eventuellen Versorgungslücke. In diesem Zusammenhang werden die gängigen Biomassevergasungsanlagen sowie andere alternative Herstellungsverfahren von Biomethan beschrieben, um ihren prognostizierten großflächigen Einsatz besser verstehen zu können. Analog dazu erfolgt ein kurzer thematischer Einwurf über die Erzeugung von Wasserstoff, da dieser als emissionsfreies Reduktionsmittel in der Hüttenindustrie eine essenzielle Rolle spielen wird. Für den Praxisteil der Arbeit werden aus genannten Analysen wichtige Erkenntnisse für die Durchführung von Expertenbefragungen abgeleitet. Ziel dieser Befragungen ist es, die Machbarkeit einer Energieautarkie in Österreich sowie die damit verbundenen technischen Herausforderungen zu diskutieren. Die Interviews wurden mittels angepasster Delphi-Methode, deren zugrundeliegendes Verfahren ebenfalls erläutert wird, strukturiert und chronologisch mit 7 Experten aus verschiedenen Bereichen geführt. Diese Methode ermöglicht es, wichtige Erkenntnisse aus jedem Interview in das Nächste einfließen zu lassen, um umfassende und möglicherweise kritische Feststellungen daraus abzuleiten. Die Ergebnisse der Interviews werden abschließend im Rahmen eines Expertengesprächs aus der energieintensiven Hüttenindustrie in Österreich, somit auch aus Verbrauchersicht, diskutiert und analysiert. Die Experten kommen unisono zu dem Schluss, dass eine vollständige Energieautarkie in Österreich - unabhängig von der zukünftigen Zusammensetzung des Primärenergiemixes - aus verschiedenen Gründen als de facto ausgeschlossen gilt. Lediglich eine bilanzielle Stromautarkie über ein Kalenderjahr hinweg sei ein realistisches Szenario bis 2030. In puncto Zukunft der erneuerbaren Energieträger gehen die Expertenmeinungen weit auseinander, wobei auch hier einheitlich von weiterhin bestehenden Energieabhängigkeiten gesprochen wird. Hierunter fällt beispielsweise der für die Energiewende notwendige Wasserstoffimport und die damit verbundene Notwendigkeit, die Diversifizierung der Abhängigkeiten aus den Erzeugungsländern zu steigern, um eine mögliche Versorgungslücke - analog zu russischem Erdgas - vermeiden zu können.
gesperrt bis 30-01-2029
Keywords: Security of supply; energy self-sufficiency; renewable energies; energy potentials; Delphi method; Versorgungssicherheit; Energieautarkie; Erneuerbare Energien; Energiepotenziale; Delphi-Methode

Ermittlung der Gelzeit mittels Nahinfrarotspektroskopie in der lösungsmittelfreien Prepreg Herstellung - Schmid, Sebastian (2024)
Die Bestimmung der Gelzeit von Faser-Kunststoff-Verbundwerkstoffen (FKV) mit duromerer Harzmatrix kann auf verschiedene Arten erfolgen. In der industriellen Praxis erfolgt die Bestimmung der Gelzeit in der Regel nach der ISO-Norm 15040:1999. Dabei wird mit einer beheizten Presse Harz aus Probenkörpern mit definierter Geometrie gepresst und die Zeit gemessen, bis dieser Harztropfen geliert. Es existieren jedoch nur sehr wenige Arbeiten, welche sich mit einer schnellen und vor allem berührungslosen Messung der Gelzeit direkt im Produktionsprozess beschäftigen. Als eine vielversprechende Messmethode dafür gilt die Nahinfrarotspektroskopie (NIRS), die im Inline Monitoring bereits für die Bestimmung unterschiedlicher Materialparameter eingesetzt wird. Aus diesem Grund wurden entlang einer Prepreg-Produktionsanlage auf Basis des Hot-Melt Verfahrens verschiedene Messpositionen eingerichtet, an denen Spektren vom imprägnierten Glasgewebe an unterschiedlichen Abschnitten des Prepreg-Herstellungsprozesses aufgenommen wurden. Die gemessenen Spektren entsprechen somit unterschiedlichen Stufen im Prepreg-Produktionsprozess. Daraufhin wird der Einfluss von unterschiedlichen Heizfeldtemperaturen sowie der Einfluss der unterschiedlichen Trennfolienfarben und Oberflächenstrukturen auf die Spektren untersucht. Auf Basis der gemessenen Spektren wurden mit dem Partial Least Squares (PLS) Verfahren Modelle entwickelt, welche die Gelzeiten der Prepregs bestimmen. Als Referenzwerte für die Modellerstellung dienen die Gelzeiten, welche nach der Industrienorm ISO 15040 bestimmt wurden. Ursachen für Abweichungen wurden identifiziert und bilden die Basis für weitere Untersuchungen. Neben den im Sinn der Aufgabenstellung vorteilhaften Messpositionen wurden auch Tendenzen von stärkeren Einflüssen unterschiedlicher Trennfolien auf die gemessenen Spektren identifiziert. Letztlich konnte gezeigt werden, dass eine Ermittlung der Gelzeit mithilfe NIRS möglich ist und die PLS-Modelle ausreichend gute Qualität liefern, die eine Bestimmung der Gelzeit erlauben.
nicht gesperrt
Keywords: Nahinfrarotspektroskopie; Gelzeit; NIRS; Prepreg; Hot-melt; Faser-Kunststoff-Verbundwerkstoffe; FKV; Partial Least Squares; PLS; Gelzeitbestimmung; inline-Monitoring; berührungslose Messung; Verbundwerkstoffe; CFK; GFK; near-infrared spectroscopy; geltime; NIRS; prepreg; hot-melt; fiber-reinforced polymers; FRP; partial least squares; pls; gel time determination; inline-monitoring non-contact measurement; composites; CFK; GFK

Evaluierung des Brennstoffeinflusses beim Schmelzen verunreinigter Schrotte mit Salz - Winter, Florian (2024)
Im Rahmen eines Projektes zur Erreichung der Klimaneutralität wird der Einsatz alternativer, emissionsfreier Beheizungskonzepte in Schmelzöfen für verunreinigte Aluminiumschrotte evaluiert. Insbesondere der Einsatz von Wasserstoffbrennern anstelle herkömmlicher Erdgasbrenner erweist sich in diesem Zusammenhang als vielversprechend. Eine Umrüstung führt jedoch zwangsläufig zu einer Veränderung der Atmosphäre in den Kipptrommelöfen. Neben dem Wegfall von brennstoffbedingten CO2-Emissionen ist vor allem mit einem Anstieg des Wasserdampfgehaltes zu rechnen. Die H2O-Konzentation in der Ofenatmosphäre steigt theoretisch von 67 Vol. % auf 100 Vol. % bei der Verbrennung von Wasserstoff anstelle von Erdgas. Bislang ist unerforscht, inwiefern eine solche Veränderung die Schmelzequalität, das Metallausbringen und die Eigenschaften der Salzschlacke beeinflussen. Um dies zu evaluieren erfolgt im Rahmen dieser Arbeit das Schmelzen mehrerer Schrottchargen zu je 10 kg mit Schmelzsalz in einem an die industriellen Aggregate angelehnten Labor-Kipptrommelofen. Der eingesetzte Brenner mit einer Nennleistung von 30 kW kann sowohl Methan, die Hauptkomponente in Erdgas, als auch Wasserstoff mit Sauerstoff verfeuern. Die Gattierung umfasst eine Mischung aus Kapselband, Blechschrott der Legierungsklasse 5xxx und magnesiumreiche Krätze. Zur Beurteilung der Schmelzequalität kommt der Dichte-Index zum Einsatz. Weiters liefert eine detaillierte Massenbilanz inklusive Aufbereitung der Salzschlacke Auskunft über die Schmelzausbeute und die Oxidationsverluste. Es zeigt sich, dass der Einsatz von Wasserstoff als Brennstoff zu einer tendenziellen Erhöhung des Dichte-Index führt. Diese ist vermutlich auf einen Anstieg des Wasserstoffgehaltes im flüssigen Metall zurückzuführen. Weiters ist das Metallausbringen im Vergleich zu den Erdgasversuchen durchschnittlich um 9,4 % höher. Die potenzielle Ursache dafür ist eine signifikant verkürzte Aufschmelz- bzw. Chargendauer bei identer Brennerleistung. Dies lässt auf einen veränderten Wärmeübergang im Ofen schließen. Die verbesserte Ausbeute ist auf einen um 7,0 % geringeren Metallanteil in der Salzschlacke und um 2,4 % verringerte Oxidationsverluste zurückzuführen. Diese Beobachtungen zeigen, dass eine Umrüstung des Beheizungskonzeptes in diesen Öfen auf Wasserstoffbrenner im Rahmen der Dekarbonisierung grundsätzlich möglich ist. Diverse Aspekte, wie die Wäremübertragung im Ofen sowie potenziell veränderte Gasbildungseigenschaften der gebildeten Salzschlacke müssen in weiterführenden Untersuchungen allerdings noch analysiert werden
gesperrt bis 17-05-2029
Keywords: hydrogen; decarbonisation; aluminiumrecycling; tilting drum furnace; density index; Wasserstoff; Dekarbonisierung; Kipptrommelofen; Aluminiumrecycling; Dichte-Index

Evaluierung des Einsatzes von Spritzgießsimulation zur Vorhersage der Maßstreuungen von Kunststoffformteilen - Schedler, Martin (2024)
Das Spritzgießen stellt einen diskontinuierlichen Prozess dar, der es ermöglicht, gut reproduzierbare Kunststoffformteile kostengünstig in Serie zu fertigen. Aufgrund von Schwankungen verschiedenster Einflussgrößen sind die Schwindung und der Verzug sowie die damit verbundene Maßhaltigkeit eines Kunststoffformteils nur sehr schwer vorherzusagen. Das Ziel dieser Arbeit bestand darin, die Vorhersagbarkeit der Maßstreuung von Spritzgussbauteilen durch die Spritzgusssimulation zu evaluieren. Dabei wurde eine Vielzahl von Einflussgrößen im Bereich des Prozesses, des Materials, der Umwelt, des Werkzeugs, der Messtechnik und der Maschine betrachtet. Insbesondere sollte die Schwankungsbreite der Einflussgrößen aufgezeigt und ihr Einfluss auf die Maßhaltigkeit untersucht werden. In dieser Arbeit wurden knapp 60 potenziell maßhaltigkeitsrelevante Einflussgrößen analysiert. Neben einer ausführlichen Literaturrecherche, Gespräche mit Experten sowie Einzeluntersuchungen wurden auch Screening-Versuche durchgeführt, um die signifikanten Einflussgrößen sowie ihre Schwankungsbreite zu bestimmen. Mittels der Monte-Carlo-Methode wurden alle signifikanten Einflussgrößen anhand ihrer Eintrittswahrscheinlichkeit und Schwankungsbreite betrachtet und so realitätsnah wie möglich in die Spritzgusssimulation integriert. Für die Berechnungen wurde die Spritzgusssimulationssoftware Autodesk Moldflow® Insight 2023 (AMI) (Autodesk Inc., USA) verwendet, während die damit ermittelten Verzugsgeometrien mit Hilfe der messtechnischen Analysesoftware GOM Inspect 2020 (Carl Zeiss GOM Metrology GmbH, Deutschland) ausgewertet wurden. Das Simulationsergebnis wurde mit den Messungen des ausgewählten Artikels während einer 14-monatigen Serienproduktion verglichen. Zusätzlich wurde die Herstellbarkeit der geforderten Formteiltoleranzen mit Hilfe der DIN ISO 20457 evaluiert. Die vorhersagten Maßstreuungen zeigten über kürzere Zeiträume Ähnlichkeiten mit den Serienmesswerten, wobei die Schwindung in der Simulation etwas überschätzt wurde. Im Gesamtzeitraum traten in der Praxis allerdings Messwertsprünge auf, die nicht nachvollzogen werden konnten. Der Vergleich mit der DIN ISO 20457 zeigte, dass die Serienmesswerte gut mit der Toleranz harmonierten, sich also alle gemessenen Daten in der Toleranz der jeweiligen Prüfmerkmale befanden. Auf Basis der Simulationen wurde mittels Minitab (Minitab GmbH, USA) und STASA QC (STASA Steinbeis Angewandte Systemanalyse GmbH, Deutschland) ein lineares bzw. nichtlineares Prozessmodell zur mathematischen Beschreibung der Maßstreuungen erstellt, die bei der Validierung eine hohe Korrelation zu den Simulationsergebnissen als auch zueinander zeigten. Abschließend wurden diverse Verbesserungspotentiale hinsichtlich Einflussgrößen und Spritzgießsimulation aufgezeigt, um die Vorhersagegenauigkeit von Maßstreuungen erhöhen zu können.
gesperrt bis 30-01-2029
Keywords: Kunststoff; Spritzguss; Spritzgusssimulation; Prozess; Maßhaltigkeit; Moldflow; Materialparameter; Prozessmodell; Toleranz; Monte Carlo; Versuchsplanung; Screening; Schwindung; Verzug; Störgrößen; Plastics; Injection moulding; Injection moulding simulation; Process; Dimensional accuracy; Moldflow; Material parameters; Process model; Tolerance; Monte Carlo; Design of experiments; Screening; Shrinkage; Warpage; Disturbance variables

Evaluierung unterschiedlicher Recyclingansätze für gebrauchte Feuerfeststeine aus der sekundären Kupferindustrie - Premm, Wolfgang (2024)
In der heutzutage üblichen pyrometallurgischen Prozessroute erfolgt die Gewinnung von Kupferstein in einem sogenannten Schwebeschmelzofen, welcher im darauffolgenden Schritt im Konverter zu Blisterkupfer verblasen und anschließend einer Feuerraffination im Drehtrommelofen oder Herdflammofen unterzogen wird. Bei Sekundärrohstoffen ist der Ablauf des Gewinnungsprozess ähnlich, mit dem grundlegenden Unterschied, dass statt eines Schwebeschmelzofens, unter reduzierenden Bedingungen betriebene Aggregate Einsatz finden. Für diese Hochtemperaturprozesse sind Feuerfestmaterialien unverzichtbar. In der Kupferindustrie finden hauptsächlich Magnesia-Chrom sowie Alumina-Chrom-Feuerfestmaterialien Anwendung. Während den ablaufenden Prozessen kommt es zu Intrusionen von der Schmelze in das Material sowie zu chemischen Reaktionen, wodurch die Zusammensetzung der Feuerfestprodukte verändert wird. Eine Rückgewinnung der feuerfesten Einsatzstoffe und der Wertmetalle ist über mechanische Aufbereitungsverfahren, Flotation, Verflüchtigung von Verunreinigungen sowie auch Laugungsverfahren möglich. Aufgrund der komplexen Zusammensetzung der Reststoffe sowie der geringen Qualität der Produkte kommen diese jedoch kaum zum Einsatz, weshalb sie zurzeit hauptsächlich auf Deponien landen. Bei den untersuchten Feuerfestausbrüchen handelt es sich um Magnesia-Chrom-Steine aus einem Schachtofen sowie Alumina-Chrom-Steine aus einem Konverter und einem Flammofen der sekundären Kupferindustrie. Nach einer umfassenden Charakterisierung wurden unterschiedliche Ansätze zur Rückgewinnung der Fraktionen Feuerfestmaterial und Wertmetall evaluiert. Dazu zählen Grobzerkleinerung mit anschließender Siebanalyse, die Bestimmung der magnetischen Eigenschaften sowie Laugungsversuche. Nach den Ergebnissen der Charakterisierung kommt es bei allen Proben an der Ofeninnenseite zu den größten Veränderungen im Material. Hier treten die höchsten Gehalte an Kupfer sowie an anderen intrudierten Metallen auf. Diese nehmen bis zur Kaltseite hin ab, wo keine merklichen Veränderungen im Stein erkennbar sind. Kupfer ist in den Materialien zum Großteil in oxidischer Form enthalten, aber es reagiert auch mit dem Feuerfestmaterial und bildet mit diesem verschiedene Mischverbindungen. Laut Siebanalyse würde sich ein grober Siebschnitt nach dem Brechen zur Abtrennung etwaiger anhaftender Metallstücke lohnen. Ebenso ist nach den Ergebnissen der Suszeptibilitätsanalyse die Abtrennung einer ferromagnetischen Fraktion möglich. Die Extraktionsraten für Kupfer sind bei den Laugungsversuchen bei Temperaturen von 90 °C, einem pH-Wert von 0,3, einer Laugungsdauer von 120 Minuten sowie einem Solid zu LiquidVerhältnis von 1:15 am höchsten. Um die hydrometallurgische Rückgewinnung zu optimieren, werden Verbesserungsvorschläge für den Aufbau sowie Ideen für weiterführende Untersuchungen diskutiert.
gesperrt bis 24-05-2029
Keywords: Recyclierbarkeit; Feuerfestausbrüche; sekundäre Kupferindustrie; Recyclability; Refractory; Secondary copper industry

Experimental and Numerical Simulation of Burst Experiment for Determining Fracture Toughness under Confining Pressure - Inal, Onur (2024)
The burst experiment is a common method that is mostly used in the petroleum industry to estimate the fracture toughness (KIC) of rocks under confinement in the laboratory. Unlike other methods, it tests rock samples subjected to confining stress, which represents the actual subsurface condition of a stressed wellbore with bi-wing fractures, and therefore it is considered advantageous to other methods. Fracture propagation in this burst experiment is only indicated by a sudden burst of the jacketed sample, where the burst pressure is measured. The fracture toughness of the sample can then be calculated after taking this recorded pressure as the critical pressure required to propagate the axially pre-notched wing fractures. However, the fracture growth may exist before the sample bursts, which might be a possible weakness of this technique. The cause is the existence of stable crack growth before the unstable ¿burst¿. Due to the challenges in the detection of this stable crack growth, there is significant uncertainty in the crack length used in the analysis of the results. The purpose of this thesis is to estimate fracture toughness accurately by comparing the stable and unstable behavior types from numerical modeling predictions with the results of a series of modified burst experiments using acoustic emission (AE) detection for certain configurations. The results indicate that stable growth will occur before sample rupture for certain sample geometry and loading combinations. The difference between stable and unstable growth cases is detected from acoustic emission monitoring records. Moreover, modifications are proposed for more accurate fracture toughness calculations after investigating the behavior of the estimated fracture toughness results. More consistent estimations of fracture toughness are obtained from experiments with unstable configurations. The results of experiments with unstable behavior indicate a positive correlation between confining pressure and fracture toughness estimations, which complies with many observations reported in the literature. Lastly, fixed confinement experiments are performed for a legitimate calculation of KIC with a range of geometry and loading conditions based on the global stability criterion. The effect of fixed confining pressure on the fracture toughness estimations has been shown, offering guidance for improved design of this frequently used test method
no embargo
Keywords: Burst experiment; rock mechanics; rock fracturing; numerical analysis; Berstversuch; Gebirgsmechanik; Bruchausbreitung im Gestein; Numerische Analysen

Experimental investigation and thermodynamic assessment of the ternary system Fe-Mn-S - Littringer, Robert (2024)
In modern steelmaking, manganese (Mn) is known as a versatile alloying element for various steel grades. Typical amounts of Mn are up to 1.5 wt.-% in low-alloyed carbon steels, around 3 to 6 wt.-% in medium Mn steels and more than 10 wt.-% in high Mn steels for special purposes. Mn increases strength and enhances toughness, ductility and weldability of steels in certain alloying ranges. In addition, Mn serves the purpose of binding residual sulfur (S) as manganese sulfides (Mn,Fe)S. In contrary, S is in general considered to be harmful in steel. S segregates in interdendritic liquid during the solidification of steel and causes hot tearing. In combination with Mn, sulfur leads to the formation of (Mn,Fe)S during the solidification in the continuous casting process, which is favorable to avoid the hot tear sensitivity. However, in the solid state, the precipitation of (Mn,Fe)S drastically decreases the ductility at elevated temperatures and thereby may induce crack formation at the surface. To assess the quality-related issues, the precise knowledge on thermodynamics of the Fe-Mn-S system and the prediction of (Mn,Fe)S stability in steel is crucial. The aim of this master¿s thesis was the experimental investigation and thermodynamic assessment of the ternary system Fe-Mn-S with emphasis on solidification of steel. Alloys with 0.5 wt.-% and 2 wt.-% Mn and up to 0.3 wt.-% S were investigated by Differential Scanning Calorimetry (DSC) regarding high-temperature phase equilibria and (Mn,Fe)S precipitation during cooling. Based on these results and experimental data from literature, thermodynamic modeling according to the CALPHAD (CALculation of PHase Diagrams) approach was carried out in the sub-systems Fe-Mn, Fe-Mn-C and Fe-Mn-S to create a database for the quaternary system Fe-Mn-S-C. For the liquid phase the Modified Quasichemical Model (MQM) in the pair-approximation was applied to formulate the solution¿s Gibbs energy. The MQM enabled to consider strong short-range-ordering (SRO) in the melt, which is typical for S-containing metal systems. The Compound Energy Formalism (CEF) was used for the descriptions of the solid solutions, e.g. austenite, ferrite, and various carbides. Several compounds were treated as stoichiometric to simplify the thermodynamic database.
no embargo
Keywords: Continuous Casting; DSC; Fe-Mn-S; solidification; CALPHAD; Stranggießen; DSC; Fe-Mn-S; Erstarrung; CALPHAD

Experimentelle Evaluierung der Fresstragfähigkeit von Kolbenringen mit verschiedenen chrombasierten Schichten - Breitegger, Matthias (2024)
Kolbenmaschinen finden in zahlreichen Gebieten in unterschiedlichsten Größen des modernen Lebens Anwendung. Dies reicht von der Automobilbranche bis hin zum Generatorbau. Hierbei werden unterschiedliche Kraftstoffe, wie Diesel, Benzin und auch Gas eingesetzt. Um diese Maschinen im Hinblick auf Nachhaltigkeit zu optimieren, ist es notwendig die Verluste der Kolbenmaschinen und somit den Kraftstoffverbrauch zu reduzieren. Ein wichtiger Bereich ist hierbei die tribologische Optimierung der Kolbengruppe, da in diesem Bereich ein großer Teil der Energie für die Reibungsüberwindung verwendet wird. Durch Verbesserung der Kontakteigenschaften zwischen Kolbenring und Zylinderwand, kann hierbei eine signifikante Menge an Energie eingespart werden. Um dies zu erzielen werden die Topologie der Reibpartner verbessert, niedrigviskose Schmierstoffe eingesetzt und verbesserte Beschichtungen der Ringe verwendet. Zusätzlich dazu soll die Leistungsdichte der Kolbenmaschine erhöht werden, was zumeist zu höheren Drücken führt. Dies ergibt hohe Beanspruchungen der Kolbenringe und deren Beschichtungen, was die Gefahr des Fressens der Ringe erhöht. In dieser Arbeit werden daher unterschiedliche Beschichtungen von Kolbenringen für große Gasmotoren in Generatoren genauer betrachtet und die Fresstragfähigkeiten ermittelt und verglichen. Die hierbei betrachteten Beschichtungen sind Chrom mit Aluminiumoxidpartikel, Chrom mit Nanodiamanten und durch physikalische Gasphasenabscheidung erstellte Chrom-Stickstoff-Kohlenstoff Schichten. Für die Zylinderproben wurde ein Zylinder aus Gusseisen mit Sphärographit verwendet. Um einen Vergleich vor und nach den Versuchen gewährleisten zu können, wurde ein Lichtmikroskop verwendet, um die Oberfläche der Proben, als auch die Querschnitte genauer betrachten zu können. Des Weiteren wurden Analysen in einem Rasterelektronenmikroskop durchgeführt, um auch die Materialzusammensetzung durch energiedispersive Röntgenspektroskopie genauer analysieren zu können. Die Versuche wurden in einem Lineartribometer durchgeführt. Nach einem langen Einlaufvorgang wurde hierbei die Kraft immer wieder nach 45 min um 50 N erhöht. Das Überschreiten der Fresstragfähigkeit ist durch einen plötzlichen starken Anstieg des Reibkoeffizienten gekennzeichnet. Um die Versuche bei Versagen abzubrechen, wurde daher ein Grenzwert des Reibkoeffizienten von 0,25 definiert. Während den Versuchen wurden mehrere Aufzeichnungen durchgeführt, welche dann genauer analysiert wurden. Da die Ringe unterschiedliche Geometrien hatten, mussten die Fresstragfähigkeiten auf die projizierten Flächen bezogen werden, um die Vergleichbarkeit der Ergebnisse zu gewährleisten. Der hierbei berechnete Druck spiegelt die realen Verhältnisse in der Kolbenmaschine auch besser wider, da das Anpressen der Kolbenringe an die Zylinderwand über einen aufgebrachten Druck erfolgt. Der ermittelte nominelle Druck war bei Ringen mit einer durch physikalische Gasphasenabscheidung erstellten Schichten am größten. Der Unterschied zu Ringen mit einer Chromschicht mit Aluminiumoxid betrug 49 %. Ringe mit Nanodiamanten anstelle von Aluminiumoxidpartikel in der Chromschicht hatten einen 15 % höheren nominellen Druck. Ringe mit PVD-Beschichtung hatten höhere Spitzen im Reibkoeffizienten bei Krafterhöhung als die anderen geprüften Ringe. Des Weiteren konnte durch Analysen im Lichtmikroskop und im Rasterelektronenmikroskop das Vorhandensein von Triboschichten und Materialübertrag durch adhäsiven Verschleiß zwischen Zylinder und Ring nachgewiesen werden. Dieser adhäsive Verschleiß war bei Ringen mit PVD-Beschichtung nicht so stark vorhanden wie bei den anderen geprüften Ringen, was womöglich auf das Verfahren der physikalischen Gasphasenabscheidung und den in der Schicht vorhandenen Stickstoff zurückzuführen ist. In weiteren Arbeiten könnte der adhäsive Verschleiß und die starke Erhöhung des Reibko
gesperrt bis 03-05-2029
Keywords: Tribologie; Kolbenringe; chrombasierte Beschichtungen; CKS; GDC; PVD; TE77; Fresstragfähigkeit; tribology; piston ring; chromium-based coating; CKS; GDC; PVD; TE77; scuffing limit

Experimentelle Untersuchung des Fluidisierungsverhaltens einer Glockendüse in einer Wirbelschichtversuchsanlage - Schlemmer, Nina (2024)
In der vorliegenden Masterarbeit wird das Fluidisierungsverhalten einer Glockendüse und einer Standarddüse für Wirbelschichtanwendungen charakterisiert und verglichen. Es soll untersucht werden, ob durch den Einsatz von Glockendüsen die Bildung von Totzonen bei der Fluidisierung einer Feststoffschüttung durch einen Gasstrom vermieden werden kann. Diese verändern den Wärmeübergang und damit die Prozessbedingungen der Wirbelschichtanlage. Die Totzonenbildung wird im Wesentlichen von der Zufuhr des Strömungsmediums und somit von der Düsengeometrie beeinflusst. Für die Charakterisierung des Fluidisierungsverhaltens werden die beiden Düsen in einem Kaltmodell einer Wirbelschichtversuchsanlage verbaut und experimentell der Druckverlust über die Düsen, das Fluidisierungsbild, der Bettdruck und die Blasenbildung ermittelt. Daraus ergibt sich, dass der Druckverlust beider Düsen ident ist und demnach nicht von der Glocke beeinflusst wird. Weiters kommt es durch die Glockendüse zu einer Vergrößerung des fluidisierten Bereiches und damit zu einer Minimierung der Totzonenbildung. Zusätzlich verhindert die Glocke das Durchfallen der Feststoffpartikel und das Erosionspotential des Innenteils der Glockendüse wird verringert. Insgesamt zeigt sich, dass der Einsatz von Glockendüsen zu einer Reduzierung des Totzonenbereichs führt.
gesperrt bis 01-02-2029
Keywords: Wirbelschicht; Düsengeometrie; Glockendüse; Wirbelschichtversuchsanlage; Fluidised bed; Nozzle geometry; Bell nozzle; Fluidised bed pilot plant

Exploration hochreiner Semmeringquarzite für die Glasindustrie - Zahrl, Marcel (2024)
Der Haupteinsatzstoff für die Produktion von Weiß- und Buntgläsern ist hochreiner Quarz. Der Bedarf an hochreinen Quarzrohstoffen für die steirische Glasindustrie wird derzeit aus nur zwei Quarzsandlagerstätten gedeckt. Um die Versorgungssicherheit zu gewährleisten, wird im Zuge des Projektes ¿MRI_Quarz - Untersuchung von Vorkommen hochwertiger Quarzrohstoffe im südöstlichen Bundesgebiet¿ auf hochreine Quarzrohstoffe prospektiert und exploriert. Auf Basis der Prospektionsergebnisse wurde die Semmeringquarzitlagerstätte des Steinbruchs Karl Friesenbichler GmbH Nfg & Co KG (Unterdissau, Bez. Weiz, Stmk.) als Explorationsziel ausgewählt. Die Lagerstätte kann geologisch den permotriassischen Metasedimenten der Vorau-Decke (Silvretta-Seckau-Deckensystem), welche lokal im Fischbacher Fenster aufgeschlossen ist, zugeordnet werden. Hauptkriterium für die Einordnung als hochreiner Quarzrohstoff ist ein Fe2O3-Gehalt von unter 0,03 m% (Weißglas) bzw. 0,5 m% (Buntglas). Als maßgebende Fe-führende Mineralphase wurden phengitische Muskovite, mit durchschnittlich 5,43 m% FeO, identifiziert. Zusätzlich zu den Haupt- und Nebengemengteilen Quarz bzw. Hellglimmer, kommen Albit, Alkalifeldspat, Apatit, Baryt, Gorceixit, Kaolinit, Monazit, limonitisierter Pyrit, Rutil und Zirkon akzessorisch vor. Auf Basis von RFA-Messungen können die grünen Quarzite (1607 ppm Fe2O3) als passend für die Buntglasherstellung, und die weißen Quarzite (309 ppm Fe2O3) als passend für die Weißglasherstellung angesehen werden. Die weißen Quarzite kommen nur als hydrothermal entfärbte Alterationszonen im grünen Quarzit vor und sind häufig mit Verheilungen aus glasigem Quarzit (65 ppm Fe2O3) assoziiert. Die Ausbildung der Alterationen zu hochreinen Quarziten dürfte mit einer tektonischen und hydrothermalen Aktivität im Zuge der der Öffnung des Fischbacher Fensters einhergegangen sein. Um die geforderten hochreinen Qualitäten zu erreichen sind vermutlich ein selektiver Abbau und eine optische Sortierung notwendig. Für zukünftige Prospektionsarbeiten wurde die Eignung einer Multielektroden-Widerstandsmessung untersucht. Eine Abgrenzung der hochreinen Quarzite zum Nebengestein sollte auf Basis ihres höheren Widerstandes, bedingt durch den geringeren Hellglimmergehalt, möglich sein. Es gilt zu bedenken, dass der kleinräumige Aufbau der Alterationszonen unterhalb der Auflösungsgrenze der Messmethode liegen könnte und potenziell nur massive Anhäufungen von Alterationszonen zuverlässig detektiert werden können. Im Zuge dieser Arbeit wird ein Methodenvergleich zwischen einer portablen LIBS-Analyse im Gelände und der Labor-RFA angestellt. Nach vorangegangener Kalibration mit Quarzit-Pulverpresslingen, die mittels wellenlängendispersiver RFA analysiert wurden, können LIBS-Messwerte in den Grenzen Si: 41-48 m%, Fe: 0-0,26 m%, Al: 0-2 m%, Mg: 0-0,07 m% und Ba: 0-0,24 m% als korrekt angesehen werden. Speziell Fe-Gehalte unter 0,05 m% werden exakt gemessen. Grundsätzlich ist festzuhalten, dass in den Semmeringquarziten des Fischbacher Fensters Alterationszonen mit hochreinen Quarzvarietäten existieren, die für die Weiß- bzw. Buntglasherstellung geeignet wären.
nicht gesperrt
Keywords: Semmeringquarzit; Quarzrohstoff; Rohstoff; hochreiner Quarzit; Glasindustrie; Fischbacher Fenster; handheld LIBS; LIBS; Semmering-Quartzite; Quartz raw material; Raw material; high-purity quartzite; glass industry; Fischbach window; handheld LIBS; LIBS

Extended Rayleigh-Ritz Autoencoder with Distribution-Free Statistics - Terbuch, Anika; Ninevski, Dimitar; O´Leary, Paul; Harker, Matthew; Mücke, Manfred (2024)

Fabrication and Mechanical Characterisation of Advanced Alumino-Borosilicate Glasses - Ladinger, Lukas (2024)
The designing of new glasses has proven to be a very challenging task due to the various complications and impacts every chemical element in use has on the resulting glass. During this master thesis the impact of the network modifier (NWM) barium on an aluminoborosilicate (ABS) glass has been analysed. To gain a better understanding of how the ratio of [NWM]/[Al_2 O_3 ] influences physical and mechanical properties, four different Ba-ABS glass compositions were created. While the content of barium differed for every composition, the [SiO_2 ]/[B_2 O_3 ] ratio as well as the portion of [Al_2 O_3 ] stayed constant throughout the series. It has been found that hardness, density and various elastic moduli (Young¿s, shear and bulk) rose with increasing barium content, whereas properties such as crack resistance and indentation fracture resistance decreased. A probable explanation for this behaviour could be the transformation of three coordinated, trigonal boron (B^III ) into four coordinated, tetrahedral boron (B^IV ) due to local charge stabilization. Other properties like brittleness and fracture toughness did not show any correlation with the amount of barium in the glasses. The results of this analysis deepen the understanding of how the amount of NWM influences the physical and mechanical properties of ABS glasses and therefore help to further tailor ABS glasses to specific applications.
no embargo
Keywords: Netzwerkmodifikator; Mikroskopie; Bruchzähigkeit; Härte; Risswiderstand; network modifier; microscopy; fracture toughness; hardness; crack resistance

Fabrication of multi-material dielectric elastomer actuators with the additive manufacturing process of material extrusion - Beier, Philipp (2024)
Dielectric elastic actuators (DEA) are versatile devices with various applications, such as in the field of soft robotics or sensor measurement technology. Additive manufacturing (AM) enables the production of various materials with complex geometries in a layer-by-layer process, and material extrusion (MEX) is a highly promising subcategory of it. In this process, filaments are utilised and passed through an extruder to create the component in a sequential manner, layer by layer. There are various methodologies for producing parts made of multiple materials. This study employed a multi-extruder approach to address the issues associated with processing soft materials that are difficult to handle. Materials that contain additives like graphite can potentially contaminate the nozzle, resulting in increased difficulty when attempting to clean it. Therefore, a novel tool was developed to manage four extruders on a single axis. Moreover, they were mounted on two separate movable carriages, each capable of accommodating two extruders. Dual extruders have become well-established in the industry and are widely used in the commercial sector. It is an efficient and simple method to simultaneously process two materials in a single print. In order to verify the precision and consistency of the custom printer, various measurements were performed, including capacitance and the overall thickness of the produced parts. The machine was required to reliably produce layers with a height of 70 ¿m. The deviation reached a maximum of 8%, which is a commendable outcome considering the limitations of the hardware. Another section of the thesis focused on the analysis of various types of polyurethanes (TPU) for the purpose of DEAs. The study examined the impact of varying shore hardness levels and printing orientations on material selection. The investigation revealed that using an infill orientation of either 0° or 90° yielded similar values for both the Young's modulus and flexural modulus. This can be attributed to the seamless melding of the strings, resulting in minimal differences between orientations. Regarding the shore hardness of the materials, they exhibited comparable bending stiffness across a range of 83A to 20D. A significant increase of over 20% in the Young's modulus was observed only when the hardness reached 40D. The moduli of the TPUs used as electric-conductive materials were even higher. This phenomenon may be attributed to the graphite particles, which embed themselves within the gaps in the chains, thereby enhancing the material's rigidity. The DEAs that were produced underwent displacement measurements to determine their functionality. As anticipated following the mechanical test, all actuators exhibited comparable displacements. The findings suggest that the capacitance of the actuator is the main factor influencing the result. When the capacitance is decreased, the displacement is proportionally reduced. Based on the actuators that were tested, a prototype application was designed and manufactured. Three actuators were linked in parallel and served as gripping arms.
no embargo
Keywords: Additive Fertigung (AF); Dielektrische Elastomeraktoren (DEA); Multimaterial-Extruder; Additive manufacturing (AM); Dielecttric elastomer actuators (DEA); Multi-material extruder

Faserbeton im Tunnelbau - Kühbacher, Manuel (2024)
Beim maschinellen Tunnelvortrieb kommen für Ausbau und Hohlraumsicherung Tübbinge zum Einsatz, welche aufgrund der aktuell in Österreich geltenden Richtlinien lediglich aus Stahlbeton realisierbar sind. Da Faserbetontübbinge in zahlreichen Ländern bereits erfolgreich eingesetzt werden, soll im Zuge eines Forschungsvorhabens mit Hilfe von umfangreichen Untersuchungen das Verhalten von Faserbetontübbingen aufgezeigt werden, um folglich eine Grundlage für deren Einsatz zu schaffen. Mit den zu Beginn dieser Arbeit durchgeführten Mischungsversuchen im Labormaßstab, konnte der Einfluss von unterschiedlicher Faserdosierung auf das Frisch- und Festbetonverhalten dargestellt werden. Als Faserwerkstoffe wurden dabei Stahl- und Kunststofffasern herangezogen. Anhand der gewonnenen Erkenntnisse der Laborversuche wurde je eine Kunststoff- und Stahlfasermischung ausgewählt, um in weiterer Folge in einem Betonfertigteilwerk Tübbinge im Realmaßstab herzustellen. Die darauffolgenden Belastungsversuche lieferten zahlreiche Erkenntnisse zum Trag- und Verformungsverhalten von Faserbetontübbingen. Die Ergebnisse der Großversuche wurden anschließend jenen aus den vorab im Labormaßstab durchgeführten Versuchen gegenübergestellt, um eine Vergleichbarkeit der Ergebnisse zu untersuchen. Einen weiteren Schwerpunkt der Untersuchungen stellte die Faserorientierung und -verteilung im Tübbing dar. Dazu wurden Bohrkerne aus Faserbetontübbingen entnommen und mittels Computertomographie analysiert. Anschließend folgten an den Bohrkernen eine Reihe petrophysikalischer und geotechnischer Versuche, um Einflüsse der Faserorientierung aufzeigen zu können. Diese umfassten auch die Durchführung von Druckversuchen an Stahlfaserbetonproben bei simultanem Röntgen im Computertomographen, um die Rissentwicklung in der Probe zu detektieren. Abschließend wurden Themen zur Nachhaltigkeit und Praxistauglichkeit von Faserbetontübbingen behandelt. Dazu wurden Versuche zur Bewertung der Streustromkorrosion durchgeführt, sowie der ökologische Aspekt von Faserbeton im Vergleich zu Stahlbeton untersucht.
nicht gesperrt
Keywords: Faserbetontübbinge; Faserorientierung; Stahlfaserbeton; Kunststofffaserbeton; Faserspritzbeton; Tübbingprüfstand; fiber reinforced concrete; fiber reinforced segmental lining elements; steel fiber reinforced concrete; synthetic fiber reinforced concrete; fiber orientation

Finite element analysis of heat transfer in ski presses - Hösele, Lukas (2024)
In this thesis the production process of press hardening in ski production is investigated in order to find out if there is an economic and efficient way to improve the effort and cost. The current process uses oil in order to heat up moulds containing the layers of a ski combined with an adhesive in between. The layered and glued ski is pressed, heated and, after a certain holding period, cooled down again. The energy for heating and holding is provided by hot oil while the cooling happens with water pumped through the heating elements which results in the need of two separate cycles. The goal of this thesis is to build up a FEM model which is able to simulate this process by analyzing the current process and the methods of how the heat transfer takes place in combination with measurements of the temperature progression along the heating elements as well as measurements of both the inlet temperatures and outlet temperatures. In addition to that the FEM model must be able to simulate an alternative process with the use of oil instead of water during the cooling phase and therefore lay the base for giving a recommendation whether an adaption of the process in this way could be possible or not. The FEM model is created with ABAQUS® while the 3D-model is built out of a combination of already existing and new models. An uncoupled heat transfer analysis is used to calculate the process. The heat transfer coefficient is controlled and calculated during the simulation by the use of a subroutine implemented in ABAQUS®. The simulation results are then compared with the measurements of the real process and the simulation is calibrated until the accuracy is sufficient. Using this FEM model, the material parameters of the fluid during the cooling phase are changed within the subroutine to calculate the expected results for the use of oil instead of water for this step. This new cooling process is simulated in two ways. With the use of the current oil and varying volume flow as well as additional cooling time and with alternative oils, which have a lower viscosity, and increased volume flow. The results indicate that increasing the volume flow for the current oil has little effect in the range that could technically be achieved as with a certain viscosity the flow profile remains laminar and therefore the heat transfer is very low and takes a lot of time. However, by using a less viscous oil it is possible to remain turbulent even at room temperatures and thus, the cooling is sufficient to achieve the necessary end temperature in the same time as with water as a coolant. Finally, the simulation results show that there are two ways to achieve the necessary cooling temperature with oil as a coolant. The first is to increase the cooling time, which is not very efficient, while the second is the use of a low viscosity oil.
embargoed until 05-02-2029
Keywords: Process analysis; Process optimization; Heat transfer analysis; Forced convection; Conduction; Finite Element simulation; Prozessanalyse; Prozessoptimierung; Wärmeanalyse; Erzwungene Konvektion; Wärmeleitung; Finite Elemente Simulation

Flexible und biobasierte Epoxidharzsysteme - Schwaiger, Markus (Entwicklung, Optimierung und Anwendung in hybriden Werkstoffen, 2024)
Um die Abhängigkeit von fossilen Rohstoffen zu verringern, gewinnen biobasierte Kunststoffe immer mehr an Bedeutung. Dazu zählen auch hybride Werkstoffe, wie Faserverbundwerkstoffe oder Verbundwerkstoffe, die aus solchen biobasierten Kunststoffen hergestellt werden. Diese biobasierten hybriden Werkstoffe weisen, durch die Kombination von Materialien mit unterschiedlichen physikalischen Eigenschaften, sowohl technologische als auch ökologische Vorteile (Einsparung fossiler Rohstoffe; reduzierte CO2-Emissionen) gegenüber herkömmlichen petrochemischen Materialien auf. Bislang wurden hier allerdings überwiegend möglichst steife Epoxidharze in Betracht gezogen, um Werkstoffe für höchste mechanische Anforderungen zu erhalten. Das Potential von flexiblen (biegeweichen) Epoxidharzen für biobasierte hybride Werkstoffe wurde bislang nicht umfassend untersucht. Aus diesem Grund beschäftigte sich diese Arbeit mit der Entwicklung, Charakterisierung und Optimierung von biobasierten hybriden Werkstoffen unter Verwendung flexibler Epoxidharze. Dies inkludiert sowohl flexible Faserverbundwerkstoffe (biegeweiche Materialien mit gleichzeitig hohen mechanischen Eigenschaften für den Einsatz als technische Textilien) als auch Verbundwerkstoffe mit erhöhter Bruchzähigkeit. Besonderer Fokus lag hierbei auf einem möglichst hohen biobasierten Kohlenstoffgehalt sowie der Vermeidung gesundheitlich bedenklicher Chemikalien.Hierfür wurde zunächst ein biobasiertes Epoxidharz auf Basis von Pflanzenölen und Sebacinsäure entwickelt, welches bei Raumtemperatur flexibel ist. Dazu wurden verschiedene industriell verfügbare epoxidierte Pflanzenöle mit variierendem Epoxid-Äquivalenzgewicht und Reinheitsgrad herangezogen. Unter Verwendung eines experimentell mittels dynamischer Differenzkalorimetrie und Infrarotspektroskopie optimierten Mischungsverhältnisses (Carboxyl/Epoxid-Gruppe im molaren Mischungsverhältnis von R=0,69), wurden mit einem epoxidertem Leinöl mit medizinischem Reinheitsgrad die besten mechanischen Eigenschaften erzielt (Zugfestigkeit von 1,3 MPa bei einer Bruchdehnung von 27%). Diese waren unabhängig vom Epoxid-Äquivalentgewicht im Bereich industrieller Schwankungen. Das biobasierte Epoxidharz war zudem unter kontrollierten Kompostierbedingungen biologisch abbaubar (32% in 52 Tagen).Für die flexiblen Faserverbundwerkstoffe wurden Gestricke als Verstärkungsstruktur herangezogen. Um Kenntnisse über das Verformungsverhalten solcher flexiblen Faserverbundwerkstoffen zu gewinnen wurden Zugversuche unter Verwendung von digitaler Bildkorrelation durchgeführt. Dies erfolgte anhand einer Interlock-Struktur und einem etablierten petrochemischen Harzsystem zum Aufbau einer soliden Wissensgrundlage. Zusätzlich wurde der Einfluss des Fasermaterials auf die Zugeigenschaften der Gestricke und Faserverbundwerkstoffe ermittelt. Basierend auf diesen Ergebnissen wurden Gestricke aus Viskose als Verstärkungsstruktur für das biobasierte Epoxidharz ausgewählt. Hierbei wurde der Einfluss drei unterschiedlicher Strickstrukturen auf die Zug-, Biege-, Weiterreiß- und Durchstoßeigenschaften untersucht. Die beste mechanische Performance (höchste Zug- und Weiterreißfestigkeit sowie absorbierte Energie im Durchstoßversuch) wurde mit der Interlock-Struktur erzielt, wobei hier der Biegemodul im mittleren Bereich lag. Allgemein zeichnen sich die entwickelten Faserverbundwerkstoffe durch eine besonders hohe Flexibilität aus (geringer Biegemodul im Bereich zwischen 21 und 207 MPa), wodurch sie äußerst vielversprechend für den Einsatz als technische Textilien sind.Beim Werkstoffverbund war das Ziel, durch den Einsatz des flexiblen, biobasierten Epoxidharzes eine Erhöhung der Bruchzähigkeit in einem steifen Epoxidharz zu erreichen. Dazu wurde ein steif-flexibel-steifer Schichtaufbau realisiert, bei welchem das entwickelte biobasierte Epoxidharz die flexible Mittelschicht bildete. Für die steifen Außenschichten wurde Zitronensäure als Härter für das epoxidierte Leinöl eingesetzt, wodurch nach Aushärtung ein steifes Epoxidharz erzielt wurde. Die Bruchzähigkeit wurde mittels monotonen 3-Punkt-Biegeversuchen an einseitig gekerbten Prüfkörpern ermittelt. Durch den gewählten Schichtaufbau wurde bereits bei einer Mittelschichtdicke von 0,1 mm die Bruchzähigkeit des steifen Epoxidharzes um das 13-fache erhöht. Allerdings nahm dabei die Steifigkeit um 44% ab. Eine Erhöhung der Mittelschichtdicke auf 1,3 mm führte zu einem weiteren Anstieg der Bruchzähigkeit auf das 24-fache, aber auch zu einer Reduktion der Steifigkeit um 67%.Schlussfolgernd wurde in dieser Arbeit die Verwendbarkeit biobasierter, flexibler Epoxidharze in hybriden Werkstoffen wie Faserverbundwerkstoffen und Werkstoffverbunden demonstriert. Um die Vorteile gegenüber herkömmlichen Epoxidharzen in Zukunft weiter auszubauen, gilt es vor allem die Aushärtedauer und somit den erforderlichen Energieaufwand bei der Herstellung zu reduzieren.
nicht gesperrt
Keywords: fiber-reinforced composite; multi-layer composite; linseed oil; epoxy; flexible; renewable; knitted fabric; biodegradable; bio; Faserverbundwerkstoff; Werkstoffverbund; Leinöl; Epoxid; flexibel; erneuerbar; Gestrick; biologisch abbaubar; bio

Flotation of a Complex Sulphide Ore: Raw Material Characterization and Optimization of Process Parameters - Huraira, Abu (2024)
This master thesis investigates the separation of complex sulphide minerals present in a fluorite-barite ore. The industrial sample analyzed in this work contains significant amounts of copper and silver-bearing phases. These phases are enriched into a valuable concentrate by flotation, with the long-term objective of maximizing the recovery of the valuable components through process optimization. Grinding tests are first conducted at a laboratory scale using a wet-operated rod mill. Critical flotation feed characteristics and comminution indexes are determined from the grinding products such as particle size distributions and specific energy consumption. Lab-scale flotation tests are thus conducted to evaluate the effects of feed particle size, conditioning parameters, collector types and dosages, and the number of flotation stages. Particle size class-specific analyses in the form of Henry-Reinhardt diagrams for the flotation tailings are finally conducted to refine the process parameters and to gain knowledge about its limits.
embargoed until 05-06-2029
Keywords: Grinding; Particle Size Distribution; Bond Work Index; Henry-Reinhardt Diagrams; Flotation; Reagents; Yield; Mahlen; Partikelgrößenverteilung; Bindungsarbeitsindex; Henry-Reinhardt-Diagramme; Flotation; Reagenzien; Ausbeute

Fracture network characterisation of the Balmuccia peridotite using drone-based photogrammetry, implications for active-seismic site survey for scientific drilling - Menegoni, Niccolò; Panara, Yuri; Greenwood, Andrew; Mariani, Davide; Zanetti, Alberto; Hetényi, György (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
The presence of discontinuities (e.g. faults, fractures, veins, layering) in crystalline rocks can be challenging for seismic interpretations because the wide range of their size, orientation, and intensity, which controls the mechanical properties of the rock and elastic wave propagation, resulting in equally varying seismic responses at different scales. The geometrical characterisation of adjacent outcrop discontinuity networks allows a better understanding of the nature of the subsurface rocks and aids seismic interpretation. In this study, we characterise the discontinuity network of the Balmuccia peridotite (BP) in the Ivrea–Verbano Zone (IVZ), northwestern Italy. This geological body is the focus of the Drilling the Ivrea–Verbano zonE (DIVE), an international continental scientific drilling project, and two active seismic surveys, SEismic imaging of the Ivrea ZonE (SEIZE) and high-resolution SEIZE (Hi-SEIZE), which aim to resolve the subsurface structure of the DIVE drilling target through high-resolution seismic imaging. For fracture characterisation, we developed two drone-based digital outcrop models (DOMs) at two different resolutions (10–3–10 m and 10–1–103 m), which allowed us to quantitatively characterise the orientation, size, and intensity of the main rock discontinuities. These properties affect the seismic velocity and consequently the interpretation of the seismic data. We found that (i) the outcropping BP discontinuity network is represented by three more sets of fractures with respect to those reported in the literature; (ii) the discontinuity sizes follow a power-law distribution, indicating similarity across scales, and (iii) discontinuity intensity is not uniformly distributed along the outcrop. Our results help to explain the seismic behaviour of the BP detected by the SEIZE survey, suggesting that the low P-wave velocities observed can be related to the discontinuity network, and provide the basic topological parameters (orientation, density, distribution, and aperture) of the fracture network unique to the BP. These, in turn, can be used for interpretation of the Hi-SEIZE seismic survey and forward modelling of the seismic response.
Keywords: Remote sensing; Fracture intensity; Digital outcrop model (DOM); Rock discontinuity; Fault; SEismic imaging of the Ivrea ZonE (SEIZE); Ivrea–Verbano Zone (IVZ); Crystalline rock

Framework for the Design as well as Economic and Environmental Optimization of Geothermal District Heating and Cooling Networks - Stipper, Paul (2024)
Climate Change and the provision of affordable, reliable energy have become an increasingly prevalent subject of discussion. Over the past decade, the European Union has made significant efforts to decarbonize its electricity sector, while the heating and cooling sector, responsible for half of Europe¿s final energy consumption, has received less attention. District heating and cooling systems exemplify best practice approaches for delivering locally available, cost effective, and low carbon thermal energy. Furthermore, they provide interesting possibilities for the substitution of climate damaging generation technologies through greener options in the heating and cooling sector on a large scale. In particular, the exploitation of the shallow geothermal potential presents interesting opportunities, prompting intensive research into how technologies such as heat pumps and auxiliary devices like thermal energy storages can be effectively integrated into these networks. One objective of this work is to provide an understanding of the district heating and cooling sector and identify measures that can be implemented for its sustainable development, with a focus on the exploitation of geothermal energy. Therefore, the thesis first examines the functionality and historical development of district heating and cooling systems, aiming to provide an understanding of the status quo and anticipate future trends. Building up on this knowledge, relevant technologies for their retrofitting, and how these technologies can be effectively integrated into such networks, are explained. The second objective, which is the main focus of this work, is to offer a framework for designing and optimizing geothermal generation facilities in district heating and cooling networks. In the design process, a hypothetical district heating and cooling network demand from Madrid, Spain was used as a representative example. Two Python based programs were written to enable a high degree of automation in the design and optimisation process, as well as to facilitate handling large amounts of data. In order to get insights into the thermodynamic behaviour of such a system, a generation facility, which exploits the shallow geothermal potential, was modelled in the simulation environment TRNSYS. With the generated data, a sensitivity analysis concerning the power plant¿s topology was conducted to examine the impact of varying topology parameters on the levelized cost of energy, specific CO2 emissions, as well as the heating and cooling coverage achievable. The results indicate the optimal sizes for heat and cold storage systems, as well as the optimal number of reversible heat pumps.
no embargo
Keywords: Fernwärme; Fernkälte; Geothermie; Wärmepumpe; Kompressionskältemaschine; Dekarbonisierung; Automatisierung; TRNSYS; Python; District heating; District cooling; Geothermal energy; Heat pump; Compression chiller; Decarbonization; Automation; TRNSYS; Python

Front Cover Story for peer-reviewed publication titled "Plasma-Treated Cobalt-Doped Nanoporous Graphene for Electrochemical Applications" - Knabl, Florian; Kostoglou, Nikolaos; Gupta, Ram K.; Tarat, Afshin; Hinder, Steven J.; Baker, Mark; Rebholz, Claus; Mitterer, Christian (C—Journal of Carbon Research, Volume 10, Issue 2, June 2024, 2024)

Functional magnetic composite materials with tuneable magnetic properties - Payer, Philipp (2024)
Sustainable electric propulsion systems require sophisticated combination of pole design and magnetic materials to provide the needed torque at a wide range of rotational speeds. One possible way to meet this challenge is the application of tailored magnetic materials. Magnetic composites often act as functional materials with properties tailored to their applications. With microstructural modification, properties like coercivity (Hc), remanence (Br), saturation magnetization (Ms) and maximum energy product (BHmax) can be optimized.In this thesis, the feasibility of magnetic composite fabrication by high-pressure torsion (HPT) is studied. Magnetic composites are fabricated using the multi-sector disk approach for bulk materials. In addition, the magnetic composites are fabricated by powder mixing and HPT. HPT-deformation experiments of single phase materials are conducted using Polymers (PTFE, PEEK, POM, PVC, PP) and commercial Y35-ferrite ceramics. To study the co-deformation of polymers, copper (Cu) –polymer composites are fabricated by a multi-sector disk approach. In a 2nd step, composites are fabricated using Sr-M-type hexaferrite phase as the hard magnetic component and iron (Fe), copper (Cu), chromium (Cr) and PTFE as a matrix. Furthermore, the effect of HPT deformation on commercial Y35-ferrites and the AlNiCo grades: AlNiCo 3, AlNiCo 5, and AlNiCo 8 are studied. Samples are examined by X-ray difraction (XRD), scanning electron microscopy (SEM), and light microscopy.The magnetic properties of pristine magnets, deformed Y35-ferrites, powder composites, and deformed AlNiCo alloys are investigated. For magnetic measurements, a hystograph is used. To determine microstructural evolution, commercial Y35-ferrite is annealed at 300 ◦C, 500 ◦C, 700 ◦C, 900 ◦C and 1100 ◦C, under atmospheric conditions and analyzed by XRD and light microscopy. HPT experiments reveal the deformability of bulk polymers to be limited. Properties of PTFE and POM are considered suitable for composite fabrication. Plastic incompatibility of bulk ferrite ceramic with metals and polymers leads to the fabrication of no structurally stable composites, using the multi-sector disc approach. Polymer-metal composites are successfully fabricated using the multi-sector disk approach. Application of post deformation annealing (PDA) combined with pressing increases the adherence between layers in polymer-metal and polymer-ceramic composites. Moreover, powder composites are successfully fabricated with ceramic-metal and ceramic-polymer combinations. Despite a homogeneous distribution and sufficient refining no coupling between the magnetic phases is observed.The evolution of magnetic and structural properties shows a dependence on the powder combination used and is in good agreement with the literature. HPT of commercial Y35-ferrites leads to a grinding of sintered grains followed by a re-consolidation by pressing and interlocking of particles. These results are in good agreement with the literature.Annealing experiments show a sufficient stabilized microtructure. In addition, observed substitution effects of calcium (Ca) and aluminum (Al) lead to a shrinkage of the unit cell accompanied by an increase of Hc.
no embargo
Keywords: Hard magnetic composites; AlNiCo; Ferrite; Magnets; HPT; Hartmagnetische Verbundwerkstoffe; AlNiCo; Ferrit; Magnete; HPT

Herstellung von Farbmasterbatches mit unterschiedlichen Trägermaterialien für die weitere Verwendung bei der Produktion von PET-Folien und -Platten - Maurer, Carina (2024)
In der folgenden Arbeit wurden verschiedene Trägermaterialien für die Herstellung von Farbmasterbatches und die Herstellung verschiedener Produkte mit Polyethylenterephthalat, kurz PET, als Basismaterial mit den Farbmasterbatches untersucht. Unter Farbmasterbatches ist die Zusammensetzung von Kunststoffen mit Farbpigmenten gemeint, welche einen höheren Anteil an Pigmenten enthält. Der Vorteil dieser Farbmasterbatches ist das Vermeiden von diversen Verarbeitungsfehlern bei der Produktherstellung aufgrund der verschiedenen Materialformen und unterschiedlicher Verarbeitungsbedingungen. Somit wird bei der Masterbatchherstellung ein Pigment mit einem Polymer vermischt und bei der eigentlichen Produktherstellung zwei Granulate. Zuerst wurde eine alternative Herstellungsmethode zum Compoundieren untersucht. Die Herstellung am Kneter ist diskontinuierlich und weist einen höheren Einfluss auf die Materialien auf, weshalb bei den fortlaufenden Untersuchungen die Materialien am kontinuierlichen Compounder verarbeitet wurden und die alternative Herstellungsmethode außer Acht gelassen wurde. Für die Masterbatches wurden zuerst die möglichen Trägermaterialien am Compounder ohne Pigment verarbeitet und anschließend mit der Zugabe der verschiedenen Pigmente. Anschließend wurden einerseits rheologische Messungen durchgeführt, um die möglichen Trägermaterialien mit dem PET zu vergleichen. Auf der anderen Seite wurden thermogravimetrische Analysen der Masterbatches durchgeführt, um die Zusammensetzung von Polymer und Pigment zu untersuchen. Im nächsten Schritt wurden die Produkte mit der Zugabe der hergestellten Masterbatches produziert und mit den Produkten wiederum die Viskosität gemessen. Anhand dieser Ergebnisse konnten bereits einige Aussagen bzgl. der möglichen Trägermaterialien getroffen werden. Außerdem wurden auch Folien am Laborextruder erzeugt, damit diese optisch beurteilt werden und deren Ergebnisse in die Bewertung miteinfließen konnten. Durch diese Untersuchungen wurden mögliche Trägermaterialien für die Produktion von färbigen PET-Produkten gefunden. Zudem wurde anhand der Arbeit auch erkannt, dass das Basismaterial nicht zwingend auch als Trägermaterial eingesetzt werden kann.
gesperrt bis 11-03-2026
Keywords: colormasterbach; color pigment; PET; polymer processing; compounder; viscosity; films; TGA; Farbmasterbatch; Farbpigmente; PET; Kunststoffverarbeitung; Compounder; Viskosität; Folien; TGA

High-pressure-torsion-induced segregation, precipitation and grain refinement of Al-(Si, Mg and Cu) binary alloys - Feng, Man; Wu, Qinli; Xue, Jing; Luo, Zhenjiao; Wang, Zhiping; An, Xianghai; Liao, Xiaozhou; LI, Jiehua; Jin, Shenbao; Sha, Gang (JOURNAL OF MATERIALS SCIENCE & TECHNOLOGY, 2024)

Hochauflösende Untersuchung der Nb-Löslichkeit in mikrolegierten Stählen - Luger, Thomas (2024)
Das Mikrolegierungselement Nb spielt bei der Herstellung hochfester niedriglegierter Stähle eine wichtige Rolle, da es die Kornfeinung während des thermomechanischen Herstellungsprozesses durch Ausscheidung feiner Karbide oder Karbonitride maßgeblich beeinflusst. In dieser Arbeit wird daher das Löslichkeitsverhalten von Nb in Abhängigkeit von der Austenitisierungstemperatur zweier mikrolegierter Nb-Ti-Stähle mit Hilfe der Atomsondentomographie untersucht. Zusätzlich werden verschiedene Gefügemerkmale mit unterschiedlichen Ätzverfahren mittels Licht- und Rasterelektronenmikroskopie analysiert. Die Ergebnisse der metallographischen Charakterisierung der mit Nital geätzten Schliffe ergaben, dass im Ausgangszustand ein ferritisch-perlitisches Gefüge vorliegt und keine Unterschiede in den Phasenanteilen und Korngröße zwischen den Legierungen messbar ist. Nach den Wärmebehandlungen liegt überwiegend ein bainitisches Gefüge mit geringem Ferritanteil vor. Die mit einem auf Pikrinsäure basierendem Ätzmittel geätzten Schliffe belegen die erwartete Zunahme der Austenitkorngröße mit steigender Austenitisierungstemperatur. Atomsonden-Messungen zeigen, dass mit steigender Austenitisierungstemperatur mehr Nb gelöst werden kann, wobei die Löslichkeit ab 950°C deutlich zunimmt und sich bei hohen Austenitisierungstemperaturen von 1150°C und darüber einem Plateau nähert. Bei Austenitisierungstemperaturen von 950 und 1050°C ist kein Einfluss des Ti/N-Verhältnisses auf die Nb-Löslichkeit festzustellen. Der Vergleich der gemessenen Ergebnisse mit dem theoretischen Löslichkeitsprodukt nach Irvine zeigt zunehmende Abweichungen bei Austenitisierungstemperaturen oberhalb von 950°C, die dadurch erklärt werden können, dass dieses Modell weder das Vorhandensein von komplexen (Nb,Ti)(C,N)-Ausscheidungen noch die Größe oder Verteilung der Ausscheidungen berücksichtigt.
gesperrt bis 18-06-2029
Keywords: HSLA-Stahl; Atomsondentomographie; Nb-Löslichkeit; Ti/N-Verhältnis; Metallographie; Nb-Ti mikrolegierter Stahl; HSLA Steel; Atom Probe Tomography; Nb-Solubility; Ti/N-Ratio; Metallography; Nb-Ti Microalloyed Steel

How cracks induced by straining influence the tribological properties of Mo films deposited on polyimide substrates - Kobierska, Edyta; Cordill, Megan J.; Franz, Robert; Rebelo de Figueiredo, Marisa (Metals : open access journal, 2024)

Hybrid Machine Learning in Conjunction with Physical Systems - Terbuch, Anika (2024)
This thesis investigates methods and architectures for machine learning that are particularly suited for the analysis of data emerging from the observation of physical processes and systems. In this context, two main areas have been addressed. The first area is centered around techniques for the detection and characterization of anomalies occurring in a physical process for multi-channel sensor data acquired in real-time. These techniques generalize to the detection of anomalies in multivariate time-series data; secondly, new mathematical approaches, together with a new machine learning architecture, are presented that enable the embedding of a-priori knowledge about the system behavior. This ensures that the solutions obtained are consistent with the physics of the system being observed. This resolves the issue that purely data-driven systems can only make statements about the data; however, to make statements about a system from data, it is necessary to embed a-priori knowledge about the behavior of the system. The second major issue addressed is combining the Rayleigh-Ritz method with machine learning. This required the development of new synthesis algorithms for admissible functions that ensure a hard fulfillment of constraints. The Rayleigh-Ritz Autoencoder embeds the admissible functions in the decoder portion of an autoencoder enabling the hard fulfillment of generalized constraints. This removes the necessity for an additional regularizing term in the cost function. In turn, this permits the learning of the solutions to problems modeled via the calculus of variations, whereby the cost function corresponds directly to the functional that needs to be minimized. Both parts are supported by a hybrid architecture for hyperparameter optimization based on a genetic algorithm. All the above concepts are presented as a collection of peer-reviewed publications and supported by code published in the form of toolboxes.
no embargo
Keywords: Scientific Machine Learning; Hybrid Machine Learning; Hyperparameter Optimization; Autoencoder; Scientific Machine Learning; Hybrides Maschinelles Lernen; Optimierung von Hyperparametern; Autoencoder

Hydrogen Embrittlement of the Precipitation Hardening Nickel-Based Alloy 718 - Seitlinger, Anna-Carina (2024)
With the urgency of the energy transition and in the context of climate change, hydrogen is gaining increasing importance as a promising alternative to fossil fuels. The key-challenge, however, is the safe transport and storage of significant quantities of the element. In this context, nickel-based alloys are of particular interest, as they are generally considered to be highly resistant to hydrogen embrittlement. However, occasional incidents of hydrogen embrittlement related failure, particularly within the oil and gas sector, have been noted with Inconel 718. This work focuses on the precipitation hardening nickel-based alloy Inconel 718, examined in three different heat treatment conditions, in order to identify potential differences regarding the susceptibility to hydrogen embrittlement. The slow strain rate technique with concomitant hydrogen charging as well as saturation simulations, implementing Python, were employed for characterization. A comprehensive microstructural analysis using scanning electron microscopy and atom probe tomography completed the experimental series. The initial segment of this thesis offers a detailed elaboration of the microstructure and precipitates in Inconel 718, as well as the behaviour of hydrogen within the alloy itself. These insights, along with the applied methods, form the scientific foundation for the conducted experiments, which are further supplemented by an in-depth discussion of the results. The alloy was analysed in both the homogenized condition and in two precipitation hardened states that differed in terms of precipitate size. The slow strain rate tests revealed a decrease in elongation at fracture, attributed to the presence of hydrogen. This serves as an indicator of embrittlement within the alloy. Moreover, the conjunction of insights derived from simulated hydrogen saturation curves and pertinent literature enabled the estimation of the influence of the individual applied heat treatments on the hydrogen diffusion rates as well as the sensitivity of Inconel 718 to hydrogen embrittlement.
embargoed until 18-06-2027
Keywords: Nickelbasis-Superlegierungen; Inconel 718; Ausscheidungen; Wasserstoffversprödung; Atomsondentomographie; Langsamzugversuche; Wasserstoffdiffusion; Wasserstoffaufnahme; Wasserstoffsättigung; Nickel-Based Superalloys; Inconel 718; Precipitates; Hydrogen Embrittlement; Atom Probe Tomography; Slow Strain Rate Technique; Hydrogen Diffusion; Hydrogen Uptake; Hydrogen Saturation

Hydrogen embrittlement in steels - Graf, Maximilian (state-of-the-art in theory and practice, 2024)
In order to reduce the enormous CO2 emissions in the iron and steel production, the direct reduction of iron ore with hydrogen will be targeted in the future. This results in an increased hydrogen content in the metal components exposed to hydrogen during steel production, which may lead to a deterioration of the mechanical properties of the structural metal components, known as hydrogen embrittlement. To enable a successful transition from carbon-containing reducing agents to pure hydrogen, codes and standards are required that take into account the detrimental effects of hydrogen on structural metals in the design and dimensioning of components. In addition, codes and standards are necessary to standardize the materials testing of metallic specimens in hydrogen-containing atmospheres. In the theoretical part of this thesis, relevant codes and standards have been reviewed and the most important points have been summarized. Additionally, various materials testing methods have been evaluated for their suitability in assessing material behavior under the influence of hydrogen. Furthermore, various steels have been reviewed regarding their deterioration of mechanical properties under the influence of hydrogen. In the experimental part of this thesis, tensile tests were performed on uncharged and hydrogen-charged specimens to investigate the influence of hydrogen on a martensitic PH 13-8 Mo and an austenitic AISI 303 steel. The tensile specimens were subjected to electrochemical hydrogen charging and the total hydrogen content in the charged and uncharged specimens was determined by thermal desorption spectroscopy. The fracture surfaces were characterized by stereo microscopy and scanning electron microscopy. A pronounced sensitivity to hydrogen embrittlement was found for PH 13-8 Mo mainly due to its high strength, martensitic matrix and low austenite content. A high susceptibility to hydrogen embrittlement was also observed for AISI 303, mainly due to its insufficient nickel content and high fraction of manganese sulfide inclusions. Compared to the austenitic steel AISI 303, the martensitic steel PH 13-8 Mo showed a significantly higher hydrogen diffusion rate, but a lower hydrogen solubility. It has been shown that only diffusible hydrogen atoms lead to hydrogen embrittlement, since specimens, which were annealed after hydrogen charging exhibited the same mechanical behavior as uncharged specimens.
no embargo
Keywords: Wasserstoffversprödung; PH 13-8 Mo; AISI 303; Elektrochemische Wasserstoffbeladung; Normen und Standards; Zugversuch; TDS; REM; Hydrogen embrittlement; PH 13-8 Mo; AISI 303; Electrochemical hydrogen charging; Codes and standards; Tensile testing; TDS; SEM

Hydrometallurgical extraction of valuable metals from electric arc furnace dust originated in stainless steel production - Howard, Thomas Wolfgang (2024)
Regarding the growing production rates of metals, there is also a direct proportional increase in the accumulation of corresponding by-products like dust. These often contain, as in the case of stainless steel production, valuable metal like Cr, Ni, and Mo, which would be lost if no actions would be taken. To counteract the resulting dependency on imports, material loss, economic and ecological effects, the interest in recycling of those residues has grown in the last decade. Though most industrially applied processes recover these metals from dust by pyrometallurgical means, the research in hydrometallurgical methods to recover metals has gained attention. This is due to the flexibility of such solutions in dealing with inhomogeneous input materials and the ease with which they can be adapted in their design. Therefore, a new hydrometallurgical approach in the extraction of Cr and Ni by dissolving stainless steel dust in five different acids has been conducted in the course of this thesis. Through these leaching experiments, the knowledge of the need for harsher conditions, like higher temperature, longer leaching time and higher acidity has been gained. Simultaneously, an optimized setup for such conditions was developed, that counteracts the disadvantages which were noticed while conducting the experimental campaigns. Based on these results and optimizations, future campaigns with and without pre-treatment of dusts to recover valuable metals by leaching and following precipitation steps, are in development.
no embargo
Keywords: Hydrometallurgie; Rückstandsaufbereitung; Gewinnung von Wertmetallen; Elektrolichtbogenofenstaub; Edelstahlwerkstaub; Hydrometallurgy; Residue processing; Extraction of valuable metals; Electric arc furnace dust; Stainless steel mill dust

INLINE PROCESS MONITORING AND FAILURE MANAGEMENT CONCEPT FOR ATL - Yadav, Neha; Schledjewski, Ralf; Fauster, Ewald (2024)

Identification of Application for Measuring Devices in the Petroleum Upstream Industry and Quantification of the Global Market Potential - Sadil, Florian Benjamin Viktor (2024)
Navigating a company through the complexities of the global economy requires a profound understanding of both intrinsic factors that determine the internal dynamics of the organization and extrinsic factors that shape the external environment. These factors play a crucial role in determining the relative performance of an organization within the context of intense competition. To achieve market differentiation and ensure the long-term viability of the company, exploring new business fields is essential. For Anton Paar, this strategic orientation is manifested in a deeper exploration of the Exploration and Production (E&P) sector within the oil and gas industry. The objective of this master's thesis is to structure the upstream process in terms of available instrumentation and to ultimately estimate the individual product opportunities that Anton Paar could realize within the "Serviceable Addressable Market" (SAM). The analysis of market potential is not solely based on numerical data; thus, this work expands the investigative framework to include research methodology and concepts for assessing both external and internal aspects of companies. A combination of qualitative and quantitative methods is used to collect data, develop theoretical approaches, test these approaches, and then modify or discard them. The integration of theory and practice plays a central role in the execution of the analyses. For the successful execution of the tasks set in this study, a comprehensive literature review provides the necessary knowledge to conduct a meaningful market potential analysis. In the practical part of the work, the business structures of the available countries are analyzed, using industry codes as a starting point to identify potential customers, particularly from the oilfield services sector. By extrapolating and refining verifiable findings to projections for the year 2024, and considering market-, business-, and product-specific factors, the potentials of the SAM for both individual instruments and product lines are determined. To further substantiate the results and to convince decision-makers, a net present value calculation is performed, taking into account fictitious manufacturing costs.
embargoed until 25-04-2029
Keywords: Market Potential Analysis; Serviceable Addressable Market; Macro- and Microenvironment; PESTEL Analysis; SWOT Analysis; Scenario Analysis; Porter's Five Forces; Analytical Instrumentation; Exploration and Production; Petroleum Upstream Sector; Oilfield Service Companies; Marktpotenzialanalyse; Makro- und Mikroumfeld; PESTEL Analyse; SWOT Analyse; Szenarioanalyse; Porter's Fünf Kräfte; Analytische Geräte und Instrumente; Öl und Gas; Exploration und Production; Erdölindustrie; Ölfeld-Dienstleistungsunternehmen

Impact of microstructural features on the fatigue strength of cast alloys by means of a layer-based approach - Oberreiter, Matthias (2024)
The manufacturing process based fatigue strength assessment of cast components is a challenging task that is continuously driven by lightweight design concepts and environmental requirements. The fatigue strength of cyclically loaded components is primarily affected by notches or defects which are statistically distributed within the component. A local fatigue assessment is usually possible only for extremal imperfections. Therefore, this work pursues a layer-by-layer, statistical analysis of microporosity to improve the fatigue strength calculation of cast components. At first, to analyse the statistical size effect of non-connected highly stressed volumes, a sample geometry for the concurrent loading of two geometrically separated, highly stressed volumes is presented, characterized, and a damage hypothesis for this statistical size effect established. Since the microstructure in the highly stressed volumes can differ significantly, the influence of secondary dendrite arm spacing on short and long crack growth is thoroughly investigated, and a three-dimensional Newman diagram is established. The interaction between highly stressed volumes and secondary dendrite arm spacing as a representative microstructural feature is discussed. A layer-based assessment of fatigue strength is conducted based on computed tomography, evaluating defect distributions layer by layer. Based on the determined size parameters of the microstructure and cyclic loading for each defined layer, the layer-based endurance limit can be calculated as probability value. Thus, a conservative prediction of fatigue strength within a range of 12% for different layers in samples of cast aluminium alloy is demonstrated. Furthermore, the component's service life is significantly influenced by the residual stress state. An elastic-plastic model to account for stabilized residual stresses in the surface layer is developed based on the analysis of vibratory finished and polished samples, considering the cyclic rearrangement of mean stress state for each assessed layer. The layer-based fatigue strength assessment methodology was established for the cast aluminium alloy AlSi8Cu3 and validated for the cast steel alloys G21Mn5+N and G12MnMo7-4+QT. For all examined cast materials, the layer-based methodology accounts for a prediction of long-life fatigue strength within a range of approximately 10%. Thus, an engineering-applicable, comprehensive assessment concept is presented, enabling layer-based, manufacturing process based design of cast components.
no embargo
Keywords: fatigue assessment; residual stress; cast steel; cast aluminium; vibratory finishing; fracture mechanics; elastic-plastic behaviour; bulk defects; surface defects; extreme value statistics; Ermüdungsfestigkeit; Eigenspannungen; Stahlguss; Aluminiumguss; Gleitschleifen; Bruchmechanik; elastisch-plastisches Verhalten; Volumendefekte; Oberflächendefekte; Extremwertstatistik

Impact of the Wire Arc Additive Manufacturing (WAAM) process on the distortion and residual stress state of rapidly rotating components in solid/liquid separation - Ruess, Leon (2024)
Wire as a feedstock referred to as Wire Arc Additive Manufacturing for Additive Manufacturing purposes has been investigated since the 1990s. The advantages of WAAM mainly are the high deposition rates, the freedom of geometry with a high dimensional accuracy and potentially low delivery times. Due to these facts, WAAM is gaining technical and economic relevance, but needs to be investigated to benefit to its advantages in comparison to conventional component manufacturing. Based on the inevitable heat input during WAAM, the knowledge of the impact on the distortion and residual stress state is essential. In this master thesis, this impact of a WAAMed flange on a decanter centrifuge¿s cylindrical bowl out of 1.4362 and 1.4462 is investigated by destructive and non-destructive measurements. In addition, mechanical properties and the microstructure of the used materials are characterized by tensile testing, hardness mappings, light optical and stereo microscope investigations. Finally, the performed WAAM process is assessed in terms of economic operation as an alternative to the conventional centrifugal casting manufacturing process. These investigations showed that the cylindrical bowl is plastically deformed in the area of the WAAMed flange and elastic deformation also occurs up to much greater distances.
embargoed until 02-02-2029
Keywords: Wire Arc Additive Manufacturing; DUPLEX Stähle; Eigenspannungen; Verzug; Mechanische Eigenschaften; Wire Arc Additive Manufacturing; Duplex Stainless Steels; Residual Stresses; Distortion; Mechanical Properties

Improved Research Technique on the Influence of CO2 on Wellbore Cement under Downhole Conditions - Plessing, Elias (2024)
Carbon Capture and Storage (CCS) is essential for achieving carbon neutrality, especially in hard-to-decarbonize industries. One of the main challenges in CCS is ensuring that CO2 is permanently contained in geological storage sites. Cement is crucial for sealing the wellbore and preventing leaks. To evaluate durability of cement against CO2, traditional tests like API Specification RP 10 are used, which test cement in pressurized conditions and analyze its properties after exposure. However, these methods have their limits and new ways of testing are to be developed for more realistic results. This thesis consists of two parts. One is about the development of a new permeability testing setup to monitor the changes in permeability and strength of different types of cement that have been exposed to super-critical CO2 for 2 weeks, 4 weeks or not at all. The changes were significant and widely depending on what type of cement was used. The second part deals with the improvement of an experimental setup that has been developed to advance the evaluation of the interaction of cement with CO2. In this setup, cement slurry is placed in an annulus between a rock cylinder and metal. It is then exposed to CO2 radially through the rock. In this method a CT scanner is used to monitor the carbonation front in real-time. It measures CO2 consumption and makes it possible to implement new sensors such as ultrasonic. Furthermore, it provides immediate insights into cement integrity and the interactions between cement and CO2, thus enhancing the security of CO2 storage in CCS applications.
no embargo
Keywords: CO2; Carbon Dioxide; Cement; Carbon Capture and Storage; CCS; CCUS; Well Integrity; CO2; Zement; Durchlässigkeit; CO2 Stabilität; CO2 Speicherung; CO2 Reaktion mit Zement

In-Situ Vibrationsmessung an Hydraulikaggregaten zur Inbetriebnahme eines Condition Monitoring Systems - Raffl, Sebastian (2024)
In Zeiten, in denen Begriffe wie Digitalisierung, Ressourcenknappheit und Nachhaltigkeit eine große Rolle im Weltgeschehen spielen, werden auch in den heimischen Konzernen Projekte zum Einsparen unnötiger Ausgaben vorangetrieben. So auch in der voestalpine BÖHLER Aerospace GmbH & Co KG, einem renommierten Zulieferer und Entwickler von sicherheitskritischen Komponenten der Luftfahrt. Im Rahmen eines internen Projektes, welches den Inhalt dieser Masterarbeit darstellt, wurde eine Schwingungsmessung an einem Elektromotor eines großen Hydraulikaggregates einer hydraulischen Schmiedepresse implementiert. Ziel des Messaufbaues ist die dauerhafte Überwachung des Maschinenzustandes, um ungeplante Betriebsausfälle, übermäßige Instandsetzung und die damit verbundenen Kosten zu verhindern. Übermäßige Instandsetzung bedeutet hierbei, den intervallmäßigen Austausch von Komponenten der Elektromotoren ohne ein vorliegendes Indiz auf Schädigungen, wodurch in keinem Fall von einer ressourcenschonenden Vorgehensweise gesprochen werden kann. Für die Überprüfung der Machbarkeit des Vorhabens wurde das Projekt zusätzlich von der Montanuniversität in Form des Lehrstuhles für Allgemeinen Maschinenbau unterstützt, durch welchen Messungen mit einem Laser-Doppler-Vibrometer durchgeführt wurden, um die optimalen Messpunkte an den Aggregaten festzulegen und im weiteren Vergleichsdaten zu generieren, mit denen die internen Daten des eigenen Messaufbaues abgeglichen werden sollen. Folgend wurde der Elektromotor nach längerer Recherche mit Beschleunigungssensoren ausgestattet und das messtechnische Equipment dauerhaft aufgebaut. Eine Vorgabe bei der Auswahl der Komponenten war es, das System so zu gestalten, dass es in das bestehende Datensystem des Betriebes integriert werden kann. Dies gilt ebenso für die Software, welche im Weiteren zur Aufzeichnung und Auswertung der Daten notwendig ist. Eine besondere Herausforderung stellte die Auswertung der Daten dar. Sowohl das raue Umfeld des Schmiedebetriebs als auch die angetriebenen Pumpen selbst führten zu starken Einflüssen auf die Ergebnisse der Messungen an dem Elektromotor. Um ungewünschte stochastische, also zufallsbehaftete Einflüsse bestmöglich zu vermeiden, wurden zur Datenaufzeichnung wöchentliche Tests unter möglichst gleichen Bedingungen durchgeführt. Neben dem Vergleich der Ergebnisse zweier unterschiedlicher Softwarepakete, stellen die Auswertung der Messdaten von 18 wöchentlichen Tests einen zentralen Punkt der Masterarbeit dar. Zusätzlich wurde eine Auswertung der gleichzeitig mit dem Lehrstuhl für Allgemeinen Maschinenbau aufgezeichneten Daten durchgeführt, um zu überprüfen, ob der interne Messaufbau valide Ergebnisse liefert. Die Ergebnisse der Messungen zeigen, dass der realisierte Aufbau der Schwingungsmessung durchaus valide Ergebnisse erzeugt, welche in Zukunft zur Erkennung von Schädigungen der Aggregate beitragen können.
gesperrt bis 13-06-2029
Keywords: Schwingungsmessung; Zustandsüberwachung; Signalverarbeitung; Signalanalyse; Wälzlager; Vibration Measurement; Condition Monitoring; Signal processing; Signalanalysis; rolling bearing

Increasing Efficiency in Sensor-Based Sorting Processes for Waste Streams consisting of Plastics - Friedrich, Karl (2024)
This doctoral thesis aims to validate new methods that increase the efficiency of sensor-based sorting processes for waste streams consisting of plastics. It deals with set boundaries on aggregate level; the plant level is not considered. The used equipment is the experimental sensor-based sorting setup at the Chair of Waste Processing Technology and Waste Management at Montanuniversität Leoben and the used sensor technology near-infrared spectroscopy.Increasing the sorting efficiency can be done by optimizing the identification of the mechanical discharge of particles. Data analytics is shown as a solution to achieve optimization, therefore this thesis focuses on using data-analytics-related methods.For optimizing the identification of particles, research is conducted in the fields:•Influence of surface roughness•Influence of reflectors as background material•Usage of machine learning approachesFor optimizing the mechanical discharge of particles, research is conducted in the fields:•Correlations between the input parameters (input composition, throughput rate) and the output parameters (purity, recovery, yield, incorrect discharged particles) of a sensor-based sorting process•Mathematical approaches to describe the optimal operation point of a sensor-based sorting machine to achieve a specific sorting resultIt is stated that this outcome allows a sorting plant to increase purity by using machine learning approaches to optimize the identification or running the plant on the optimal operation point, both without substantially adapting the plant. Superordinate considered these solutions help to increase the amount of recycled plastic so that less plastic waste is thermally treated.
no embargo
Keywords: Sensorgestützte Sortierung; Sortiereffizienz; NIR-Sortierung; Datenanalytik; Maschinelles Lernen; Regressionsmodell; Optimaler Betriebspunkt; Durchsatz; Transflektion; Oberflächenrauigkeit; Sensor-Based Sorting; Sorting Efficiency; NIR-Sorting; Data Analytics; Machine Learning; Regression Model; Optimal Operation Point; Throughput Rate; Transflection; Surface Roughness

Industry 4.0 @ Chair of Metal Forming - Prabitz, Konstantin Manuel; Stockinger, Martin; Walzl, Alexander; Wenda, Alexander; Czipin, Marcel (2024)

Influence of binder compositions, solvents, and material extrusion parameters on aluminum additive manufacturing via SDS - Hufnagl, Margarete (2024)
Material extrusion (MEX) is an additive manufacturing technique that can serve as the shaping step to create green parts, in the shape, debinding, and sintering (SDS) process of metal specimens. Employing SDS with MEX for aluminum offers a promising cost-effective production method for parts with complex geometry. However, this process requires a highly filled thermoplastic binder system for AlSi1 powder, to produce filament for the MEX process. The filament is needed to feed the 3D printer with the material required to shape the specimens. An important challenge in utilizing MEX in SDS is the development of an appropriate binder composition that meets the requirements for the printing step as well as the debinding and sintering step. For the printing step, the filaments should be a combination of the following characteristics - tough, flexible and low viscous. The debinding step requires a dual-component binder system, where one component is soluble in the chosen solvent, while the other one is resistant to this solvent. The solvents evaluated in this master thesis are cyclohexane, acetone, and water. Additionally, the binder components should posses a lower thermal degradation temperature than the sintering temperature of aluminium. This is particularly challenging since the AlSi1 sintering temperature is similar to the degradation temperature of most thermoplast degrade. This is important because the binder must be completely removed to reduce the risk of high levels of residual oxygen and carbon, as well as the formation of Al2O3, which can significantly affect the quality of the sintered part. The objective of the master thesis, conducted as part of the project ALF³, was to enhance the understanding of the binder components required for this specific process. Therefore the impact of various backbone materials as a binder component, along with the influence of several main binder materials on the rheological, thermal, printing, and debinding properties of the AlSi1 feedstocks were analyzed. The thermal properties of the binder systems and feedstocks were investigated using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) testing. The rheological behavior was examined using high-pressure capillary rheometers. Additionally, the contact angle measurements were performed to see the effect on the wetting behavior of the binder components and the particle distribution of AlSi1 in the Feedstock. This was followed by the production of feedstock filaments, analysis with scanning electron microscopy (SEM) and MEX printing. The findings demonstrated the possibility of producing three optimized binder formulations for each solvent employed in the debinding process. Moreover, there is potential to refine the printing process to meet the specific demands of highly packed filaments with a volume fraction of 55 vol.%.
no embargo
Keywords: aluminum additive manufacturing; Material Extrusion; MEX; Shaping Debinding Sintering; SDS; binder development; Materialextrusion; MEX; SDS; Shaping Debinding and Sintering; Entwicklung von Bindersystem; aluminum additive manufacturing

Influence of the properties of different waste streams on gas-collecting base- and levelling layers with special focus on carbonate content in landfill technology - Flechsenhar, Selina (2024)
To achieve the European goal of a fully circular economy, it is necessary to develop new recycling options for mineral waste to preserve landfill capacities in the long term. One solution is to use landfill substitute construction materials (SCM), which can be made by recycling specific waste streams. These reduce the reliance on conventional building raw materials. The use of landfill SCM is an innovative and sustainable approach to landfill construction that helps to conserve natural resources in the long term. This master´s thesis deals with the use of different mineral waste streams, such as electric arc furnace slag, hollow glass, municipal solid waste incineration bottom ash, tar-containing asphalt, and track ballast, as SCM. It analyzes their impact on the properties of gas-collecting base- and levelling layers in landfill technology and focuses on the influence of the carbonate content. The evaluation of waste streams for use as landfill SCM considers both technical requirements and ecological aspects. The tests conducted adhere to the German legal frameworks and utilize a hierarchically structured decision tree to assess the suitability of future landfill SCM. The study identified methodological limitations in the prescribed regulations and formulated recommendations for future action. In the assessment of waste streams as SCM for landfill purposes, all samples show potential suitability, although some exceeded the carbonate limit value. All tested materials met the geotechnical requirements. A correlation between carbonate content and other tested parameters could not be established. The spatial differences in the carbonate content in the examined waste streams could be attributed to the regional geology and the availability of industrial raw materials in their original use. Finally, it was pointed out that there is a need for a comprehensive revision of the prescribed testing methods and their defined limiting values. This will enable waste streams to be recycled more efficiently while minimizing environmental impact. This work provides important insights into the assessment of the suitability of landfill SCM and demonstrates ways in which a circular construction industry can be further promoted.
embargoed until 18-04-2029
Keywords: Landfill substitute construction materials; carbonate content; decision tree for suitability assessment; sustainable landfill construction method; Deponieersatzbaustoffe; Karbonatgehalt; Entscheidungsbaum zur Eignungsbewertung; nachhaltige Deponiebauweise

Innerbetrieblicher Transport von Kunststoffabfällen - Hack, Philipp (2024)
Die OMV plant eine Anlage, um aus Kunststoff- Recyclingmaterial wieder Rohöl herzustellen. Da die Platzverhältnisse auf dem Raffineriegelände sehr begrenzt sind, soll das Material an eine Entladestation außerhalb der Raffinerie per LKW oder Bahn transportiert werden. Für den Weitertransport zu dieser Anlage werden im Rahmen dieser Arbeit geeignete Förderanlagen, Recyclingmaterialien und Anlieferpositionen sowohl wirtschaftlich als auch umwelttechnisch miteinander verglichen. Untersucht wurden 3 Kunststoffmaterialien: POS- Flakes, POS- Pellets und Vierkantballen. Weiters wurden 6 Anlieferpositionen rund um die Raffinerie, sowie die Anlieferung per LKW als auch per Bahn betrachtet. Um die Szenarien zu vergleichen, wurden die Routenführungen geplant, Fördersysteme bewertet, Angebote unterschiedlicher Hersteller für eine Standardstrecke eingeholt und diese auf die unterschiedlichen Förderstrecken mit Hilfe einer Berechnung eines Gurtförderers skaliert. Die Skalierung erfolgt durch die Berechnung eines offenen Gurtförderers für jede Förderstrecke und der dafür benötigten Leistung. Daraus können Umrechnungsfaktoren zur Standardstrecke erstellt werden. Mittels dieser Umrechnungsfaktoren werden die Leistungen der Angebote der Hersteller auf die unterschiedlichen Förderstrecken umgerechnet und können somit in die Kostenkalkulation einfließen. Abschließend wurde eine Kostenaufstellung erstellt, um die unterschiedlichen Szenarien miteinander vergleichen und eine Empfehlung aussprechen zu können. Die Erkenntnis der Wahl des Kunststoffmaterials ist die, dass die folierten Vierkantballen die niedrigsten Kosten in Bezug auf die Herstellung und Anlieferung hervorrufen. Durch das Wickeln der Ballen ist die Gefahr der Verschmutzung der Umwelt auch besonders gering. Als Fördermittel eignet sich die Seilbahn sehr gut, da diese in Kombination mit den Containern es ermöglicht, die Ballen erst direkt vor der Anlage zu öffnen und somit von der hohen Schüttdichte der Ballen zu profitieren. Der Nachteil der Seilbahn liegt in der geraden Streckenführung und darin, dass bewohntes Gebiet nicht überquert werden darf. Ein großer Vorteil sind die geringen Lagerkosten, da Ballen direkt in den Containern gelagert werden können. Durch die geschlossenen Container profitiert dieses System stark in Bezug auf die Verschmutzung der Umwelt mit Kunststoffmaterial. Hinsichtlich der Anlieferung kann die Aussage getroffen werden, dass die Anlieferung per Bahn zu bevorzugen ist. Dies ergibt sich aus den zukünftigen Anforderungen, die insbesondere den LKW-Transport von Abfällen reduzieren sollen und der Tatsache, dass vor Ort geeignete Gleisanlagen vorhanden sind. Die Empfehlung dieser Arbeit ist, aus den oben genannten Gründen, die Anlieferung von folierten Vierkantballen in Containern per Bahn auf dem Abstellgleis der Borealis. Diese Container werden mittels einer Seilbahn zur Anlage transportiert. Sollte die Anlieferung per LKW erfolgen erweist sich auch die Anlieferposition in der Hainburgerstraße als sinnvoll. Auch von dort können Vierkantballen in Containern mittels einer Seilbahn zur Anlage transportiert werden.
nicht gesperrt
Keywords: Kunststofförderung; Kunststofftransport; Konversionsanlage; Polyolefine; Polystyrol; fördern; Plastic conveying; Plastic transport; Conversion plant; Polyolefins; Polystyrene

Instrumentation and Signal Processing for the Verification of Directional Drilling - O'Leary, Paul; Terbuch, Anika; Ninevski, Dimitar; Mevec, Daniel; Fruhmann, Robert; Khalilimotlaghkasmaei, Negin; Habacher, Michael (2024)

Integration of ESG into decision making - Baranowski, Alexander (Options, trade-offs and comparison - case study OMV, 2024)
This thesis presents a novel methodology for assessing energy projects through ESG factors, explicitly focusing on their integration into NPV calculations and qualitative performance scoring. As the energy industry faces increasing pressure to address climate change and societal expectations, OMV, a leading multinational integrated energy company, acknowledges the necessity of embedding ESG considerations into its strategic and financial decision-making to maintain competitiveness and sustainability. This study advances OMV's current ESG framework by developing a dual approach: a monetary integration within NPV calculations and a non-monetized ESG KPI scoreboard. The thesis harnesses a rich compilation of literature, industry best practices, and expert insights to identify pertinent ESG indicators and frame a comprehensive evaluation method. A case study contrasts a fossil fuel project with a renewable initiative, demonstrating the methodology's practicality and its capacity to encapsulate a project's full spectrum of ESG-related risks, costs, and benefits. This research contributes to the growing discourse on sustainable project valuation, providing actionable insights for stakeholders and policymakers in the energy sector and beyond, advocating for informed, responsible energy project decisions that align with long-term sustainability objectives.
embargoed until 05-02-2029
Keywords: Sustainability; ESG; Decision-Making; Energy Industry; Project Valuation; Renewable Energy; Fossil Fuels; Net Present Value; Financial Analysis; NPV in Energy Projects; ESG Integration; ESG Metrics; Climate Change Impact; Sustainable Energy; Financial Decision Making; Nachhaltigkeit; ESG; Entscheidungsfindung; Energiewirtschaft; Projektbewertung; Erneuerbare Energien; Fossile Brennstoffe; Kapitalwert; Finanzanalyse; Kapitalwert in Energieprojekten; ESG-Integration; ESG-Metriken; Auswirkungen des Klimawandels; nachhaltige Energie; finanzielle Entscheidungsfindung

Integration of Underground Hydrogen Storage and Transmission Networks - A Simulation-Based Analysis of holistic Hydrogen Networks - Fink, Justin (2024)
The transition to a low-carbon future requires the exploration of alternative energy sources. In this regard, hydrogen has emerged as a promising option. However, establishing a fully functional hydrogen economy is a complex endeavor with numerous challenges. A significant obstacle to achieving the sustainability goals of the European Union is the limited infrastructure, particularly in terms of storage capacity and integration into the future hydrogen network (Eurostat, 2023). To develop this network effectively, the entire system, including hydrogen transport and distribution networks, as well as storage, must be considered. Underground hydrogen storage in geological formations offers a potential solution for large-scale storage. Various types, such as porous media storage or caverns, can be considered. Thermal turbomachinery (e.g., gas turbines, turbo compressors) play a crucial role in the hydrogen transport and distribution network, alongside reciprocating compressors (Flis and Deutsch, 2021). They drive compressors that are essential for maintaining pressure within the network and ensuring safe and reliable transportation. Furthermore, thermal turbomachinery enables the adjustment of hydrogen flow rates and fluid pressures to meet the specific requirements of different end-users, optimizing the overall system performance. Consequently, investigating the performance and efficiency of integrated systems that combine hydrogen transport with coupled underground hydrogen storage is essential. This work aims to address the challenge of holistic system analysis and optimization of hydrogen networks to understand the key factors influencing the final delivered hydrogen costs. This will be achieved through the development of a standalone software program (H2Net) capable of simulating comprehensive hydrogen networks, including performance and economic analyses. By analyzing the interplay of storage, transmission, and utilization, this research aims to improve the operation of hydrogen networks and ultimately contribute to the advancement of hydrogen-based energy systems, supporting the transition to a sustainable hydrogen economy.
no embargo
Keywords: Wasserstoffwirtschaft; nachhaltige Energiesysteme; Europäische Union; unterirdische Wasserstoffspeicherung; thermische Turbomaschinen; Netzwerksimulationen; wirtschaftliche Analysen; hydrogen economy; sustainable energy systems; European Union; underground hydrogen storage; thermal turbomachinery; network simulation; economic analysis

Integration of Well Life Cycle Data to Predict Electrical Submersible Pump Remaining Run Life - Ibrahem, Mohamed Abdullateif (2024)
Electrical submersible pumps (ESPs) are one of the most significant artificial lifts used worldwide. However, the capital and operating costs of such equipment are higher than those of other artificial lift (AL) methods, and extensive work has been done to increase their reliability. The ESPs' reliability is mainly expressed through run-life metrics such as Mean Time Between Failure (MTBF), where significant research has been made to develop methodologies to calculate and interpret run-life metrics and eventually improve designs and operational efficiency. Dominantly, the ESP run life depends on the design and operating conditions, and there are still significant challenges that these systems are experiencing, especially in harsh environmental conditions where extensive gas, solids, and water production can deteriorate pump run life. To tackle these challenges and continuously improve ESP design, the industry has adopted a culture of continuous improvement practices reflected through failure analysis. Since ESPs can fail due to multiple reasons, failure analysis and identifying the failure's root cause are critical in improving future designs. In general, failure analysis can be divided into three types: detection, isolation, and prognosis. Failure detection is simply recognizing that the failure occurred without acting or knowing the root cause. Failure isolation identifies the root cause of failure, while prognosis refers to predicting the time the equipment will fail. Failure analysis concludes when the exact root cause of failure is determined, and data and captured lessons are documented, which in turn improves workover planning and helps improve the future design in the long run. Understanding the main drivers and factors affecting ESP performance is essential to improve system reliability continuously. In addition, to run life metrics, the industry has been using several statistical models, such as survival analysis, to estimate and compare run life metrics better. However, these statistical models only include operational data generated through part of the well life cycle (e.g., well events) to predict the run life effectively. This Thesis will investigate available solutions data models (databases) to acquire failure and operational data, and it will explore the statistical model to estimate the pump's remaining run life through slow feature analysis (SFA).
embargoed until 03-02-2029
Keywords: ESP; Elektrische Tauchpumpe; Künstlicher Hebeverfahren; Ausfallanalyse; Überlebenszeitanalyse; Statistische Analyse; Slow Feature Analysis (SFA); Erdölfördertechnik; Öl und Gas Produktion; Restnutzungsdauer (RUL); ESP; Electrical Submersible Pump; Artificial lift; Failure analysis; Survival analysis; Statistical analysis; Slow Feature Analysis (SFA); Petroleum production engineering; Oil and gas production; Remaining useful life (RUL)

Investigating Hydrogen Diffusion in Filled Polymers with Simple Geometries: An ABAQUS Simulation Study - Graf, Alexander Lukas (2024)
This work was carried out in the context of the module "Polymers 4 Hydrogen" at the Polymer Competence Center Leoben GmbH. The aim of this thesis was to create a Finite Element Method (FEM) model for the simulation of hydrogen diffusion through particle filled membranes with an interface zone around the filler particles. This FEM model was based on an extended Nielsen model and was implemented in ABAQUS. At the end of this thesis, a comparison was made between the interface model, a standard FEM model without interface zone and the analytical solution of the extended Nielsen model. For all simulations performed in this thesis, it was assumed that the polymer matrix is a homogeneous material and the filler particles act as absolute barriers which were therefore implemented as holes in the matrix. Each filler particle was modelled with a thin interface around its boundary edges that separates the particle from the matrix. In this interface zone, an orientation is applied to the mesh nodes that allows the diffusivity of the interface zone to be changed depending on the direction of flow and the adhesion coefficient. The purpose of this interface zone was to represent the true interfacial diffusion behavior between a filler particle and the matrix material. Several ways to implement such an interface zone in an FEM model were evaluated. In the final version of the model, the interface zone was implemented at the mesh node level through the use of ABAQUS subroutines. In these models, the filler particles were regularly and periodically arranged in the membrane according to the assumptions of the Nielsen model. The evaluation and comparison of the analytical model results with the results of the FEM simulations with and without the interface zone showed that the FEM simulations with an interface zone were in better agreement with the analytical data than the simulations without the zone.
no embargo
Keywords: Wasserstoff; Permeation; Finite Elemente Methode; FEM; ABAQUS; Partikel verstärkte Polymermembranen; Simulation; Hydrogen; Permeation; Finite Element Method; FEM; ABAQUS; Filler Particle Reinforced Polymer Membranes; Simulation

Investigating mechanical properties of silicon carbide coated carbon nanotube composite at elevated temperatures - Mo, Jiarui; Schaffar, Gerald J.K.; Du, Leiming; Maier-Kiener, Verena; Kiener, Daniel; Vollebregt, Sten; Zhang, Guoqi (IEEE access, 2024)

Investigation of Carbon Produced by Pyrolysis: Characterisation and Processing - Agho, Osamudiamen Emmanuel (2024)
The generation of pyrolytic carbons through pyrolysis is rising due to energy recovery in the form of pyrolysis gas and pyrolysis oil from various waste sources, as well as the production of hydrogen from methane decomposition. In parallel, the demand for many forms of carbon is on the rise. In order to make pyrolytic carbon viable for further applications, processing steps are necessary. In this thesis, pyrolytic carbons derived from the pyrolysis of polyolefin (PyCP) and methane gas (CMP) were investigated. Separation methods such as flotation, settling velocity, and wet magnetic separation were used for the purification of PyCP. Reverse flotation of PyCP showed some promising results for carbon grade improvement. CMP is considered the purest and finest of all pyrolytic carbon samples received. Agglomeration tests were performed on CMP to improve its transportability and applicability. Lignosulfonate binders were considered the best based on high compressive strength test results in comparison with other binders. There are many potential applications for the purified carbons of the PyCP, such as improving the carbon surfaces.
embargoed until 03-06-2029
Keywords: Pyrolyse; Agglomeration; Polyolefine; Flotation; Druckfestigkeit; Pyrolysis; agglomeration; Polyolefins; flotation; Breakage force

Investigation of lining solutions for a lined rock cavern at the site of Zentrum am Berg - Loucky, Gabriel (2024)
In this thesis, different options for the lining of hydrogen storage facilities and their dimensioning are shown using an analytical calculation from the field of pressure tunnel construction. The first part of the thesis deals with existing concepts for the storage of hydrogen and their geological requirements, the effects considered and their advantages and disadvantages. The second part of the thesis is dedicated to the necessary adaptations of the existing concept of the Lined Rock Cavern for the storage of hydrogen to the analytical solution from pressure tunnel construction. In the following, the required boundary conditions are defined, the necessary rock mechanical input parameters are listed and, if necessary, calculated. In a further step, the analytical solution is derived and influences such as temperature influence, buckling and creep are explained. This is done first for a steel lining and then for a prestressed concrete lining. The two analytical solutions are then applied to three different geologies and three different storage pressures from hydrogen storage as examples and the results are compared with each other. As a result of this work, it can be said that a steel lining is better suited for pressurized storage. Furthermore, a verification of the analytical solution is carried out using two design examples and then the influence of the different input parameters of geology, lining material and influences from the underground temperature are determined using sensitivity analysis. In the discussion, possible improvements, and optimizations of the steel lining as well as which changes to the concept of the prestressed concrete lining are necessary to meet the requirements of a pressure reservoir are listed. Finally, the next necessary steps for the construction of a Lined Rock Cavern pilot facility at the Zentrum am Berg are listed.
no embargo
Keywords: Tunnelbau; Zentrum am Berg; Wasserstoffspeicherung; Lined; Rock Cavern; Tunneling; Zentrum am Berg; Hydrogen Storage; Lined Rock Cavern

Investigation of phase transformations and ordering mechanisms in a Pd–Cu–Ag–Ru alloy - Lumper, Lea; Fecher, Jonas; Stark, Andreas; Maier-Kiener, Verena (Advanced engineering materials, 2024)

Investigation of the hydrogeology of the pore aquifer in the Bodenbauer-St.Ilgen area using geophysical methods - Fachathaler, Patrick (2024)
The pore aquifer in the Bodenbauer-St.Ilgen area on the southern side of the Hochschwab Massif is of great significance for the water supply of the city of Graz and its neighboring municipalities. Hydrogeological investigations on the southern Hochschwab side in the 1970s and 1980s raised public interest in the potential of the water seeping into the subsoil in this area for the first time. The establishment of the Wasserverband Hochschwab Süd, nowadays known as the Zentral-Wasserversorgung Hochschwab Süd (ZWHS), laid the foundation for the development and utilization of this catchment area. Today, around 6.2 million m³/a, which correspond to around 195 l/s, are consumed by the surrounding communities. These hydrogeological investigations were carried out more than 40 years ago, which has increased the demand for further examination. The aim of this study was to identify the groundwater-bearing layers (Aquifer) in the Bodenbauer-St.Ilgen area, as well as the level of the groundwater table and the depth of the pre-Quaternary bedrock. Initially, two profiles were measured using geoelectrical resistivity tomography (ERT) during this thesis, which were later supplemented by two vertical electrical sounding (VES) profiles. The former profiles, designed to detect the water-bearing horizons in the Bodenbauer area, were positioned close to the seismic survey shot in the 1970s in order to ensure the best possible comparability. The results of the ERT verify the historical data along the first profile (hs01), as both a layered subsurface structure and an aquifer were detected. An answer to the previously unresolved question of a possible aquifer was found for profile hs02, which runs perpendicular to hs01, as the high resistivities indicate the presence of dry sediments and therefore not water-bearing layers. The depth soundings, positioned along the ERT profiles, were intended to determine the depth of the pre-Quaternary bedrock, but did not lead to the desired result, partly due to topographical constraints. The depth of the basin bedrock could not be determined either by the ERT or the VES for profile hs01. In the case of hs02, however, the possibility remains that the pre-Quaternary basement can be encountered at a depth of 100 m, due to the steeply dipping flanks. The results of these measurement campaigns generally agree well with those of the former investigations and can also answer previously unresolved questions, such as the presence and the distribution of groundwater-bearing layers.
no embargo
Keywords: Hochschwab; Bodenbauer; St.Ilgen; ZWHS; Hydrogeology; ERT; VES; Pore aquifer; pre-Quaternary basement; Hochschwab; Bodenbauer; St.Ilgen; ZWHS; Hydrogeologie; ERT; VES; Porenaquifer; prä-Quartärer Beckenuntergrund

Investigation of the lifetime of sintered interconnects in power electronics - Prutti, Maria Theresa (2024)
This thesis examines the lifetime of sintered silver and copper interconnects in power electronic applications. Therefore, shear test samples were designed and prepared. The sintered samples were thermally aged using a thermal shock test. The analysis included the observation of the microstructure, elastic modulus and hardness of the sintered silver and copper-material as well as their adhesion towards surrounding interface materials after defined thermal cycling sequences. For the evaluation of the microstructure scanning electron microscopy (SEM) images were taken and electron backscatter diffraction was performed. SEM images were used to evaluate the porosity of the sinter materials. The elastic modulus and hardness were analyzed by nanoindentation. The adhesion was measured using the shear test method. The material data of both chosen sinter materials was gathered during the different stages of thermal cycling and evaluated separately. The microstructure and physical properties change considerably in the initial thermal cycling, which points to an incomplete sintering with the chosen sinter parameters. The adhesion of the Ag material to the Cu surfaces is considerably lower than with the Cu material. The average shear test values after thermal cycling in the Cu samples is about 15% higher than in the Ag samples. In the Ag sample a slight thermal degradation in the shear test values is found. No such degradation is apparent in the Cu samples, indicating good long-term reliability.
embargoed until 23-04-2029
Keywords: Interconnect techology; lifetime of sintered interconnects; silver sinter; copper sinter; Ag sinter; Cu sinter; die attach; power electronics; Verbindungstechnik; Lebensdauer von gesinterten Verbindungen; Silbersinter; Kupfersinter; Ag-Sinter; Cu-Sinter; Die Attach; Leistungselektronik

Investigation of the relationship between circular economy practices and circular economy outcomes in the manufacturing sector - Ganzi, Alexander (2024)
The circular economy has gained increasing academic and industrial interest over the last years and especially in the manufacturing sector it is seen as an effective strategy to lower the environmental burden and still be able to be competitive through new opportunities the circular economy brings with it. However, due to the great extent of research performed in this field of study, the practices, policies and outcomes get mixed up with other environmental or ecological approaches. This study investigates the relationship between certain circular economy practices and circular economy outcomes. Through a systematic literature review, the most commonly mentioned practices and outcomes, which qualify as circular, have been identified. Based on the resource-based view (RBV) two hypotheses were formulated regarding the relationship between recycling and redesign with five circular economy outcomes. Multiple linear regression analysis was used to indicate significant correlations between the practices and the outcomes. The data used in the regression analysis derives from the EIKON database and contains data regarding circular economy practices, firm size and location and several quantitative outcome variables of 447 manufacturing companies all over the world. The results show that recycling has a significant relation with the reduction of energy consumption and the increase of the recycling ratio. While the redesign strategy shares this positive significance regarding the recycling ratio, further results also indicate that redesign leads to a significant reduction of waste and CO2 emissions. This is due to the reason that, unlike recycling, redesign is a prevention strategy, so the generation of waste and emissions is already prohibited in the design phase of the products. These findings suggest that circular economy practices can be an effective method to target certain indicators and benefit from the increase of circularity. This study contributes to the circular economy theory by providing evidence for a significant relationship between circular economy practices and circular economy outcomes, which can be used by manufacturers to implement in their operations or policymakers to introduce new rules based on well-grounded scientific research.
no embargo
Keywords: circular economy; circular economy practices; Logistics 5.0; manufacturing industry; sustainable logistics; Kreislaufwirtschaft; Praktiken der Kreislaufwirtschaft; Logistics 5.0; produzierende Industrie; nachhaltige Logistik

Investigations of selected influences on the hydrogen-based reduction of iron ore ultra-fines in a fluidized bed - Wolfinger, Thomas (2024)
The hydrogen-based reduction of iron ore is considered to be a key technology in transforming the iron and steel industry towards climate neutrality. The combination of hydrogen-based reduction with the fluidized bed technology leads to a promising approach to lower greenhouse gas emissions and energy consumption. This preference is given due to the direct feeding of iron ore fines without a prior agglomeration step and the use of hydrogen. The present thesis introduces an approach for the analysis of the hydrogen-based reduction of iron ore fines and ultra-fines in a conventional low-velocity fluidized bed. Therefore, using a cold fluidization testing model, mathematical correlations were established to describe the fluidization behavior, including the carried-out material. In the case of magnetite-based ultra-fines, the effect of prior oxidation on the reduction kinetics using hydrogen as reducing agent was investigated in a thermogravimetric analyzer. Oxidized iron ore fines and ultra-fines were analyzed regarding their fluidization and reduction behavior in a hot fluidized bed reactor using hydrogen as reducing and fluidizing gas. The results showed controversial restrictions to fluidize iron ore fines and ultra-fines. High gas velocities were required to avoid partly fluidization and channeling, and low gas velocities to avoid gas by-passing and high entrainment rates. A prior oxidation of magnetite-based ultra-fines increased the reduction rate, whereby a moderate degree of oxidation of 50 % was sufficient. The high reduction rate of the solid material and the low gas velocities led to a limitation of the hydrogen supply up to 70 to 80 % degree of reduction. Two effects led to an additional decrease in gas utilization; first, due to the occurrence of a dense iron shell around the particles and thus solid-state diffusion as the rate-limiting mechanism; second, due to the moderate gas interchange between gas bubbles and particles. Therefore, iron ore fines and ultra-fines are suitable under certain restrictions for hydrogen-based reduction in a conventional low-velocity fluidized bed.
embargoed until 08-02-2029
Keywords: wasserstoffbasierte Reduktion von Eisenerz; Fein- und Feinst-Eisenerz; Wirbelschicht; magnetitische Feinst-Eisenerz; hydrogen-based reduction; low-velocity fluidized bed; iron ore fines and ultra-fines; magnetite-based ultra-fines

Isothermal and Non-Isothermal DSC Analysis towards the Formulation of a Low-Temperature Curing Epoxy-Alcohol Resin - Lang, Johanna (2024)
Sustainability issues regarding conventional epoxy resins from non-renewable resources led to investigations of bio-based alternatives. One of these alternatives, based on renewable feedstocks, is eugenol, which can be epoxidised at the allyl functionality. In this thesis, the curing behaviour of this monomer was compared to the most frequently used epoxy resin, diglycidyl ether of bisphenol A (DGEBA), with the aid of dynamic and isothermal differential scanning calorimetry (DSC) measurements. The anionic ring-opening homo- and copolymerisation of these monomers in various ratios was initiated by tertiary amines, namely 1-methylimidazole (1-MI) and 2,4,6-tris(dimethylaminomethyl)phenol (K54). This thesis aimed to develop a low-temperature curing epoxy-alcohol formulation without amine co-curing agents. The homopolymerisation showed that K54 was advantageous for low-temperature curing, while 1-MI performed better at elevated temperatures. This was also confirmed by a proton nuclear magnetic resonance (1H NMR) study with phenyl glycidyl ether (PGE) as a soluble model compound. The apparent activation energies calculated based on the Kissinger and Ozawa method were about 10 kJ mol-1 lower for K54 than for 1 MI. Moreover, the dynamic DSC revealed that formulations with epoxidised eugenol (EE) exhibited lower onset temperatures than DGEBA alone. The acceleration of the curing reaction due to hydroxyl groups was even more prevalent in isothermal DSC measurements at 80 °C than in dynamic DSC analysis. The same trends were observed during the copolymerisation of DGEBA and EE. A significant acceleration of the epoxy polymerisation by hydroxyl groups was found for an EE content of only 10 mol%. However, the acceleration due to the phenolic hydroxyl of EE was not confirmed at room temperature in an 1H NMR study. Finally, benzyl alcohol was investigated as an alternative alcohol with a more promising reactivity at room temperature. To conclude, K54 was found to be beneficial for curing at low temperatures and the acceleration of an epoxy-alcohol formulation was shown at 80 °C. However, a monomer with more reactive functionalities than EE should be used for room temperature curing.
embargoed until 11-03-2026
Keywords: Epoxy; DGEBA; Epoxidised eugenol; Tertiary amines; DSC; Kissinger; Epoxy; DGEBA; Epoxidiertes Eugenol; Tertiäre Amine; DSC; Kissinger

Karbonatisierung von Betonabbruch mit einem Industrieabgasstrom - Lashin, Nagi (2024)
Diese Masterarbeit beschäftigt sich mit der Karbonatisierung von Betonabbruchmaterialien, einem Prozess, der das Binden von Kohlendioxid in Form von Karbonat an Betonkörner beschreibt. Eine umfangreiche Literaturstudie legt dar, dass Beton durch Verwitterungsprozesse langsam bis zu einer bestimmten Tiefe karbonatisiert, ähnlich wie Minerale. Durch forcierte Behandlungsmethoden lässt sich das Karbonatisierungspotential steigern und die Reaktionszeit signifikant reduzieren. Die Untersuchung zeigt, dass Faktoren wie die Temperatur, die relative Feuchtigkeit, die spezifische Oberfläche der Körner, der Anteil der Zementsteinphase sowie die Art und Dauer der Behandlung entscheidend sind. Technologien in diesem Bereich teilen sich in direkte und indirekte Verfahren, wobei letztere trotz höherer CO2-Aufnahme aus wirtschaftlichen Gründen weniger bevorzugt werden. Zusätzlich zu der Literaturanalyse erfolgt eine Patentrecherche, die das starke Interesse an der Patentierung von Karbonatisierungsverfahren verdeutlicht. Viele dieser Methoden sind jedoch technisch aufwendig und oft nur marginale Weiterentwicklungen des bestehenden Standes der Technik. Ein weiterer Kernpunkt der Arbeit stellt die Auslegung einer Pilotanlage dar, an welcher Versuche zur Karbonatisierung durchführt werden sollen. Die Anlage soll 15-20 kg Betonabbruchmaterialien verschiedener Qualitäten und Korngrößen in einen modular gestalteten Reaktor fassen und eine Behandlung mit einem CO2-reichen Abgasstrom ermöglichen. Die Planung zeigt, dass bei der Dimensionierung der Anlage erhebliche Vereinfachungen und Annahmen nötig waren, besonders im Hinblick auf den Druckverlust und den Temperaturverlauf. Probleme wie Kondenswasserbildung werden anlagentechnisch zu lösen versucht. Abschließend bietet die Arbeit einen detaillierten Vorschlag für die Durchführung von Karbonatisierungsexperimenten. Es kommen verschiedene Behandlungszeiten von 60 bis 720 Minuten zum Einsatz sowie Untersuchungen zum Einfluss der Temperatur auf den Karbonatisierungsprozess durch isolierte und nicht isolierte Rohrleitungen. Das Karbonatisierungspotential wird auch im Vergleich verschiedener Korngrößen bewertet.
gesperrt bis 17-05-2029
Keywords: Betonabbruch; Karbonatisierung; CCU; CCS; Pilotanlage; forcierte Karbonatisierung; indirekte Karbonatisierung; direkte Karbonatisierung; Concrete demolition material; carbonation; CCU; CCS; pilot plant; forced carbonation; indirect carbonation; direct carbonation

Knowledge Constrained Optimization - Handler, Johannes (Signal Separation and Optimal Control, 2024)
This thesis introduces a set of methods for optimization problems in engineering applications. Some methods focus on modeling and separating signal mixtures, particularly those containing periodic and aperiodic components. These types of signals are often encountered in the monitoring of industrial machinery. Another series of methods propose a new numerical approach for optimal system control, applicable to a broad spectrum of engineering systems described by ordinary differential equations. The unifying principle across all methods is the utilization of a-priori system knowledge, to limit the solution space to outcomes that are physically valid. In signal separation, this involves restricting solutions to periodic and aperiodic mixtures, that have a dominant global periodic component. The optimal control methods guarantee attainable results by integrating the system dynamics through mathematical representations. These methods are presented through a series of peer reviewed papers. The thesis is divided into two main parts - Signal Separation & Data Analysis and Optimal Control. The signal separation algorithms are based on the method of variable projection, due to its accurate modeling and good numerical properties. The algorithms are first designed for handling batch data, and are subsequently extended to work recursively, making them more suitable for processing streaming data. The performance of these algorithms is demonstrated on industrial measurement data. The optimal control problem, in particular optimal reference tracking, is posed as an inverse problem of finding an optimal system input in order to achieve a desired output behaviour. Using the calculus of variations framework, a set of differential equations is derived, that constitute an optimality condition, i.e. the Euler-Lagrange equations. To compute the optimal solution numerically, matrix methods for solving differential equations are introduced. This methodology is first applied to derive a feed-forward optimal control trajectory for a multidimensional tracking problem, for both single and multi-agent systems. It is further extended to a closed-loop control formulation, resembling a form of model predictive control with soft constraints. Additionally, the discretization method is used to cast the optimal control task as a quadratic programming problem, which also supports hard constraints. Furthermore, these methods are applicable not only to tracking problems, but also to general full-state feedback control design.
no embargo
Keywords: Signalzerlegung; Datenmodellierung; Numerische Methoden zur optimalen Regelung; Trajektorienverfolgung; Signal Separation; Data Modelling; Numerical Methods for Optimal Control; Trajectory Tracking

Konzept zur innerbetrieblichen Rückverfolgbarkeit von Rohmaterialien und Halbfabrikaten unter Berücksichtigung der EU-Lieferkettenrichtlinie - Hirschhuber, Katarina (2024)
Die Rückverfolgbarkeit von Produkten birgt eine große Bandbreite an Nutzungspotenzialen. Das macht sie für Unternehmen aus unterschiedlichen Industriefaktoren zu einem erstrebenswerten Ziel. Durch neue Regelungen, wie der EU-Lieferkettenrichtlinie (CSDDD) rücken auch Aspekte des Umweltschutzes und der Menschenrechte in den Fokus der Rückverfolgbarkeit. Die Zielsetzung dieser Arbeit ist es deshalb ein geeignetes Rückverfolgbarkeitssystem für das Unternehmen Maschinenfabrik Liezen zu konzipieren. Dies wird in Anbetracht interner Anforderungen und unter Berücksichtigung der CSDDD umgesetzt. Dazu wird zunächst eine qualitative Literaturrecherche zur Schaffung einer Wissensbasis durchgeführt. Als wesentliche Elemente eines Rückverfolgbarkeitssystems werden die Identifikation und Kennzeichnung von Material und Produkten, Rückverfolgbarkeitsdaten und die Verwaltung von Daten definiert. Im Weiteren werden drei Herangehensweisen zur Konzipierung eines Rückverfolgbarkeitssystems vorgestellt und deren Parallelen betrachtet. Als wichtigste Schritte werden die Festlegung der Ziele eines Systems, die Anforderungen an ein System, die Analyse der Geschäftsprozesse und die Auswahl geeigneter Komponenten identifiziert. Darüber hinaus werden Inhalte der CSDDD beleuchtet. Es werden der Geltungsbereich, die enthaltenen Sorgfaltsplichten und entstehende Auswirkungen für Unternehmen analysiert. Zudem wird der Zusammenhang zwischen Rückverfolgbarkeit und der CSDDD ausgearbeitet. Die gewonnen Erkenntnisse werden im zweiten Teil der Arbeit zur Erreichung der gesetzten Zielsetzung genutzt. Das konzipierte Rückverfolgbarkeitssystem verfolgt dabei das Ziel der internen Rückverfolgbarkeit von verarbeiteten Rohmaterialien und erzeugten Halbfabrikaten.
nicht gesperrt
Keywords: Rückverfolgbarkeit; Rückverfolgbarkeitssystem; Identifikation; CSDDD; Supply Chain; Traceability; Traceability-System; Identification; CSDDD; Supply Chain

Konzepte für die Gewinnung von Polyolefinen aus gemischten Gewerbeabfällen für das Recycling - Gwandner, Jonas (2024)
Die vorliegende Masterarbeit befasst sich mit der Entwicklung und der Durchführung von Anlagenkonzepten für die Gewinnung von Polyolefinen aus gemischten Gewerbeabfällen für das Recycling. Zu Beginn wurden drei Vorversuche durchgeführt. Im Anschluss folgten insgesamt drei Materialgewinnungsversuche in einer österreichischen Abfallbehandlungsanlage, wobei zwei verschiedene Anlagenkonzepte ausgetestet wurden. Nach den ersten Versuchen wurde beschlossen, nur Polypropylen-Partikel mechanisch zu recyceln. Das gewonnene Material wurde im Digital Waste Research Lab der Montanuniversität Leoben zweifach nachsortiert. Dabei konnte ein Polypropylen-Konzentrat mit einer Gesamtmasse von 551,3 kg hergestellt werden. Anschließend folgte die Vorbereitung für das mechanische Recycling des erzeugten Konzentrates. Dabei fanden eine Zerkleinerung des Materials sowie ein Waschvorgang statt. Nach der Herstellung des finalen Polypropylen-Konzentrates, das eine Masse von 534,1 kg aufwies, erfolgte die Planung von zukünftigen Schritten und weiteren Anlagenkonzepten mit dem Ziel, diesen Recyclingprozess zu industrialisieren. Zudem wurden die erreichten Recyclingraten zunächst beschrieben und anschließend berechnet.
nicht gesperrt
Keywords: recycling; mixed commercial waste; polyolefins; Recycling; gemischter Gewerbeabfall; Polyolefine

Kreislaufwirtschaft in österreichischen KMU: Erfolgsfaktoren und Herausforderungen der Transformation des Produktions- und Logistiksystems vom linearen zum zirkulären Modell - Jöbstl, Lara (2024)
Das lineare Wirtschaftsmodell, ¿take-make-use-dispose¿, ist in den österreichischen Unternehmen seit dem Zeitalter der Industrialisierung etabliert. Durch die globale Klimakrise und die Notwendigkeit der Erreichung der Klimaziele steigt der Druck zum Wandel im gesamten Wirtschaftssystem. Die Kreislaufwirtschaft bietet dafür eine nachhaltige und zukunftsorientierte Lösung. Die Transformation zur Kreislaufwirtschaft initiiert insbesondere einen Wandel des Produktions- und Logistiksystems, da für die Realisierung einer zirkulären Wirtschaft die gesamten Waren- und Informationsflüsse optimiert und verändert werden müssen. Die österreichische Wirtschaftslandschaft besteht zum größten Teil aus Klein- und Mittelunternehmen (KMU), die bei der Transformation zur Kreislaufwirtschaft besonders gefordert sind. Das Ziel dieser Arbeit ist es, die Erfolgsfaktoren und Herausforderungen für österreichische KMU in der Transformation zur Kreislaufwirtschaft mit Fokus auf das Produktions- und Logistiksystem zu identifizieren. Der erste Teil dieser Arbeit besteht aus einer Analyse des aktuellen Standes der Forschung, welche mit einer systematischen Literaturrecherche (SLR) in der Datenbank ¿Scopus¿ gemäß PRISMA durchgeführt wird. Dabei werden relevante Studien anhand des Titels und des Abstracts analysiert, um sie nach festgelegten Inklusions- und Exklusionskriterien zu kategorisieren. Nachfolgend werden die Studien deskriptiv und inhaltlich untersucht, um die Ergebnisse in interne und externe Erfolgsfaktoren und Herausforderungen zusammenzufassen. Darauf aufbauend werden, unter Berücksichtigung der vorangegangenen Literaturrecherche und Kategorisierung, sieben Experteninterviews mit Experten aus dem österreichischen Wirtschaftsraum durchgeführt und mittels einer inhaltlich strukturierenden qualitativen Inhaltsanalyse nach Kuckartz aufbereitet. Die Zusammenfassung der theoretischen Ergebnisse aus der SLR und der praktischen Erkenntnisse aus den Experteninterviews bildet die grundlegenden unternehmensinternen und -externen Erfolgsfaktoren und Herausforderungen für KMU im Übergang des Produktions- und Logistiksystems zur Kreislaufwirtschaft ab. Durch diese Synthese leistet diese Arbeit einen wesentlichen Beitrag zur Unterstützung der Transformation zur Kreislaufwirtschaft in österreichischen KMU.
nicht gesperrt
Keywords: Kreislaufwirtschaft; Nachhaltigkeit; lineares Wirtschaftsmodell; zirkuläres Wirtschaftsmodell; Erfolgsfakotren; Herausforderungen; SLR; Experteninterviews; Circular Economy; sustainability; linear economic model; circular economic model; success factors; challenges; SLR; expert interviews

Local fatigue strength assessment of cast steel components considering manufacturing effects - Horvath, Michael (2024)
Cast steel components are affected by manufacturing process-based imperfections, which alter the local stress state leading to significantly reduced fatigue life. Due to the arbitrary spatial shape of intrinsic defects, the application of local fatigue assessment concepts is encouraged to ensure safe operation of defect-afflicted components. This research work focusses on the investigation of the fatigue life limiting effect of casting defects. Based on extensive experimental work, the material behavior of the cast steel alloys G12MnMo7-4+QT and G21Mn5+N is characterized utilizing plain and notched small-scale specimens made from near defect-free bulk material. Additional high-cycle fatigue tests of bulk and surface defect-afflicted large-scale samples provide experimental assertions on the adverse effect of immanent imperfections. In order to quantify the influence of the defect geometry, the investigated imperfections are geometrically characterized by non-destructive testing methods and fracture surface analyses. The obtained results serve as basis for the fatigue analysis of defect-afflicted specimens. Based on the theory of critical distances and the strain energy density concept, a statistical procedure is presented which facilitates the fatigue assessment in the finite- and long-life fatigue regime, considering the local defect size, shape and orientation as well as both size and mean stress effect. The devised numerical framework bases on planar defect projections in the form of radiographs, emphasizing the application-oriented focus of the present work. In order to investigate the effect of local plastic deformations, a novel approximation framework is introduced, facilitating the evaluation of the elastic-plastic strain energy density based on linear-elastic finite element analyses. The resulting holistic fatigue assessment concept merges the experimental results of plain and notched small- as well as bulk and surface defect-afflicted large-scale specimens into a unique narrow scatter band. The novel elastic-plastic concept possesses enhanced prediction accuracy compared to linear-elastic approaches, which is attributed to the consideration of cyclic mean stress relaxation and the resulting formation of a locally effective stress ratio. As the established fatigue assessment framework solely bases on planar defect projections and linear-elastic finite element analyses, numerical efficiency is significantly enhanced, confirming the holistic concept as engineering-feasible approach to facilitate the comprehensive assessment of defect-afflicted cast steel components.
no embargo
Keywords: Cast steel; Defects; Local fatigue assessment; Theory of critical distances; Strain energy density; Stahlguss; Defekte; Lokale Ermüdungsfestigkeitsbewertung; Konzept des kritischen Abstandes; Verzerrungsenergiedichte

Lokales Verformungsverhalten von gehipptem Molybdän - Heim, Christopher (2024)
Die Nanoindentation ist ein tiefenregistrierendes Härteprüfverfahren, welches nicht nur auf die Messung der Härte beschränkt ist. Mit geeigneter Methodik können unter anderem der Elastizitätsmodul, die Dehnratenabhängigkeit und lokale Mikroplastizität eines Werkstoffes gemessen werden. Durch die einfache Probenpräparation ist das Messverfahren eine ausgezeichnet Wahl als Screening Methode für Fertigungsprozesse, in der Werkstoffentwicklung und zur Validierung von Modellierungsansätzen. Diese Arbeit befasst sich mit dem lokalen Verformungsverhalten einer Molybdänlegierung mit Hauptaugenmerk auf die Entwicklung einer neuen Nanoindenter Messmethode zur Bestimmung des lokalen Ermüdungsverhalten. Bei dem untersuchten Material handelt es sich um DUMOMET der Plansee SE, welches eine mikrodotierte Molybdänlegierung ist. Untersucht wurden drei Fertigungszustände Sinter, HIP und gewalzt und rekristallisiert. Es erfolgte eine umfassende Mikrostrukturanalyse mittels REM, EBSD-Messungen und Lichtmikroskop, um die Vergleichbarkeit der Fertigungszustände zu überprüfen. Mittels Nanoindentierung wurden Versuche mit einer Berkovichspitze bei konstanter Dehnrate durchgeführt zur Bestimmung der Härte und des Elastizitätsmoduls, Dehnratenwechselversuche zur Bestimmung der Dehnratenabhängigkeit und Kriechversuche mit konstanter Last zur Bestimmung von zeitabhängiger lokaler Mikroplastizität. Um mögliche Vergleiche zu ziehen, wurde die Makro- und Mikrohärte nach Vickers bestimmt. Zusätzlich erfolgte die Aufnahme lokaler Fließkurven des Werkstoffes durch Kugeleindrücke. Die neu entwickelte Ermüdungsmethode mittels Nanoindenter basiert auf der Steuerung der Belastungszyklen über das globale Eindringtiefensignal. Vorangegangene Versuche mit Belastungszyklen durch das überlagerte CSM-Signal führten nicht zur Ermüdung des Werkstoffes, weshalb der Wechsel auf die globale Eindringtiefensteuerung folgte, da diese größere Amplitudenänderungen und partielle Entlastungen ermöglicht. Die Auswertung der entwickelten Methode wird durch Pythonskripte durchgeführt, die für jeden Entlastungsast eines Belastungszykluses die Steifigkeit des Werkstoffes und die Entwicklung der Belastungs-Hysteresenbreite bestimmt. Somit kann die Entwicklung der Steifigkeit und Hysteresenbreite mit der Lastspielzahl beziehungsweise mit der Zeit untersucht werden. Die Auswirkung der Entlastungshöhe und Messfrequenz auf die automatisierte Auswertung wurde analysiert, um Unterschiede festzustellen und Versuchsparameter zu optimieren. Die Nanoindenterversuche wurden, bis auf die Kugeleindrücke (nur RT), für Raumtemperatur, 100 °C und 300 °C durchgeführt, um die Entwicklung der Werkstoffkennwerte mit steigender Temperatur zu untersuchen. Um mögliche Vergleiche ziehen zu können erfolgten zudem makroskopische Ermüdungsversuche im HCF- und Dauerfestigkeitsbereich bei Raumtemperatur. Diese Arbeit zeigt wieder aufs Neue die Flexibilität und die breit gefächerten Anwendungsmöglichkeiten der Nanoindentation, wobei die entwickelte Nanoindenter Ermüdungsmethode eine solide Grundlage für weitere Forschung darstellt.
nicht gesperrt
Keywords: Nanoindentation; Molybdenum; local deformation behaviour; CSM; local creep; strain rate jump test; fatigue; local fatigue; ball indents; microplasticity; Nanoindentierung; Molybdän; lokales Verformungsverhalten; CSM; lokales Kriechen; Dehnratenwechselversuche; Ermüdung; lokale Ermüdung; Kugeleindrücke; Mikroplastizität

Manufacturing bio-based fiber-reinforced polymer composites: Process performance in RTM and VARI processes - Kirschnick, Ulrike; Feuchter, Michael; Ravindran, Bharath; Salzmann, Moritz; Duretek, Ivica; Fauster, Ewald; Schledjewski, Ralf (Advanced Manufacturing: Polymer and Composites Science, 2024)

Material Selection and Process Development of Droplet Based Additive Manufacturing for Medical Implants - Hentschel, Lukas (2024)
Additive manufacturing (AM) or 3D-printing has developed from a research topic to an emerging manufacturing technology in the last decades. Many different technologies and applications have been found, ranging from design prototypes, and small batch products to highly complex lightweight aircraft parts. Especially polymers play an important role in AM in general. In recent years, 3D-printing has undergone a significant market growth due to unique applications. The novel AM technology, ARBURG Plastic Freeforming (APF), was developed by ARBURG GmbH Co & KG (Lossburg, Germany) in 2006. Due to its relatively young age, only a small amount of research has been performed.The APF technology has the potential to process any thermoplastic polymer material available in granulate shape, hence no development of a filament must be done. This technology uses an injection molding unit and a piezo-electronic shut-off nozzle for the deposition of molten polymer droplets. To guarantee a proper part performance, proper processing parameters must be specified. In this context, a procedure must be researched for this technology that allows a suitable set of parameters to be determined. Therefore, high-influencing parameters must be detected as well as a proper qualification procedure. Within the scope of this Ph.D. thesis, these two questions have been answered by describing a possible parameter qualification procedure and the demonstration of parameter optimization.Therefore, the Drop Aspect Ratio (DAR) was identified as the most critical processing parameter for geometrical and mechanical properties. The DAR is defined by the ratio of the drop width (W) to the drop height (H) and is used for the definition of the machine path. In general, a low DAR led to high part filling and part density. It was found that the part density can be directly related to the tensile properties of the printed part. Furthermore, it has been demonstrated that the morphology of semi-crystalline polymers can be influenced by the print envelope temperature and part properties can thus be optimized. At evaluated print envelope temperature, weld lines disappeared and a homogeneous morphology in the cross-section of printed parts could be achieved. A real isotropic material behavior was not accomplished, but an improvement was also achieved here.AM also finds increasing numbers of applications in the medical and healthcare sectors. Medical applications like models, tools, prostheses, and even implants can be printed. These devices must fulfill many requirements like mechanical integrity, functionality, and repeatability. In this work, different polymers have been studied for cranial implants. Therefore, one standard prothesis was printed in different orientations and materials and tested on impact strength. The results were compared with those of a bone cement sample. Although the bone cement sample achieved a higher impact strength, the printed samples also met the requirements and can be used after further parameter and design optimization. The results thus showed that polycarbonate, polycarbonate urethane or polymethyl methacrylate can be established for the manufacture of cranial implants.A novel concept of a multi-material rib replacement implant was presented, to imitate soft and hard tissue within a single part. This further enhances the possibility of AM for medical devices. Therefore, the bonding between two similar polymers with different stiff- and hardnesses was studied by tensile testing. Distinctive geometrical contact areas were designed to ensure the best load transfer between the materials. Simple plain contact areas led to the best results. Based on these findings a model of the rib implant was designed. The implant was successfully printed and implanted in a human body donor. A reanimation trial was performed, and the movements of the implant were observed. The implant could withstand the upcoming forces and prove its integrity. In conclusion, it was possible to fabricate a multi-material rib replacement implant.To summarize, this Ph.D. thesis highlights the potential of the APF process for medical applications from a technical point of view. Proper parameter qualification for any given polymer was proposed and the most critical factors influencing the process on the resulting mechanical properties were determined. Parameter optimization was performed on amorphous and semi-crystalline polymers and can serve as a guideline for other parameter optimization using the APF technology. Further, implants were produced and tested mechanically for their impact strength, showing the feasibility of such applications.
no embargo
Keywords: Additive Manufacturing; Medical Applications; Process Optimization; Medical Implants; Arburg Plastic Freeforming; Mechanical Properties; Additive Fertigung; Medizinische Anwendungen; Medezinische Implantate; Arburg Kunststoff-Freiformen; Mechanische Eigenschaften

Mean-Field-Model Development for Void Formation in SAC305-Solder Bumps - Huber, Alexander (2024)
The formation of pores is frequently observed during the ageing process of soldered semiconductor components in the microelectronics industry. Sn-Ag-Cu-based solders used in the industry form the intermetallic phases Cu3Sn and Cu6Sn5, which expedites the problem. Insights into the formation of pores and their distribution are of significant importance for the assessment of the operating limits and are analysed in the present Master's thesis. A mean-field model is developed from a model based on thermodynamic considerations in a non-equilibrium state. This is generalised with regard to the geometry, initial pore and vacancy distribution and the characterisation of the individual phases. A descriptive differential equation is obtained from the considerations on vacancy diffusion underlying the pore evolution characterisation. In addition to the intermetallic phases, the pure phases Cu and Sn also occur. Moreover to the contributions of the surface energy and chemical bonding energy, the mechanical portion of the Gibbs energy must be taken into account through the strain energy. Therefore, the stress and strain state of the material points of the continuum must be represented. In particular, the anisotropy, the plastic material behaviour including hardening mechanisms and the creep behaviour must be realistically implemented in the numerical model. The implementation of the model is performed by means of the finite element method. Various subroutines are used to flexibly design the interpolation of the material behaviour between the individual phases. Furthermore, a suitable constitutive law is derived in order to be able to determine the influence of pore formation on the stiffness of the solder joint and the consideration of transformation strains. The modelling is followed by the validation of initial simulation results using the experimental data provided and by fitting previously unknown parameters to predict dissipative influences. An essential aspect is the evaluation of impurities in the solder, especially through an increasing Cl-content. The influence is to be taken into account by adapting the thermodynamic parameters.
embargoed until 28-06-2029
Keywords: SAC305; Porösität; Lötstellen; Kirkendall-Effekt; FEM; Porenwachstum; Cl-Kontamination; SAC305; porosity; solder bumps; Kirkendall-effect; FEM; pore growth; Cl-contamination

Measurement of diffusion and activity coefficients in slags - Halwax, Alexander (2024)
Slags are important in iron and crude steel making as well as in secondary metallurgical treatments. Slag properties, such as viscosity, density, liquidus temperature, oxidation potential, foaming behavior, etc., have a significant influence on the efficiency of metallurgical processes. These properties are largely defined by the slag composition. The slag composition is adjusted in all metallurgical processes by the addition of additives. These are usually CaO- and/or MgO-containing additives. Knowledge of diffusion coefficients of the respective oxide in slags is necessary to describe dissolution processes of additives in slags and therefore to optimize existing processes or develop new ones. Furthermore, the knowledge of thermodynamic activities of individual slag components is of great interest for understanding and optimizing metallurgical processes. A low activity of the species to be extracted (e.g. P or S) in the slag leads to an efficient removal of these components from the steel. The capacity of slags to absorb unwanted steel by-elements is influenced by the composition of the slag. The determination of these two parameters (diffusion coefficient and activity) in slags was the objective of this work. For the investigation of diffusion coefficients in slags, an experimental setup was designed which allows dissolution experiments to be carried out under reproducible conditions. In addition to the construction of the experimental setup, a calculation model was developed, which enables the calculation of the diffusion coefficient from the data of the dissolution tests. This model includes a density model and five different viscosity models. Since each viscosity model is valid for a certain temperature and composition range, it was necessary to use several models to investigate different slags. Besides the design of the experimental setup and the development of a suitable calculation model, a device as well as procedures for CaO sample production had to be planned. The diffusion coefficients of CaO and MgO in a blast furnace, calcium aluminate and wollastonite slag at 1500 and 1600 °C, and in a BOF slag at 1400 and 1500 °C were obtained by various dissolution experiments. Additionally, the diffusion coefficients or dissolution rates of Al2O3, SiO2 and MgAl2O4 were measured in a ladle furnace slag at 1550 °C. The results and the comparison with literature data showed in general a decrease of the diffusion coefficient with increasing slag viscosity. Comparison with literature data also confirmed the suitability of the experimental setup and the calculation model. A method allowing the determination of activities of individual slag components without the need for literature data was required. Such a procedure could be realized using Knudsen effusion mass spectrometry (KEMS). The KEMS measurements were carried out at Forschungszentrum Jülich. Since this method was rarely used in the metallurgical research field, the experiments, in the course of this work, were able to establish a basis for further research. In addition to the determination of the activity of CaO and MgO in various slags, the KEMS measurements also allowed the calculation of the enthalpies of formation of both oxides. Comparison of the measurements with literature values confirmed the suitability of this method for activity measurements of slag components.
no embargo
Keywords: Metallurgische Schlacken; Auflösung; Diffusion; KEMS; Aktivität; Calciumoxid; Magnesiumoxid; Metallurgical slags; Dissolution; Diffusion; KEMS; Activity; Calcium oxide; Magnesium oxide

Measurement of the heat transfer in the primary cooling area of a laboratory direct chill casting plant for alloy design. - Weidinger, Andreas (2024)

Mechanical and electronic properties of monolayer TMDCs - Ziegler, Maximilian (A DFT study, 2024)
In recent years, materials research in electronics has been tied to the trend of downsizing, where the focus lies on creating smaller and smaller structures that can be integrated into electronic devices. With the advent of graphene, a two-dimensional carbon structure, new atomically thin materials have become a reality, some of which exhibit desired chemical and structural stability alongside sought-after electronic and optical properties. Among these, transition metal dichalcogenides (TMDCs), have attracted interest of the scientific community. These materials possess the chemical formula MX2, where “M” denotes any transition metal of the periodic table and “X2” represents two covalently bonded chalcogen atoms. These include Sulfur (S), Selenium (Se), Tellurium (Te), and also a combination of these.Simulation studies of the exotic properties of TMDCs have accumulated, sometimes surpass- ing experimental evidence. However, a comprehensive overview that presents the different types and fundamental properties of these materials in a clear and straightforward manner is missing. The first objective of this thesis is to close this gap, with the primary interest lying in providing an overview of the basic elastic and electronic properties of these emerg- ing materials as a function of their structure and composition. Its second objective is to investigate the effects of straining and shearing on TMDC structures, mainly to investigate the influence of chosen deformations on the bandgaps.In the frame of this thesis, simulations were performed using the Vienna Ab Initio Simulation Package (VASP), a density functional theory (DFT) code that allows an insight into the mechanical and electronic properties of these materials.
no embargo
Keywords: TMDCs; 2D-materials; DFT; VASP; TMDCs; 2D-Materialien; DFT; VASP

Methodenentwicklung zur Herstellung von stickstofflegierten Stählen mittels Laborschmelzen und deren thermodynamischen Charakterisierung im Hochtemperaturbereich - Donauer, Patrick (2024)
Die Kontrolle von Stickstoff in der Stahlherstellung ist von hoher Bedeutung und gewinnt zusehends an Relevanz. Stickstoff als unauffälliger, jedoch essentieller Bestandteil des Stahls beeinflusst maßgeblich die Materialeigenschaften. Die vorliegende Arbeit behandelt eine Methodenentwicklung zur Herstellung von stickstoffhaltigen Stahlproben im Labor und die thermische Analyse dieser Stähle. Für die Laborprobenherstellung wurde ein Setup zur Einstellung des N2-Partialdrucks in Abhängigkeit der chemischen Analyse der Schmelze für einen kleinen Labor-Induktionsofen (Hochfrequenzumschmelzanlage) entwickelt. Mittels gezielter Ar-N2 Partialdruckmischungen wurden im Rahmen dieser Arbeit Proben der Systeme Fe-Cr-N, Fe-Mn-N, Fe-Nb-C-N mit dem gewünschten Ziel-Stickstoffgehalt hergestellt. Besonders niedriglegierte Stähle und Fe-10%Cr Legierungen konnten bis hin zu höchsten N-Gehalten sehr zuverlässig hergestellt werden. Der zweite Teil der Arbeit fokussierte sich auf die thermische Analyse von Fe-Cr-N Stählen mittels Differenz-Thermoanalyse (DTA) und Dynamischer-Differenzkalorimetrie (DSC) zur Bestimmung der Phasenumwandlungstemperaturen im Hochtemperaturbereich. Vorversuche an einer Simultanen-Thermischen-Analyse (DTA-TG) mit einer gekoppelten Abgasanalyse mittels eines Massenspektrometers (QMS) konnten aufzeigen, dass bereits beim Aufheizen unter Ar-Atmosphäre einer Fe-10Cr-0,1N Legierung der Stickstoff ab 1200°C aus der Probe herausdiffundiert und sich somit die chemische Analyse der Probe ändert. Für die DSC-Anlage wurde ein Versuchskonzept mit einer softwaregesteuerten Ar-N2 Gasmischung zur Stabilisierung des N2-Partialdruckes während der Messung entwickelt. Jedoch dominierten unerwünschte oberflächliche Oxidationsvorgänge durch den Restsauerstoffgehalt im Stickstoffgas, sodass mit den derzeit verfügbaren technischen Möglichkeiten keine sichere Messung von stickstofflegierten Stählen möglich ist.
nicht gesperrt
Keywords: Stickstofflöslichkeit; Sievertsches Gesetz; Fe-Cr-N; Fe-Mn-N; Probenherstellung; Thermische Analyse; Nitrogen solubility; Sievert's law; Fe-Cr-N; Fe-Mn-N; Sample preparation; Thermal analysis

Microfacies, biostratigraphy and sequence stratigraphy of the Upper Triassic Dachstein fore-reef facies in the East Bosnian-Durmitor megaunit (northern Montenegro) - Zöhrer, Oliver (2024)
In this work the microfacies development, biostratigraphy, and sequence stratigraphy of four different successions of Upper Triassic Dachstein fore-reef limestones in Poros and Pra¿ica in northern Montenegro have been investigated, so far unknown in the Dinarides. The successions have a biostratigraphic age from the Tuvalian 3 to the Alaunian 3-?Sevatian (Upper Carnian to Upper Norian) dated by conodont assemblages. Generally five microfacies types could be distuinguished, ranging from an open-marine filament rich packstone deposited in a distal reef position, oligomictic microbreccias with different (fore-)reefal carbonate clasts, shallow-water influenced turbiditic grainstones, and rudstones as well as blocks of framestones with preserved in-situ reef building organisms in the blocks. The general sedimentation pattern shows a cyclic deposition of shallow-water influenced grainstones, rudstones and framestones in an open-marine lower slope environment. The shallow-water fauna consists of A) foraminifera: Agathammina austroalpina (Kristan-Tollmann & Tollmann), Alpinophragmium perforatum (Flügel), Decapoalina schaeferae (Zaninetti, Altiner, Dager & Ducret), Paraophtalmidium carpathicum (Samuel & Borza), Kaeveria fluegeli (Zaninetti, Altiner, Dager & Ducret), Endoteba sp, Duotaxis sp., Ophtalmidium sp., Duostomina sp., Trochamina sp., Reophax sp., Ammobaculites sp., B) microproblematica: Baccanella floriformis (Panti¿), Microtubus communis (Flügel), Tubiphytes obscurus (Maslov), Radiomura cautica (Senowbari-Daryan & Schäfer), Actinotubella gusici (Senowbari-Daryan), Muranella sphaerica (Borza), ?Porforitubus buseri (Senowbari-Daryan) and C) calcified sponges: Cryptocoelia sp., Uvanella sp., Celyphia sp., beside D) various not determinable corals of the Upper Triassic Dachstein reef habitat. For the biostratigraphic age dating following conodonts are determined: M. communisti (Hayashi), M. praecommunisti (Mazza, Rigo and Nicora), Q. tuvalica (Mazza & Rigo), E. primitia (Mosher), E. quadrata (Orchard), E. rigoi (Kozur), E. triangularis (Budurov), E. spatulata (Hayashi), E. cf. multitendata A sensu Krystyn , E. multitendata (Mosher), E. postera (Kozur &Mostler), N. navicula (Huckriede), N. hallstattensis (Mosher), and N. steinbergensis (Mosher). The combined sequence stratigraphic analyses of all investigated successions show the onset of the Dachstein Carbonate Platform in the Tuvalian 3 and aggradation in the lower Lacian 1 subsequently followed by progradation of the platform in the middle Lacian 1 to highest Lacian 2. Again, after a sea-level drop aggradation in the Lacian 3 is followed by progradation in the Alaunian and ?Sevatian, with a short interruption at the Alaunian 2/3 boundary. A comparison with the short-term sea-level curve of Haq et al. (2018) shows a generally good correlation with only minor offsets between the different system tracts. However, major discrepancies exist when they are compared with other time equivalent sequence stratigraphic developments located in the Northern Calcareous Alps and Southern Alps.
no embargo
Keywords: Montenegro; Dinarides; Microfacies; Biostratigraphy; Upper Triassic; Norian; Dachstein; Reef limestone; Fore-reef limestone; Montenegro; Dinariden; Mikrofazies; Biostratigraphie; Obertrias; Nor; Dachstein; Riffkalk; Vorriffkalk

Microplastic response of 2PP-printed ceramics - Sänger, Johanna C.; Riechers, Birte; Pauw, Brian R.; Maaß, Robert; Günster, Jens (Journal of the American Ceramic Society, 2024)
Publisher Copyright: © 2024 The Author(s). Journal of the American Ceramic Society published by Wiley Periodicals LLC on behalf of American Ceramic Society.
Keywords: additive manufacturing; mechanical properties; microstructure; plasticity; zirconia: yttria stabilized

Microstructure and magnetic properties of high-pressure torsion synthesized hard magnetic materials - Weissitsch, Lukas Emanuel (2024)
The rising public awareness of green technologies manifests itself in the increasing demand for renewable energy and electric mobility, leading to an annually raising production of permanent magnets. Performance and efficiency of generators, motors and electric components, rely on the use of high-performance permanent magnets, which contain a significant amount of cobalt or rare-earth elements. However, their production is associated with questionable working conditions and environmental problems related to mining and the availability of these materials is subject to a monopolistic situation. Supply shortages, already recognized by international institutions, represent a critical bottleneck for modern economic and social development.This work is dedicated to the search of alternatives regarding hard-magnetic materials. Herein, the focus is on two main approaches. First, the utilization of magnetic coupling effects, namely 'exchange bias' and 'exchange coupling', to reduce the amount of critical elements. Second, the formation of a rare-earth free ferro-magnetic phase, in particular $\upalpha$-MnBi. For material processing, severe plastic deformation by high-pressure torsion is conducted, which allows for the application of a high, tunable amount of strain. Using phases with different magnetic properties, this top-down technique results in both, microstructural refinement and strongly refined composite structures, all while maintaining bulk sized samples.In the pursuit of achieving an exchange bias, extensive microstructural processing and characterization of the Fe-Cr material system are performed. An observed co-deformation of powders limits a sufficient refinement for exchange bias due to a significant hardness increase. The deformation behavior is improved by using arc-melted Fe-Cr ingots as starting material, leading to a refined solid solution. A remarkable temperature stability is reported, hindering a decomposition into finely dispersed Fe and Cr phases. This holds true for both increased annealing temperatures and prolonged annealing times. A multi-sector 2-stage high-pressure torsion process is developed to refine the phases and simultaneously prevent intermixing of Fe and Cr. Despite promising results, no exchange bias is achieved within this material system.SmCo$_5$ is deformed by high-pressure torsion and serves as a hard magnetic phase for an exchange coupled spring magnet. The coupling is demonstrated across a broad variation of chemical compositions. A change in the operating temperature allows switching between a coupled spring magnet and the uncoupled state. The influence of a high-pressure torsion deformation induced textured microstructure results in the formation of an anisotropic permanent magnet.In obtaining bulk sized samples, the successful processing of the rare-earth free $\upalpha$-MnBi phase is emphasized. The high microstructural defect density induced by high-pressure torsion enhances the $\upalpha$-MnBi phase formation during a subsequent annealing procedure. A deformation at 2~GPa is preferred over 5~GPa, as well as a higher amount of applied strain. The thermal treatment is improved by applying vacuum conditions and an external magnetic field during annealing. The formed $\upalpha$-MnBi phase is studied and an influence of the sample's shear texture with respect to the applied field direction during annealing is found. This allows to tune the magnetic properties between an isotropic and anisotropic behavior.
no embargo
Keywords: Hochverformung; Hochdrucktorsion; Gefügestrukturabstimmung; nanokristallines Material; Dauermagnet; Selten-Erd frei; hartmagnetisches Material; magnetische Kopplungsmechanismen; severe plastic deformation (SPD); high-pressure torsion (HPT); microstructure tuning; nanocrystalline material; permanent magnet; rare-earth free; hard magnetic material; magnetic coupling mechanism

Microstructure evolution and mechanical properties at ambient and elevated temperatures of in‑situ TiB2/2219Al matrix composites during cold rolling - Li, Linwei; Zhou, Donghu; Wei, Chengbin; Han, Zhenhao; LI, Jiehua; Kang, Huijun; Guo, Enyu; Zhang, Yubo; Chen, Zongning; Wang, Tongmin (Metals and materials international, 2024)

Modeling Desiccation Cracks in Opalinus Clay at Field Scale with the Phase-Field Approach - Cajuhi, Tuanny; Ziefle, Gesa; Maßmann, Jobst; Nagel, Thomas; Yoshioka, Keita (InterPore Journal, 2024)

Modeling and simulation of the copper recycling from wastewater in AT&S - Notter, Sarah (2024)
The objectives of this master thesis are the implementation of a simulation software, the subsequent development of a process model and a simulation framework. This should simplify the roll-out and implementation of the in-house recycling plant for copper and hydrochloric acid in other AT&S plants. Extensive literature research introduces the topics of copper as a raw material, industrial wastewater and wastewater treatment. Moreover, the AT&S in-house recycling plant is also explained in detail, which is then modeled. The theory of process modeling and simulation is also briefly discussed. The practical part starts with the definition of requirements, the selection of the software and following implementation of ITHACA. By collecting process data from the existing recycling plant in AT&S Hinterberg (Austria), a model and a simulation framework can be created to complement future tests of the applicability of the recycling concept. The model development, validation, verification and creation of a simulation framework are also documented.
no embargo
Keywords: Modeling; Simulation; Waste water; Recycling; Copper; AT&S; Process engineering; Modellierung; Simulation; Abwasser; Recycling; Kupfer; AT&S; Verfahrenstechnik

Modeling of CO2 Injection and Sinking in Supercritical Geothermal Systems - Scherounigg, Christoph (2024)
In supercritical geothermal systems in deep volcanic areas, where pressures exceed 22 MPa and temperatures exceed 374°C, supercritical carbon dioxide (CO2) has a higher density than water. In the context of CO2 injection and storage, this poses the opportunity of having a sinking plume of CO2 while utilizing in-situ geothermal fluids as a renewable energy source. Following an overview of ongoing efforts in the prospection and development of supercritical geothermal systems, this thesis aims to provide extensive finite element simulation of CO2 transport in both homogeneous and fractured supercritical reservoirs. For creating models in a 3D domain, the multi-physics simulation framework MOOSE is used. The fracture network itself is realized as a discrete network based on stochastic distributions of parameters, including fracture dimensions, strike and dip angles, and fracture density. A parallel simulation approach is applied to simplify the complicated meshing process of a single combined model. Instead of embedding the discrete fracture 2D mesh within the 3D matrix mesh, the use of two separate models communicating with each other is demonstrated and applied. Furthermore, the numerical implications of this approach are discussed. In addition to analyzing the CO2 plume phenomenologically, the dependency on varying permeability and fracture network parameters, specifically fracture dimensions and fracture aperture, are investigated. As critical factors for geothermal energy production, CO2 breakthrough analysis was performed, and temperature distributions within the models were studied. From the simulations, it was concluded that the effect of CO2 sinking in reservoirs is more pronounced in high-permeability formations compared to low-permeability ones, where viscous forces dominate. Although CO2 still tends to sink in fracture networks, fluid flow is mainly controlled by the network path towards the producer, displacing all water uniformly. Cooling of the reservoir has been observed to be limited to a zone around the injector for the investigated scenarios.
no embargo
Keywords: Supercritical Water; Supercritical CO2; CO2; Sinking CO2; CCS; Carbon Capture and Storage; Geothermal Energy; Discrete Fracture Network; Fractured Reservoirs; MOOSE; Supercritical Geothermal Reservoirs; Überkritisches Wasser; Überkritisches CO2; CO2; Sinkendes CO2; CCS; Kohlendioxidabscheidung und -speicherung; Geothermische Energie; Diskretes Frakturen-Netzwerk; Frakturierte Reservoire; MOOSE; Überkritische geothermische Reservoire

Modeling the concurrent growth of inter- and intragranular Si precipitates during slow cooling of the alloy AA6016 - Falkinger, Georg; Kahlenberg, Robert; Theissing, Moritz; Mitsche, Stefan; Thum, Angela; Pogatscher, Stefan (European journal of materials, 2024)
Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Al-Mg-Si alloy; collector plate model; hot rolling; Si phase

Modellierung eines Pyrolyseprozesses zur optimalen Aufbereitung von Sekundärrohstoffen unter Nutzung von verfügbaren Abwärmepotentialen - Cont, Alexander (2024)
Die europäischen CO2-Reduktionsziele können nur mit signifikanten Verbesserungen von privaten und industriellen Anwendungen und Prozessen erreicht werden. Der industrielle Wärmesektor spielt bei der Erreichung dieser Klimaziele eine wesentliche Rolle, da der Großteil der Wärmeerzeugung in Europa aus fossilen Energiequellen stammt (ca. 75 %). Eine Dekarbonisierung kann bspw. durch die Steigerung der Prozesseffizienz, dem Einsatz von erneuerbaren Energien oder der Nutzung von Abwärme (in der Europäischen Union fallen ca. 3.000 TWh pro Jahr an) vorangetrieben werden. Auch die Kreislaufwirtschaft von Rohstoffen stellt eine Möglichkeit dar, um den Primärenergieeinsatz, und somit die entstehenden Emissionen, zu verringern.An diesen Punkten setzt das Unternehmen Seccon GmbH an und hat ein Patent entwickelt, um bestehende Abwärmepotentiale für die Aufbereitung von verschiedenen Abfallfraktionen zu nutzen. Dabei wird ein heißes Abgas einer thermischen Produktionsanlage verwendet, um Abfälle in einem Drehrohrofen zu pyrolysieren und eine Abtrennung der darin enthaltenen Wertstoffe zu erzielen. Durch den Einsatz von Abwärme, die anderenfalls ungenutzt bleibt, können, im Vergleich zu herkömmlichen Aufbereitungs-Techniken, sowohl Kosten-, als auch Energieeinsparungen erreicht werden. Außerdem wirkt sich die Nachnutzung des Abgases positiv auf die CO2-Bilanz des industriellen Prozesses aus.Das Ziel der vorliegenden Arbeit besteht darin, die Energieflüsse der bereits bestehenden Pilotanlage und einer geplanten Großanlage zu modellieren und zu analysieren. Im ersten Teil wird auf den theoretischen Hintergrund des Prozesses eingegangen. Das Patent von Seccon wird beleuchtet und ein Überblick über die verwendete Python-Bibliothek gegeben.Im praktischen Teil dieser Arbeit wird unter Verwendung der OEMOF-Bibliothek ein Python-Modell entwickelt, um den Aufbereitungsprozess darzustellen und den Energieeinsatz zu optimieren. Das OEMOF-Modell wird um Nebenbedingungen erweitert, damit die Temperaturabhängigkeit der Pyrolyse in die Modellierung mit einfließt. Um die Optimierungspotentiale zu analysieren, werden vier beispielhafte Szenarien berechnet und bewertet. Eines davon betrachtet die Pilotanlage, die anderen drei stellen den Prozess der zukünftigen Großanlage zu verschiedenen Betrachtungszeiträumen und mit unterschiedlichen Prozessbedingungen dar. Die Randbedingungen und Eingabeparameter der Optimierungen werden vom Projektpartner Seccon vorgegeben, sofern sie mittels Pilotanlage bereits bestimmt und für die Großanlage hochskaliert wurden. Die fehlenden erforderlichen Parameter werden anhand von Literaturwerten ergänzt.Die Zielfunktion der Optimierung ist die Minimierung der Gesamtkosten, nicht die Minimierung der eingesetzten Energiemenge. Deshalb sind bei den Berechnungen nur geringe Einsparungen der Energiemenge zu beobachten (kleiner als 1 %). Dies ist darauf zurückzuführen, dass die Abfallmenge eine vorgegebene, nicht veränderbare, Energiemenge benötigt, damit sie vollständig pyrolysiert werden kann. Die Optimierung wählt deshalb den zeitlichen Abfalleinsatz anhand der Energiepreise so aus, dass die Kosten für den Aufbereitungsprozess minimiert werden.Durch die Optimierung der Pilotanlage ergibt sich eine spezifische Gewinnerhöhung von ca. 0,025 €/kg. Bei der Großanlage kann eine Gewinnsteigerung von ca. 0,002 €/kg erreicht werden, wenn ein heißes Abgas aus einer nebenstehenden Anlage zur Verfügung steht. Wenn die gesamte Prozessenergie für die Pyrolyse in der Großanlage zugekauft werden muss, ergibt sich eine Gewinnsteigerung von ca. 0,04 €/kg. Die Ergebnisse zeigen, dass die Optimierung vor allem in Zeiträumen, wo keine Abwärme zur Verfügung steht, hohe Gewinnsteigerungen ermöglicht. Zusätzlich bestimmt der Optimierer die Abfallfraktionen, deren Verarbeitung sich nur bei verfügbarer Abwärme positiv auf das Betriebsergebnis auswirkt.
nicht gesperrt
Keywords: Energy Model; Processing of Secondary Resources; Waste Heat Usage; Pyrolysis; Rotary Kiln; Optimization; Python; OEMOF; Open Energy Modelling Framework; Energiemodell; Aufbereitung Sekundärrohstoffe; Abwärmenutzung; Pyrolyse; Drehrohrofen; Optimierung; Python; OEMOF; Open Energy Modelling Framework

Modellierung und Experimentelle Validierung einer Antriebswinde zur Erstellung eines Digitalen Zwillings für die Überprüfung der Software einer Programmierbaren Logischen Einheit - Wenk, Ines (2024)
Die folgende Arbeit beschäftigt sich mit der Erstellung eines digitalen Zwillings einer in einem Raupenkran eingebauten Hubwinde. Ziel ist es, die Simulation so allgemein wie möglich zu gestalten, damit sie für eine Vielzahl von Kranmodellen verwendet werden kann. Aus diesem Grund werden zwei verschiedene (aber relativ ähnliche) Simulationsmodelle erstellt. Eines für einen offenen hydraulischen Kreislaufes und eines für einen geschlossenen Kreislauf. Die Simulation wird mit dem Computerprogramm MATLAB-Simulink durchgeführt, das eine einfache Änderung der Parameter (z. B. unterschiedliche Abmessungen der Seiltrommel) ermöglicht. Es werden die wichtigsten Variablen (Hubgeschwindigkeit, Länge des aufgewickelten Seils, Druck in den Rohren usw.) berechnet und über der Zeit abgebildet. Bei der Erstellung des Simulationsmodells werden einige Vereinfachungen vorgenommen, um die Berechnungen zu erleichtern und die Laufzeit so gering zu halten, dass die Simulation in Echtzeit parallel zu einer realen Anlage laufen kann. Dies sollte auch weitere zukünftige Forschungen und Verbesserungen ermöglichen. Die Korrektheit der Simulation wird anhand von, an der realen Maschine durchgeführten, Tests überprüft. Die gemessenen Werte werden mit den Berechnungsergebnissen der Simulation verglichen und ihre Abweichungen werden berechnet. Dafür werden unterschiedliche Methoden (absoluter und relativer Fehler; Bildung der Abstandsquadrate zwischen den Kurven) verwendet, um eine möglichst gute Abbildung der Qualität der Simulation zu erhalten.
gesperrt bis 05-09-2028
Keywords: Digitaler Zwilling; Antriebswinde; Simulationsmodell; Raupenkran; digital twin; drive winch; simulation model; crawler crane

Modellierung von Grundwasserströmung und reaktivem Stofftransport im mit PFAS kontaminierten Aquifer Westliches Leibnitzer Feld, Steiermark und Ableitung von Sanierungsvarianten - Moderegger, Richard (2024)
Die vorliegende Arbeit beschäftigt sich mit der PFAS-Belastung im Porengrundwasserleiter Westliches Leibnitzer Feld, Steiermark, welche mit hoher Wahrscheinlichkeit vom Standort der Feuerwehr- und Zivilschutzschule Steiermark in Lebring - Sankt Margarethen ausgeht. Dabei steht die Modellierung der Grundwasserströmung und des PFAS-Transports im betroffenen Gebiet im Mittelpunkt. Ein für den Untersuchungsraum bereits etabliertes Grundwassermodell zeigte Abweichungen zwischen der damals berechneten Grundwasserströmungsrichtung und der gemessenen PFAS-Schadstofffahne. Für das bestehende Grundwassermodell wurde daher der Einfluss der Modellparameter auf die Grundwasserströmung herausgearbeitet. Die Ergebnisse zeigen, dass insbesondere die Leckage der Mur im Raum Lebring sowie eine mögliche Anisotropie der Durchlässigkeit deutliche Auswirkungen auf die Grundwasserströmungsrichtung haben. Durch aus geologischer Sicht vertretbare Anpassungen lässt sich bei einer geringfügigen Erhöhung des Modellfehlers bezogen auf die Grundwasserspiegelhöhen eine deutlich bessere Übereinstimmung der Grundwasserströmungsrichtung mit der Ausbreitung der Schadstofffahne erreichen. Zudem wurde der zeitliche Rahmen bis in das Jahr 2023 erweitert. In weiterer Folge wurde der chemische Fingerabdruck der Kontamination untersucht. PFOS, PFHxS, PFPeA und PFHxA stellen die Hauptkontaminanten dar. Während die Ausbreitung von PFOS und PFHxS über die gesamte Fahnenlänge nachweisbar ist, beschränkt sich die Belastung mit PFPeA und PFHxA auf den Quellennahbereich. Mögliche Gründe sind eine Verlangsamung der Ausbreitung durch eine höhere Adsorption von PFPeA und PFHxA, oder aber eine spätere Freisetzung dieser beiden PFAS. Für die Hauptkontaminanten wurde der reaktive Stofftransport an die Grundwasserströmung gekoppelt und für verschiedene Adsorptionskoeffizienten modelliert. Die Ergebnisse erlauben die Ableitung eines standortspezifischen und von der Quellenkonzentration unabhängigen linearen Zusammenhangs zwischen der Höhe des Adsorptionskoeffizienten und der Ausbreitungsgeschwindigkeit der PFAS. Darüber hinaus zeigt das reaktive Stofftransportmodell qualitativ gute Übereinstimmungen mit der gemessenen Schadstoffausbreitung. Abschließend wurden einige mögliche Sanierungs- und Sicherungsvarianten beleuchtet und zudem für ausgewählte Methoden die Kosten anhand von Fallbeispielen eingeordnet. Auf Basis einer überschlägigen Berechnung und Modellierung können zwei mögliche Sperrbrunnenanordnungen mit den dafür nötigen Förderraten vorgestellt werden. Die Ergebnisse dieser Arbeit liefern somit einen wertvollen Beitrag zur Erstellung eines Standortmodells und unterstützen zukünftige Sanierungsambitionen.
nicht gesperrt
Keywords: PFAS; Feuerwehrschule Lebring; Feuerlöschschäume; Leibnitzer Feld; Grundwassermodell; Stofftransportmodell; Altlastensanierung; Adsorption; PFAS; firefighting training site Lebring; AFFF; Leibnitzer Feld; groundwater flow model; contaminant transport model; site remediation; adsorption

Monitoringsystem für Gurtförderer - Industrieanwendung - Winkler, Daniela (2024)
Die nachfolgende Arbeit befasst sich mit der Testung des E-PrimeTrackers im industriellen Umfeld. Beim E-PrimeTracker handelt es sich um ein Gurtschieflaufüberwachungs- und Korrektursystem, das am Lehrstuhl für Bergbaukunde, Bergtechnik und Bergwirtschaft der Montanuniversität Leoben von der Arbeitsgruppe Fördertechnik und Konstruktionslehre in Zusammenarbeit mit der Firma ScrapeTec Trading GmbH (Kamp-Lintfort, Deutschland) entwickelt wurde. Überprüft werden soll, ob und unter welchen Bedingungen eine Führung bzw. Lenkung des Gurtes durch den E-PrimeTracker gegeben ist. Außerdem soll untersucht werden, ob eine Wiederholbarkeit eines auf den Fördergurt aufgebrachten Fehlers unterschiedlicher Belastungen vom Monitoringsystem ermittelt werden kann. Dazu wird die um ein Monitoringsystem erweiterte Lenkstation in das Leertrum zweier Gurtförderer der Sinteranlage der voestalpine Stahl Donawitz GmbH mit Sitz in Leoben, Österreich, verbaut. Es wird versucht, durch gezieltes Aufbringen exzentrischer Belastungen auf den Fördergurt, mithilfe einer im Zuge dieser Arbeit entworfenen Vorrichtung, den Gurt aus seiner Grundposition zu zwingen und so einen Gurtschieflauf zu verursachen. Dieser erzwungene Gurtschieflauf wird von zwei im Monitoringsystem verbauten Ultraschallsensoren sowie einem an der Umlenktrommel verbauten Lasersensor aufgezeichnet, ausgewertet und in weiterer Folge mit Wiederholversuchen verglichen. Der E-PrimeTracker soll den Gurtschieflauf dabei minimieren bzw. verhindern. Um den Einfluss der Gurtanpresskraft des E-PrimeTrackers auf die Gurtlenkfähigkeit zu untersuchen, wurden Versuche bei unterschiedlichen Umschlingungswinkeln des Fördergurtes am E-PrimeTracker durchgeführt. Darüber hinaus wurde eine Versuchsreihe ohne E-PrimeTracker vorgenommen, um das Verhalten des Fördergurtes bei erzwungenem Gurtschieflauf mit und ohne E-PrimeTracker vergleichen zu können.
gesperrt bis 17-05-2029
Keywords: E-PrimeTracker; PrimeTracker; steering station; monitoring system; belt misalignment; belt error; conveyor belt; belt conveyor; belt tracking; E-PrimeTracker; PrimeTracker; Lenkstation; Monitoringsystem; Gurtschieflauf; Gurtfehler; Fördergurt; Gurtförderer; Gurtlaufüberwachung

Multiphysics simulations of PVT process for SiC growth - Moya Merino, Carlos (2024)
In the recent years, silicon carbide (SiC) is emerging as a main material in the semiconductor industry thanks to its outstanding properties. The production method is known as Physical Vapor Transport (PVT), nonetheless, the setup configuration does not allow to get information in-situ. Therefore, computational simulations became the main approach to control and predict the PVT parameters, especially using Finite Element Method (FEM) modelling. Although the construction of a FEM model for modelling a growth process could be complex due to the physics involved. This master thesis deals with the validation of different algorithm to account heat transfer by radiation physics. COMSOL Multiphysics is a FEM software which has different algorithms (direct area integration, hemicube and ray shooting) to describe surface-to-surface radiation. These algorithms are tested and validate to determine their accuracy in a simple and initial PVT model, which could be the basis for more complex models.
no embargo
Keywords: Siliziumkarbid; physikalischer Gasphasentransport; Finite Elemente Methode; Modellierung der Wärmeübertragung; strahlende Wärmeübertragung; silicon carbide; physical vapor transport; finite element method; heat transfer modelling; radiative heat transfer

NIKE-Med - Hofer, Peter; Kulcar, Vanessa; Eder, Julian; Fischer, Philipp; Wegscheider, Thomas; Roszipal, Benjamin; Egger-Lampl, Sebastian; Galler, Robert; Weitzer, Mario Franz; Camacho, Aurora; Wenighofer, Robert; Lindenthal, Michael; et al. (Nachhaltige Interdisziplinarität bei Komplexen Einsätzen unter Tage / MEDical Treatment, 2024)

Nanoindentation of polymers - Christöfl, Petra (2024)
Instrumented Nanoindentation (NI) has been a valuable tool to measure mechanical properties such as hardness and elastic modulus for various materials over the last 20 years. As a further development of hardness testing, it served as an appropriate method to determine mechanical properties, especially on thin films, on a small amount of sample or from special regions on a sample. NI of polymers have only been a marginal phenomenon over the last few years. The basic method in NI evaluation is the O&P method, which assumes elastic material relaxation after deformation. A polymer relaxes viscoelastic after deformation which makes the interpretation of NI data complex. In this work, the emphasis lies on the investigation of polymers by NI. The main goals of this cumulative work are:(I)Evaluation of the O&P analysis and creep method in combination with material modelling on an isotropic (amorphous) material and compare it to a common macroscopic test.(II)Expansion of the evaluation from (I) to a more complex semi-crystalline system to evaluate the influence of morphology on the NI results.(III)Bring results from (I) and (II) into application where the occurrence of polymeric aging are detected by NI.(IV)Introduce an innovative sample preparation method to investigate polymeric multilayers in cross-section.After a short introduction to NI of polymers a state-of-the-art section reviews literature ranging from the mechanical behaviour of polymers to NI methods and techniques. In the first publication NI was used to examine the viscoelastic properties of poly(methyl methacrylate) (PMMA) as an amorphous polymer model. An evaluation combining adhesive contact and empiric spring-dashpot models was applied to obtain the instantaneous elastic modulus E0 and the infinitely elastic modulus E∞ from NI creep curves. The value of E0 was compared to moduli obtained with atomic force microscopy-based NI (AFM-NI) and macroscopic compression tests. Furthermore, the elastic modulus was evaluated by the O&P method for the NI and AFM-NI results. Comparison of the elastic modulus E0 from the creep measurements of NI and AFM-NI to compression tests revealed good agreement of the results. However, only the O&P-based AFM-NI results yielded to lower values.In paper two the material selection was expanded from amorphous to semi-crystalline polymers, as the influence of morphological structures such as spherulites or crystal-lamellae on localized NI depth-force behaviour is discussed controversially in literature. The main objective of paper two was to determine the influence of crystalline zones of semi-crystalline POM (Polyoxymethylene) on NI results. A POM tensile bar was investigated by NI at various positions of the cross-section. Areas at the edge of the sample had a lower modulus than areas in the middle of the cross-section. This agreed with polarized light microscopy results showing a skin layer with less crystallinity close to the sample edge. Semi-crystallinity influenced the NI results obtained for POM. The mean of the modulus distribution over the POM cross-section was in good agreement with macroscopic compression test results.In paper three a fast and sensitive method to detect polymer aging at an early stage was developed by NI. For this purpose, a commercially available transparent and 50 micrometer thick polyethylene terephthalate (PET) film was aged under different artificial conditions. The evolution of mechanical properties with rising aging time was investigated via NI methods established in paper one and two and macroscopic tensile testing. Physical aging was monitored by the first heating of differential scanning calorimetry (DSC) and chemical aging was studied with gel permeation chromatography (GPC). NI data was compared to tensile test data with good agreement between the results on the nano- and macroscale. A correlation between GPC data and NI creep data indicated a primarily chemical aging of the present PET films. Paper three states that NI is an appropriate method to determine the degradation of PET at an early stage.In paper four NI on thin, polymeric multilayer film cross-sections were studied. Here NI violated assumptions of semi-infinite and homogeneous samples because NIs were always near free edges and heterophase interfaces. The structural compliance method was used to correct NI results for specimen-scale flexing and edge effects, where the effect of both edges and specimen-scale flexing is to introduce a structural compliance (Cs). The Cs showed a strong position dependence applied to a polymeric multilayer. The effect was larger near the edges and layer interfaces. The Cs correction had little effect on the hardness values; however, the influence on measured elastic modulus was significant. The corrected modulus values tended to be higher than the uncorrected ones in the stiff layers.
no embargo
Keywords: Nanoindentation; polymers; viscoelastic; indentation; nanoscale; Nanoindentation; Kunststoffe; Nano

Natural Hydrogen, Exploration at the Southeastern Edge of the Bohemian Massif - Weitz, Johannes (2024)
Natural hydrogen is an environmentally friendly energy carrier and source that can play a major role in the energy transition. It can be produced by various subsurface geological processes. These include degassing of primordial hydrogen, fluid-rock interactions (e.g. serpentinization) or radiolysis of water. Hydrogen from microbial production probably plays a minor role only. Biological processes are rather involved in the metabolization and thus oxidation of hydrogen in soil.The aim of this master´s thesis is to investigate the occurrence of natural hydrogen along the southeastern edge of the Bohemian Massif. The study area has been chosen, because it includes two favourable factors for the occurrence of natural hydrogen. Firstly, the Bohemian Massif is made up of the root zone of the Variscan orogen comprised of lithologies with considerable radioactive content. Secondly, the old but still tectonically active, Diendorf fault may provide pathways for fluid migration. Two areas were studied along the Diendorf fault. The Dunkelsteiner Wald area was studied more closely because this section of the Diendorf fault has the highest frequency of recorded earthquakes. The area of Maissau was selected, because of the prominent fault scarp of the Maissauer Berg due to the Diendorf fault.As part of the study, soil gas measurements were carried out at 763 measurement locations and were subjected to a statistical analysis. The hydrogen concentrations observed in the Dunkelsteiner Wald were higher overall than in Maissau. The statistical analysis was carried out using a Quantile-Quantile (Q-Q) plot to differentiate the nature of the hydrogen concentration signal in the soil. It is possible to distinguish a background signal (H2 ≤ 9 ppm) and a geological signal (H2 > 48 ppm). The transitional interval (10 - 48 ppm H2) in the Q-Q plot is interpreted as a natural influx that is exceeding the hydrogen uptake capacity of the soil. The result of the statistical analysis is then illustrated with spatial referencing.In the Dunkelsteiner Wald, the background signal is observed directly in the fault zone, while increased (“geologic”) signal values occur in the vicinity of the fault zone. This is probably related to mylonitization in the core of the fault zone, which reduces permeabilities. In contrast, the brittle deformation of the adjacent crystalline rock resulted in the opening of fractures and the creation of pathways. In the Maissau area, this effect is observed in a similar way, but is less pronounced due to the lower overall hydrogen concentrations in the soil.It was possible to exclude exogenous addition of carbon dioxide, as oxygen and carbon dioxide concentrations indicate biological respiration. As a conclusion, the work conducted in this thesis is not of sufficient extent to derive information about the actual origin of the hydrogen observed by the soil gas measurements, but highlights that natural hydrogen exists along the Diendorf fault and probably migrates to the surface along the zone of brittle deformation.
embargoed until 13-02-2029
Keywords: Natural Hydrogen; Primordial Hydrogen; Fluid-Rock Interactions; Radiolysis; Hydrogen Exploration; Bohemian Massif; Diendorf Fault; Dunkelsteiner Wald; Maissau; Surface Geochemistry; Soil Gas Measurements; Soil Gas concentration; Geostatistics; Geophysics; Electromagnetic Resistivity Measurements; Gamma Spectroscopy; Natürlicher Wasserstoff; Primordialer Wasserstoff; Fluid-Gesteins-Reaktionen; Radiolyse; Wasserstoffexploration; Böhmische Masse; Diendorf Störung; Dunkelsteiner Wald; Maissau; Oberflächengeochemie; Bodengasmessungen; Bodengaskonzentrationen; Geostatistik; Geophysik; Elektromagnetische Widersatndsmessungen; Gammaspektroskopie

NbC-Ausscheidungen in einem PH 15-5 Stahl - Kaufmann, Martina (2024)
Die Qualitätssicherung und Kontrolle der verarbeiteten Materialien spielen besonders in der Luftfahrt eine große Rolle. Eines dieser Materialien ist der ausscheidungshärtende Edelstahl PH 15-5. Dieser weist eine gute Kombination aus Festigkeit und Bruchzähigkeit neben guten Korrosionseigenschaften auf und ist auch aufgrund seiner Verfügbarkeit ein wichtiges Material in verschiedensten Branchen. Die guten mechanischen Eigenschaften kommen aus für metallische Werkstoffe typischer Kombination aus mehreren Verfestigungsmechanismen. Diese sind unter anderen die Kornfeinungsverfestigung, die martensitische Umwandlung und die Ausscheidungsverfestigung. Bei der letzteren bewirken vor allem Cu-Ausscheidungen in der Matrix eine Erhöhung der Festigkeit. Zudem befinden sich in der Matrix ebenso Primär- als auch Sekundärkarbide. Dabei sollten diese Karbide innerhalb des Vormaterials möglichst homogen verteilt sein. In diesem speziellen Fall des PH 15-5 handelt es sich um Niobkarbide (NbC), welche in der martensitischen Matrix verteilt sind. Die Größe dieser hängt vom Herstellungsprozesses des Vormaterials und dessen Weiterverarbeitung (z.B. Schmieden) ab. So unterscheiden sich die Dimension und Anzahl der NbC abhängig von dem Lieferanten und dem Durchmesser des Vormaterials. Standardmäßig werden diese Karbide mittels REM-Untersuchung detektiert und ausgemessen. Ziel dieser Arbeit ist einen Zusammenhang zwischen NbC, Vormaterialdurchmesser und Lieferant zu finden sowie eine Abhängigkeit von der Querschnittsposition zu untersuchen. Im Zuge dessen soll auch ermittelt werden, ob die NbC-Verteilung mittels Lichtmikroskop (LIMI) gemessen werden kann, um damit die Kosten der Untersuchungen zu minimieren, indem die REM-Messungen eingespart werden könnten. Untersucht wurden insgesamt sieben Proben mit insgesamt vier unterschiedlichen Vormaterialdurchmessern von zwei Lieferanten. Die Untersuchungen fanden mittels LIMI und REM an drei Positionen im runden Vormaterial statt. Diese waren das Zentrum, der halbe Radius und der Rand. Das Vormaterial mit den meisten Karbiden, den wenigsten Karbiden und der am häufigsten verwendete Durchmesser bei voestalpine Böhler Aerospace GmbH & Co KG wurden ebenso für Umformversuche am Dilatometer herangezogen, um den Einfluss der Umformung bei schmiedenahen Temperaturen zu untersuchen. Im Zuge der Masterarbeit konnten herstellerabhängige Ergebnisse als auch eine Positionsabhängigkeit der NbC-Verteilung innerhalb von Vormaterialstangen festgestellt werden. Darüber hinaus zeigten sich deutliche Unterschiede zwischen den LIMI- und REM-Ergebnissen an denselben Proben.
gesperrt bis 06-02-2029
Keywords: NbC; Ausscheidungen; PH 15-5; Vormaterialcharakterisierung; Verteilung; NbC; Precipitates; PH 15-5; Pre-material characterisation; Distribution

Normal and Shear Compliance Estimation for Inclined Fractures Using Full-Waveform Sonic Log Data - Zhou, Zhenya; Caspari, Eva; Barbosa, Nicolas Daniel; Hollinger, Klaus (IEEE transactions on Geoscience and Remote Sensing, 2024)
In this work, we propose a phase delay approach to estimate the normal and shear fracture compliances utilizing refracted P- and S-waves from full-waveform sonic (FWS) log data generated by a monopole transmitter in a fluid-filled borehole. We derive analytical plane-wave expressions of fracture-induced P- and S-wave phase time delays for inclined compliant fractures, based on which an inversion scheme to infer fracture compliances is built. A parametric test demonstrates that, for realistic fracture compliance values from ${10}^{-14}$ to ${10}^{-11}$ m/Pa, the proposed method is capable of inferring accurate normal and shear compliance estimates for individual fractures with inclinations up to ${\sim }89^{° }$. The applicability of the plane-wave technique to refracted waves in FWS experiments is validated by performing numerical wave propagation simulations for a fluid-filled borehole in a hard-rock environment embedding an inclined fracture. Finally, we apply the method to FWS data acquired in the Bedretto Underground Laboratory for Geosciences and Geoenergies (BULGG) in Switzerland along a borehole intersected by a fracture inclined at 71° in a granitic formation. The inferred normal and shear compliances are $(4.20± 0.93) {}× {}{10}^{-13}$ and $(2.96± 1.42) {}× {}{10}^{-13}$ m/Pa, respectively. These values are realistic given the effective fracture scale sensed by refracted sonic waves and consistent with previously reported results for normal compliance of the same fracture. Both the numerical and field experiments show that the accuracy of shear compliance estimates is much more susceptible to fracture inclination than that of normal compliance, thus, underlining the necessity of taking fracture inclination into account for reliable shear compliance estimates.
Publisher Copyright: © 1980-2012 IEEE.
Keywords: Compliance ratio , full-waveform sonic (FWS) log data , inclined fractures , normal and shear compliance; Compliance ratio; full-waveform sonic (FWS) log data; inclined fractures; normal and shear compliance

Numerical and Stochastic Interpretation of CO2-Brine Primary Displacement - Amrollahinasab Mahdiabad, Omidreza (2024)
The burning of fossil fuels leads to an increasing concentration of carbon dioxide (CO2) in the atmosphere and consequently to global climate change. Despite the shift towards renewable energy, the dominant role of fossil fuels in global energy consumption necessitates solutions like Carbon Capture and Storage (CCS). CCS involves capturing CO2 from large emission sources and storing it deep underground, where CO2 displaces native fluids, such as brine. The efficiency of this displacement process is influenced by various geological and physical factors. Understanding and optimizing these factors is crucial. This work provides a comprehensive investigation of CO2 brine displacement in porous rock, using both experimental and numerical methods. The experimental data are analyzed more rigorously than in previous studies, leading to a robust stochastic description of the two-phase flow in heterogeneous porous media. Additionally, numerical experiments were conducted to investigate the displacement stability, providing a new and unexpected scaling for viscous instabilities. Thus, this work provides a comprehensive and solid basis for risk analysis of CO2 plume migration in CCS processes. The migration of the CO2 plume and the efficiency of CO2 displacement are primarily determined by multiphase flow parameters, namely relative permeability, and capillary pressure saturation functions, which are usually derived experimentally. In the frame of this work, the underlying numerical data analysis was developed based on the solid foundation of a combined stochastic interpretation of complementary experimental data sets. In the developed approach, data from different experimental methods (Special Core Analysis - SCAL) are analyzed simultaneously, and their uncertainty is rigorously determined by state-of-the-art stochastic methods. The resulting uncertainty intervals of the saturation functions refer to the intrinsic uncertainty of SCAL experiments, however, not to variations in rock properties. By interpreting and combining experiments derived from various methods and on various samples, the analyses provide a certain access to the heterogeneity of the rock formation. To underscore the impact of rock heterogeneity on CO2 migration, the approach was lifted to a larger length scale at which rock heterogeneity cannot be ignored anymore. Traditional SCAL methodologies typically do not account for heterogeneity, leading to discrepancies in measurements and field observations in terms of multiphase-flow saturation functions. Heterogeneity is vital for understanding the dynamics of plume migration and is explored in depth in this thesis. The thesis introduces an upscaling workflow that combines SCAL interpretations with continuum-scale experiments, emphasizing the need for rigorous upscaling procedures for CO2 storage in heterogeneous formations, such as carbonates.Plume migration in heterogeneous formations is particularly affected when the mobility of the displacing fluid is higher than that of the displaced fluid. In this situation, viscous instabilities are to be expected, which can enhance fluid bypassing (sweep efficiency) in heterogeneous rock, depending on the characteristic length scale of the perturbation versus the finger width of the unstable front. This research challenges and extends existing theories on viscous fingering and its relation to interfacial tension and formation permeability. It further elucidates the findings from Darcy-scale numerical simulations that reveal finger wavelengths ranging from tens to a hundred meters under. Such a scale contrasts sharply with traditional predictions based on the Saffman & Taylor model, which significantly underpredicts the wavelengths. This insight is crucial for accurately predicting plume migration in CCS projects, as it accounts for the substantial deviation from expected behavior based on conventional models. The findings offer a novel perspective on the complexities of viscous-unstable displacement, challenging existing theories and providing a more accurate framework for understanding and predicting CO2 plume migration in CCS scenarios.This thesis substantially advances our understanding of CO2 plume migration, addressing critical aspects of CO2-brine displacement, uncertainties in ideal homogeneous and stabilized systems, and the effects of laboratory-scale heterogeneity and viscous instability. By rigorously investigating the scaling of finger wavelengths and their implications, this work reveals the significant impact of viscous-unstable displacement on plume migration, reshaping our approach to CCS modeling and implementation. The research's holistic examination, spanning from traditional measurements to advanced numerical methodologies, elevates the field's understanding of geological CO2 storage, paving the way for more informed and effective carbon sequestration strategies and the associated risk assessment.
embargoed until 15-02-2025
Keywords: Kohlendioxid (CO2); globaler Klimawandel; erneuerbare Energien; Carbon Capture and Storage (CCS); Emissionsquellen; unterirdische Speicherung; CO2-Wasser-Verdrängung; poröses Gestein; experimentelle Methoden; numerische Methoden; Zweiphasenströmung; heterogene poröse Medien; viskose Instabilitäten; CO2-Migration; Risikoanalyse; Mehrphasenströmungsparameter; relative Fluidphasen Permeabilität; Kapillardruck-Sättigungsfunktionen; Spezialkernanalyse (SCAL); stochastische Methoden; Gesteinsheterogenität; Upscaling-Workflow; großskalige Experimente; Karbonatformationen; viskoses Fingering; Sweep-Effizienz; Saffman & Taylor-Modell; Darcy-Skala Simulationen; CO2-Sole-Verdrängung; Labormaßstab-Heterogenität; viskose Instabilität; CCS-Modellierung; Kohlenstoffabscheidungsstrategien; geologische CO2-Speicherung.; carbon dioxide; global climate change; renewable energy; Carbon Capture and Storage (CCS); CO2 emission sources; underground storage; CO2 brine displacement; porous rock; experimental methods; numerical methods; two-phase flow; heterogeneous porous media; viscous instabilities; CO2 plume migration; risk analysis; multiphase flow parameters; relative permeability; capillary pressure saturation functions; Special Core Analysis (SCAL); stochastic methods; rock heterogeneity; upscaling workflow; continuum-scale experiments; carbonate formations; viscous fingering; sweep efficiency; Saffman & Taylor model; Darcy-scale simulations; CO2-brine displacement; laboratory-scale heterogeneity; viscous instability; CCS modeling; carbon sequestration strategies; geological CO2 storage.

Oberflächenmodifikationen in geschmierten Kontakten - ein Multiskalenansatz zur Verschleiß- und Reibungsbewertung - Maier, Michael (2024)
Ohne geschmierte Kontakte würden zahlreiche Maschinen aus dem täglichen Gebrauch nicht in gewünschter Art und Weise funktionieren. In Zeiten des globalen Klimawandels stellt die Effizienzsteigerung geschmierter Kontakte eine besondere Herausforderung dar. Einerseits besteht durch gezielte Maßnahmen, beispielsweise in Form von interimisitischen Stopps, oder niederviskosen Schmiermittel, die Möglichkeit der Effizienzsteigerung. Aufgrund der Systemeigenschaften des Kontaktes führt dies unter Umständen zu ungünstigen Betriebsbedingungen, welche in einem Betriebszustand im Mischreibungsbereich und in weiterer Folge in Verschleiß resultieren. Andererseits können durch gezielte Oberflächentexturierungen Reibungsverluste reduziert werden. Für die ganzheitliche Auslegung eines geschmierten Kontaktes sind dazu entsprechende Modelle erforderlich. Für physikalische Prozesse in geschmierten Kontakten, sind unterschiedlichen Größenskalen relevant. Um diese in einem Simulationsmodell zu beschreiben, sind mehrere Submethodiken obligatorisch. Die Charakterisierung der Oberflächentopografie erfolgt dabei in Mikromodellen. Die Mikrohydrodynamik und der Festkörperkontaktdruck sind die maßgeblichen Kennwerte aus dem Mikromodell, für welche entsprechende Simulationsmodelle erstellt wurden. Der Übergang der Oberflächentopografie vom Initialzustand zum eingelaufenen Zustand wurde mittels Simulationsmodelle der verschleißenden Oberfläche analysiert. Für die makroskopische Verschleißsimulation, am Beispiel eines hydrodynamischen Gleitlagers, wurde ein lokaler Ansatz herangezogen, wobei die verschleißabhängige Oberflächentopografie in Form eines variablen Mikromodells implementiert wurde. Parameter für die Quantifizierung des Verschleißes wurden dabei auf einem entkoppelten System ermittelt. Die Effekte von Oberflächentexturierungen auf die Hydrodynamik wurde mit Simulationsmodellen, basierend auf unterschiedlichen Gleichungssets erhoben. Die Validierung erfolgt auf einem neuartigen Prüfstand mit Pin on Disc Konfiguration zur Untersuchung von texturierten Schmierkeilen. Durch die Kombination der einzelnen Submethoden wird die Verschleißsimulation in texturierten Kontakten unter Berücksichtigung verschleißabhängiger Oberflächentopografien ermöglicht. Die Validierung der Verschleißsimulationen mit Experimenten zeigt die Signifikanz der verschleißabhängigen Oberflächentopografie auf die Verschleißentwicklung. Das Potenzial von künstlichen Oberflächentexturierungen zur Reibungsreduzierung konnte sowohl mit der Simulationsmethodik, als auch mit dem neuartigen Prüfstand aufgezeigt werden. Neben einem Auslegungswerkzeug ermöglicht die vorgestellte Methodik den Aufbau eines tieferen Verständnisses über die Verschleißprozesse und Wirkungsweise von Texturierungen in geschmierten Kontakten.
nicht gesperrt
Keywords: Contactsimulation; Wear; Surface textures; Finite Elements; Multiscalesimulation; Tribokontaktsimulation; Verschleiß; Texturierungen; Finite Elemente; Multiskalensimulation

Optimierung der Auswahl erneuerbarer Energiespeichertechnologien - Raschl, David (2024)
Ziel dieser Masterarbeit ist es die Auswahl der unterschiedlichen erneuerbaren Energiespeichertechnologien, unter Berücksichtigung von technischen Aspekten sowie wirtschaftlichen Gesichtspunkten zu analysieren und auf Basis der Modellierungsergebnisse zu optimieren. Die Arbeit und das dafür entwickelte Modell sollen eine quantitative Einschätzung ermöglichen, welche Speichertechnologie sich für welche Anwendungsfälle eignet und welche Kosten dadurch entstehen. Dadurch soll eine optimierte Auswahl, bezogen auf unterschiedliche Szenarien ermöglicht werden. Um dieses Modell entwickeln zu können, bedarf es einer umfassenden Literaturrecherche über verschiedene Energiespeichertechnologien. Der erste Teil dieser Arbeit beinhaltet diese Literaturrecherche. Darauf aufbauend erfolgt im zweiten Teil die Beschreibung des erstellten Modells und der im Modell verwendeten Regelung. Im abschließenden dritten Teil wird das erstellte Modell für verschiedene Anwendungsfälle angewendet und auf Basis der modellierten Ergebnisse optimiert. Ziel ist es eine optimale Speichertechnologie oder eine Kombination verschiedener Speichertechnologien, für die untersuchten Anwendungsfälle zu eruieren. Dafür ist es erforderlich alle notwendigen Parameter aus veröffentlichten Berichten oder Datenblätter zu ermitteln und übersichtlich aufzubereiten. Durch diese Ausarbeitung der unterschiedlichen Leistungsparameter konnte das Modell mit aktuellen und teils bereits in Versuchen erprobten Werten gefüttert werden. Somit kann eine reale, auf Basis aktueller Daten fundierte Berechnung erfolgen, aus welcher aussagekräftige Schlussfolgerungen getroffen werden können. Diese gewonnenen Informationen dienen dazu, erste Einschätzungen über die optimale Energiespeicherstruktur treffen zu können und dabei sowohl die technische Machbarkeit zu berücksichtigen als auch die dadurch entstehenden Kosten aufzuzeigen. Die Berechnungen erfolgen mit Hilfe des erstellten Modells, für die zu Beginn selektierten Energiespeichertechnologien. Damit sollen ideale Systemarchitekturen in Bezug auf Effizienz, Autarkie und Kosten identifiziert werden. Abschließend wurden anhand beispielhafter Anwendungsfälle Modellierungen durchgeführt und auf Basis verschiedener Parameter analysiert. Durch die Diskussion vorhandener Limitierungen, die aus den Modellierungen hervorgehen, werden weitere Möglichkeiten zur Adaptierung des Modells aufgezählt. Dadurch soll bereits der Grundstein für die weiterführende Arbeit am Modell gelegt sein.
gesperrt bis 20-02-2029
Keywords: Renewable energy storage; modelling; optimized system architectures; generation profiles; demand profiles; self-sufficiency; efficiency; costs; Lithium-ion-batteries; Vanadium-redox-flow-batteries; electrolyzer technologies; hydrogen storage; Erneuerbare Energiespeicher; Modellierung; Optimierung der Systemarchitekturen; Erzeugungsprofile; Verbraucherprofile; Autarkie; Effizienzen; Kosten; Lithium-Ionen-Batterien; Vanadium-Redox-Flow-Batterien; Elektrolysetechnologien; Wasserstoffspeicher

Optimierung der Eisen/Phosphor - Trennung von LD-Schlacke durch selektive Drucklaugung mit CO2 - Mayer, Josef (2024)
In den österreichischen Stahlwerken der voestalpine fallen jährlich rund 650.000 t LD-Schlacke bei der Stahlerzeugung an. Die Dissertation Moaveni (Lehrstuhl für Aufbereitung und Veredlung, Montanuniversität Leoben, 2019) zeigte, dass der Hauptgehalt an Phosphor, der zu Störungen im Stahlprozess führt, in einer C2S-Phase (2CaO*SiO2) konzentriert ist. In CO2-Atmosphäre (48h/16bar) kann ein Aufschluss erreicht werden. In der anschließenden Magnetscheidung wurde ein Eisenausbringen von 75 % im Magnetprodukt bei einer Halbierung des P2O5-Gehalts auf 0,54 % erreicht. Um bessere Ergebnisse zu erzielen, wurde von A. Böhm in Zusammenarbeit mit Cemtec eine Hochdruck-Rührwerkskugelmühle (HD-RWKM) entwickelt, in der Druckniveaus von bis zu 50 bar möglich sind. Sie ermöglicht die Kombination der Reaktion von C2S und CO2 und einer mechanischen (Oberflächen ) Reibung, mit dem Ziel die Trennwirkung zu verbessern. Die Hochdruckmühle wurde im Rahmen der Arbeit in Betrieb genommen und ein Sicherheitskonzept entwickelt. Die Untersuchungen zeigten, dass eine höhere CO2-Aufnahme, die laut Moaveni als Indikator für den Aufschlusserfolg steht, bei kürzeren Versuchszeiten (1h/40bar bzw. 2h/30bar) möglich ist. Auch die Notwendigkeit von ständig freien Oberflächen und eine höhere CO2-Sequestrierung in den Feinfraktionen wurden beobachten. Trotz Begasungserfolg war in der Magnetscheidung ein Eisenausbringen von ca. 75 ¿ 80 % mit einem Phosphorausbringen von rund 60 ¿ 70 % ins Magnetprodukt verbunden. Die Datenanalyse der bisherigen Versuche zeigte, dass bei der gewählten Einstellung von 80 U/min in der HD-RWKM, noch keine Mahlwirkung zu beobachten ist.
gesperrt bis 06-02-2029
Keywords: iron; phosphorus; separation; pressure-leaching; LD-slag; CO2-sequestration; C2S-phase; high-pressure-stirred-mill; Eisen; Phosphor; Trennung; Drucklaugung; LD-Schlacke; CO2-Sequestrierung; C2S-Phase; Hochdruck-Rührwerkskugelmühle

Optimierung der Warenwirtschaft mit Hilfe eines vollautomatisierten Ausgabesystems für Verbrauchsmaterial in der Elektroindustrie - Roth, Ulrike Elisabeth (2024)
Die steigenden Herausforderungen in der Bewirtschaftung von Hilfs- und Betriebsstoffen, getrieben durch den Druck zur Optimierung der Wertschöpfungsketten, erfordern von Industrieunternehmen eine verstärkte Aufmerksamkeit für dieses Thema. Hilfs- und Betriebsstoffe beeinflussen die Produktion in verschiedenen Aspekten, wie zum Beispiel Auswahl und Qualität der Hilfs- und Betriebsstoffe, sowie hinsichtlich Arbeitssicherheit und Umweltauswirkungen. Hilfs- und Betriebsstoffe sind daher von entscheidender Bedeutung für die Effizienz der Prozesse, die Wirtschaftlichkeit und der ökologische Fußabdruck des Unternehmens sowie die Qualität und Durchführbarkeit der Produktionsabläufe. Das erste Kapitel widmet sich den theoretischen Grundlagen der Materialwirtschaft. Hierzu gehören verschiedene Bedarfsarten, insbesondere die genaue Definition von Hilfs- und Betriebsstoffen. Die Beschaffungslogistik und die Materialdisposition werden ebenso behandelt, einschließlich der Bedeutung von Stücklisten und Dispositionsverfahren. Im Bereich der Lagerhaltung werden speziell Lager für Hilfs- und Betriebsstoffe betrachtet, wobei auch Aspekte wie Mindesthaltbarkeit, Kühlung und die Handhabung von Gefahrenstoffen diskutiert werden. Die Arbeit verdeutlicht die Schwierigkeiten bei der Aufrechterhaltung einer reibungslosen Materialversorgung in einem Unternehmen. Es ist umso wichtiger ein geeignetes Bewirtschaftungsmodell für Hilfs- und Betriebsstoffe zu finden. Im praktischen Teil der Arbeit wird in Zusammenarbeit mit der Firma Siemens Mobility GmbH nach Anbietern gesucht, die automatisierte Lösungen für die Warenbewirtschaftung von Hilfs- und Betriebsstoffen anbieten. Die Analyse und Auswahl der Ausgabemethoden für Hilfs- und Betriebsstoffe für die Firma Siemens Mobility GmbH werden präsentiert. Abschließend wird nach der Implementierung eine Umfrage zur Mitarbeiterzufriedenheit durchgeführt und die daraus gewonnenen Ergebnisse werden vorgestellt. Die Ergebnisse der Arbeit liefern konkrete Handlungsempfehlungen für die Firma Siemens Mobility GmbH, um die Warenbewirtschaftung und das Handling gemeinsam mit den Mitarbeitern und dem Dienstleister kontinuierlich zu verbessern.
gesperrt bis 16-02-2029
Keywords: Auxiliary and operating materials; Auxiliary materials; Operating materials; Inventory management; Automatic dispensers; Electrical industry; Consumables; Automated system; Parts lists; Hilfs- und Betriebsstoffe; Hilfsstoffe; Betriebsstoffe; Lagerbewirtschaftung; Ausgabeautomaten; Elektroindustrie; Verbrauchsmaterial; automatisiertes System; Stücklisten

Optimization of Reaction Parameters for Hydrogen Reduction of Electric Arc Furnace Dust - Keuschnig, Aaron (2024)
The recycling of galvanized scrap generates a zinc-containing dust fraction, usually called Electric Arc Furnance Dust EAFD, which is currently mainly treated in the carbon-based Waelz process. While the process is efficient in terms of zinc-recovery and process economy, it produces a secondary zinc concentrate with a large carbon footprint and underutilizes other valuable elements that are present in the EAFD. Climate change mitigation efforts require the substitution of carbon-based processes with carbon-neutral alternatives, such as hydrogen. To achieve this objective, it is important to have a fundamental understanding of the reaction kinetics of the reduction reactions with hydrogen. The present work investigates the influence of the temperature and H2O/H2 ratio on the reaction kinetics during the EAFD reduction. Experiments were conducted in a Thermogravimetric Analyzer TGA that was coupled with a Mass Spectrometer MS. The second objective was to develop an algorithm, that allows to distinguish between the reduction of zinc-oxide and iron-oxide by coupling the TGA and MS datasets. Experimental data demonstrated a full recovery of zinc (¿ 99 %) within a 60-minute hydrogen reduction period. The remaining solid material, which can be described as secondary-grade direct reduced iron (DRI), exhibited a high degree of metallization and a high iron concentration (¿ 70 %). Up to 1.150 °C, the reaction kinetics increased with the temperature. Above this point, the reactivity of the material decreased rapidly. During the reduction, the material shrinkage increased within reaction temperatures of 900-1.050 °C, but stagnated above that temperature. Interestingly, the H2O/H2 ratio of the atmosphere influenced the shrinkage behavior. A higher H2O concentration in the gas led to a higher material shrinkage. In contrast, the reaction kinetics decreased with higher H2O concentrations. The influence of the process parameters on the reaction kinetics of the EAFD could be identified. Additionally, the experimental setup was optimized to facilitate further investigations of the reaction kinetics.
no embargo
Keywords: Reaction Kinetics; Electric Arc Furnace Dust; Decarbonization; Hydrogen Reduction; Zinc Recovery; Reaktionskinetik; Stahlwerksstaub; Zinkrückgewinnung; Wasserstoffreduktion; Dekarbonisierung

Optimization of heat transfer model used in the continuous casting of stainless steel - Wahib, Muhammad (2024)
The continuous casting process is a crucial step-in stainless-steel production that involves the solidification of molten steel into continuous slabs or blooms. This casting process involves transferring of molten steel from a tundish to a water-cooled mold, where solidification starts. As the solidifying strand exits the mold, it is supported by rotating rollers in the secondary cooling zone. Water and air mist is continuously sprayed to achieve complete solidification. After complete solidification, the slabs are cut and sent for further processing. The efficient control of heat transfer is crucial to optimize the casting process, preventing casting defects and enhancing production efficiency. A key challenge in continuous casting is preventing breakout of the liquid metal, which occurs when the solid shell is too thin, leading to rupture and spilling of liquid metal. The shell thickness depends on the heat transfer behaviour during solidification. This thesis is performed in collaboration with the stainless-steel company Aperam and focuses on optimizing the heat transfer model used in continuous casting of stainless steel. The heat transfer model is influenced by the thermodynamic properties of steel including heat capacities, solidification enthalpy, and heat transfer coefficients. The primary objective is to provide Aperam with accurate thermodynamic inputs for steel grade 304L and 316L, enabling a thorough understanding of the model¿s dependence on these values. For this Thermo-Calc and IDS databases are used to collect different thermophysical parameters. Additionally, a CFD heat transfer and solidification model is developed considering the Aperam continuous casting plant conditions, and respective heat transfer coefficients (HTCs) are calculated for the mold and the secondary cooling region. These inputs are used to predict the temperature and solidification profiles at different sets of casting speeds and superheat values for both steel grades in the DYNACS and CFD model. Further these models¿ temperature results are compared with the real temperature data acquired from a pyrometer at the continuous caster. The findings of this study highlighted the importance of accurate thermophysical parameters and heat transfer conditions. Further, the parametric study investigated the role of individual thermophysical parameters on the temperature and solidification profiles and helped to predict the behaviour of steel grades under varying process conditions such as casting speeds and superheat values. This study provides Aperam a valuable insight into the relationship between the thermophysical parameters and solidification profiles. This knowledge will enable the company to optimize the process conditions, such as casting speed, maximizing the production efficiency, and minimizing the risk of breakout defects.
no embargo
Keywords: continuous casting; stainless steel; heat transfer; solidification; breakout; thermodynamic properties; CFD modeling; casting speed; superheat; pyrometer; thermo-calc; IDS; production efficiency; Stranggussverfahren; Edelstahl; Wärmeübertragung; Erstarrung; Ausbruch; Thermodynamische Eigenschaften; Thermo-Calc und IDS-Datenbanken; CFD-Modellierung; Gießgeschwindigkeit und Überhitzung; DYNACS; Pyrometer; Produktionseffizienz

Optimizing Performance of High-Temerature Aquifer Thermal Energy Storage in the Vienna Basin - A Design of Experiments Approach - Werkl, Philipp (2024)
This thesis is about the design and optimization of a High-Temperature Aquifer Thermal Energy Storage (HT-ATES) system in the Vienna Basin, with a focus on the aquifer component. There are numerous parameters that influence the thermal recovery efficiency (R) of ATES, one main characteristic for the successful implementation of this kind of underground thermal energy storage (UTES). Therefore, the objective of this thesis is to determine the most influencing parameters and find the optimal combination of these to maximize the efficiency. To investigate the impact, assumptions are made on parameters and their respective range in agreement with a local geologist and numerical simulations are conducted to evaluate their influence on the performance of the aquifer. Ultimately, a design of experiments (DoE) approach is used to obtain a thorough analysis of the results. By analyzing the simulations, statements about the pressure and temperature distribution within an aquifer are made and the combination of parameters within the specified range that yield the highest performance are determined.
no embargo
Keywords: ATES; HT-ATES; UTES; DoE; Thermal recovery efficiency; ATES; HT-ATES; UTES; DoE; Thermal recovery efficiency

PLASMA MODIFICATION OF POLYACRYLONITRILE POWDER OR SOLUTION PRIOR ELECTROSPINNING - Pijáková, Barbora; Elbataioui, Adam; Rafailovic, Lidija; Bautista, Angus Daniel; Schlögl, Sandra; Dvořáková, Eva; Mühlbacher, Inge; Ráheľ, Jozef (15th International Conference on Nanomaterials - Research and Application, NANOCON 2023, 2024)
Publisher Copyright: © 2024 NANOCON Conference Proceedings - International Conference on Nanomaterials. All rights reserved.
Keywords: DCSBD; electrospinning; PAN nanofiber; Plasma modification; polyacrylonitrile

Parametrization of a numerical model for rolling contact calculations - Otipka, Dominik (2024)
Cyclic contact between wheel and rail is a critical factor impacting the maintenance and service life of railway components. One key concern is ratcheting, a cyclic plastic deformation occurring under alternating loads. Additionally, changes in wheel and rail geometry influencing the contact surface further affect performance and durability, contributing to potential rail failures. To comprehensively investigate these relationships, Meyer developed a cyclic finite element model plugin [1]. The scope of this thesis is to extend the functionality of the existing plugin to provide a more detailed description of the plastic behavior of materials in cyclic rolling contact phenomena. Specifically, an investigation by using this extended plugin whether ratcheting or plastic shakedown occurs in materials subjected to multiple rolling cycles and various initial conditions takes place. To enable faster calculations, the wheel-rail geometry is simplified to cylindrical forms to create an elliptical contact patch based on Hertzian theory. A major optimization of the extended plugin includes evaluating only a specific selection of rollovers, thereby reducing simulation time. Furthermore, the model structure of the rail is simplified compared to the standard plugin by eliminating the need for sketch insertion, ensuring further optimization and easier creation of a parameter study. Thus, an extended plugin with automated creation of a wheel-rail model is developed, featuring an automated evaluation of contact parameters as well as stresses and strains in the rail. Using the optimized and extended plugin, a parameter study with different variants is conducted and carefully evaluated. The results of this parameter study are summarized in a comprehensive table that serves as a basic reference for future simulations with complex geometries and numerous real-world influences related to contact phenomena.
no embargo
Keywords: FEM Simulation; Cyclic wheel-rail rolling contact; Ratcheting; Elastic-plastic material; Rolling contact fatigue; FEM Simulation; Zyklischer Rad-Schiene Rollkontakt; Ratcheting; Elastisches-Plastisches Material; Ermüdung durch Rollkontakt

Pathways Towards the Functionalization of Three-Dimensional Substrates - Knabl, Florian (2024)
Materials science has always been on the forefront of human progress, with a current focus on developing functional materials. These materials are designed to perform sophisticated tasks beyond mere structural applications. This necessitates advanced synthesis strategies that synergistically combine the properties of various constituent phases into high-performance nanocomposite material systems. This thesis explores three distinct physical surface modification methods to develop advanced material systems: dielectric barrier discharge plasma treatment on a mixture of few-layer graphene and cobalt powder, conventional magnetron sputtering on nanoporous carbon cloth, and magnetron sputter inert gas condensation for nanoparticle deposition on silicon substrates. The first method produces a cobalt-graphene nanocomposite with enhanced electrochemical performance, with potential scalability to three-dimensional substrates when employing an additional binder phase. The second method creates a nanocomposite of activated carbon cloth with palladium islands, showcasing successful functionalization of flexible three-dimensional substrates with potential applications as energy materials and sensing. The third approach enhances process control and deposition rates for nanoparticle depositions via magnetron sputter inert gas condensation. Initially, quadrupole mass spectrometry is employed for in situ measurements to advance process control. Subsequently, applying a substrate bias voltage significantly increases the output of nanoparticles from the source, thus incrementally improving this method for future research and applications. To summarize, this thesis presents significant advancements in three physical surface modification methods, highlighting their respective capabilities in functionalizing surfaces and showing pathways towards the functionalization of three-dimensional substrates, marking an important step forward towards the industrial application of advanced high-performance nanocomposite materials.
no embargo
Keywords: Dünnschichten; Magnetronsputtern; Nanopartikel-Herstellung; Funktionswerkstoffe; Kohlenstoff; thin film; magnetron sputtering; nanoparticle synthesis; functional materials; carbon

Photogrammetrische Aufnahme und 3D-Punktewolken-Prozessierung einer Ortsbrust im maschinellen Tunnelvortrieb und deren Vergleich mit einem Laserscan - Schachner, Simone (2024)
In dieser Arbeit wurde die mit bildverarbeitender Software durchgeführte Bildverknüpfung von photogrammetrisch erfassten ringförmigen Teilabschnitten, den sogenannten Aufnahmespuren einer Ortsbrust im kontinuierlichen Tunnelvortrieb, untersucht. Zur Qualitätskontrolle wurde neben der inneren Genauigkeit besonderes Augenmerk auf die äußere Genauigkeit der rekonstruierten Ortsbrust gelegt. Der Bildverband wurde im nördlichen Zugangsstollen der zweiten Röhre des Gotthard-Straßentunnels mit dem Kamerasystem der Montanuniversität und der Firma Geodata MT GmbH photogrammetrisch aufgenommen. Das Kamerasystem wurde im Rahmen einer Forschungszusammenarbeit entwickelt und dient dem digitalen Ortsbrustmonitoring im maschinellen Tunnelvortrieb. Die Ergebnisse der vorliegenden Arbeit zeigen, dass durch sorgfältige Einstellung der Aufnahmeparameter qualitativ hochwertige Aufnahmen erzielt wurden, die den Bildverarbeitungsprozess und die Bildverknüpfung nicht beeinträchtigten. Jedoch gestaltete sich die Realisierung einer ausreichenden seitlichen Bildüberlappung aufgrund der festen Kameramontagepositionen, die von der spezifischen Schneid-Diskenanordnung am Bohrkopf abhängig waren, als problematisch. Demzufolge konnten während dem Bildverarbeitungsprozess keine Bildverknüpfungen zwischen den Aufnahmespuren hergestellt werden. Aufgrund dessen resultierten aus der Simultankalibrierung Orientierungsparameter auf Basis eines unvollständig verknüpften Bildverbandes, die zu voneinander unabhängigen Aufnahmespuren mit hoher innerer Genauigkeit führten. Durch Distanzermittlung zu einem Laserscan wurde eine unzureichende äußere Genauigkeit der photogrammetrisch prozessierten Rekonstruktion der Ortsbrust festgestellt. Die Ergebnisse der Evaluierung der äußeren Genauigkeit verdeutlichen, dass die Korrektur der Kameraausrichtung nicht optimal möglich war, wodurch diese zwar mit einer hohen inneren Genauigkeit rekonstruiert werden konnten, jedoch die äußere Genauigkeit negativ beeinflussten. Zur Verbesserung der Verknüpfung einzelner Aufnahmespuren wurden Lösungsansätze wie die Optimierung der Überlappung der Aufnahmespuren und der Kameraausrichtung vorgeschlagen. Die erzielten Fortschritte ermöglichen nicht nur eine effizientere Nutzung des Kamerasystems, sondern eliminieren auch den zusätzlichen Verarbeitungsschritt der Koregistrierung der Aufnahmespuren.
nicht gesperrt
Keywords: Geomonitoring; Photogrammetrie; Tunnelbau; Ortsbrustkartierung; Vergleich von Punktewolken; Laserscan; Agisoft-Metashape; CloudCompare; Kamerasystem; Bildverknüpfung; Orientierungsparameter; innere und äußere Genauigkeit; Geomonitoring; photogrammetry; tunnel construction; face mapping; comparison of point clouds; laser scan; Agisoft-Metashape; CloudCompare; camera system; image linking; orientation parameters; internal and external accuracy

Planung von Pilotversuchen für den Laugungsprozess von LD-Schlacke mit Zitronensäure - Brand, Lorenz (2024)
In dieser Arbeit im Rahmen des K1-MET Projektes 1.7 (Valorisation of steelmaking slags) wird die selektive Laugung von Phosphor aus der C2S-Phase der LD-Schlacke mit Zitronensäure aus bisherigen Forschungsarbeiten weiter verfolgt. Ziel der Arbeit ist die Planung eines Kreislaufversuchs im Pilotmaßstab. Im Literaturteil wird auf Ionentauscherverfahren für die Gewinnung von Phosphor aus der flüssigen Phase eingegangen. Auch einige Aspekte für Fällungs- bzw. Kristallisationsreaktionen werden beschrieben. Der experimentelle Teil widmet sich für den Prozessablauf wesentlicher Schritte. In erster Linie wird die Korngrößenabhängigkeit der Laugung untersucht. Im Hinblick auf einen Pilotversuch sollte die Feststoffkonzentration in der Laugung erhöht werden. Des Weiteren wird die Fest-/Flüssig-Trennung in drei unterschiedlichen Prozessschritten untersucht. Dazu werden Filtrationswiderstände ermittelt. Um den Kreislauf zu schließen wird auch auf Rückgewinnung der Zitronensäure eingegangen. Auf einer Labor-RWKM werden Mahlversuche durchgeführt um das charakteristische Mahlverhalten zu beschreiben sowie den spezifischen Energieeintrag zu bestimmen. Damit wird die Auswahl an Zerkleinerungsaggregaten erweitert. Aus den Erkenntnissen der Laborversuche wird ein Prozessablauf für eine Kreislaufversuchsführung erstellt. Der Laugungsprozess wird auf der Grundlage von Massenbilanzen durch Berechnung der Elementverteilung der verschiedenen Produkte charakterisiert. Das Hauptaugenmerk liegt dabei in der Phosphorverteilung der jeweiligen fertigen und im Kreislauf geführten Produkte.
nicht gesperrt
Keywords: LD-Schlacke; Zitronensäure; Rührwerkskugelmühle; selektive Laugung; BOF; slag; citric acid; stirred media mill; selective leaching

Plasma-treated cobalt-doped nanoporous graphene for advanced electrochemical applications - Knabl, Florian; Kostoglou, Nikolaos; Gupta, Ram K.; Tarat, Afshin; Hinder, Steven J.; Baker, Mark; Rebholz, Claus; Mitterer, Christian (C – journal of carbon research, 2024)

Possible charge ordering and anomalous transport in graphene/graphene quantum dot heterostructure - Roy, Rajarshi; Holec, David; Michal, Lukas; Hemzal, Dusan; Sarkar, Saikat; Kumar, Gundam Sandeep; Nečas, David; Dhankhar, Meena; Kaushik, Preeti; Gómez, I. Jénnifer; Zajíčková, Lenka (Journal of physics (Condensed matter), 2024)

Potentialerhebung zur Wärmerückgewinnung aus Elektroofenschlacken - Watzka, Lorenz (2024)
Ziel dieser Arbeit ist es, einen Überblick über die verschiedensten Möglichkeiten zur Wärmerückgewinnung (WRG) von Elektroofenschlacke (electric arc furnace slags, EAFS) zu bieten. Zu Beginn werden die Ausgangssituation und die theoretischen Grundlagen anhand einer Literaturrecherche betrachtet. Der zweite Teil beschäftigt sich mit der detaillierten Berechnung des praktischen Anwendungsfalles einer Implementierung eines Verfahrens zur WRG in der Stahl- und Walzwerk Marienhütte GmbH (MH). Hierfür gilt es im Vorfeld die notwendigen Daten in entsprechender Qualität zu erheben. Massen- und Energiebilanz der anfallenden Schlackenmenge, konnten durch die MH bereitgestellt werden. Betreffend der spezifischen Wärmekapazität der EAFS wurde eine Modellierung in FactSage sowie eine systematische Literaturrecherche durchgeführt. Anschließend wurde das bestgeeignete Verfahren zur WRG anhand der Anlagengröße, der Erstarrungsform des Endproduktes sowie des Technology Readiness Levels (TRL) ausgewählt und anhand technischer und wirtschaftlicher Betrachtungen für eine Implementierung in der MH durchkalkuliert. Das erhobene Potential der WRG aus EAFS in der MH, bei Einsatz des RecHeat-Verfahrens, ist mit 3,2 GWh/a anzunehmen. Abschließend gibt diese Arbeit einen Ausblick auf eine mögliche Umsetzung einer Kupferplatte, basierend auf den Forschungsergebnissen von DEWEOS.
nicht gesperrt
Keywords: Wärmerückgewinnung; Elektrolichtbogenofen; EAF; Schlacke; Heat recovery; electric arc funace; EAF; slag

Primary Drivers, Obstacles and Economic Effects of Digitalization in the Energy-Intensive Industry - Grogger, Daniel (2024)
In an era of rapid technological advancements, the energy-intensive industry finds itself at the nexus of innovation and transformation. The profound wave of digitalization has swept across sectors, reshaping traditional paradigms and fostering unprecedented opportunities. This master’s thesis delves into the intricate interplay of primary drivers, formidable obstacles, and the economic effects of digitalization and energy efficiency within the energy-intensive industry. As the global community grapples with the imperative of sustainable development, the energy-intensive sector is pivotal in shaping the trajectory towards a more efficient and environmentally conscious future. Digitalization, marked by the integration of cutting-edge technologies such as artificial intelligence (AI), the Internet of Things (IoT), and advanced data analytics, emerges as a catalyst for redefining industrial processes, resource utilization, and overall operational dynamics. New energy production and consumption methods are becoming possible because of advancing digital technology, declining costs, and widespread connections. The development of new, linked energy system designs with digitalization has the potential to dissolve existing issues (cf. IEA, 2017a).The primary objective of this master’s thesis is to unravel the forces driving digital transformation in the energy-intensive industry. A thorough analysis of the drivers, ranging from technological advancements to more transparent processes, will yield a detailed understanding of the impetus behind this disruptive wave. Concurrently, this research will investigate the barriers that significantly hinder the smooth integration of digital technology in this intricate industrial environment. Moreover, digitalization, including its technologies and energy efficiency, is discussed further. Ultimately, the literature part is completed by economic evaluation methods in corporate environments to make digitalization effects feasible.To gain practical insights and to better understand the role of digitalization and energy efficiency in energy-intensive industries, a survey was conducted based on the literature review findings in Chapter 2. The survey was sent to selected professionals who work in or have expertise in this field. The objective was to gather knowledge and insights from these professionals, which is crucial in drawing meaningful conclusions and future trends to deepen the understanding of the drivers and obstacles of digitalization in the energy-intensive industry.This empirical survey delves into critical facets such as digitalization’s current status, its impact on energy demand, primary drivers, and obstacles shaping its implementation. Additionally, it examines digitalization’s role in enhancing energy efficiency, the challenges encountered in its execution, and future trends within the industry. By navigating through these dimensions, the study aims to comprehensively understand the intricate relationship between digitalization and energy efficiency in the energy-intensive sector.
no embargo
Keywords: Digitalisierung; Energie Effizienz; digitale Technologien; Digitalisierung Treiber; Digitalisierung Hürden; Energie-Intensive Industrie; Digitalization; Energy efficiency; digital technologies; digilatization driver; digitalization obstacles; Energy-intensive industry

Probabilistic-Based Algorithm for Detecting Downhole Drilling Abnormalities - Grasser, Philipp (2024)
The oil and gas industry, like many others, is facing challenges brought about by the energy transition, demanding the optimization of operations within defined boundaries. In terms of geo-energy exploration related activities, this is associated with a cost-effective and safe drilling operation. In this regard, it is crucial to minimize the occurrence of undesired downhole problems, which may delay the drilling process, potentially causing non-productive time. One of the essential keys to achieving that is the early detection of anomalous downhole behaviour by continuously monitoring the surface-measured drilling parameters. The hydraulic system, along with other key surface parameters, plays a crucial role in successful drilling operations. It not only facilitates the circulation of drilling fluids, hole cleaning, and bit colling, but also provides valuable insights of the current downhole condition. Accurate modelling and monitoring of the surface-measured standpipe pressure can serve as a reliable indicator of potential anomalous downhole behaviour. However, the conventional physics-based approach for modelling standpipe pressure faces limitation in accurately representing the dynamic and complex nature of the downhole condition. Regarding this issue, the ultimate goal of this thesis is to develop a data-driven model based on a machine learning concept to predict standpipe pressure with only three controllable surface parameters as input for the model and still provide robust estimates of the target variable. The models are trained with trouble-free drilling data, which should allow the model to represent the normal trend and thus provide means for analysis and trend identification by comparison of the actual value with the modelled values. In conclusion, the applied methodology and algorithm can provide acceptable estimates of the target variable utilizing minimum required datapoints stemming from the same well. However, an optimization of the applied approach can possibly lead to improved results. The provided confidence interval provides a range of possible values for the target variable, thus can be useful for analysis and real-time monitoring. However, the predicted confidence interval cannot be directly interpreted as a safe operation window.
no embargo
Keywords: maschinelles Lernen; überwachtes maschinelles Lernen; Standrohrdruck; datengesteuertes Modell; Vorhersagemodell; Datenanalyse; machine learning; supervised machine learning; standpipe pressure; data-driven model; predictive model; data analysis

Probing local adhesion: A miniaturized multi-photon lithography design demonstrated on silanized vs. Untreated surfaces - Jelinek, Alexander; Kiener, Daniel; Alfreider, Markus; Rossegger, Elisabeth; Schlögl, Sandra (Materials and Design, 2024)
As multi-photon lithography technology matures, advanced integrated device design concepts become possible, positioned onto small surfaces, such as optical fibres. Only local adhesion anchors the printed object on the surface and ensure proper print-development without structure loss and long-term usability. Although surface treatments such as silanization are well known to considerably increase adhesion strength, quantification of adhesion is not straightforward and commonly assessed indirectly by surface characteristics and technological methods. The present work aims to quantify adhesion on a micrometer scale through SEM in situ tension experiments, that utilize a newly developed specimen geometry. Multiple specimens, with various footprints, were manufactured on both silanized and untreated fused silica substrates, allowing the comparable quantification of adhesion stresses between different surface conditions. Specimens on an untreated substrate failed with a high scatter in detaching force, whereas specimens on a silanized substrate tend to fail within the photoresist, either at the gauge section or just above the substrate, rather than at the interface itself. Thus, the adhesion stress was increased at least by a factor of 1.4 by the silanization treatment. Generally, a novel approach was developed, that can quantify local adhesions properties in realistic packaging or integrated circuits.
Keywords: Multi-photon lithography; Adhesion; Tensile specimen; Micromechanics; Photoresist

Processing, visualizing, and using Energy Data from the Battery Innovation Center in order to create a Digital Battery Passport - Schindler, Richard (2024)
At the Battery Innovation Center of AVL List GmbH in Graz, prototypes, and serial products of traction batteries, e.g., for electric vehicles, are manufactured. From 2027 onwards, battery related data, e.g., the global warming potential of the manufacturing process, must be documented in a Battery Passport, according to European Union battery regulations. To create this mandatory battery passport application, generate meaningful dashboards, and potentially optimize the manufacturing processes regarding efficiency, energy data is measured, processed, visualized, and utilized in different manners. This is done in the underlying thesis by several consecutive and partly interconnected tasks, which are described in the introduction and represented in the following chapters. First, the state of the art of the manufacture of traction batteries is investigated by the means of a literature research to understand the general build-up and challenges involved in this process. This involves a description of the major battery components. Also, the crucial aspects of data acquisition, management and quality are addressed. Next, the Battery Innovation Center at AVL List GmbH is described to analyze the production capabilities, processes, individual stations and involved machines. This step is crucial to identify processes and relevant stakeholders that are involved in different subsections and applications regarding the assembly and testing of the traction batteries. The centerpiece of this thesis is the energy data analysis, where before-mentioned production, processes, and involved machines are assessed regarding energy consumption, in order to consequently compute energy inputs needed for subsequent analyzes. With the results of the energy analysis, a Life Cycle Assessment is conducted, in which the initially mentioned global warming potential can be identified and quantified. This is done by the means of Carbon-Dioxide-Equivalents related to the necessary energy inputs, consumables, and process gases needed for manufacturing the traction battery under assessment. By interviewing categorizable stakeholders, their professional needs, relevant metrics and Key Performance Indicators can be derived. This is done according to a questionnaire which is an extension of past research projects realized at the Battery Innovation Center. Computed data and the identified professional needs, relevant metrics, as well as Key and Energy Performance Indicators are used to create dashboard mock-ups. The dashboard mock-ups serve as a basis for future demands and efforts in visualizing relevant data to specific stakeholders for monitoring and improving (energy) efficiency and processes at AVL. As a final step, the regulation by the European Union regarding the Battery Passport is analyzed, in order to derive action recommendations on how data can be implemented in such product passports. The initial situation and the existing minimum viable product are briefly explained and necessary data for a digital battery passport creation is described. Finally, a summary of the most important results is given, including an outlook and recommendations for future (research) projects regarding battery manufacturing, energy, and life cycle assessments at the Battery Innovation Center at AVL List GmbH.
embargoed until 08-05-2029
Keywords: Batterie; Produktion; Digitaler Batteriepass; Energiedaten; Ökobilanz; Stakeholderanalyse; Schlüsselkennzahlen; Dashboard; battery; manufacturing; digital battery passport; energy data; life cycle assessment; stakeholder-analysis; key performance indicator; dashboard

Processing-structure-properties relationships of PH 13-8 Mo maraging steels - Rosenauer, Andreas (2024)
PH 13-8 Mo maraging steels are structural materials that are widely used in the aerospace industry for safety-critical components due to their good strength and toughness relation as well as their high corrosion resistance. The microstructure of these alloys consists mainly of a Fe-Ni lath martensite in which both reverted austenite and intermetallic NiAl precipitates are formed during an aging treatment. Owing it to complex microstructure of PH 13-8 Mo maraging steels, many questions with regard to the influence of the manufacturing process, i.e., heat treatment and hot forming, on the microstructure remain. Furthermore, knowledge about the effect of other microstructural constituents such as delta ferrite on the mechanical properties is insufficient and needs to be assessed. Therefore, the aim of the present work is to further investigate the relationships between the manufacturing process and the microstructure as well as between the microstructure and the mechanical properties using novel characterization techniques. The results will be used to deduce processing strategies for improving the mechanical properties of these alloys. Attention was given to delta ferrite and its influence on the toughness. Increasing the content of this phase resulted in a drastic decrease in impact toughness. Microstructural analysis revealed that the embrittlement is caused by cracks originating in delta ferrite. Moreover, multiscale in-situ techniques provided evidence for the austenite memory effect and recrystallization without prior cold deformation occurring in PH 13-8 Mo maraging steels. The latter effect causes a significant refinement of the microstructure, which has a positive effect on the mechanical properties. It was found that further refinement can be achieved by conducting ausforming. In addition, investigations on the effect of ausforming on the microstructure development during subsequent aging showed that finer precipitates and thus increased hardness can be reached by applying this thermomechanical treatment. Ultimately, a large part of the investigations was dedicated to intercritical annealing prior to aging. A detailed microstructural analysis by means of atom probe tomography and transmission electron microscopy revealed that Ni enriched zones, which promote the formation of reverted austenite during subsequent aging, result from this annealing step. In-situ high-energy X-ray diffraction tensile tests showed that this phase exhibits a high mechanical stability.
embargoed until 07-02-2029
Keywords: Maraging steel; PH 13-8 Mo; Precipitates; Reverted austenite; Delta ferrite; Intercritical annealing; Austenite memory effect; Ausforming; Mechanical properties; In-situ characterization; Atom probe tomography; Maragingstahl; PH 13-8 Mo; Ausscheidungen; Rückumgewandelter Austenit; Delta-Ferrit; Interkritisches Glühen; Austenite memory effect; Ausforming; Mechanische Eigenschaften; In-situ Charakterisierung; Atomsondentomographie

Purity and surface area: Key factors on thermal stability and oxidation resistance of BN nanoplatelets - Kostoglou, Nikolaos; Stock, Sebastian; Solomi, Angelos; Holzapfel, Damian M.; Hinder, Steven J.; Baker, Mark; Constantinides, Georgios; Ryzhkov, V.; Maletaskic, Jelena; Matovic, Branko; Schneider, Jochen M.; Rebholz, Claus; et al. (2nd International Conference on Innovative Materials in Extreme Conditions (IMEC 2024), 2024)

Qualifizierung von Linepipe-Stählen für Wasserstoff - Baumer, Martin (2024)
Der Klimawandel stellt eine der drängendsten wirtschaftlichen, technischen und politischen Herausforderungen unserer Zeit dar. Essentiell für den Übergang hin zu einer nachhaltigen Zukunft ist die Dekarbonisierung unserer Energieversorgung. Dieses Unterfangen erfordert jedoch einen monumentalen technischen Aufwand. Die schrittweise Abkehr von Erdgas hinterlässt eine Versorgungslücke die teilweise mit grünem Wasserstoff aus Elektrolyse gefüllt werden soll. Somit erscheint es naheliegend freiwerdende Transportkapazitäten der Pipeline-Infrastruktur für den Transport von Wasserstoff zu nützen. Mit dem Wechsel von Erdgas zu Wasserstoff geht die Gefahr der Wasserstoffversprödung einher. Dieser Effekt ist seit den 1870ern bekannt und stellt ein Risiko für die Sicherheit von mit Druckwasserstoff belasteten Pipelines dar. Diese Arbeit trägt zur Qualifizierung des Linepipe-Stahls X42Q, gefertigt durch die voestalpine Tubulars GmbH & Co KG, bei und vergleicht diesen mit P235. Um die Empfindlichkeit der untersuchten Werkstoffe gegenüber Wasserstoffversprödung zu quantifizieren wurde zunächst die Wasserstoffaufnahme zufolge verschiedener elektrochemischer Beladungen und Gasbeladungen verglichen. Durchgeführt wurden Experimente in saurer (0,5 M H2SO4) sowie neutraler (3 % NaCl) Lösung mit den Rekombinationsgiften Arsenoxid und Thioharnstoff. Beladen wurde mit Stromdichten von 1 und 10 mA/cm2 für eine Dauer von 24 bzw. 48 Stunden. Die Gasbeladungen sind bei Drücken von 100 sowie 1000 bar für je 7 Tage durchgeführt worden. Ausgehend von den Ergebnissen der Beladungsversuche wurden die Beladungsbedingungen für SSRT-Zugversuche mit einer Dehnrate von 10-5 s-1 festgelegt. Die resultierende Versprödung wurde weiters durch SEM-Aufnahmen der Bruchflächen untersucht. Die Ergebnisse zeigen den Zusammenhang zwischen Beladungsbedingungen, Wasserstoffsättigungskonzentration und der folgenden Versprödung. Im Vergleich zeigt X42Q eine geringere Versprödung als P235. An P235 konnte überdies Blisterbildung nachgewiesen werden.
gesperrt bis 24-05-2027
Keywords: Hydrogen embrittlement; P235; X42 : Linepipe; Blistering; gaseous charging; electrochemical charging; SSRT; Wasserstoffversprödung; Linepipe; P235; X42; SSRT; Elektrolytische Beladung; Gasbeladung; Blistering

Quantification and Localisation of the Planned Hydrogen Amount in Styria until 2050 and Development of a Transformation Path for Establishing a Styrian Hydrogen Infrastructure - Schlömicher, Theresa (2024)
The global energy system is currently to a large part built on fossil energy sources. In order to achieve a reduction of CO2-Emissions, it is essential to reshape the current energy system. This requires an increased use of renewable energy sources. In the gas sector, renewable hydrogen, which is seen as a highly versatile energy carrier, is considered a crucial component of a sustainable energy system of the future. For this purpose, the construction of a Paneuropean Hydrogen Network is planned to supply Europe with hydrogen on a large scale. On a national level also plans exist for the Hydrogen Core Network in Austria for the years of 2030 and 2040. As an energy network operator, Energienetze Steiermark GmbH is responsible for providing the necessary transport infrastructure for hydrogen in Styria. Within this master's thesis, a quantification and location of the future demand and procurement of predicted hydrogen quantities is carried out based on existing data. In the context of quantification, predicted CH4 quantities are also included. Therefore, data from industry surveys and calculated scenarios is used. The location of the quantities is determined based on defined main pipeline routes of the Styrian gas network. By examining how the H2 and CH4 demands develop per data source and pipeline route over time, it can be deduced which regions should be supplied with hydrogen from today's perspective. This results in a phased construction of the hydrogen network in Styria. The evaluation reveals that in 2030, the Styrian hydrogen supply should be carried out from the south. For this purpose, the construction of the Southern Line 4 pipeline, the construction of the Southern Line 3 pipeline, and the repurposing of the Southern Line 2 pipeline are required. At the same time, the necessary connection pipelines for the industry, which already have a hydrogen demand by 2030, should be established. By 2040, a gradual expansion of the hydrogen network in Styria will take place through the connection of industrial companies and grid-supportive electrolyzers to the Styrian hydrogen grid. In a further step, in 2040 the repurposing of the Southern Line 1 pipeline is intended to achieve additional hydrogen supply to Styria from the east as well as the connection of further important industrial companies. It is expected that by 2040, the construction of around 145 km of hydrogen pipelines and the repurposing of around 135 km of currently gas-carrying pipelines will be necessary to establish a hydrogen core network in Styria and to cover any gas demands.
no embargo
Keywords: Hydrogen; Hydrogen Grid; Hydrogen Infrastructure; H2; H2-Infrastructure; Hydrogen Demand; Hydrogen Quantities; Styrian Hydrogen Grid; Repurposing; Hydrogen Pipelines; Wasserstoff; Wasserstoffnetz; Wasserstoffinfrastruktur; H2; H2-Infrastruktur; Wasserstoffbedarf; Wasserstoffmengen; steirisches Wasserstoffnetz; Umwidmung; Wasserstoffleitungen

Raman Spectroscopy of carbonaceous material thermometry in the Carnic Alps (Austria, Italy) - Rantitsch, Gerd (Austrian journal of earth sciences, 2024)

Ramp-Up Management im Kontext des schnellen industriellen Wachstums - Eine Fallstudie zur analytischen Modellierung als Leitfaden - Widmann, Rupert-Stefan (2024)
Diese Arbeit analysiert die Herausforderungen, denen Industriebetriebe aufgrund des rasanten Wachstums durch außergewöhnliche externe Faktoren wie den Klimawandel gegenüberstehen. Politische Interventionen, Regelungen und Subventionen beeinflussen die Wirtschaft, schaffen jedoch auch neue Märkte und Wachstumschancen. Industrieunternehmen stehen vor der Aufgabe, diese Chancen zu nutzen und langfristige Wettbewerbsvorteile zu sichern. Das Management, ausgehend von der Strategie, muss die Produktions- und Logistikprozesse sowie die Wertschöpfung des Unternehmens analysieren, gestalten und steuern. Die vorliegende Masterarbeit bietet hierbei einen Leitfaden zur Bewältigung des Wachstums. Der zweite Teil dieser Masterarbeit fokussiert sich auf die Entwicklung eines konzeptionellen Planungsunterstützungstools für den Produktionshochlauf im Kontext des rasanten Wachstums. Ziel ist es, einen Informationssystem-Ansatz für das Ramp-Up Management zu schaffen und somit effektiv auf die entstehenden Chancen zu reagieren.
nicht gesperrt
Keywords: Unternehmenswachstum; Logistik- und Produktionssystem; Ramp-Up Management; Planungsunterstützungssystem; Company growth; Logistics and production system; Ramp-up management; Planning support system

Reduktion von CO2-Emissionen im Zuliefernetzwerk von einem produzierenden Unternehmen durch verstärkte Nutzung des unbegleiteten kombinierten Verkehrs - Becaj, Manuel (2024)
Vor dem Hintergrund der EU-Klimaschutzziele gewinnt die Reduktion von CO2- Emissionen in Unternehmen zunehmend an Bedeutung. Um diese Ziele zu erreichen, sind Unternehmen bestrebt, ihre Prozesse in Richtung Nachhaltigkeit umzugestalten. Gerade im Transportsektor, der einen erheblichen Anteil der CO2-Emissionen verursacht, bietet es sich an, die Transportprozesse näher zu betrachten. Insbesondere der Lkw als das am häufigsten genutzte Transportmittel trägt erheblich zu den Treibhausgasemissionen bei. Eine vielversprechende Möglichkeit zur Emissionsreduktion ist die Verlagerung von Straßentransporten auf umweltfreundlichere Alternativen wie Bahn oder Binnenschiff. Dieser spezielle Ansatz, bei dem der Lkw nur für den Transport zwischen dem Terminal oder Hafen und dem Unternehmen eingesetzt wird, wird als intermodaler Verkehr bezeichnet. Das Ziel dieser Arbeit ist es, innovative Routen für den Kombinierten Verkehr im Zulieferernetzwerk eines produzierenden Unternehmens zu identifizieren. Dieser Prozess wird durch den Einsatz eines leistungsfähigen Visualisierungstools ermöglicht, mit dem die Routen in einer visuell ansprechenden Weise dargestellt werden können. Die Identifikation der effizientesten Routen beginnt mit der Einteilung des geographischen Gebietes in verschiedene Cluster, wobei jedem Cluster ein potenziell geeigneter KV- Terminal zugeordnet wird. Um sicherzustellen, dass dieser Rahmen möglichst aussagekräftig ist, wurden umfangreiche Recherchen über die vorhandene Infrastruktur und die Güterverkehrsbedingungen durchgeführt. Ein wesentlicher Schwerpunkt dieser Arbeit liegt in der Berechnung der CO2-Emissionen sowohl im Straßen- als auch im kombinierten Verkehr. Durch diesen Vergleich ist es möglich, die Umweltauswirkungen und die Vorteile des kombinierten Verkehrs gegenüber dem konventionellen Straßentransport darzustellen. Durch die Kombination von Visualisierungstechniken, Routenplanung und der Bewertung von CO2-Emissionen und Kosten sollen wertvolle Erkenntnisse für die Optimierung des Kombinierten Verkehrs im Zuliefernetzwerk von dem produzierenden Unternehmen gewonnen werden.
nicht gesperrt
Keywords: CO2-Emissionsreduzierung; Nachhaltige Prozesse; Transportsektor; Intermodaler Verkehr; Kombinierter Verkehr; Routenoptimierung; CO2 Emission Reduction; Sustainable Processes; Transport Sector; Intermodal Transport; Combined Traffic; Route Optimization

Refractory breakouts: Comminution technology validation for MgO-C refractories - Zhang, Zixuan (2024)
Recycling has grown increasingly popular in the refractory industry. The recycling of used refractory bricks into high-quality, secondary raw materials can help to reduce the consumption of primary raw materials and thus conserve deposit reserves as well as significantly reduce the CO2 footprint resulting from extraction, preparation and further processing. However, because of their complex compositions and combinations, spent refractory materials are not sorted automated and manually instead. The investigations carried out in the course of this master's thesis focussed on MgO-C, which is frequently used as a refractory material. During the relining of ovens, a not inconsiderable amount of these used refractory bricks accumulate as waste, which is currently mainly sent to landfill. Since dumpingbring up costs, recycling the MgO-C refractory breakouts is also significant from an economic point of view. In this thesis, the focus is on recycling of MgO-C in order to create sufficient liberation conditions for subsequent sorting by applying five different comminution technologies, including electrodynamic fragmentation on lab-scale, electrodynamic fragmentation on semi-industrial scale, impact crusher, cone crusher and jaw crusher. In order to detect apparent colour differences, the samples were examined separately under a microscope before and after the density tests. Preliminary investigations showed that the first completely free phases of MgO-C could already be present from a size of less than 4 mm. The final particle fractions used in the course of raw material characterisation and for separation tests are 4 - 3.15 mm and 3.15 - 1 mm respectively. Float/sink analyses were performed by using the density differences of the phases contained in MgO-C. In order to detect apparent colour differences, the samples were examined separately under a microscope before and after the float/sink analyses. The samples were then investigated for Magnesia and Carbon enrichment using XRF and LECO. Finally, it was determined which is the most suitable for comminuting this refractory bricks. It also defines the particle sizes and density ranges that are best for generating enriched MgO and Carbon. As it was to be expected, the Henry-Reinhardt diagrams show that Carbon is enriched in < 3.0 g/cm³ while MgO is enriched in > 3.0 g/cm³. Extensive fractional class analyses were applied to some of the produced fractions of the comminution products in order to determine the comminution technology that best favours the liberation of the contained phases and the subsequent separation. The results suggest that both jaw crushers and cone crushers are suitable aggregates for this essential process step.
no embargo
Keywords: MgO-C; Refractory; Recycling Comminution; Density; MgO-C; Feuerfest; Recycling Brecher; Dichte

Removal of crystal violet dye from aqueous solutions through adsorption onto activated carbon fabrics - Mulla, Batuhan; Ioannou, Kyriacos; Kotanidis, Gkerman; Ioannidis, Ioannis; Constantinides, Georgios; Baker, Mark; Hinder, Steven J.; Mitterer, Christian; Pashalidis, Ioannis; Kostoglou, Nikolaos; Rebholz, Claus (C – journal of carbon research, 2024)

Research into PEM electrolysis and the related degradation mechanisms - Haupt, Michael (2024)
The ever-advancing transformation of the fossil fuel-based energy system towards a sustainable circular economy based on renewable sources is causing an ever-increasing demand for hydrogen as an energy source. The desired hydrogen economy is leading to an increasing number of research projects in the field of hydrogen production, storage and utilization, which means that also the topic of hydrogen production from water electrolysis is constantly gaining importance. In particular, the PEM electrolysis discussed in this thesis offers the potential to assume the leading role in sector coupling between the electrical and gas grid as well as the possibility for the hydrogen supply of fuel cell drives or hydrogen engines in the mobility sector.In collaboration with AVL, the monitoring of hydrogen production by use of the PEM electrolysis has been investigated throughout this thesis. It is focused on the research of the existing degradation mechanisms that may occur during the operation to develop a new diagnostic tool for degradation monitoring that can be used to provide information about the PEM electrolyser. Given to the enormous complexity of such a monitoring system, an initial knowledge base for the further development of the diagnostic tool is being produced in this thesis. For this purpose, the thesis is divided into two sections, the technical and the development part.In the beginning, the technical section is dedicated to the general technological basics of electrolysis, followed by the specialization in the PEM electrolysis technology and ending with their occurring degradation mechanisms. The subsequent development part initially presents a physical modeling approach that captures the transport mechanisms during the operation of an electrolyser. This is followed by the determination of the most important influencing factors on degradation monitoring by identifying the so-called “stressors” and categorizing them into the four main categories: Thermal, Hydration, Mechanical and Potential. These operational stressors represent the events that trigger the stress situations during the operation and are required for the creation of the so-called “Failure-Fingerprint trees” for the main components of the PEM electrolyser.In the end, these flowcharts provide an overview of the cause-effect relationship for the individual degradation mechanisms at the component level of a PEM electrolyser and are necessary for tracking and preventing the occurring degradation processes. Additionally, the diagrams also record those events that are usually overlooked during the stress tracking and lead to actual deterioration. The results of these visualizations represent the first starting point for the additional development of the desired diagnostic tool for degradation monitoring.
embargoed until 04-03-2029
Keywords: PEM-electrolysis; Degradation mechanisms; Degradation monitoring; Degradation stessors; PEM-Elektrolyse; Degradationsmechanismen; Degradationsüberwachung; Degradationsstressoren

Residual stress measurement using surface acoustic waves - Pfeiffer, Maximilian (2024)
This thesis deals with the development and testing of an industrially suitable, robust and costefficient measurement setup for carrying out residual stress measurements with surface acoustic waves. In the beginning, the necessary theoretical background on residual stresses, the acoustoelastic effect and sound waves in solids is explained. The relationship between mechanical stress and acoustic waves in solid materials has been known for a long time, but the research results are inconsistent. Stress induced changes of the wave velocity are in a range of around 0.002 %/MPa, which is why the measuring system must be very precise. The sampling rate of the analog-to-digital converter and the measuring distance required to measure these velocity changes are calculated. Furthermore, the influences of various factors that affect time of flight measurement such as signal shape, dispersion, roughness and temperature are illustrated with examples from literature and own results. The necessary measuring devices such as transducers, laser vibrometer, oscilloscope and laser ultrasound equipment are then explained and the differences between the individual measurement methods were outlined. Afterwards, verification experiments are done with piezoelectric surface actuators that are glued to a 25CrMo4 sample. In various tests, the sample was subjected to tensile and bending stresses and the resulting change of wave velocity was determined by measuring the time of flight. The results were able to prove the acoustoelastic effect, i.e. the stress-dependent change of wave velocity. This means that in the future this simple measurement setup can be used to detect changes in residual stress during maintenance.
embargoed until 21-05-2029
Keywords: Eigenspannung; Spannungsmessung; Spannung; akustisch; Wellen; Oberflächenwellen; Ultraschall; Rayleigh; Residual stress; stress measurement; surface acoustic waves; ultrasonic; Rayleigh wave; transducer

Revealing dynamic-mechanical properties of precipitates in a nanostructured thin film using micromechanical spectroscopy - Alfreider, Markus; Meindlhumer, Michael; Ziegelwanger, Tobias; Daniel, Rostislav; Keckes, Jozef; Kiener, Daniel (MRS Bulletin, 2024)
Nanostructured materials with their remarkable properties are key enablers in many modern applications. For example, industrial dry-milling processes would not be as widely spread without the use of hard, wear-resistant metal nitride coatings to protect the cutting tools. However, improving these nanostructured thin films with regard to dynamical properties is demanding as probing respective parameters of (sub-)micron layers without any substrate influence is still challenging. To extend the scientific toolbox for such spatially confined systems, a novel methodological approach based on resonance peak measurements of a cantilever-transducer system termed micromechanical spectroscopy (µMS) is developed and applied to a Al0.8Cr0.2N model system. The mainly wurtzite type supersaturated Al0.8Cr0.2N system showed precipitation of cubic CrN at grain boundaries and local Cr variations upon annealing at 1050°C. This was accompanied by an increase in the previously unknown damping capability of 63 percent and an increase in Young’s modulus by 36 percent.
Publisher Copyright: © 2023, The Author(s).
Keywords: AlCrN; Dynamic testing; Grain-boundary segregation engineering; Heat treatment; Micromechanical testing; Precipitation

Rotationszerstäubung als Methode der Inwertsetzung von mineralischen Reststoffen - Eisner, Peter (2024)
Der Klimawandel stellt alle energie- und treibhausgasintensiven Industrien vor die Herausforderung, ihre Produktionsprozesse hinsichtlich deren Klimafreundlichkeit zu verbessern. Mit einem Anteil von jeweils 7 % an den globalen CO2-Emissionen haben dabei die Eisen- und Stahl- sowie die Zementindustrie eine zentrale Schlüsselposition inne. Neben der intrinsischen Motivation der Unternehmen spielen auch extrinsische Faktoren, wie die Änderungen der gesetzlichen Rahmenbedingungen, oder das wachsende Interesse an Nachhaltigkeit von Seite der Investoren eine große Rolle. In der Eisen- und Stahlindustrie führt diese ¿Greentransformation¿ zu neuen Produktionsprozessen wie der Direktreduktion von Eisenerz mit Wasserstoff und dem Ausbau von Elektrolichtbogenöfen, was auch Änderungen in den Flüssen der Nebenprodukte zur Folge hat. Es kommt zur Verringerung der Verfügbarkeit von Hochofenschlacke, die als Hüttensand in der Zementindustrie als Ersatz für den Klinker eingesetzt wird. Somit ist es notwendig, Alternativen zum Hüttensand zu finden und zu erforschen, um die prozessbedingten CO2-Emissionen in der Zementindustrie weiter mitigieren zu können. Bei der Produktion von Hüttensand wird dieser in einem amorpher Zustand erstarrt, damit sich latent hydraulische Eigenschaften ausbilden, die zur Bindemitteleignung führen. In der Vergangenheit wurde dies mit einer Nassgranulation gelöst. Dabei kommt es nicht nur zum Verlust der gesamten nutzbaren Energie der mineralischen Phase, es wird weiters noch Energie zur Trocknung des Hüttensandes benötigt. Die Trockengranulation mittels Rotationszerstäubung hingegen erlaubt es, die thermische Energie des Produktes nutzbar zu machen und gleichzeitig die Trocknungsenegie einzusparen. Dabei wird mittels Fliehkraft ein Zerfall des schmelzflüssigen Materials in Tropfen herbeigeführt. Die an die Luft übertragene Wärme kann anschließend als Prozesswärme eingesetzt werden. Um die Effekte bei der Rotationszerstäubung von verschiedenen mineralischen Reststoffen untersuchen zu können, wird eine entsprechende Anlage benötigt. Ziel dieser Arbeit ist es daher, eine Rotationszerstäubungsanlage im Labormaßstab am Lehrstuhl für Thermoprozesstechnik auszulegen, zu konstruieren und zu errichten. Diese soll dabei mit der bereits vorhandenen Induktionsschmelzanlage kombinierbar sein. Die Ergebnisse der ersten Versuche der Rotationszerstäubung zeigen, dass die Partikel der produzierten mineralischen Phase den gegenständlichen Ansprüchen für eine Bindemittelnutzung genügen und mit den zuvor durchgeführten Berechnungen in Einklang stehen.
nicht gesperrt
Keywords: Rotationszerstäubung; mineralische Reststoffe; Hüttensand; Hochofenschlacke; Klinker; Substitut; Klimawandel; Eisen- und Stahlindustrie; Zementindustrie; Nachhaltigkeit; Bindemittel; Greentransformation; CO2-Emissionen; Elektrolichtbogenofen; Induktionsschmelzanlage; Thermoprozesstechnik; Rotary Atomizer; Mineral Residues; Granulated Blast Furnace Slag; Blast Furnace Slag; Clinker; Substitute; Climate Change; Iron and Steel Industry; Cement Industry; Sustainability; Binder; Green Transformation; CO2-Emissions; Electric Arc Furnace; Induction Melting Plant; Thermal Processing Technology

Scalable synthesis of biomass-derived three-dimensional hierarchical porous activated carbons for electrochemical energy storage and hydrogen physisorption - Selvaraj, Aravindha Raja; Kostoglou, Nikolaos; Rajendiran, Rajmohan; Cho, Inho; Rebholz, Claus; Chakravarthi, Nagarajan Deepan; Prabakar, Kandasamy (Journal of energy storage, 2024)

Scarring of Acoustic Waves - Indirect Detection of Sub-µm Defects in TSVs at Wafer Level - Paulachan, Priya (2024)
The development of More than Moore (MtM) technology continues to drive the miniaturization of semiconductor devices and the integration of various functionalities. This MtM-driven trend increasingly emphasizes the need for 3D integration techniques to achieve superior miniaturization and improved performance. However, the rapid advances in 3D integration technology have brought new challenges in the area of failure analysis (FA). Overcoming these challenges requires the use of non-destructive methods that provide high-resolution insights while being cost-efficient and time-saving. The scanning acoustic microscope (SAM) is proving to be a crucial tool for non-destructive, cost-efficient and time-critical failure analysis. In this context, the imaging resolution and penetration depth of the conventional SAM are traditionally limited by the frequency of the transducer used. In this work, a modified SAM interferometry setup is tailored for defect detection in 3D integration technology, focusing on the characterization of through silicon vias (TSVs). This approach is more independent of the transducer frequency. Special acoustic lens configurations are used for the controlled excitation of surface acoustic waves (SAWs). The interference patterns resulting from the interaction of the SAWs and bulk acoustic waves contain valuable information about the quality of the TSVs. Artificial intelligence is used to localize and classify the interference patterns obtained and can be effectively used for error analysis of the TSVs. The different SAM interference patterns on the TSVs are investigated in detail in this thesis using acoustic simulation and validated using the scanning electron microscope (SEM). Essentially, this thesis contributes to the advancement of 3D integration technology by presenting innovative approaches for non-destructive defect analysis, automatic defect localization and comprehensive characterization of TSVs. Furthermore, it focuses on deepening the understanding of the behaviour of SAWs and their role in the context of quality detection in modern semiconductor technologies.
embargoed until 11-12-2028
Keywords: Akustische Rastermikroskopie; Through Silicon Vias (TSVs); Elastodynamischen Finite-Integrations-Technik (EFIT); Akustische Oberflächenwellen; Fehleranalyse; Zerstörungsfreie Prüfung; Scanning Acoustic Microscopy; Through Silicon Vias (TSVs); Elastodynamic Finite Integration Technique (EFIT); Surface Acoustic Waves(SAWs); failure analysis; non-destructive testing

Schienengüterverkehr - eine realistische Alternative für Post-Transporte? - Kramer, Erich Josef Johann (2024)
In der vorliegenden Arbeit wurde grundlegend untersucht, unter welchen Vorausset-zungen der Schienengüterverkehr für ein Postunternehmen eine Alternative zum heu-te dominierenden Straßengüterverkehr ist. Auf der Basis von Erkenntnissen aus einer Literaturrecherche wurde in Kooperation mit der Österreichischen Post AG eine Studie durchgeführt, welche die Möglichkeiten und Grenzen einer solchen Verlagerung von Postsendungen aufzeigen konnte. Die Randbedingungen für den Schienengüterverkehr sind grundsätzlich günstig, denn Österreich belegt im europäischen Quervergleich immerhin den dritten Platz in der Kategorie des transportierten Volumens pro Einwohner. Um eine entsprechende Infra-struktur für dieses Verkehrsaufkommen bereitzustellen, investiert der österreichische Staat am viertmeisten in Europa. Auch von Seiten der Österreichischen Post AG be-steht ein reges Interesse, immerhin will sie bis 2040 ein Net-Zero Ziel erreichen. Hierfür müsste eine umfassende Lösung für den Langstreckentransport im Hauptlauf der Post-sendungen noch gefunden werden. Um den Schienengüterverkehr im Allgemeinen konkurrenzfähig zu gestalten, wurden folgende Faktoren als wesentlich erkannt: Hohes Transportvolumen (mind. 2 Contai-ner), große Transportdistanz (>300 km), langfristig planbare Transporte, relativ lange Transportzeit (mind. 1 Tag) und Nähe zu Güterterminals. Viele dieser Anforderungen konnten im Projekt mit der Österreichischen Post erfüllt werden. Aus historischen Gründen liegt ein Großteil der Logistikzentren in unmittelbare-rer Nähe zu Güterbahnhöfen, die täglichen Transportvolumina könnten mehrere Züge auslasten und die Transporte finden täglich zur selben Zeit statt. Die Transportdistanzen sind für einen nationalen Schienengüterverkehr, auch auf der West-Ost-Achse jedoch relativ kurz, wodurch, ein Kostenvorteil zum Straßengüterverkehr schwierig zu realisie-ren ist. Auf der Grundlage eines Angebotes der RailCargo Austria wurde ein Break-Even Point zum LKW-Transport von 879 km berechnet. Nachdem die Österreichische Post mehrere Tochterfirmen im Süden besitzt, wurde auch dieses Szenario evaluiert, jedoch fehlt auf diesen Relationen das nötige Sendungsvolumen (< 1 WAB). Eine Steigerung der Transportkosten von xx% könnte im Ausgleich zu einer Reduktion der Emissionen von 80% in Kauf genommen werden, jedoch konnte keines der ge-wählten sieben konkreten Umsetzungsszenarien die Anforderungen an die Laufzeit der Post-Produkte vollkommen erfüllen. Das Hauptproblem besteht darin, dass bei volu-menstarken Produkten (Paket E+1) eine Laufzeit bis zur Zustellung von maximal einem Tag nach Aufgabe besteht. Bei Produkten mit längerer Laufzeit (3-5 Tage) fehlt ein entsprechendes Volumen, um einen eigenen Zug auszulasten, wodurch man auf zeit-lich fixierte Routen im Einzelwagenverkehr angewiesen ist. Diese meist nächtlichen Transportzeiten passen sehr schlecht mit den Prozesszeiten bzw. bestehenden Zeitab-läufen der Post zusammen, wodurch bis zu 15 Stunden Stehzeit entstehen können und Szenarien nur tageweise erfüllt werden können. Ein paralleler Prozess für den Bahn-transport zum bestehenden Prozess für einzelne Tage wird von Seiten der Post ausge-schlossen. Ein weiteres Problem im Einzelwagenverkehr ist die Verfügbarkeit von Rou-ten. Umsetzungsrelevante Unterschiede zu Ländern mit aktivem Post-Transport über die Schiene sind folgende: ¿Priorität von Postzügen ¿ ermöglicht den Transport während der Personenver-kehrszeit (Schweiz) ¿Güterterminal im Logistikzentrum integriert ¿ flexible Be-/Entladung bei Post-internen Wagons (Schweiz) ¿Lange Transportstrecken ¿ ermöglicht durch internationale Transporte oder Ver-bindungen von Achsen bei großflächigen Ländern (Norwegen, Frankreich, Niederlande, Dänemark) ¿Zusätzliche Auslastung der eigenen Postzüge als Spediteur (Schweiz) ¿Kombination mit Personenverkehr ¿ nur bei Expresssendungen möglich, welche
nicht gesperrt
Keywords: Rail freight transport; Postal company; Road-rail modal shift; Case study; Conditions for a road-rail modal shift; Schienengüterverkehr; Postunternehmen; Straßen-Schienen-Verlagerung; Fallstudie; Voraussetzungen für eine Straßen-Schiene-Verlagerung

Seismic insights into the structure of the Balmuccia Peridotite within the Ivrea Verbano Zone - Pasiecznik, Damian; Greenwood, Andrew; Bleibinhaus, Florian (EGU General Assembly 2024, 2024)
In the Ivrea Verbano Zone (IVZ) Italy, which is characterized with lower-crustal rocks and fragments of upper mantle rocks, a high-resolution seismic survey is conducted across the Balmuccia Peridotite. This study is in preparation of a proposed deep scientific drilling project which focuses on targeting mantle rocks and understanding the region's complex geology. Specifically, we target characterizing structures within the peridotite body.The seismic survey employs a fixed spread of 200 vertical geophones and 160 3C-sensors, spaced at ca. 10 m along three sub-parallel receiver lines spaced 40-80 m apart. Vibroseis source points are at 22 m stations along a 2.2 km line utilizing a 12-140 Hz 10 s linear sweep with 3 s listening time. The survey aims to explain the seismic characteristics of the peridotite body and its relation to the surrounding geological structures.The P-wave traveltime tomography reveals a range of seismic velocities within the peridotite from 6 to 8 km/s, with a mean velocity of ca. 7 km/s. These variations reflect the heterogeneity of the peridotite, influenced by the presence of fractures and faults. Notably, the higher velocities observed are consistent with findings from laboratory studies on small-scale samples from the area. The reflection seismic analysis shows subvertical reflectors that coincide with the peridotite boundaries mapped at the surface. These reflectors come together at a depth of 0.175 km b.s.l., suggesting that the peridotite has a lens-like structure. In addition, several features within the peridotite suggest a highly fractured body. Nevertheless, limitations in the imaging process do not allow for a thorough interpretation of the area below the imaged lens-shaped body. A deep reflector is identified at approximately 1.3 km depth. This feature potentially marks the top of the Ivrea Geophysical Body (IGB), aligning with previous geophysical estimations.

Sektorkopplungslösungen für das Energienetz der Zukunft in Oberösterreich - Moser, Lukas Peter (2024)
Im Zuge des Pariser Klimaschutzabkommens hat sich die Staatengemeinschaft erstmalig auf verpflichtende Maßnahmen zur Begrenzung des Klimawandels verständigt. Daher strebt auch die österreichische Bundesregierung bis 2040 einen vollständigen Ausstieg aus der fossilen Energiewirtschaft an. Als führender Energieversorger Oberösterreichs hat die Energie AG deshalb den Auftrag, auf die durch diese Maßnahmen entstehenden Änderungen im Energiesystem vorbereitet zu sein. Zu den Kernaufgaben zählen unter anderem die Integration neuerer Technologietrends und der Umgang mit einem erhöhten Anteil an volatiler Energieerzeugung, der mit einer erhöhten Energieerzeugung aus erneuerbaren Energien einhergeht. Daraus ergibt sich das Ziel dieser Arbeit, auf Basis eines zeitlich und örtlich aufgelösten Modells des oberösterreichischen Energiesystems mittels einer Lastflussrechnung im hybriden Simulationstool HyFlow Engpässe im zukünftigen elektrischen Energienetz zu identifizieren, da dieses als kritischste Netzinfrastruktur festgemacht wird. Anschließend werden Methodiken entwickelt, um diese Bottlenecks mit Hilfe sektorkoppelnder Hybridelemente zu beheben. Diese Simulationen werden in Abstimmung mit dem Auftraggeber für die Jahre 2030 und 2040 durchgeführt. Die entwickelten Methoden zur Entlastung des Stromnetzes umfassen Batteriespeicher, Power-to-Gas und Power-to-Heat Anwendungen. Anhand einer Bestandsaufnahme der Auslastung des Stromnetzes des jeweiligen Berechnungsjahrs werden diese Methodiken durch die Analyse von regionalisierten Erzeugungs- und Residuallastprofilen entwickelt. Dabei wird versucht, Erzeugungs- und Lastspitzen zu minimieren und somit eine Glättung des Erzeugungs- bzw. Lastprofils zu erreichen. Die Ergebnisse zeigen, dass vor allem der Einsatz von Power-to-Gas-Anlagen zur Reduktion der durch die gesteigerte erneuerbare Energieerzeugung verursachte erhöhte Auslastung der Netzinfrastruktur beitragen kann. Der Einsatz von Hybridelementen zur Netzentlastung ist allerdings nur ein Teil der Lösung, da die Veränderungen im Energiesystem so gravierend sind, dass dafür eine Vielzahl an Maßnahmen getroffen werden muss.
nicht gesperrt
Keywords: Sector Coupling; Hybrid energy systems; HyFlow; Bottlenecks; Sektorkopplung; Hybride Energiesysteme; HyFlow; Bottlenecks

Separation of copper from aluminum in an eddy current separator product by dry density separation - Ali, Muhammad (2024)
The global shift toward green technology increases the demand for metals, which causes pressure on primary resources. To fulfil the demand for metals and to decrease the exploitation of primary resources, efficient recycling of metals is essential, but the issue is, that e metals are lost during processing or downgrade due to impurities as the presence of lead in copper is difficult to eliminate and it has to be downgraded. This thesis deals with the analysis of fluidized bed separator performance, which is a newly developed technology for the separation of different metals in scrap based on their density. For characterizing head grades, separation success, and the efficiency of separation, hand sorting, XRF sorting, and physical separation at the analytical grade of feed and product were done in order to evaluate the analysis effort and the increase the accuracy of particle-based analytical methods. Within the experimental work, samples were taken from the fluidized bed separator, which separates the conductant product of an eddy current process into a heavier and a lighter fraction, based on its threshold density. The efficiency of the fluidized bed separator was elaborated by sink float analysis. The accuracy of hand sorting was analyzed for the copper and brass content in the heavier fraction using XRF analysis. Results indicate that fluidized bed separator was very efficient, which documents that the separator sufficiently enriches metals of a density higher than 4.5 g/cm³. Hand sorting based on visual inspection of the surface faces some limitations in separating the materials compared to XRF sorting. The work reflects the variance in materials recovery based on the employed analytical methods, highlights the strengths, and limitations of each analytical technique, and the amount of different constituents present in the feed samples.
no embargo
Keywords: Fluidized bed separator; Hand sorting; X-ray fluorescence analysis; Density separation; copper recycling; Dichtesortierung; Wirbelschichtabscheider; Handsortierung; Röntgenfluoreszenzanalyse; Kupfer-Recycling

Simulationsorientierte Analyse des Einsatzes alternativer Antriebe und Energieträger im europäischen Straßengüterverkehr - Schieler, Patrick (2024)
Die Transportbranche steht aktuell vor der Herausforderung ihre Abhängigkeit von fossilen Kraftstoffen zu reduzieren, um die Dekarbonisierung ihrer Prozesse voranzutreiben. Es gilt einen Umstieg auf alternative Kraftstoffe in Verbindung mit weiteren Verkehrskonzepten, wie dem kombinierten Verkehr, zu fokussieren. Die vorliegende Arbeit untersucht dahingehend die gegenwärtig verfügbaren zukunftsweisenden Antriebstechnologien und integriert die als die vielversprechendsten Antriebe identifizierten in ein Simulationsframework. Anhand mehrerer Fallbeispiele und Szenarien werden Eigenschaften, wie auftretende Kosten und Emissionen sowie Herausforderungen, etwa zeitliche Auswirkungen auf die Transportprozesse, der einzelnen Alternativen herausgearbeitet, analysiert und gegenübergestellt. Die Resultate der Simulationsdurchläufe sollen eine Übersicht der Eigenschaften der aktuellen Auswahl an Antriebskonzepten darlegen und Unternehmen, hinsichtlich der Flottenumstellung, Handlungsempfehlungen bieten. Die Ergebnisse deuten dabei auf einen Kosten- und partiellen Emissionsvorteil der batterieelektrischen Antriebe gegenüber jenen mit fossilen Energieträgern betriebenen Fahrzeuge hin. Demgegenüber steht aber auch der signifikante Nachteil bezüglich des erhöhten Planungs- und Zeitaufwands, da die Ladevorgänge einen erheblichen zusätzlichen Zeitfaktor implizieren. Die für alternative Transporte benötigte Versorgungsinfrastruktur ist, unabhängig der Antriebstechnologie, bislang rar und Routenplanungen gestalten sich komplex. Die Resultate der Simulationsdurchläufe umfassen nur operative Kosten. Unterschiede hinsichtlich Subventionen, Abschreibungen oder Anschaffungspreise der Antriebstechnologien werden nicht berücksichtigt. Weiters wird von einer unbeschränkten Fahrzeugverfügbarkeit sowie einer maximalen Reichweitenkapazität, ermöglicht durch betriebseigene oder öffentliche Infrastrukturen am Ausgangspunkt, ausgegangen.
nicht gesperrt
Keywords: Alternative Kraftstoffe; Transport; Simulation; Kombinierter Verkehr; Alternative Antriebe; Transportlogistik; alternative fuels; transport; simulation; combined transport; alternative drives; transport logistics

Single Crystalline 2D Material Nanoribbon Networks - Aslam, Muhammad Awais (Optical and Electrical Properties, 2024)
Two-dimensional (2D) material nanoribbons offer vast opportunities ranging from next generation quantum electronics to enhanced sensing. However, the existing fabrication routes are mostly restricted to graphene nanoribbons where the majority of methods rely on solution processed nanoribbons which hinders their integration into devices. Methods opted for the fabrication of other 2D material nanoribbons do not offer sufficient quality, yield, and control over the nanoribbons¿ edge terminations. This has been a bottleneck in the experimental studies of nanoribbons to explore their electrical and optical properties. This work aims to propose a universal approach to synthesize networks of nanoribbons from arbitrary 2D materials while maintaining high crystallinity, narrow size distribution, and straightforward device integrability. Moreover, the resulting devices do not suffer from junction resistance issues. This is supported by in-operando Kelvin Probe Force Microscopy of nanoribbon field effect transistors (FETs). The single crystalline nature of the nanoribbons is verified by Raman spectroscopy. By relying on self-aligning organic nanostructures as masks, the possibility of controlling the predominant crystallographic direction of the nanoribbon¿s edges is also demonstrated. Electrical characterization shows record charge carrier mobilities and very high ON-currents despite extreme width scaling. Particularly, for graphene nanoribbons a well-defined and highly controllable system of hexagonal boron nitride encapsulated graphene nanoribbon networks with water terminated edges is also presented. The system exhibits a robust hysteresis of the remnant dipolar fields, which affect and modulate the conductivity of graphene nanoribbon networks. So far, such ambipolar behaviour in graphene nanoribbons has been only predicted theoretically. The undertaken experimental approach sheds light on the mechanisms governing the ferroelectric behavior in graphene nanoribbons and supports it theoretically via molecular dynamic simulations. This offers insights for the design of ferroelectric heterostructures and neuromorphic circuits. Lastly, the thesis presents all van-der-Waals semiconducting PtSe2 field effect transistors with high-performance transport characteristics. PtSe2 is proposed as an alternative channel material below thicknesses of 4 nm, a critical thickness limit below which Si electronics performance start to deteriorate. The work is also inspired by the need to address the challenges faced for the co-integration of 2D materials into back end of line processes used in Silicon technology.
no embargo
Keywords: Nanobänder; Ferroelektrizität; 2D Materialien; KPFM; Feldeffekt-Transistoren; Nanoribbons; Ferroelectricity; 2D Materials; KPFM; Field Effect transistors

Strength testing of additive manufactured ceramics – A round robin using the CharAM-methodology - Staudacher, Maximilian; Scheithauer, Uwe; Reichel, Maria; Schwentenwein, Martin; Lube, Tanja (Open ceramics, 2024)

Study on the Briquetting of the Siderite- Based Direct Reduced Iron and Factor Affecting its Briquettes' Quality - Wicaksono, Aris Hadyo (2024)
Most direct reduced iron (DRI) in the world is produced from hematite or magnetite ore. Siderite is rarely used as main raw material for ironmaking and steelmaking industries. However, as one of the biggest producer of iron ore concentrate (IOC) from siderite, VA Erzberg GmbH focuses to conduct some researches to produce DRI from new emerging process named Hydrogen Based Fine-Ore Reduction (HYFOR). Unlike conventional direct reduction process (DRP), HYFOR generates DRI in smaller size, which is below 6.3 mm. In this study, it is found that almost 53.5% of the siderite-based DRI product from HYFOR is in the size below 0.5 mm. Considering that the fine size of DRI is quite susceptible to undergo re-oxidation due to its high porosity and is not suitable for direct charging to electric arc furnace (EAF) or direct shipment to foreign steel industries, briquetting process, either cold or hot briquetting, of siderite-based DRI will be exercised. Chemical characterization shows that the sample of siderite-based DRI (HYFOR, <7500C) used in this study contains low metallic iron content (19.54 wt%). It is found that upgrading metallic iron of the siderite-based DRI is applicable by reducing the feed size from -6.3 into 100% below 1 mm and separating it using magnetic separation before the briquetting is performed. The study also shows that direct use of the feed without magnetic separation with size -6.3 and -1 mm (HYFOR feed) into briquetting process is also possible at the room temperature (cold briquetting). Without the addition of water and binder, the cold briquetting already achieves the apparent density required by the MO maritime Safety Committee, International Maritime Solid Bulk Cargoes (IMSBC) which is 2.5 gr/cm3 by using 105-107 MPa as the briquetting pressure. Beside the apparent density, its porosity volume fraction also decreases by 42%. However, in order to achieve better compressive strength, direct use of HYFOR feed or the upgraded HYFOR is not sufficient. Specific amount of binder and water shall be used to improve the mechanical properties in the cold briquetting step. In general, the briquette formed by the upgraded HYFOR (high metallic iron) with binder and water has better strength compared to its counterpart that is made of HYFOR feed. Particle size distribution also has effect to the briquette¿s strength and compressibility. HYFOR material with higher feed size (-6.3) produces lower strength briquette than the HYFOR feed -1 mm although it has a good compressibility. Another factor is compaction pressure. The higher the pressure, the better compressive strength of the briquette. In terms of hot briquetting, the experimental work shows that the usage of high temperature during compaction can increase the strength and compressibility although the preliminary results obtained in this study do not fulfil the expectation. Further improvements in the test setup are necessary.
embargoed until 31-05-2029
Keywords: Direct Reduced Iron (DRI); siderite-based DRI; briquetting; porosity; compressibility; compressive strength; Direktreduziertes Eisen (DRI); Siderit-basiertes DRI; Brikettierung; Porosität; Kompressibilität; Druckfestigkeit

Sustaining Prosperity - Becker, Silvester (A Comprehensive Analysis of EU Regulations and their Ripple Effect on Corporate Capital in the Financial Landscape, 2024)
The effects of climate change are getting increasingly pervasive and it is evident that the global economy is not suited to fight it. The European Union (EU) has since its founding established itself as an advocate for future-orientated legislature and as the ruling example for ethics in politics, with its notable posing as the moral norm of democratic countries through its written down values per §2 TEU. (Manners, 2002) Similarly, they made the first step towards a more sustainable world when establishing a new and concise regulatory framework targeting the reorientation of capital flows into the direction of sustainable finance. With the creation of the European Green Deal, the EU is now providing an unparalleled piece of legislature for sustainability concerning its scope and the size of economy affected. In the course of the establishment of the Green Deal, many policies have been implemented and some are already showing their effects on the European economy. This thesis analyses how the new regulatory framework is affecting capital costs and investment decisions of firms located within the EU¿s legislation and how prepared the EU¿s companies are regarding the upcoming regulatory challenges. To achieve this, an overview and summary of the most relevant EU legislative documents is provided with a timeline to track upcoming regulatory responsibilities. The main focus lies on the new reporting obligations connected to the new Corporate Sustainability Reporting Directive (CSRD) and the regulatory framework to identify sustainable economic activities, also known as the EU Taxonomy. Understanding how different stakeholders like non-financial corporates, investors and banks are dealing with these new regulatory requirements and whether they impact stakeholder¿s financing decisions is essential to this analytical piece. To achieve this, 15 expert interviews have been conducted for this thesis. Through them, objective information and qualified opinions have been gathered on how capital providers and capital receivers are currently or should be operating with sustainability regulation in mind and on how they are or may be integrated in investment decisions. The findings of this thesis describe that the earlier sustainability aspects are adopted in the company strategy and the better the data availability is, the earlier cost savings occur and the easier it is to later implement new regulatory developments into company structure and decision-making. Capital providers also prefer their clients to act accordingly as data gaps provide challenges not only for sustainable investment decisions but also for a bank¿s risk management which will further affect how banks will be able to allocate capital. These findings are particularly significant with further regulatory developments like the Corporate Due Diligence Directive and the proposal for a Green Claims Directive, as they could have direct impacts on costs and capital.
no embargo
Keywords: sustainability; sustainable finance; green finance; EU Taxonomy; CSRD; ESG; regulation; regulatory framework; Nachhaltigkeit; Nachhaltige Finanzierungen; Grüne Finanzierungen; EU Taxonomy; CSRD; ESG; Regulatorik; Regulatorisches Rahmenwerk

Symmetric Quadratic Traveling Salesman Problem with Reload Costs - Hanzlovic, Michael (Applications & Solution Approaches, 2024)
This thesis delves into the intricate world of the Symmetric Quadratic Traveling Salesman Problem (SQTSP), particularly focusing on instances where reload costs are incurred when switching between two types of edges during the traversal. Such a scenario is not only realistic in various practical applications, like logistics and route planning, but also poses unique challenges to traditional solution methods. The primary objective of this research is to rigorously test and evaluate the effectiveness of existing Integer Linear Programming (ILP) linearizations, various Subtour Elimination Constraints (SEC), and heuristics, as documented in the literature, when applied to the SQTSP that models the reload cost component. In addition to the evaluative study, this thesis contributes by the development of a novel heuristic specifically designed for this unique variant of the SQTSP. This new heuristic is tailored to effectively handle the complexities introduced by the reload costs, aiming to optimize the traversal sequence in a manner that balances the traditional optimization goals of the SQTSP with the specific cost considerations. The findings unveil a nuanced interdependence between graph composition and solver complexity, particularly under the influence of the balance of flagged to unflagged edges and the relative magnitude of reload costs. Notably, solver times manifest a bell-shaped curve akin to a normal distribution when related to the percentage of flagged edges, peaking as this percentage nears a 50/50 equilibrium. Concurrently, solver times respond to an increase in reload costs relative to average edge weights in an exponential fashion, highlighting the intricate, non-linear dynamics at play. The exploration and findings presented in this thesis not only contribute to the theoretical advancement in the field of operations research but also have implications for practical applications. By extending the existing knowledge on SQTSP and introducing new methodologies for addressing the complexities of reload costs, this research provides valuable insights for both academics and practitioners in the field of optimization and logistics. In essence, this thesis navigates through the theoretical and practical landscapes of the SQTSP with reload costs, offering a comprehensive analysis of existing methods and pioneering a new approach to address the nuanced challenges of this problem.
no embargo
Keywords: SQTSP; Reload Costs; Linearization; ILP; Subtour Elimination Constraint; SQTSP; Umladekosten; Linearisierung; ILP; Subtour Eliminierungs-Ungleichung

Synthetic Load and Generation Profiles in Industry - Binderbauer, Paul (2024)
The introduction of new technologies and processes, particularly the adoption of renewable energy sources, brings increased volatility into the dynamic relationship between manufacturing industries and their counterparts in the energy markets. To address this challenge, industrial energy research is dedicated to bringing forth dynamic, holistic and more straightforward solutions. One of these solutions involves the development of load and generation profiles, which allows for a detailed examination of how individual industries consume and generate energy over time. These valuable insights enhance the collaboration among key stakeholders, including grid operators, energy suppliers, and industrial players. As a result, it significantly improves decision-making processes, fostering advancements in the industrial sector.Throughout an extensive literature research, it can be concluded that a holistic solution on synthetic load and generation profiles in industry has not been developed yet. State-of-the-art works either rely on vast amounts of data or focus solely on selected applications such as generating electricity load profiles for specific industrial subsectors. Recognizing this research gap, this thesis presents novel developments for generating load (and generation) profiles (LPs) and waste heat profiles (WHPs) of the entire industrial sector encapsulated in an all-in-one software solution named “Ganymed”.Overall, the industrial sector is divided into energy-intensive and non-energy-intensive subsectors. As the energy-intensive subsectors exhibit a limited product and process variety, a bottom-up methodology starting with data on the process level is applied. Throughout the enhancement of the simulation method of discrete event simulation, these processes can be accumulated to whole production routes, which offers the basis for generating LPs and WHPs for energy-intensive subsectors. It can be stated that processes must contain data on energy-relevant and time-resolved properties to achieve LP and WHP generation. Here, the most energy-intensive processes influence the resulting LPs and WHPs of individual industries to the greatest extent. Especially batch-operated processes make up for main shares in peak loads. Non-energy-intensive subsectors exhibit more complex production routes, deeming a top-down approach to be the more suitable methodology for depicting them. Various industrial databases form the basis for novel findings within these energy system analyses, which are further deployed to generate LPs and WHPs for these subsectors. For example, this thesis uncovers subsector-specific “economy of scale” effects for industrial energy systems, correlations of shift models and deployed employees at the plant, calculations for maximum outlet temperatures of industrial waste heat etc.Both methodological approaches are embedded into the software environment “Ganymed”, being the first-of-its-kind of software for generating synthetic LPs and WHPs of the industry.
no embargo
Keywords: Load profile; energy system; industry; generation profile; energy-intensive; energy-extensive; waste heat; Lastprofil; Energiesystem; Industrie; Software; Erzeungsprofil; Energieintensiv; Energieextensiv; Abwärme

Techno-Economic Assessment of H2-Supply for an Industrial Site - Wechner, Lukas (2024)
To advance the mitigation of global warming by decarbonization, the industrial sector has to transform towards low emission energy sources. Green hydrogen is seen as an important part of this transformation. However, the absence of a well-established hydrogen transport infrastructure slows the implementation of production capacities and industrial applications. Moreover, investments in hydrogen infrastructure align close to the production of hydrogen and the industrial demand. Therefore, companies willing to transform toward clean energy have to make a strategic decision, if the supply should rely on regional infrastructure or if an investment in on-site production facilities should be considered. To support this decision-making process a calculation model is developed to evaluate the techno-economic concept for hydrogen supply of an industrial site. The model is created within the Python programming environment utilizing the Open Energy Modelling Framework ¿OEMOF¿. It is further supported by Excel spreadsheets to ease user interaction, result processing and graphical representation. The model can be tailored to investigate different scenarios focusing on on-site hydrogen production strategies through water electrolysis. Furthermore, an aboveground hydrogen storage as a flexibility option is taken into account evaluating the economic influence. The model is cost optimized by a mixed linear integer solver in regard of fluctuating electricity prices. Moreover, the flows, the capacities of the components component and their corresponding costs are determined to enable a detailed analysis. Additionally, an exemplary calculation is carried out by providing technical and economic parameters for hydrogen production in near future. Together with an electricity price profile and a load profile the influences on costs and on the operational strategy are determined. It turns out that the utilization of a hydrogen storage can reduce the hydrogen supply costs up to a certain point depending on the storage capacity. However, the implementation of larger hydrogen storage leads to a rise in hydrogen supply costs. Increasing the storage capacity by compressing or liquifying the hydrogen turned out to be not favourable under these assumptions. The electricity price was identified as the main cost driver necessitating a further expansion of renewable energy sources to reduce electricity prices and utilize fluctuations. For an industrial site with an annual hydrogen demand of 72 GWh the hydrogen supply costs for merchant hydrogen delivered by different transport routes and the on-site production lie within the same range. Depending on the underlying assumptions on-site production can be a competitive alternative for merchant hydrogen.
no embargo
Keywords: Hydrogen Production; Hydrogen Transport; Electrolysis; Industrial Use of Hydrogen; Supply Costs; Cost Optimization; Hydrogen Storage Option; Renewable Energy Sources; Wasserstoffproduktion; Wasserstofftransport; Elektrolyse; Industrielle Wasserstoff Nutzung; Versorgungskosten; Kostenoptimierung; Wasserstoffspeicher; Erneuerbare Energie

Techno-Economical Assesment of HT-ATES in the Vienna Region - Studenka, Josef (2024)
High Temperature – Aquifer Thermal Energy Storage (HT-ATES), enables the storage and retrieval of unused or wasted energy during periods of low or representatively high demand. It is presenting a sustainable solution for the currently decarbonizing energy market. Vienna, being the largest city in Austria, has a lot of unused potential when it comes to energy that could be used to heat up water. Moreover, the city already has an established district heating network (DHN). Integrating this storage system within the DHN, would significantly decrease the carbon footprint as the current predominance lies on gas. This work contributes to the limited literature on HT-ATES experiences by presenting a reservoir model established using Modflow, a groundwater-simulating code capable of modelling aquifer systems. Utilizing the graphical user interface, ModelMuse, a simulation is created with varying input parameters. The resulting temperature profile reflects the behaviour of the system forming the foundation for the establishment of the recovery efficiency and the economic variables. Initially, the model was to set to a production rate of 3500 m3/day, a cut-off temperature (temperature at which the fluid is reinjected back to the reservoir) of 50°C and a reservoir thickness of 50m. During the simulation process, it was of interest to prove the importance of the constantly held thermal radius at 500m, in which the production rate was increased to 4000 m3/day. During this scenario, there no breakthrough was encountered, although the produced temperatures were lower compared to the initial production rate. Increasing the reservoir thickness to 75m boosted the recovery efficiency significantly. Even despite the increased thickness, the initial layout, intended for a volume of 3500 m3/day showed a higher recovery efficiency than a setup with 4000 m3/day. Although the recovery efficiency favours the lower production volume, it does not align with the results of the Levelized Cost of Heat (LCOH) or Net Present Value (NPV). These economic parameters directly benefit from the increase in energy output through the elevated production rate. The evaluation reveals promising outcomes, with the NVP yielding 3,23€ million and LCOH resulting at 55,17€/MWh.
no embargo
Keywords: HT-ATES; ATES; Seasonal storage; LCOH; Modflow; HT-ATES; Modflow; LCOH; ATES; Saisonspeicher

Test Specimen for Strength Testing of Additive Manufactured Ceramics by the VPP Process: the CharAM-Specimen - Lube, Tanja; Staudacher, Maximilian; Scheithauer, Uwe; Schwentenwein, Martin; Brouczek, Dominik; Schmid, Harald (2024)

The Ball-on-Three-Balls strength test - Staudacher, Maximilian; Eggel, Anna Elisa; Supancic, Peter Hans; Lube, Tanja (Journal of the European Ceramic Society, 2024)
In order to compare the strength results of brittle materials from various testing methods or use the data for design purposes, it is essential to know the effective volume (Veff) or surface (Seff) for every loading scenario. For the Ball-on-Three-Balls-test (B3B), Veff and Seff have to be determined and investigated through Finite-Element-Analysis due to the lack of an accurate analytical description of the stress field. Through this work, the effective volume and surface of the B3B-test are made available as tabulated data for a wide range of specimen geometries and materials, along with the tools to utilize the data. A fitting model for the dependency of Veff and Seff on the Weibull-modulus for any given specimen geometry is provided. The influence of load-dependent non-linear effects on Veff and Seff is discussed. Finally, the necessity of Veff and Seff for statistical strength analysis is demonstrated through a practical example.
Publisher Copyright: © 2023 The Authors
Keywords: B3B-test; Biaxial testing; Effective volume; Strength testing; Weibull theory

The Hydrogen Uptake of L360 Pipeline in Varied H2 Environments - Gouda, Ahmed Hamed Mahmoud Eid; Mori, Gregor Karl (Science 4 Technology @MUL, 2024)

The Kinematics of an Impact Crusher's Impact Swing Mechanism as a Mathematical Model - Kemper, Dietmar; Antretter, Thomas; Egger, Martin; Flachberger, Helmut; Fimbinger, Eric (Results in Engineering, 2024)
Keywords: The Kinematics; Impact Crusher's; Impact Swing Mechanism; Mathematical Model

The Toarcian Posidonia Shale at Salem (North Alpine Foreland Basin; South Germany) - Ajuaba, Stephen; Sachsenhofer, Reinhard; Galasso, Francesca; Garlichs, Thorsten U.; Groß, Doris; Schneebeli-Hermann, Elke; Misch, David; Oriabure, Jonathan E. (International Journal of Earth Sciences, 2024)
The Posidonia Shale in the basement of the North Alpine Foreland Basin of southwestern Germany represents an important archive for environmental changes during the Toarcian oceanic anoxic event and the associated carbon isotope excursion (T-CIE). It is also an important hydrocarbon source rock. In the Salem borehole, the Posidonia Shale is ~ 10 m thick. The lower 7.5 m (1763.5–1756.0 m) of the Posidonian Shale and the uppermost part of the underlying Amaltheenton Formation were cored and studied using a total of 62 samples. Rock–Eval, palynological, maceral, biomarker and carbon isotope data were collected to assess variations in environmental conditions and to quantify the source rock potential. In contrast to most other Toarcian sections in southwest Germany, TOC contents are high in sediments deposited during the T-CIE, but reach a peak in post-CIE sediments. Biomarker ratios suggest that this reflects strong oxygen-depletion during the T-CIE (elegantulum to lower elegans subzones), but also during the falciferum Subzone, which is also reflected by a prolonged dinoflagellate cyst blackout. While sediments of the tenuicostatum Zone to the elegans Subzone are thinner than in neighbouring sections (e.g., Dotternhausen), sediments of the falciferum Subzone are unusually thick, suggesting that increased subsidence might have contributed to anoxia. The T-CIE interval is very thin (0.75 m). δ13C values of n-alkanes show that the maximum negative isotope shift predates the strongest basin restriction during the T-CIE and that the carbon isotope shift is recorded earlier for aquatic than for terrigenous organisms. In Salem, the Posidonia Shale is thermally mature and highly oil-prone. The residual source petroleum potential is about 0.8 tHC/m2. Graphical Abstract: (Figure presented.).
Publisher Copyright: © The Author(s) 2024.
Keywords: Biomarkers; Carbon isotope excursion; Lower Jurassic; Palynology; Stable carbon isotopes; Toarcian oceanic anoxic event

The roles of impurities and surface area on thermal stability and oxidation resistance of BN nanoplatelets - Kostoglou, Nikolaos; Stock, Sebastian; Solomi, Angelos; Holzapfel, Damian M.; Hinder, Steven J.; Baker, Mark; Constantinides, Georgios; Ryzhkov, Vladislav; Maletaskic, Jelena; Matovic, Branko; Schneider, Jochen M.; Rebholz, Claus; et al. (Nanomaterials, 2024)

Thermal treatment of continuous alumina fibers - Gruber, Fabian Ingo (2024)
Today´s challenges faced in different sectors of industry require materials working at high temperatures exposed to chemically aggressive environments. All-Oxide Ceramic Matrix Composites (OCMC) have proven to be promising materials due to their stability under high temperatures and oxidizing conditions. The properties of the OCMCs are largely depending on the properties of the used alumina fibers and therefore the processing of continuous alumina fibers is of special interest. This thesis focuses on the thermal treatments of green continuous alumina fibers and the characterization of green, pyrolyzed and sintered fibers, aiming to understand the influence of temperature, heating rate, holding time, thermal radiation and applied tension on the chemical, physical and mechanical properties of the obtained fibers. Green continuous alumina fibers based on aluminum chlorohydrate were analyzed using DTA, TGA and SEM. The results of the DTA and TGA showed that between 100°C - 600°C volatile components leave the fiber and a mass loss of 58% was observed. The transformation to ¿-alumina happened at 875°C and the transformation to ¿-alumina at 1130°C. No peaks for ¿-alumina or ¿-alumina were observed. Microscopical investigations revealed different abnormalities of the green fibers. The mean filament diameter was 21 µm. Fibers which were pyrolyzed at 825°C and 875°C, at slow and fast heating rates with 5 min and 15 min holding time had mean filament diameters between 15 µm - 16 µm. Only at 15 min holding time ¿-alumina was the only crystalline phase present. The microstructure of the fibers consisted of grains smaller than 250 nm. The densities were with 2,123 g/cm³ - 2,377 g/cm³ very low and the tensile strengths were between 380 MPa - 692 MPa. Longer holding times and applied tension lead to higher densities with same grain sizes but not to higher tensile strengths. Radiation did not affect the properties of pyrolyzed fibers. The fibers which were sintered between 1100°C - 1700°C for 1 min ¿ 9 min had mean filament diameters of 13 µm -18 µm. Fibers which were sintered at 1200°C, 9 min; 1300°C, 6 min; 1400°C, 3 min; 1400°C, 5 min; 1500°C, 3 min; 1700°C, 2 min; consisted of an ¿-alumina microstructure with grain sizes smaller than 250 nm. Densities of 2,234 g/cm³ -3,007 g/cm³ were measured and tensile strengths of 179 MPa -326 MPa. The mechanical properties of the sintered fibers fell below the properties of pyrolyzed fibers. It was found out that even at long holding times, no proper densification was observed. No tension could be applied during the sintering. Radiation did lead to a different arrangement of the grains which was observed on the fracture surfaces of the filaments. The findings of this thesis provide detailed information of the effect of different parameters during the thermal treatment on the chemical, physical and mechanical properties of alumina fibers and may help fabricating continuous alumina fibers with desired properties for the final application.
embargoed until 02-05-2029
Keywords: Oxidische Endlosfasern; Endlosfasern; Fasern; Aluminiumoxid; CMC; Verbundwerkstoff; Wärmebehandlung; thermische Behandlung; alumina fibers; continuous alumina fibers; fibers; CMC; composite; thermal treatment; alpha alumina; aluminum oxide

Treatment of carbon electrodes with Ti3C2Tx MXene coating and thermal method for vanadium redox flow batteries: a comparative study - Teenakul, Kavin; Alem, Sayed Ali Ahmad; Gond, Ritambhara; Thakur, Anupma; Anasori, Babak; Khataee, Amirreza (RSC Advances, 2024)
One of the significant challenges of vanadium redox flow batteries is connected to the negative electrode where the main reaction of V(II)/V(III) and the side reaction of hydrogen evolution compete. To address this issue, we used titanium carbide (Ti3C2Tx) MXene coating via drop-casting to introduce oxygen functional groups and metals on the carbon electrode surface. Characterization through scanning electron microscopy and X-ray photoelectron spectroscopy confirmed the even distribution of Ti3C2Tx MXene on the electrodes and the presence of titanium and termination groups (–O, –Cl, and –F). The cyclic voltammetry analysis of MXene-coated electrodes showed more sharp electrochemical peaks for the V(II)/V(III) reaction than thermal-treated electrodes, even at relatively high scan rates. Notably, a relatively high reaction rate of 5.61 × 10−4 cm s−1 was achieved for the V(II)/V(III) reaction on MXene-coated electrodes, which shows the competitiveness of the method compared to thermal treatment (4.17 × 10−4 cm s−1). The flow battery tests, at a current density of 130 mA cm−2, using MXene-coated electrodes showed pretty stable discharge capacity for over 100 cycles. In addition, the voltage and energy efficiency were significantly higher than those of the system using untreated electrodes. Overall, this work highlights the potential application of MXene coating in carbon electrode treatment for vanadium redox flow batteries due to remarkable electrocatalytic activity and battery performance, providing a competitive method for thermal treatment.
Keywords: Redox Flow Battery; Carbon Materials; MXene; 2D Materials; Surface Chemistry; Functionalization

Two-phase flow Thermo-Hydro-Mechanical (THM) modelling for a water flooding field case - Liu, Yuhao; Zhang, Fengshou; Weng, Dingwei; Liang, Hong; He, Chunming; Yoshioka, Keita (Rock Mechanics Bulletin, 2024)

Umgebungsbedingte Spannungsrissbildung in Polyethylen - Ladinig, Alexander (Analyse verschiedener Testmethoden, 2024)
Durch den weltweiten Anstieg von Kunststoffprodukten und -anwendungen und den damit einhergehenden zunehmenden Kunststoffabfällen verschärfte sich die globale Sichtweise in Bezug auf das Thema Nachhaltigkeit verstärkt im letzten Jahrzehnt. Ein Paradebeispiel hierfür ist der Europäische „Green Deal“, welcher die Kreislaufwirtschaft zu einer seiner Hauptprioritäten macht. Der Übergang zu einer Kreislaufwirtschaft hat jedoch erhebliche Auswirkungen auf die Abfallwirtschaft und die Wiederverwendung von Materialien. Neue verbindliche Recyclingziele für Kunststoffe – zum Beispiel die Sicherstellung, dass alle Verpackungen auf dem EU-Markt bis 2030 auf wirtschaftlich tragfähige Weise wiederverwendbar oder recycelbar sind – werden zukünftig also zu einer hohen Verfügbarkeit von Rezyklaten führen. Für diese Rezyklate müssen geeignete Anwendungen gefunden werden. Eine Möglichkeit dafür ist etwa die Blasformung von Flaschen und Behältern zur Lagerung und/oder zum Transport von „Non Food“ Inhalten, wie etwa Kosmetika, Haushaltsmittel oder Chemikalien. Allerdings kommt es vor allem durch den Medieneinfluss in solchen Anwendungen oftmals zum vorzeitigen Versagen durch die sogenannte „umgebungsbedingte Spannungsrissbildung“ (Environmental Stress Cracking, ESC).Aus diesem Grund wurde der Fokus dieser Arbeit auf das Verhalten von verschiedenen Polyethylen (PE)-Typen gegenüber ESC gelegt. Zu diesem Zweck wurden acht verschiedene PE-Typen, darunter vier High-Density Polyethylene (HDPE), zwei Low Density Polyethylene (LDPE) und zwei PE Rezyklate auf die ESC Beständigkeit anhand unterschiedlicher Prüfmethoden und bedingungen getestet. Hierzu wurde ein in der Industrie weitverbreiteter Standardtest für die Ermittlung von ESC von PE ausgewählt – der sogenannte Bell Test (BT, ASTM D1693). Weiteres wurde ein weniger verbreiteter ESC Test, der sogenannte Buckled Plate Test (BPT) nach Chang und Donovan 1989 verwendet. Beide Tests wurden bei unterschiedlichen Temperaturen (50 °C und 80 °C) und Medieneinflüssen (Luft vs. 2 % haltige Lauramin-Oxid Lösung) durchgeführt. Als ergänzender bruchmechanischer Test wurde ein statischer Kompakt-Zugversuch (Compact Tension, CT), zur Ermittlung der Rissausbreitungsgeschwindigkeit angewendet.Aus der Basischarakterisierung (z.B. Dichte, Schmelzfließrate (MFR), mechanische Kennwerte, etc.) ging hervor, dass die beiden Rezyklate im Vergleich zu den anderen HDPEs anorganische Verschmutzungen in Form von Füllstoffen, oder Fremdpartikeln besitzen. Bei den Fließeigenschaften bestätigten sich, die laut Hersteller angegeben Verarbeitungstypen der einzelnen Materialien. Die mechanischen Eigenschaften haben gezeigt, dass sowohl das Biegemodul, als auch die Biegespannung stark von der Temperatur abhängten. Die Werte der HDPEs lagen jedoch generell höher als jene der LDPEs. Auch die Rezyklate lagen auf dem Niveau der HDPEs.Bei der Ermittlung der ESC-Beständigkeit ging aus dem BT und BPT hervor, dass die HDPEs die beständigeren Materialien gegenüber den anderen Materialien sind. Die Rezyklate weisen die geringste ESC Beständigkeit in beiden Tests auf. Die ESC-Beständigkeit verschlechterte sich bei Erhöhung der Prüftemperatur mit der Ausnahme von den LDPEs, welche so weit erweichen, dass ein duktiles Versagensbild, anstelle von Spannungsrissen entsteht.Der bruchmechanische CT-Versuch unterstreicht ebenfalls große Differenzen zwischen den getesteten Materialien und gibt ähnliche Tendenzen im Risswachstumsverhalten wie die ESC Tests wieder. Rezyklate wiesen die höchste Rissausbreitungsgeschwindigkeit auf, während neuwertige HDPEs am resistentesten gegenüber Rissausbreitung waren. Für die LDPEs wurden keine CT Versuche durchgeführt, da diese bei 80 °C zu stark erweichen und keine Messungen im Rahmen der linear elastischen Bruchmechanik möglich sind.Die in dieser Masterarbeit erzeugten Ergebnisse zeigen, dass der in der Ausführung wenig aufwendige BT einen guten Überblick auf die ESC-Beständigkeit geben kann. Der Nachteil dieser Methode liegt darin, dass die Versagenszeit der einzelnen Prüfkörper stark streuten, was die Beurteilung erschwerte. Der Buckled Plate Test ist im Vergleich aufwendiger, bringt jedoch ähnliche Ergebnisse in der ESC-Beständigkeit wie der BT. Es wurde bei diesem Test eine unterschiedliche Risskinetik im Vergleich zum CT-Test festgestellt, welche den Einfluss des Spannungs- und Dehnungszustand gut wiederspiegelt. Weiteres geht aus dieser Arbeit hervor, dass die getesteten Rezyklate, im Vergleich zu Neuware eine wesentlich schlechtere ESC-Beständigkeit aufwiesen. Somit sollte für gewünschte Produkte und Anwendungen der Rezyklatanteil so geregelt werden, dass ein vorzeitiges Versagen, auch durch die verminderten Eigenschaften des gegebenen Rezyklates, ausgeschlossen werden kann.
nicht gesperrt
Keywords: Umgebungsbedingte Spannungsrissbildung; Polyethylen; Rezyklate; Bell-Test; Gebogene Platte Test; Kompakt-Zugversuch; Environmental Stress Cracking; Polyethylene; Recyclates; Bell-Test; Buckled Plate Test; Compact Tension

Umweltgeologische Evaluierung von Entsorgungs- und Verwertungsmöglichkeiten für Tunnelausbruchsmaterial im Rahmen des FCC-Projekts - Joldić, Amra (2024)
Die Masterarbeit widmet sich der umweltgeologischen Bewertung von Entsorgungs- und Verwertungsmöglichkeiten für Tunnelausbruchsmaterial im FCC-Projekt. Schwerpunkt bildete eine vergleichende Analyse der rechtlichen Rahmenbedingungen und experimentellen Untersuchungen in Österreich, der Schweiz und Frankreich. Aus dem Material erster Probebohrungen wurden zwei Proben (qSTP1 und qSTP2) chemisch analysiert und auf ihre Verwertungsmöglichkeiten in verschiedenen Branchen basierend auf technischen und rechtlichen Vorgaben bewertet. Für die Analysen wurden einerseits die Gesamtgehalte (Metalle nach Königswasseraufschluss und Totalaufschluss sowie RFA) und andererseits die Eluatgehalte ermittelt. Ein Abgleich der Ergebnisse von qSTP1 und qSTP2 mit Rückstellproben aus vorangegangenen Arbeiten bestätigte die Repräsentativität der gezogenen Proben. Die Zusammensetzung der RFA zeigt das Vorliegen folgender Hauptkomponenten: 47 % SiO2, 12 % CaO, 11 % Al2O3, 7 % MgO, 5 % Fe2O3, 2% K2O und 1 % Na2O. Im Rahmen der XRD-Untersuchung wurden folgende Phasen festgestellt: 20 % CaCO3 (Calcit), 19 % KAl2[(OH,F)2|AlSi3O10] (Glimmer-Gruppe (Muskovit/Illit)), 14 % (Fe,Mg,Al)6(Si,Al)4O10(OH) (Chlorit), 12 % NaAlSi3O8 (Plagioklas (Albit)), 11 % SiO2 (Quarz), 11% CaMg(CO3)2 (Dolomit), 11% (Ca,Na,K)(Mg,Fe,Al)9(Si,Al)8O20(OH)10¿nH2O (Corrensit) und 4 % KAlSi3O8 (Kalifeldspat (Mikroklin)). Gemäß österreichischer Deponieverordnung wird das Tunnelausbruchsmaterial als nicht gefährlicher Abfall betrachtet und erfüllt die Grenzwerte für Baurestmassendeponien sowie Massenabfalldeponien. Allerdings ist dies die ungünstigste Entsorgungsmethode. Gemäß dem Bundesabfallwirtschaftsplan erfüllt das Tunnelausbruchmaterial keine Qualitätsklasse. Es hält jedoch die Grenzwerte der österreichischen Recycling-Baustoffverordnung (Zuschlagstoff für recycelten Asphalt oder für die ungebundene Oberschicht gemäß § 13 Z 9) ein, allerdings ist der Einsatz des Materials auch rechtlichen Gründen derzeit nicht zulässig. In der Schweiz erfüllt das Tunnelausbruchmaterial die Grenzwerte gemäß der Verordnung über die Vermeidung und die Entsorgung von Abfällen (VVEA) und wird entsprechend in die Kategorien Typ D und Typ E klassifiziert. Laut Étarès Environnement erfüllt das Tunnelausbruchmaterial in Frankreich die Grenzwerte für Klasse 2 sowie für Klasse 3. Aufgrund der großen Menge (9 Millionen m3) und der möglichen Schwankungen in der Materialzusammensetzung wurden Branchen, die das Tunnelausbruchsmaterial nur in kleinen Mengen verwenden können, nachrangig behandelt. Das galt auch für Branchen mit geringer Toleranz gegenüber Schwankungen in Qualität und Zusammensetzung ihrer Rohstoffe. Die Bewertung des Tunnelausbruchsmaterials im Rahmen der Masterarbeit kommt zu folgenden Ergebnissen: Das Tunnelausbruchsmaterial zeigt als Ersatzrohstoff Potenzial zur Verwertung in der Zementindustrie aufgrund hoher Hauptrohstoffmengen wie SiO2, CaO, Al2O3 und Fe2O3. In der Ziegelindustrie wäre ein Einsatz für Mauerziegelmassen denkbar, doch erhöhte Magnesium- und Calciumoxid-Gehalte könnten Probleme verursachen, sodass es nur als Zuschlagstoff zum Einsatz kommen kann. Für die Glasindustrie ist es ungeeignet aufgrund des hohen Verunreinigungsgrades (z.B. Eisen). In der Landwirtschaft ist es aufgrund der hohen Nickelkonzentration und begrenzter Nährstoffgehalte ungeeignet.
nicht gesperrt
Keywords: Tunnelausbruch; Zementindustrie; Deponierung; Prüfverfahren; tunnel excavation; cement industry; landfill; test methods